Application of Self-Organizing Maps to characterize subglacial bedrock properties based on gravity, magnetic and radar data – an example for the Wilkes and Aurora Subglacial Basin region, East Antarctica - Liebsch, Jonas; Ebbing, Jörg; Matsuoka, Kenichi (Solid Earth, 2025)
Keywords: Antarktis; geovitenskap; glasiologi; innlandsis; subglasial geologi

Time series of the summertime atmospheric water vapour isotopic composition at Concordia station, East Antarctica - Ollivier, I.; Lauwers, T.; Dutrievoz, N.; Agosta, C.; Casado, M.; Fourré, E.; Genthon, C.; Jossoud, O.; Prié, F.; Steen-Larsen, H. C.; Landais, A. (Earth Syst. Sci. Data, 2025)
Measurements of stable water isotopes in the atmospheric water vapour can be used to better understand the physical processes of the atmospheric water cycle. In polar regions, the atmospheric water vapour isotopic composition is a key parameter to understand the link between the precipitation and snow isotopic compositions and interpret isotope climate records from ice cores. In this study we present a novel 2.5-month accurate record of the atmospheric water vapour isotopic composition during the austral summer 2023–2024 (6 December 2023 to 14 February 2024) at Concordia Station (East Antarctica), from two laser spectrometers based on different measurement techniques, which are independently calibrated and both optimised to measure in low humidity environments. We show that both instruments accurately measure the summertime diurnal variability in the water vapour δ18O, δD, and d-excess, when the water vapour mixing ratio is consistently higher than 200 ppmv. We compare these measurements to outputs of the isotope-enabled atmospheric general circulation model LMDZ6-iso and show that the model exhibits biases in both the mean water vapour isotopic composition and the amplitude of the diurnal cycle, consistent with previous studies. Hence, this study provides a novel dataset of the atmospheric water vapour isotopic composition on the Antarctic Plateau, which can be used to evaluate isotope-enabled atmospheric general circulation models. The dataset is available on the public repository PANGAEA (https://doi.org/10.1594/PANGAEA.974597, Landais et al., 2024b).
Keywords: Antarktis; meteorologi

Basal Melt Rate Variability and Tidal Current Vertical Structure From Observations Beneath Ronne Ice Shelf, Antarctica - Anselin, J.; Nicholls, K. W.; Holland, P. R.; Taylor, J. R.; Østerhus, S.; Makinson, K. (Journal of Geophysical Research: Oceans, 2025)
This study examines the interplay between water column structure, tidal currents, and basal melting at a site beneath Ronne Ice Shelf, using a 3-year data set of oceanographic measurements, and a collocated year-long time series of radar-derived melt rate estimates. Currents at the site are characterized by mixed semidiurnal tides with strong spring-neap variability, superimposed on a nontidal flow. The product of current speed and thermal driving, both measured approximately 19 m from the ice base, explains 88% of the melt rate variability. Although current speed is the dominant driver of this variability, thermal driving also contributes non-negligibly on spring-neap and longer timescales. The semidiurnal tidal ellipses feature marked vertical variations, transitioning from nearly rectilinear in the mid-water column to more circular and clockwise (CW)-rotating near the ice. This depth-dependence of the semidiurnal tide is attributed to the differential influence of boundary friction on the CW and anticlockwise (ACW) rotary components near the critical latitude (where the tidal frequency equals the Coriolis frequency). A theoretical model, which assumes depth-independent eddy viscosity, successfully reproduces the observed 3-year mean vertical structure of the tidal ellipses. Considering the total tidal current rather than individual constituents, ice base friction damps both the time-mean flow speed and the tidal fluctuations, with attenuation varying over the spring-neap cycle, peaking during spring tides. The observed latitude- and time-dependent effects of ice base friction on the barotropic tide are not captured in parameterizations that estimate tide-induced friction velocity by scaling the time-averaged barotropic tidal speed with a constant drag coefficient.
Keywords: Antarktis; Sørishavet; Weddellhavet; glasiologi; hydrografi; isshelf; oseanografi

Abundance and Diversity of Aerobic Anoxygenic Phototrophic Bacteria in Polar Plant Microbiomes - Mäkinen, Emilia A.; Franz, Ole; Ihalainen, Janne A.; Helander, Marjo; Nissinen, Riitta; Mathew, Suni A.; Saloniemi, Irma; Saikkonen, Kari (Physiologia Plantarum, 2025)
ABSTRACT Here, we examined the occurrence of plant-associated aerobic anoxygenic phototrophic bacteria (AAPB) across polar regions. Recently found in polar soils and cold-climate plants, AAPBs are photoheterotrophs that rely on environmental organic carbon but capture solar energy via anoxygenic photosynthesis. We revealed the abundance of AAPBs by extracting bacteria from plant tissues and imaging the colonies with bacteriochlorophyll-based near-infrared fluorescence. The taxonomic distribution of AAPBs was determined via 16S rRNA gene analysis. From the northern hemisphere, we describe AAPBs from the leaf endo- and phyllospheres of numerous sub- and Arctic plant species in Northern Finland, Svalbard, and Greenland. In the southern hemisphere, we focused on AAPBs in the root and leaf endospheres and the phyllospheres of Deschampsia antarctica in Chilean Patagonia and maritime Antarctica. Additionally, we describe AAPB from the tissues of several other plant species in Patagonia. We found AAPBs commonly associated with the sampled plant species across both hemispheres. A diversity of Alphaproteobacteria was found to contain the AAP capability: at all sampling sites, Sphingomonas was the most abundant taxon (up to 60%), while Methylobacteria made up a notable proportion of sub-Arctic and sub-Antarctic AAPB samples (up to 32%). In contrast to previous studies describing Methylobacteria frequently in various plant communities, AAP-containing Methylobacteria were virtually absent from our high-latitude sites. With diverse AAPB taxa found ubiquitously across polar regions and plant tissues, our results call attention to the potential ecological interaction between AAPBs and their plant hosts.
Keywords: Antarktis; biodiversitet; biogeografi; biologi; mikroorganismer; polarområdene

Investigation on morphological and molecular fingerprints of penguin brain using label-free optical imaging and spectroscopic techniques - Bhatt, Sunil; Verma, Ashwani Kumar; Dastidar, Prabir G.; Kumar, Punit; Thapa, Pramila; Jacob, Tony George; Roy, Tara Sankar; Iyengar, Soumya; Kumaran, Senthil; Ahluwalia, Balpreet Singh; Mehta, Dalip Singh (Scientific Reports, 2025)
The morphology and molecular study of the penguin brain are crucial to define its survival in the extreme conditions of Antarctica. The present study focusses on extracting different optical parameters of the penguin brain using label-free optical imaging and spectroscopic techniques. In label-free optical imaging, we have used quantitative phase imaging, which provides morphological information about the neurons in brain tissue, giving the quantitative phase value of 5 to 20 radians corresponding to the 8 µm tissue section. In label-free spectroscopic techniques, we have used autofluorescence and Raman spectroscopy. Autofluorescence spectroscopy provides molecular information about nicotinamide dinucleotide, flavins, lipofuscins, and porphyrins in the brain’s spectral range of 420 nm to 700 nm. Raman spectroscopy provides multiple peaks associated with different molecules in the brain; among them, few signals are observed at approximately 1305 cm−1, 1448 cm−1, and 1661 cm−1, which correspond to vibrational modes indicative of vibrational features within lipids and protein structures, as well as the presence of amide groups within brain tissue constituents. All these techniques provide the microscopic and molecular fingerprint of the penguin brain, which can be useful for understanding penguin’s anatomical, physiological, and social behavior.
Keywords: Antarktis; anatomi; biofysikk; biologi; biomarkører; fysiologi; morfologi; nevrologi; pingviner

The carbon footprint of Antarctic tourism: an update of carbon emissions based on satellite Automatic Identification System (AIS) data - Cajiao, Daniela; Tejedo, Pablo; Aase, Johnny; Benayas, Javier; Vereda, Marisol; Obermann, Anisja; Lamers, Machiel; Amelung, Bas (Journal of Sustainable Tourism, 2025)
Cruise and aircraft operations constitute the primary transportation modes for accessing Antarctica, and both are highly carbon-intensive. Since the first carbon calculations, the number of tourists has increased twentyfold; routes have expanded further south, involving different modalities, activities, and itineraries. This study presents an assessment and discussion of the carbon footprint of Antarctic tourism based on a comprehensive methodology for calculating emissions. We used satellite data to reconstruct vessel itineraries, gathered individual vessels’ engine specifications, and integrated multiple databases to improve accuracy. We analyzed emissions for four tourism modalities, also incorporating their corresponding aircraft emissions. We found that the Cruise-only modality has the lowest emissions, while the Seaborne Ross Sea & Continent modality has the highest emissions per capita. Despite introducing more efficient fuels and the near-total renovation of the Antarctic fleet, emissions have not decreased significantly. This may be attributed to extended journeys and a higher frequency of trips. The significant carbon footprint of Antarctic tourism poses a challenge in the context of the global climate crisis, influencing perceptions of the industry’s environmental image. We expect that this research will contribute to debates on how to manage growth and diversification of tourism if the aim is Antarctica’s conservation.
Keywords: Antarktis; bærekraft; cruiseturisme; karbonavtrykk; menneskelig påvirkning; turisme; utslipp

Editorial: Microplastics and nanoplastics in polar areas: Arctic, Antarctica, and the world’s glaciers - Corami, Fabiana; Iannilli, Valentina; Hallanger, Ingeborg G. (Frontiers in Marine Science, 2025)
Plastic particles are present in biotic and abiotic matrices; hence, plastic pollution is a global issue involving terrestrial and marine fauna and poses a threat to humans. Ocean circulation is a crucial vector of microplastics worldwide. Plastic pollution is among the significant threats to the ocean ecosystem. Studies and papers on plastic pollution in the oceans worldwide have been reported. However, the distribution, characterization, and abundance of micro- and nano plastics in the global ocean still need to be carefully investigated. Once plastics are present in the environment, they denature, degrade, and are more prone to fragmentation. It is well established that large plastic objects and macroplastics fragment into mesoplastics and large microplastics through photodegradation and weathering. Hence microplastics easily break up into fragments <100 µm (small microplastics, SMPs) or even into sub-micrometric particles, the nanoplastics. The small size of these SMPs and nanoplastics allows them to be ingested by different organisms according to their mouthparts’ size. Besides, this fragmentation will enable additives and plasticizers to be released into the environment, where they may pose a threat to biota throughout the trophic web in various ecosystems, e.g., from oceans and soils to glaciers. Micro- and nanoplastics (MNPs) can be transported over long distances, together with the other airborne particles. As a result of long-range transport and short-range transport, airborne MNPs can be carried from worldwide to mountain glaciers; from mid-latitudes, they can reach the very high and very low latitudes, i.e., the Arctic and Antarctica. Due to global climate change, warm ocean streams heavily affect the sea circulation in polar areas, carrying regulated and emerging pollutants, microplastics being among them. In this scenario, polar environments may be significantly enriched by MNPs carried by warmer ocean currents intruding into the polar oceans and those in atmospheric aerosol. MNPs may threaten the sea ice formation and enhance the melting of glaciers. The melting and disappearance of glaciers and the intrusion of warm currents into polar areas are also compounded by the thawing of permafrost, which can release pollutants, including MNPs. This Research Topic aims to study the interconnected pathways of MNPs that are paramount to understanding the global microplastic cycle and how climate change alters polar environments and the rest of the world. Furthermore, we aim to identify bioindicators in marine species, populations, and ecosystems, while acknowledging the interconnectedness of freshwater, terrestrial and atmospheric environments to the polar environment. Research on world glaciers will provide a comprehensive evaluation of the impacts of plastic pollution on the marine polar environment and biota, including impacts on humans.
Keywords: Antarktis; forurensning; isbreer; klimaendringer; mikroplast; miljøgifter; polarområdene; økologi; økosystemer

Antarctic Water Stable Isotopes in the Global Atmospheric Model LMDZ6: From Climatology to Boundary Layer Processes - Dutrievoz, Niels; Agosta, Cécile; Risi, Camille; Vignon, Étienne; Nguyen, Sébastien; Landais, Amaëlle; Fourré, Elise; Leroy-Dos Santos, Christophe; Casado, Mathieu; Masson-Delmotte, Valérie; Jouzel, Jean; Dubos, Thomas; et al. (Journal of Geophysical Research: Atmospheres, 2025)
Observations of water stable isotopes in Antarctic surface snow, precipitation and water vapor are key for improving our understanding of the atmospheric water cycle and past climate reconstructions from ice cores. In this study, we use isotopic observations in Antarctica to assess the skill of the isotope-enabled atmospheric general circulation model LMDZ6, nudged to ERA5 above the boundary layer (1980?2023 period). The model has no significant bias for time-mean temperature and snow accumulation over the ice sheet. Sensitivity test on parameterized supersaturation strength highlights its opposite effect on precipitation ${δ }^{18}$O and d-excess. Selecting an intermediate supersaturation strength resulted in a minimal bias for surface snow ${δ }^{18}$O across the continent, with a reduced but systematic positive bias in surface snow d-excess ( ${\sim} $5?). We then assessed seasonal and diurnal isotope variability with daily precipitation and continuous vapor isotopes at Dumont d?Urville (DDU, coastal station) and Concordia (inland station). On a seasonal scale, LMDZ6iso accurately reproduces the seasonal cycle of precipitation ${δ }^{18}$O and d-excess at both stations. Moving from statistical evaluation to physical analysis, we use the individual process contributions to boundary-layer water vapor isotopes to identify the main drivers controlling the clear-sky isotopic daily cycles. At Concordia, daily isotope variations are mainly driven by surface sublimation, whereas at DDU they are driven by surface sublimation and advection by the katabatic flow. Our results suggest that to further improve water isotopes in LMDZ6iso, fractionation during surface sublimation should be included and fractionation at condensation for low temperature should be better constrained.
Keywords: Antarktis; global klimamodell; iskjerner; klimamodeller; klimatologi; meteorologi; paleoklimatologi; vannstabile isotoper

Using a multi-layer snow model for transient paleo-studies: surface mass balance evolution during the Last Interglacial - Hoang, Thi-Khanh-Dieu; Quiquet, Aurélien; Dumas, Christophe; Born, Andreas; Roche, Didier M. (Clim. Past, 2025)
During the Quaternary, ice sheets experienced several retreat–advance cycles, strongly influencing climate patterns. In order to properly simulate these phenomena, it is preferable to use physics-based models instead of parameterizations to estimate the surface mass balance (SMB), which strongly influences the evolution of the ice sheet. To further investigate the potential of these SMB models, this work evaluates the BErgen Snow SImulator (BESSI), a multi-layer snow model with high computational efficiency, as an alternative to providing the SMB for the Earth system model iLOVECLIM for multi-millennial simulations as in paleostudies. We compare the behaviors of BESSI and insolation temperature melt (ITM), an existing SMB scheme of iLOVECLIM during the Last Interglacial (LIG). Firstly, we validate the two SMB models using the regional climate model Mod- èle Atmosphérique Régional (MAR) as forcing and reference for the present-day climate over the Greenland and Antarctic ice sheets. The evolution of the SMB over the LIG (130–116 ka) is computed by forcing BESSI and ITM with transient climate forcing obtained from iLOVECLIM for both ice sheets. For present-day climate conditions, both BESSI and ITM exhibit good performance compared to MAR despite a much simpler model setup. While BESSI performs well for both Antarctica and Greenland for the same set of parame- ters, the ITM parameters need to be adapted specifically for each ice sheet. This suggests that the physics embedded in BESSI allows better capture of SMB changes across varying climate conditions, while ITM displays a much stronger sen- sitivity to its tunable parameters. The findings suggest that BESSI can provide more reliable SMB estimations for the iLOVECLIM framework to improve the model simulations of the ice sheet evolution and interactions with climate for multi-millennial simulations.
Keywords: Antarktis; innlandsis; klimamodeller; paleoklimatologi; polarområdene

Unmanned Aerial Vehicles for Real-Time Vegetation Monitoring in Antarctica: A Review - Lockhart, Kaelan; Sandino, Juan; Amarasingam, Narmilan; Hann, Richard; Bollard, Barbara; Gonzalez, Felipe (Remote Sensing, 2025)
The unique challenges of polar ecosystems, coupled with the necessity for high-precision data, make Unmanned Aerial Vehicles (UAVs) an ideal tool for vegetation monitoring and conservation studies in Antarctica. This review draws on existing studies on Antarctic UAV vegetation mapping, focusing on their methodologies, including surveyed locations, flight guidelines, UAV specifications, sensor technologies, data processing techniques, and the use of vegetation indices. Despite the potential of established Machine-Learning (ML) classifiers such as Random Forest, K Nearest Neighbour, and Support Vector Machine, and gradient boosting in the semantic segmentation of UAV-captured images, there is a notable scarcity of research employing Deep Learning (DL) models in these extreme environments. While initial studies suggest that DL models could match or surpass the performance of established classifiers, even on small datasets, the integration of these advanced models into real-time navigation systems on UAVs remains underexplored. This paper evaluates the feasibility of deploying UAVs equipped with adaptive path-planning and real-time semantic segmentation capabilities, which could significantly enhance the efficiency and safety of mapping missions in Antarctica. This review discusses the technological and logistical constraints observed in previous studies and proposes directions for future research to optimise autonomous drone operations in harsh polar conditions.
Keywords: Antarktis; droner; dyp læring; fjernmåling; kartlegging; kunstig intelligens (KI); kybernetikk; maskinlæring; teknologi; vegetasjon

Evaluating Cloud Properties at Scott Base: Comparing Ceilometer Observations With ERA5, JRA55, and MERRA2 Reanalyses Using an Instrument Simulator - McDonald, Adrian J.; Kuma, Peter; Panell, M.; Petterson, Orlon K. L.; Plank, Graeme E.; Rozliaiani, M. A. H.; Whitehead, Luke E. (Journal of Geophysical Research: Atmospheres, 2025)
This study compares CL51 ceilometer observations made at Scott Base, Antarctica, with statistics from the ERA5, JRA55, and MERRA2 reanalyses. To enhance the comparison we use a lidar instrument simulator to derive cloud statistics from the reanalyses which account for instrumental factors. The cloud occurrence in the three reanalyses is slightly overestimated above 3 km, but displays a larger underestimation below 3 km relative to observations. Unlike previous studies, we see no relationship between relative humidity and cloud occurrence biases, suggesting that the cloud biases do not result from the representation of moisture. We also show that the seasonal variation of cloud occurrence and cloud fraction, defined as the vertically integrated cloud occurrence, are small in both the observations and the reanalyses. We also examine the quality of the cloud representation for a set of weather states derived from ERA5 surface winds. The variability associated with grouping cloud occurrence based on weather state is much larger than the seasonal variation, highlighting weather state is a strong control of cloud occurrence. All the reanalyses continue to display underestimates below 3 km and overestimates above 3 km for each weather state. But the variability in ERA5 statistics matches the changes in the observations better than the other reanalyses. We also use a machine learning scheme to estimate the quantity of supercooled liquid water cloud from the ceilometer observations. Ceilometer low-level supercooled liquid water cloud occurrences are considerably larger than values derived from the reanalyses, further highlighting the poor representation of low-level clouds in the reanalyses.
Keywords: Antarktis; dataanalyse; forskningsstasjoner; meteorologi

Multi-model assessment of the deglacial climatic evolution at high southern latitudes - Obase, T.; Menviel, L.; Abe-Ouchi, A.; Vadsaria, T.; Ivanovic, R.; Snoll, B.; Sherriff-Tadano, S.; Valdes, P. J.; Gregoire, L.; Kapsch, M.-L.; Mikolajewicz, U.; Bouttes, N.; et al. (Climate of the Past, 2025)
The Quaternary climate is characterized by glacial–interglacial cycles, with the most recent transition from the last glacial maximum to the present interglacial (the last deglaciation) occurring between ∼ 21 and 9 ka. While the deglacial warming at high southern latitudes is mostly in phase with atmospheric CO2 concentrations, some proxy records indicate that the onset of the warming occurred before the CO2 increase. In addition, high southern latitudes exhibit a cooling event in the middle of the deglaciation (15–13 ka) known as the “Antarctic Cold Reversal”. In this study, we analyse transient simulations of the last deglaciation performed with six different climate models as part of the 4th phase of the Paleoclimate Modelling Intercomparison Project (PMIP4) to understand the processes driving high-southern-latitude surface temperature changes. As the protocol of the last deglaciation sets the choice of freshwater forcing as flexible, the freshwater forcing is different in each model, thus complicating the multi-model comparison. While proxy records from West Antarctica and the Pacific sector of the Southern Ocean suggest the presence of an early warming before 18 ka, only half the models show a significant warming at this time (∼ 1 °C or ∼ 10 % of the total deglacial warming). All models simulate a major warming during Heinrich Stadial 1 (18–15 ka), concurrent with the CO2 increase and with a weakening of the Atlantic Meridional Overturning Circulation (AMOC) in some models. However, the simulated Heinrich Stadial 1 warming over Antarctica is smaller than the one suggested from ice core data. During the Antarctic Cold Reversal, simulations with an abrupt AMOC strengthening exhibit a high-southern-latitude cooling of 1 to 2 °C, in relative agreement with proxy records, while simulations with rapid North Atlantic meltwater input exhibit a warming. Using simple models to extract the relative AMOC contribution, we find that all climate models simulate a high-southern-latitude cooling in response to an AMOC increase with a response timescale of several hundred years, suggesting the choice of the North Atlantic meltwater forcing substantially affects high-southern-latitude temperature changes. Thus, further work needs to be carried out to reconcile the deglacial AMOC evolution with the Northern Hemisphere ice sheet disintegration and associated meltwater input. Finally, all simulations exhibit only minimal changes in Southern Hemisphere westerlies and Southern Ocean meridional circulation during the last deglaciation. Improved understanding of the processes impacting Southern Hemisphere atmospheric and oceanic circulation changes accounting for deglacial atmospheric CO2 increase is needed.
Keywords: Antarktis; Sørishavet; deglasiasjon; klimamodeller; paleoklimatologi

Surface processes and drivers of the snow water stable isotopic composition at Dome C, East Antarctica – a multi-dataset and modelling analysis - Ollivier, I.; Steen-Larsen, H. C.; Stenni, B.; Arnaud, L.; Casado, M.; Cauquoin, A.; Dreossi, G.; Genthon, C.; Minster, B.; Picard, G.; Werner, M.; Landais, A. (The Cryosphere, 2025)
Water stable isotope records in polar ice cores have been largely used to reconstruct past local temperatures and other climatic information such as evaporative source region conditions of the precipitation reaching the ice core sites. However, recent studies have identified post-depositional processes taking place at the ice sheet's surface, modifying the original precipitation signal and challenging the traditional interpretation of ice core isotopic records. In this study, we use a combination of existing and new datasets of precipitation, snow surface, and subsurface isotopic compositions (δ18O and deuterium excess (d-excess)); meteorological parameters; ERA5 reanalyses; outputs from the isotope-enabled climate model ECHAM6-wiso; and a simple modelling approach to investigate the transfer function of water stable isotopes from precipitation to the snow surface and subsurface at Dome C in East Antarctica. We first show that water vapour fluxes at the surface of the ice sheet result in a net annual sublimation of snow, from 3.1 to 3.7 mm w.e. yr−1 (water equivalent) between 2018 and 2020, corresponding to 12 % to 15 % of the annual surface mass balance. We find that the precipitation isotopic signal cannot fully explain the mean, nor the variability in the isotopic composition observed in the snow, from annual to intra-monthly timescales. We observe that the mean effect of post-depositional processes over the study period enriches the snow surface in δ18O by 3.0 ‰ to 3.3 ‰ and lowers the snow surface d-excess by 3.4 ‰ to 3.5 ‰ compared to the incoming precipitation isotopic signal. We also show that the mean isotopic composition of the snow subsurface is not statistically different from that of the snow surface, indicating the preservation of the mean isotopic composition of the snow surface in the top centimetres of the snowpack. This study confirms previous findings about the complex interpretation of the water stable isotopic signal in the snow and provides the first quantitative estimation of the impact of post-depositional processes on the snow isotopic composition at Dome C, a crucial step for the accurate interpretation of isotopic records from ice cores.
Keywords: Antarktis; fysisk geografi; geologi; klimamodeller; kryosfæren; paleoklimatologi

Advances and shortfalls in knowledge of Antarctic terrestrial and freshwater biodiversity - Pertierra, L. R.; Convey, P.; Barbosa, A.; Biersma, E. M.; Cowan, D.; Diniz-Filho, J. A. F.; de los Ríos, A.; Escribano-Álvarez, P.; Fraser, C. I.; Fontaneto, D.; Greve, M.; Griffiths, H. J.; et al. (Science, 2025)
Antarctica harbors many distinctive features of life, yet much about the diversity and functioning of Antarctica?s life remains unknown. Evolutionary histories and functional ecology are well understood only for vertebrates, whereas research on invertebrates is largely limited to species descriptions and some studies on environmental tolerances. Knowledge on Antarctic vegetation cover showcases the challenges of characterizing population trends for most groups. Recent community-level microbial studies have provided insights into the functioning of life at its limits. Overall, biotic interactions remain largely unknown across all groups, restricted to basic information on trophic level placement. Insufficient knowledge of many groups limits the understanding of ecological processes on the continent. Remedies for the current situation rely on identifying the caveats of each ecological discipline and finding targeted solutions. Such precise delimitation of knowledge gaps will enable a more aware, representative, and strategic systematic conservation planning of Antarctica.
Keywords: Antarktis; biodiversitet; biogeografi; biologi; biomonitorering; mikroorganismer; økologi; økosystemer

Bedmap3 updated ice bed, surface and thickness gridded datasets for Antarctica - Pritchard, Hamish D.; Fretwell, Peter T.; Fremand, Alice C.; Bodart, Julien A.; Kirkham, James D.; Aitken, Alan; Bamber, Jonathan; Bell, Robin; Bianchi, Cesidio; Bingham, Robert G.; Blankenship, Donald D.; Casassa, Gino; et al. (Scientific Data, 2025)
We present Bedmap3, the latest suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of the Antarctic south of 60 °S. Bedmap3 incorporates and adds to all post-1950s datasets previously used for Bedmap2, including 84 new aero-geophysical surveys by 15 data providers, an additional 52 million data points and 1.9 million line-kilometres of measurement. These efforts have filled notable gaps including in major mountain ranges and the deep interior of East Antarctica, along West Antarctic coastlines and on the Antarctic Peninsula. Our new Bedmap3/RINGS grounding line similarly consolidates multiple recent mappings into a single, spatially coherent feature. Combined with updated maps of surface topography, ice shelf thickness, rock outcrops and bathymetry, Bedmap3 reveals in much greater detail the subglacial landscape and distribution of Antarctica’s ice, providing new opportunities to interpret continental-scale landscape evolution and to model the past and future evolution of the Antarctic ice sheets.
Keywords: Antarktis; geofysikk; geomorfologi; glasiologi; hydrologi; oseanografi

Surface darkening by abundant and diverse algae on an Antarctic ice cap - Thomson, Alex Innes; Gray, Andrew; Colesie, Claudia; Thomas, Naomi; Moulton, Hannah; Convey, Peter; Smith, Alison G.; Fretwell, Peter; Peck, Lloyd; Davey, Matthew P. (Nature Communications, 2025)
Algal blooms play important roles in physical and biological processes on glacial surfaces. Despite this, their occurrence and impacts within an Antarctic context remain understudied. Here, we present evidence of the large-scale presence, diversity and bioalbedo effects of algal blooms on Antarctic ice cap systems based on fieldwork conducted on Robert Island (South Shetland Islands, Antarctica). Algal blooms are observed covering up to 2.7 km2 (~20%) of the measured area of the Robert Island ice cap, with cell densities of up to 1.4 × 106 cells ml−1. Spectral characterisation reveal that these blooms increase melting of the ice cap surface, contributing up to 2.4% of total melt under the observed conditions. Blooms are composed of typical cryoflora taxa, dominated by co-occurring Chlorophyceae, Trebouxiophyceae, and Ancylonema. However, morphological variation and genetic diversity in Ancylonema highlight the influence of regional endemism and point to a large and under-characterised diversity in Antarctic cryoflora.
Keywords: Antarktis; Sør-Shetlandsøyene; biogeografi; biologi; kryosfæren; snøalger; økologi

Community estimate of global glacier mass changes from 2000 to 2023 - Zemp, Michael; Jakob, Livia; Dussaillant, Inés; Nussbaumer, Samuel U.; Gourmelen, Noel; Dubber, Sophie; A, Geruo; Abdullahi, Sahra; Andreassen, Liss Marie; Berthier, Etienne; Bhattacharya, Atanu; Blazquez, Alejandro; et al. (Nature, 2025)
Glaciers are indicators of ongoing anthropogenic climate change1. Their melting leads to increased local geohazards2, and impacts marine3 and terrestrial4,5 ecosystems, regional freshwater resources6, and both global water and energy cycles7,8. Together with the Greenland and Antarctic ice sheets, glaciers are essential drivers of present9,10 and future11–13 sea-level rise. Previous assessments of global glacier mass changes have been hampered by spatial and temporal limitations and the heterogeneity of existing data series14–16. Here we show in an intercomparison exercise that glaciers worldwide lost 273 ± 16 gigatonnes in mass annually from 2000 to 2023, with an increase of 36 ± 10% from the first (2000–2011) to the second (2012–2023) half of the period. Since 2000, glaciers have lost between 2% and 39% of their ice regionally and about 5% globally. Glacier mass loss is about 18% larger than the loss from the Greenland Ice Sheet and more than twice that from the Antarctic Ice Sheet17. Our results arise from a scientific community effort to collect, homogenize, combine and analyse glacier mass changes from in situ and remote-sensing observations. Although our estimates are in agreement with findings from previous assessments14–16 at a global scale, we found some large regional deviations owing to systematic differences among observation methods. Our results provide a refined baseline for better understanding observational differences and for calibrating model ensembles12,16,18, which will help to narrow projection uncertainty for the twenty-first century11,12,18.
Keywords: Antarktis; fjernmåling; glasiologi; havnivåstigning; hydrologi; isbreer; klimaendringer; kryosfæren; polarområdene

Global biochemical profiling of fast-growing Antarctic bacteria isolated from meltwater ponds by high-throughput FTIR spectroscopy - Akulava, Volha; Tafintseva, Valeria; Blazhko, Uladzislau; Kohler, Achim; Miamin, Uladzislau; Valentovich, Leonid; Shapaval, Volha (PLOS ONE, 2024)
Fourier transform infrared (FTIR) spectroscopy is a biophysical technique used for non-destructive biochemical profiling of biological samples. It can provide comprehensive information about the total cellular biochemical profile of microbial cells. In this study, FTIR spectroscopy was used to perform biochemical characterization of twenty-nine bacterial strains isolated from the Antarctic meltwater ponds. The bacteria were grown on two forms of brain heart infusion (BHI) medium: agar at six different temperatures (4, 10, 18, 25, 30, and 37°C) and on broth at 18°C. Multivariate data analysis approaches such as principal component analysis (PCA) and correlation analysis were used to study the difference in biochemical profiles induced by the cultivation conditions. The observed results indicated a strong correlation between FTIR spectra and the phylogenetic relationships among the studied bacteria. The most accurate taxonomy-aligned clustering was achieved with bacteria cultivated on agar. Cultivation on two forms of BHI medium provided biochemically different bacterial biomass. The impact of temperature on the total cellular biochemical profile of the studied bacteria was species-specific, however, similarly for all bacteria, lipid spectral region was the least affected while polysaccharide region was the most affected by different temperatures. The biggest temperature-triggered changes of the cell chemistry were detected for bacteria with a wide temperature tolerance such Pseudomonas lundensis strains and Acinetobacter lwoffii BIM B-1558.
Keywords: Antarktis; bakterier; biokjemi; mikrobielle organismer; mikrobiologi

Outlining three arguments for Rights of Antarctica - Baard, Patrik; Mancilla, Alejandra (The Polar Journal, 2024)
In this article, we investigate three arguments for Rights of Antarctica (RoA), understood as recognising the whole continent as a rights-holder with legal standing. For this, we draw inspiration from the Antarctica Declaration, a text developed by an interdisciplinary and international group of scholars and activists. We scrutinise three justifications that could potentially be used in support of RoA. First, we investigate whether arguments for Rights of Nature (RoN) elsewhere can support RoA. RoN has been accepted in several domestic legislations. Unfortunately, we discover important disanalogies between RoA and RoN, defeating the purpose of justifying RoA with reference to RoN. Second, we scrutinise potential arguments that focus on giving rights to specific Antarctic ecoregions or places. However, such arguments would only cover parts of the continent, thus going against the holistic approach of RoA, and they would require using a broader understanding of ?attachments? as grounds for justifying rights for parts of Antarctica. In contrast, we construct an argument for accepting RoA based on four components: (1) Antarctica?s intrinsic value, (2) wider forms of human attachments, (3) Antarctica?s substantial role as a global systemic resource, and (4) the fact that Antarctica is under recurrent and substantial threats. While none of these are individually sufficient for recognising RoA, they can jointly make RoA appropriate. We conclude that it remains an open question whether international law or, more specifically, the Antarctic Treaty, would be open to such conceptual and normative innovation, adopting a new paradigm in our treatment of the nonhuman natural world. At the same time, we hope to kickstart a discussion of what RoA would require and how it should relate more generally to RoN discourses.
Keywords: Antarktis; Antarktistraktaten; jus

A virtual geobibliography of polar tourism and climate change - Demiroglu, O. Cenk; Bohn, Dorothee; Dannevig, Halvor; Hall, C. Michael; Hehir, Christy; Lundmark, Linda; Nilsson, Robert O.; Olsen, Julia; Tervo-Kankare, Kaarina; Vereda, Marisol; Welling, Johannes (Journal of Sustainable Tourism, 2024)
The polar regions are increasingly at the center of attention as the hot spots of climate crisis as well as tourism development. The recent IPCC reports highlight several climate change risks for the rather carbon-intensive and weather-based/dependent polar tourism industry in the Arctic and the Antarctic. This study presents the scholarly state-of-knowledge on tourism and climate change in the polar regions with a literature survey extending beyond the Anglophone publications. As a supporting tool, we provide a live web GIS application based on the geographical coverages of the publications and filterable by various spatial, thematic and bibliographical attributes. The final list of 137 publications indicates that, regionally, the Arctic has been covered more than the Antarctic, whilst an uneven distribution within the Arctic also exists. In terms of the climate change risks themes, climate risk research, i.e. impact and adaptation studies, strongly outnumbers the carbon risk studies especially in the Arctic context, and, despite a balance between the two main risk themes, climate risk research in the Antarctic proves itself outdated. Accordingly, the review ends with a research agenda based on these spatial and thematic gaps and their detailed breakdowns.
Keywords: Antarktis; bibliografi; geobibliografi; klimaendringer; polarområdene; turisme

Early aerial expedition photos reveal 85 years of glacier growth and stability in East Antarctica - Dømgaard, Mads; Schomacker, Anders; Isaksson, Elisabeth; Millan, Romain; Huiban, Flora; Dehecq, Amaury; Fleischer, Amanda; Moholdt, Geir; Andersen, Jonas K.; Bjørk, Anders A. (Nature Communications, 2024)
During the last few decades, several sectors in Antarctica have transitioned from glacial mass balance equilibrium to mass loss. In order to determine if recent trends exceed the scale of natural variability, long-term observations are vital. Here we explore the earliest, large-scale, aerial image archive of Antarctica to provide a unique record of 21 outlet glaciers along the coastline of East Antarctica since the 1930s. In Lützow-Holm Bay, our results reveal constant ice surface elevations since the 1930s, and indications of a weakening of local land-fast sea-ice conditions. Along the coastline of Kemp and Mac Robertson, and Ingrid Christensen Coast, we observe a long-term moderate thickening of the glaciers since 1937 and 1960 with periodic thinning and decadal variability. In all regions, the long-term changes in ice thickness correspond with the trends in snowfall since 1940. Our results demonstrate that the stability and growth in ice elevations observed in terrestrial basins over the past few decades are part of a trend spanning at least a century, and highlight the importance of understanding long-term changes when interpreting current dynamics.
Keywords: Antarktis; Thorshavn ekspedisjon; flyfotografering; geografi; glasiologi; kartlegging; klimaendringer; klimatologi; kryosfæren; topografi

Conjugate aurora observations by the Gjøa and Discovery expeditions - Egeland, Alv (Hist. Geo Space. Sci., 2024)
From 1901 to 1912 – known as the “heroic period” of Arctic and Antarctic exploration – great inroads were made (not only geographic but also scientific) to our knowledge of the continent. At Amundsen's Expedition through the Northwest Passage, measurements of the geomagnetic field and visual auroras were carried out for 19 months at Gjoa Haven (Gjøahavn in Norwegian; geographic coordinates 68°37′10′′ N, 95°53′25′′ W). Scott's Discovery Expedition – at Cape Armitage, McMurdo (coordinates 77.86° S, 166.69° E), Antarctica – carried out the same type of measurements. Their observations were carried out geomagnetically conjugate to Gjoa Haven, with both stations close to 78° magnetic latitude. In addition, measurements were overlapping in time during 1903–1904. However, these two stations are located at different longitudes, so there is a difference in local time between the stations of about 6.5 h. Gjoa Haven and Cape Armitage are conveniently located for separating disturbances in the polar cap regions caused by solar electromagnetic radiations or the solar wind. Auroras were observed during 7 months per year. This gave a unique possibility to compare conjugate characteristics of polar cap auroras. Comparing conjugate geophysical data introduces some difficulties. During the winter season at Gjoa Haven, they had a bright summer in Antarctica, and visa versa. Thus, simultaneous temporal and spatial ionospheric variations can be marked differently. Still, the average diurnal and seasonal variations were similar. The quantity of the auroral data from Cape Armitage was larger because there they had a continuous watch of the sky. The main findings regarding polar cap auroras are the following. Three different auroral forms dominate the polar cap. Low-intensity auroral bands – then called streamers – were the dominating auroral forms morning and afternoon. The number of auroral events in 1903 was nearly twice that in 1902 and 1904. A marked midwinter maximum was observed at both stations. Many displays were observed poleward of the oval. The large fraction was associated with weak magnetic disturbances. Some forms of polar cap aurora have special magnetic signatures and seem to be anti-correlated with Kp. They can be mapped even if they are not seen. According to recent satellite measurements (Newell et al., 2009), they are probably caused by polar rain and/or photoelectrons.
Keywords: Antarktis; Discoveryekspedisjonen; fysikk; polarfarere; polarområdene; romfysikk; sørlys

Short- and long-term variability of the Antarctic and Greenland ice sheets - Hanna, Edward; Topál, Dániel; Box, Jason E.; Buzzard, Sammie; Christie, Frazer D. W.; Hvidberg, Christine; Morlighem, Mathieu; De Santis, Laura; Silvano, Alessandro; Colleoni, Florence; Sasgen, Ingo; Banwell, Alison F.; et al. (Nature Reviews Earth & Environment, 2024)
The variability of the Antarctic and Greenland ice sheets occurs on various timescales and is important for projections of sea level rise; however, there are substantial uncertainties concerning future ice-sheet mass changes. In this Review, we explore the degree to which short-term fluctuations and extreme glaciological events reflect the ice sheets’ long-term evolution and response to ongoing climate change. Short-term (decadal or shorter) variations in atmospheric or oceanic conditions can trigger amplifying feedbacks that increase the sensitivity of ice sheets to climate change. For example, variability in ocean-induced and atmosphere-induced melting can trigger ice thinning, retreat and/or collapse of ice shelves, grounding-line retreat, and ice flow acceleration. The Antarctic Ice Sheet is especially prone to increased melting and ice sheet collapse from warm ocean currents, which could be accentuated with increased climate variability. In Greenland both high and low melt anomalies have been observed since 2012, highlighting the influence of increased interannual climate variability on extreme glaciological events and ice sheet evolution. Failing to adequately account for such variability can result in biased projections of multi-decadal ice mass loss. Therefore, future research should aim to improve climate and ocean observations and models, and develop sophisticated ice sheet models that are directly constrained by observational records and can capture ice dynamical changes across various timescales.
Keywords: Antarktis; glasiologi; innlandsis; klimaendringer; polarområdene

The Use of Weather, Water, Ice, and Climate (WWIC) Information in the Polar Regions: What Is Known after the Decadelong Polar Prediction Project? - Heinrich, Victoria J.; Stewart, Emma J.; Liggett, Daniela; Carrasco, Jorge F.; Dawson, Jackie; Lamers, Machiel; Ljubicic, Gita J.; Jeuring, Jelmer; Thoman, Rick (Weather, Climate, and Society, 2024)
The polar regions are facing a wide range of compounding challenges, from climate change to increased human activity. Infrastructure, rescue services, and disaster response capabilities are limited in these remote environments. Relevant and usable weather, water, ice, and climate (WWIC) information is vital for safety, activity success, adaptation, and environmental protection. This has been a key focus for the World Meteorological Organization’s (WMO) Polar Prediction Project (PPP), and in particular its “Societal and Economic Research and Applications” (PPP-SERA) Task Team, which together over a decade have sought to understand polar WWIC information use in relation to operational needs, constraints, and decision contexts to inform the development of relevant services. To understand research progress and gaps on WWIC information use during the PPP (2013–23), we undertook a systematic bibliometric review of aligned scholarly peer-reviewed journal articles (n = 43), examining collaborations, topics, methods, and regional differences. Themes to emerge included activity and context, human factors, information needs, situational awareness, experience, local and Indigenous knowledge, and sharing of information. We observed an uneven representation of disciplinary backgrounds, geographic locations, research topics, and sectoral foci. Our review signifies an overall lack of Antarctic WWIC services research and a dominant focus on Arctic sea ice operations and risks. We noted with concern a mismatch between user needs and services provided. Our findings can help to improve WWIC services’ dissemination, communication effectiveness, and actionable knowledge provision for users and guide future research as the critical need for salient weather services across the polar regions remains beyond the PPP. Significance Statement Every day, people in the Arctic and Antarctic use weather, water, ice, and climate information to plan and carry out outdoor activities and operations in a safe way. Despite advances in numerical weather prediction, technology, and product development, barriers to accessing and effectively communicating high-quality usable observations, forecasts, and actionable knowledge remain. Poorer services, prediction accuracy, and interpretation are exacerbated by a lack of integrated social science research on relevant topics and a mismatch between the services provided and user needs. As a result, continued user engagement, research focusing on information use, risk communication, decision-making processes, and the application of science for services remain highly relevant to reducing risks and improving safety for people living, visiting, and working in the polar regions.
Keywords: Antarktis; klimaendringer; klimatologi; meteorologi; polarområdene

Arctic copepod copper sensitivity and comparison with Antarctic and temperate copepods - Heuschele, Jan; Dinh, Khuong V.; Lode, Torben; Jager, Tjalling; Borgå, Katrine (Ecotoxicology, 2024)
The ongoing global climate crisis increases temperatures in polar regions faster and with greater magnitude than elsewhere. The decline of Arctic sea ice opens up new passages, eventually leading to higher anthropogenic activities such as shipping, fishing, and mining. Climate change and anthropogenic activities will increase contaminant transport from temperate to Arctic regions. The shipping industry uses copper as an antifouling coating. Copper is an essential element but becomes toxic at excess concentrations, and its use may inadvertently affect non-target organisms such as copepods. Copper affects copepods by lowering reproductive output, prolonging developmental time, and causing increased mortality. As data on copper sensitivity of polar copepods at low temperatures are rare, we conducted onboard survival experiments with the Arctic region’s most common copepod species (Calanus finmarchicus, C. glacialis, C. hyperboreus). Acute survival tests were done for up to 8 days on individuals in 70 ml bottles at 1 °C with nominal copper concentrations ranging from 3 to 480 μg L−1. We used a reduced General Unified Threshold model for Survival (GUTS) to analyse the data, and placed our results in the context of the few published copper sensitivity data of the Antarctic and temperate copepod species at low temperatures. The sensitivity of Cu exposure was similar between the three Calanus species. However, a model comparison suggests that the tested C. glacialis population is less sensitive than the other two species in our experiments. Compared to published data, the three Arctic species appear slightly less sensitive to copper compared to their Antarctic counterparts but more compared to their temperate ones. Our literature search revealed only a few available studies on the copper sensitivity of polar copepods. In the future, this species group will be exposed to more pollutants, which warrants more studies to predict potential risks, especially given possible interactions with environmental factors.
Keywords: Antarktis; copepoder; forurensning; hoppekreps; klimaendringer; marin biologi; miljøgifter; polarområdene; økotoksikologi

Ocean warming as a trigger for irreversible retreat of the Antarctic ice sheet - Hill, Emily A.; Gudmundsson, G. Hilmar; Chandler, David M. (Nature Climate Change, 2024)
Warmer ocean conditions could impact future ice loss from Antarctica due to their ability to thin and reduce the buttressing of laterally confined ice shelves. Previous studies highlight the potential for a cold to warm ocean regime shift within the sub-shelf cavities of the two largest Antarctic ice shelves—the Filchner–Ronne and Ross. However, how this impacts upstream ice flow and mass loss has not been quantified. Here using an ice sheet model and an ensemble of ocean-circulation model sub-shelf melt rates, we show that transition to a warm state in those ice shelf cavities leads to a destabilization and irreversible grounding line retreat in some locations. Once this ocean shift takes place, ice loss from the Filchner–Ronne and Ross catchments is greatly accelerated, and conditions begin to resemble those of the present-day Amundsen Sea sector—responsible for most current observed Antarctic ice loss—where this thermal shift has already occurred.
Keywords: Amundsenhavet; Antarktis; Sørishavet; global oppvarming; innlandsis; klimaendringer; klimatologi

The case for a Framework for UnderStanding Ice-Ocean iNteractions (FUSION) in the Antarctic-Southern Ocean system - McCormack, Felicity S.; Cook, Sue; Goldberg, Daniel N.; Nakayama, Yoshihiro; Seroussi, Hélène; Nias, Isabel; An, Lu; Slater, Donald; Hattermann, Tore (Elementa: Science of the Anthropocene, 2024)
We are in a period of rapidly accelerating change across the Antarctic continent and Southern Ocean, with land ice loss leading to sea level rise and multiple other climate impacts. The ice-ocean interactions that dominate the current ice loss signal are a key underdeveloped area of knowledge. The paucity of direct and continuous observations leads to high uncertainty in the glaciological, oceanographic and atmospheric fields required to constrain ice-ocean interactions, and there is a lack of standardised protocols for reconciling observations across different platforms and technologies and modelled outputs. Funding to support observational campaigns is under increasing pressure, including for long-term, internationally coordinated monitoring plans for the Antarctic continent and Southern Ocean. In this Practice Bridge article, we outline research priorities highlighted by the international ice-ocean community and propose the development of a Framework for UnderStanding Ice-Ocean iNteractions (FUSION), using a combined observational-modelling approach, to address these issues. Finally, we propose an implementation plan for putting FUSION into practice by focusing first on an essential variable in ice-ocean interactions: ocean-driven ice shelf melt.
Keywords: Antarktis; Sørishavet; glasiologi; innlandsis; klimamodeller; klimatologi; oseanografi

Antarctic Blue Ice Areas are hydrologically active, nutrient rich and contain microbially diverse cryoconite holes - Nowak, Aga; Isaksson, Elisabeth; Sunde, Øyvind; Elvevold, Synnøve; Sandven, Håkon; Moholdt, Geir; Hudson, Stephen R.; Urset, Anne; Edwards, Arwyn; Rassner, Sara M. E.; Pearce, David; Hamre, Børge; et al. (Communications Earth & Environment, 2024)
Antarctica is the coldest, windiest and least inhabited place on Earth. One of its most enigmatic regions is scoured by katabatic winds blue ice that covers 235,000 km2 of the Antarctic fringe. Here, we demonstrate that contrary to common belief, high-altitude inland blue ice areas are not dry, nor barren. Instead, they promote sub-surface melting that enables them to become “powerplants” for water, nutrients, carbon and major ions production. Mapping cryoconite holes at an unprecedented scale of 62 km2 also revealed a regionally significant resource of dissolved nitrogen, phosphorus (420 kg km−2), dissolved carbon (1323 kg km−2), and major ions (6672 kg km−2). We discovered that unlike on glaciers, creation of cryoconite holes and their chemical signature on the ice sheet is governed by ice movement and bedrock geology. Blue ice areas are near-surface hotspots of microbial life within cryoconite holes. Bacterial communities they support are unexpectedly diverse. We also show that near-surface aquifers can exist in blue ice outside cryoconite holes. Identifying blue ice areas as active ice sheet ecosystems will help us understand the role ice sheets play in Antarctic carbon cycle, development of near-surface drainage system, and will expand our perception of the limits of life.
Keywords: Antarktis; biogeokjemi; geografi; geologi; mikrobielle organismer; mikrobiologi

The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi

TerrANTALife 1.0 Biodiversity data checklist of known Antarctic terrestrial and freshwater life forms - Pertierra, Luis R.; Varliero, Gilda; Barbosa, Andrés; Biersma, Elisabeth M.; Convey, Peter; Chown, Steven L.; Cowan, Don; De Los Rios, Asunción; Escribano-Alvarez, Pablo; Fontaneto, Diego; Fraser, Ceridwen; Harris, Mathew; et al. (Biodiversity Data Journal, 2024)
Incomplete species inventories for Antarctica represent a key challenge for comprehensive ecological research and conservation in the region. Additionally, data required to understand population dynamics, rates of evolution, spatial ranges, functional traits, physiological tolerances and species interactions, all of which are fundamental to disentangle the different functional elements of Antarctic biodiversity, are mostly missing. However, much of the fauna, flora and microbiota in the emerged ice-free land of the continent have an uncertain presence and/or unresolved status, with entire biodiversity compendia of prokaryotic groups (e.g. bacteria) being missing. All the available biodiversity information requires consolidation, cross-validation, re-assessment and steady systematic inclusion in order to create a robust catalogue of biodiversity for the continent.We compiled, completed and revised eukaryotic species inventories present in terrestrial and freshwater ecosystems in Antarctica in a new living database: terrANTALife (version 1.0). The database includes the first integration in a compendium for many groups of eukaryotic microorganisms. We also introduce a first catalogue of amplicon sequence variants (ASVs) of prokaryotic biodiversity. Available compendia and literature to date were searched for Antarctic terrestrial and freshwater species, integrated, taxonomically harmonised and curated by experts to create comprehensive checklists of Antarctic organisms. The final inventories comprises 470 animal species (including vertebrates, free-living invertebrates and parasites), 306 plants (including all Viridiplantae: embryophytes and green algae), 997 fungal species and 434 protists (sensu lato). We also provide a first account for many groups of microorganisms, including non-lichenised fungi and multiple groups of eukaryotic unicellular species (Stramenophila, Alveolata and Rhizaria (SAR), Chromists and Amoeba), jointly referred to as "protists". In addition, we identify 1753 bacterial (obtained from 348117 ASVs) and 34 archaeal genera (from 1848 ASVs), as well as, at least, 14 virus families. We formulate a basic tree of life in Antarctica with the main lineages listed in the region and their “known-accepted-species” numbers.
Keywords: Antarktis; Sørishavet; biodiversitet; database; fauna; flora; mikroorganismer

The Late Holocene deglaciation of James Ross Island, Antarctic Peninsula: OSL and 14C-dated multi-proxy sedimentary record from Monolith Lake - Roman, Matěj; Píšková, Anna; Sanderson, David C.W.; Cresswell, Alan J.; Bulínová, Marie; Pokorný, Matěj; Kavan, Jan; Jennings, Stephen J.A.; Lirio, Juan M.; Nedbalová, Linda; Sacherová, Veronika; Kopalová, Kateřina; et al. (Quaternary Science Reviews, 2024)
Lentic waterbodies provide terrestrial sedimentary archives of palaeoenvironmental change in deglaciated areas of the Antarctic. Knowledge of the long-term evolution of Antarctic palaeoenvironments affords important context to the current marked impacts of climate change in the Polar regions. Here, we present a comprehensively dated, multi-proxy sedimentary record from Monolith Lake, a distal proglacial lake in one of the largest ice-free areas of the Antarctic Peninsula region. Of the two defined sedimentary units in the cores studied, the lower Unit 1 exhibits a homogeneous composition and unvarying proxy data profiles, suggesting rapid clastic deposition under uniform, ice-proximal conditions with a sedimentation rate of ∼1 mm yr−1. 14C and optically stimulated luminescence (OSL) dating bracket the deposition interval to 1.5–2.5 ka BP, with the older age being more probable when compared to independent dating of the local deglaciation. The uppermost 11 cm of the record spans the last ∼2.2 ka BP (maximum age), suggesting a markedly decreased sedimentation rate of ∼0.05 mm yr−1 within Unit 2. Whereas Unit 1 shows only scarce evidence of biological activity, Unit 2 provides an uninterrupted record of diatoms (with 29 species recorded) and faunal subfossils, including the fairy shrimp Branchinecta gaini. Concentrations of organically-derived elements, as well as diatoms and faunal remains, are consistent, implying a gradual increase in lake productivity. These results provide an example of long-term Antarctic ‘greening’ (i.e. increasing organic productivity in terrestrial habitats) from a palaeolimnological perspective. The boundary between Units 1 and 2, therefore, marks the timing of local deglaciation at the final stages of a period of negative glacier mass balance, i.e. the Mid-Late Holocene Hypsithermal. Subsequent Neoglacial cooling is evidenced by the abated influence of glacial meltwater streams and turbidity decline linked to reduced glacier runoff, although most proxy responses mirror the natural proglacial lake ontogeny.
Keywords: Antarktis; diatomeer; geografi; geologi; holocene; innsjøer; paleolimnologi; paleoøkologi

Permafrost Hydrogeology of Taylor Valley, Antarctica: Insights From Deep Electrical Resistivity Tomography - Romano, Valentina; Fischanger, Federico; Wilson, Gary; Sciarra, Alessandra; Mazzini, Adriano; Mazzoli, Claudio; Florindo, Fabio; Tartarello, Maria Chiara; Ascani, Massimiliano; Anderson, Jacob; Worthington, Rachel; Hardie, Richard; et al. (Geophysical Research Letters, 2024)
Abstract Global warming has prompted globally widespread permafrost thawing, resulting in enhanced greenhouse gas release into the atmosphere. Studies conducted in the Northern Hemisphere reveal an alarming increase in permafrost thawing. However, similar data from Antarctica are scarce. We conducted a 2-D Deep Electrical Resistivity Tomography (DERT) survey in Taylor Valley, Antarctica, to image the distribution of permafrost, its thicknesses, lower boundaries, and hydrogeology. Results show resistive, discontinuous domains that we suggest represent permafrost units. We also find highly conductive layers (5?10 Ω·m), between 300?350 m and 600?650 m below ground level and a shallower (?50?100 m depth) conductive layer. The combined data set reveals a broad brine system in Taylor Valley, implying multi-tiered groundwater circulation: a shallow, localized system linked with surface water bodies and a separate deeper, regional circulation system. The arrangement of these brines across different levels, coupled with the uneven permafrost distribution, underscores potential interplay between the two systems.
Keywords: Antarktis; geologi; global oppvarming; hydrogeologi; klimaendringer; permafrost

Evolution of the Antarctic Ice Sheet Over the Next Three Centuries From an ISMIP6 Model Ensemble - Seroussi, Hélène; Pelle, Tyler; Lipscomb, William H.; Abe-Ouchi, Ayako; Albrecht, Torsten; Alvarez-Solas, Jorge; Asay-Davis, Xylar; Barre, Jean-Baptiste; Berends, Constantijn J.; Bernales, Jorge; Blasco, Javier; Caillet, Justine; et al. (Earth's Future, 2024)
Abstract The Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6) is the primary effort of CMIP6 (Coupled Model Intercomparison Project?Phase 6) focusing on ice sheets, designed to provide an ensemble of process-based projections of the ice-sheet contribution to sea-level rise over the twenty-first century. However, the behavior of the Antarctic Ice Sheet beyond 2100 remains largely unknown: several instability mechanisms can develop on longer time scales, potentially destabilizing large parts of Antarctica. Projections of Antarctic Ice Sheet evolution until 2300 are presented here, using an ensemble of 16 ice-flow models and forcing from global climate models. Under high-emission scenarios, the Antarctic sea-level contribution is limited to less than 30 cm sea-level equivalent (SLE) by 2100, but increases rapidly thereafter to reach up to 4.4 m SLE by 2300. Simulations including ice-shelf collapse lead to an additional 1.1 m SLE on average by 2300, and can reach 6.9 m SLE. Widespread retreat is observed on that timescale in most West Antarctic basins, leading to a collapse of large sectors of West Antarctica by 2300 in 30%?40% of the ensemble. While the onset date of retreat varies among ice models, the rate of upstream propagation is highly consistent once retreat begins. Calculations of sea-level contribution including water density corrections lead to an additional ?10% sea level and up to 50% for contributions accounting for bedrock uplift in response to ice loading. Overall, these results highlight large sea-level contributions from Antarctica and suggest that the choice of ice sheet model remains the leading source of uncertainty in multi-century projections.
Keywords: Antarktis; geovitenskap; glasiologi; innlandsis; klimamodeller

Eccentricity pacing and rapid termination of the early Antarctic ice ages - van Peer, Tim E.; Liebrand, Diederik; Taylor, Victoria E.; Brzelinski, Swaantje; Wolf, Iris; Bornemann, André; Friedrich, Oliver; Bohaty, Steven M.; Xuan, Chuang; Lippert, Peter C.; Wilson, Paul A. (Nature Communications, 2024)
Earth’s obliquity and eccentricity cycles are strongly imprinted on Earth’s climate and widely used to measure geological time. However, the record of these imprints on the oxygen isotope record in deep-sea benthic foraminifera (δ18Ob) shows contradictory signals that violate isotopic principles and cause controversy over climate-ice sheet interactions. Here, we present a δ18Ob record of high fidelity from International Ocean Drilling Program (IODP) Site U1406 in the northwest Atlantic Ocean. We compare our record to other records for the time interval between 28 and 20 million years ago, when Earth was warmer than today, and only Antarctic ice sheets existed. The imprint of eccentricity on δ18Ob is remarkably consistent globally whereas the obliquity signal is inconsistent between sites, indicating that eccentricity was the primary pacemaker of land ice volume. The larger eccentricity-paced early Antarctic ice ages were vulnerable to rapid termination. These findings imply that the self-stabilizing hysteresis effects of large land-based early Antarctic ice sheets were strong enough to maintain ice growth despite consecutive insolation-induced polar warming episodes. However, rapid ice age terminations indicate that resistance to melting was weaker than simulated by numerical models and regularly overpowered, sometimes abruptly.
Keywords: Antarktis; geologi; paleoklimatologi; paleoseanografi

A satellite-derived baseline of photosynthetic life across Antarctica - Walshaw, Charlotte V.; Gray, Andrew; Fretwell, Peter T.; Convey, Peter; Davey, Matthew P.; Johnson, Joanne S.; Colesie, Claudia (Nature Geoscience, 2024)
Terrestrial vegetation communities across Antarctica are characteristically sparse, presenting a challenge for mapping their occurrence using remote sensing at the continent scale. At present there is no continent-wide baseline record of Antarctic vegetation, and large-scale area estimates remain unquantified. With local vegetation distribution shifts now apparent and further predicted in response to environmental change across Antarctica, it is critical to establish a baseline to document these changes. Here we present a 10 m-resolution map of photosynthetic life in terrestrial and cryospheric habitats across the entire Antarctic continent, maritime archipelagos and islands south of 60° S. Using Sentinel-2 imagery (2017–2023) and spectral indices, we detected terrestrial green vegetation (vascular plants, bryophytes, green algae) and lichens across ice-free areas, and cryospheric green snow algae across coastal snowpacks. The detected vegetation occupies a total area of 44.2 km2, with over half contained in the South Shetland Islands, altogether contributing just 0.12% of the total ice-free area included in the analysis. Due to methodological constraints, dark-coloured lichens and cyanobacterial mats were excluded from the study. This vegetation map improves the geospatial data available for vegetation across Antarctica, and provides a tool for future conservation planning and large-scale biogeographic assessments.
Keywords: Antarktis; alger; biodiversitet; botanikk; lav; planter

Monitoring persistent organic chemicals in Antarctica in support of global chemical policy: a horizon scan of priority actions and challenges - Bengtson Nash, Susan; Bohlin-Nizzetto, Pernilla; Galban-Malagon, Cristobal; Corsolini, Simonetta; Cincinelli, Alessandra; Lohmann, Rainer (The Lancet Planetary Health, 2023)
Summary Global production and emission of chemicals exceeds societal capacities for assessment and monitoring. This situation calls for improved chemical regulatory policy frameworks and increased support for expedited decision making within existing frameworks. The polar regions of the Earth represent unique sentinel areas for the study of global chemical behaviour, and data arising from these areas can strengthen existing policy frameworks. However, chemical pollution research and monitoring in the Antarctic is underdeveloped, with geopolitical complexities and the absence of legal recognition of international chemical policy serving to neutralise progress made in other global regions. This Personal View represents a horizon scan by the action group Input Pathways of Persistent Organic Pollutants to Antarctica, of the Scientific Committee for Antarctic Research. Four priority research and research facilitation gaps are outlined, with recommendations for Antarctica Treaty parties for strategic action against these priorities.
Keywords: Antarktis; Sørishavet; forskning; forvaltning; helse; miljøgifter

Regional polar warming linked to poleward moisture transport variability - Bintanja, Richard; Graversen, Rune Grand; Kolbe, Marlen (Environmental Research: Climate, 2023)
Polar warming, ice melt and strong precipitation events are strongly affected by episodic poleward advection of warm and moist air (Woods and Caballero 2016 J. Clim. 29 4473–85; Wille et al 2019 Nat. Geosci. 12 911–6), which, in turn, is linked to variability in poleward moisture transport (PMT) (Nash et al 2018 J. Geophys. Res. Atmos. 123 6804–21). However, processes governing regional impacts of PMT as well as long-term trends remain largely unknown. Here we use an ensemble of state-of-the-art global climate models in standardized scenario simulations (1850–2100) to show that both the Arctic and the Antarctic exhibit distinct geographical patterns of PMT-related warming. Specifically, years with high PMT experience considerable warming over subarctic Eurasia and West-Antarctica (Raphael et al 2016 Bull. Am. Meteorol. Soc. 97 111–21), whereas precipitation is distributed more evenly over the polar regions. The warming patterns indicate preferred routes of atmospheric rivers (Woods and Caballero 2016 J. Clim. 29 4473–85), which may regionally enhance atmospheric moisture content, cloud cover, and downward longwave radiative heating in years with comparatively high PMT (Scott et al 2019 J. Clim. 32 665–84). Trend-analyses reveal that the link between PMT-variability and regional precipitation patterns will weaken in both polar regions. Even though uncertainties associated with intermodel differences are considerable, the advection of warm and moist air associated with PMT-variability is likely to increasingly cause mild conditions in both polar regions, which in the Arctic will reinforce sea-ice melt. Similarly, the results suggest that warm years in West-Antarctica disproportionally contribute to ice sheet melt (Trusel et al 2015 Nat. Geosci. 8 927–32), enhancing the risk of ice-sheet instabilities causing accelerated and sudden sea-level rise.
Keywords: Antarktis; global oppvarming; klimamodeller; meteorologi; polarområdene

A continent-wide detailed geological map dataset of Antarctica - Cox, Simon C.; Smith Lyttle, Belinda; Elkind, Samuel; Smith Siddoway, Christine; Morin, Paul; Capponi, Giovanni; Abu-Alam, Tamer; Ballinger, Matilda; Bamber, Lauren; Kitchener, Brett; Lelli, Luigi; Mawson, Jasmine; et al. (Scientific Data, 2023)
A dataset to describe exposed bedrock and surficial geology of Antarctica has been constructed by the GeoMAP Action Group of the Scientific Committee on Antarctic Research (SCAR) and GNS Science. Our group captured existing geological map data into a geographic information system (GIS), refined its spatial reliability, harmonised classification, and improved representation of glacial sequences and geomorphology, thereby creating a comprehensive and coherent representation of Antarctic geology. A total of 99,080 polygons were unified for depicting geology at 1:250,000 scale, but locally there are some areas with higher spatial resolution. Geological unit definition is based on a mixed chronostratigraphic- and lithostratigraphic-based classification. Description of rock and moraine polygons employs the international Geoscience Markup Language (GeoSciML) data protocols to provide attribute-rich and queryable information, including bibliographic links to 589 source maps and scientific literature. GeoMAP is the first detailed geological map dataset covering all of Antarctica. It depicts ‘known geology’ of rock exposures rather than ‘interpreted’ sub-ice features and is suitable for continent-wide perspectives and cross-discipline interrogation.
Keywords: Antarktis; geologi; geomorfologi

Antarctic Bedmap data: Findable, Accessible, Interoperable, and Reusable (FAIR) sharing of 60 years of ice bed, surface, and thickness data - Frémand, A. C.; Fretwell, P.; Bodart, J. A.; Pritchard, H. D.; Aitken, A.; Bamber, J. L.; Bell, R.; Bianchi, C.; Bingham, R. G.; Blankenship, D. D.; Casassa, G.; Catania, G.; et al. (Earth System Science Data, 2023)
One of the key components of this research has been the mapping of Antarctic bed topography and ice thickness parameters that are crucial for modelling ice flow and hence for predicting future ice loss and the ensuing sea level rise. Supported by the Scientific Committee on Antarctic Research (SCAR), the Bedmap3 Action Group aims not only to produce new gridded maps of ice thickness and bed topography for the international scientific community, but also to standardize and make available all the geophysical survey data points used in producing the Bedmap gridded products. Here, we document the survey data used in the latest iteration, Bedmap3, incorporating and adding to all of the datasets previously used for Bedmap1 and Bedmap2, including ice bed, surface and thickness point data from all Antarctic geophysical campaigns since the 1950s. More specifically, we describe the processes used to standardize and make these and future surveys and gridded datasets accessible under the Findable, Accessible, Interoperable, and Reusable (FAIR) data principles. With the goals of making the gridding process reproducible and allowing scientists to re-use the data freely for their own analysis, we introduce the new SCAR Bedmap Data Portal (https://bedmap.scar.org, last access: 1 March 2023) created to provide unprecedented open access to these important datasets through a web-map interface. We believe that this data release will be a valuable asset to Antarctic research and will greatly extend the life cycle of the data held within it. Data are available from the UK Polar Data Centre: https://data.bas.ac.uk (last access: 5 May 2023​​​​​​​). See the Data availability section for the complete list of datasets.
Keywords: Antarktis; database; glasiologi

The stability of present-day Antarctic grounding lines – Part 1: No indication of marine ice sheet instability in the current geometry - Hill, E. A.; Urruty, B.; Reese, R.; Garbe, J.; Gagliardini, O.; Durand, G.; Gillet-Chaulet, F.; Gudmundsson, G. H.; Winkelmann, R.; Chekki, M.; Chandler, D.; Langebroek, P. M. (The Cryosphere, 2023)
Theoretical and numerical work has shown that under certain circumstances grounding lines of marine-type ice sheets can enter phases of irreversible advance and retreat driven by the marine ice sheet instability (MISI). Instances of such irreversible retreat have been found in several simulations of the Antarctic Ice Sheet. However, it has not been assessed whether the Antarctic grounding lines are already undergoing MISI in their current position. Here, we conduct a systematic numerical stability analysis using three state-of-the-art ice sheet models: Úa, Elmer/Ice, and the Parallel Ice Sheet Model (PISM). For the first two models, we construct steady-state initial configurations whereby the simulated grounding lines remain at the observed present-day positions through time. The third model, PISM, uses a spin-up procedure and historical forcing such that its transient state is close to the observed one. To assess the stability of these simulated states, we apply short-term perturbations to submarine melting. Our results show that the grounding lines around Antarctica migrate slightly away from their initial position while the perturbation is applied, and they revert once the perturbation is removed. This indicates that present-day retreat of Antarctic grounding lines is not yet irreversible or self-sustained. However, our accompanying paper (Part 2, Reese et al., 2023a) shows that if the grounding lines retreated further inland, under present-day climate forcing, it may lead to the eventual irreversible collapse of some marine regions of West Antarctica.
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Communicating the best available science to inform Antarctic policy and management: a practical introduction for researchers - Hughes, Kevin A.; Lowther, Andrew; Gilbert, Neil; Waluda, Claire M.; Lee, Jasmine R. (Antarctic Science, 2023)
Communication at the science-policy interface can be bewildering not only for early-career researchers, but also for many within the research community. In the context of Antarctica and the Southern Ocean, decision-makers operating within the Antarctic Treaty System (ATS) aspire to use the best available science as a basis for their decision-making. Therefore, to maximize the impact of Antarctic Treaty Parties' substantial investment in southern polar research, researchers wishing to contribute to policy and management must understand 1) how their work relates to and can potentially inform Antarctic and/or global policy and 2) the available mechanisms by which their research can be communicated to decision-makers. Recognizing these needs, we describe the main legal instruments relevant to Antarctic governance (primarily the ATS) and the associated meetings and stakeholders that contribute to policy development for the region. We highlight effective mechanisms by which Antarctic researchers may communicate their science into the policy realm, including through National Delegations or the Scientific Committee on Antarctic Research (SCAR), and we detail the key contemporary topics of interest to decision-makers, including those issues where further research is needed. Finally, we describe challenges at the Antarctic science-policy interface that may potentially slow or halt policy development.
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forskning; forvaltning; kommunikasjon

Turned 60, is the Antarctic treaty system in good health? - Mancilla, Alejandra; Jabour, Julia Ann (The Geographical Journal, 2023)
Signed in 1959, the Antarctic Treaty is usually hailed as an example of what states can achieve when they leave aside their interests and truly collaborate. It was over 30?years ago, however, that the last significant legal instrument of the Antarctic Treaty System (namely, the Protocol on Environmental Protection) was signed. Since then, no new legal instruments have been drafted, despite a number of growing internal and external challenges. In this special issue, an interdisciplinary group of scholars examine some of these challenges and evaluate whether the system is well prepared to tackle them. Their point of agreement is that, if not severely ill, the system's chronic ailments?particularly laggardness?must be addressed if it is to respond satisfactorily to rapid social, political, environmental and economic changes on a global scale.
Keywords: Antarktis; Antarktistraktaten; miljøvern; politikk

Large-scale seabird community structure along oceanographic gradients in the Scotia Sea and northern Antarctic Peninsula - Ollus, Victoria Marja Sofia; Biuw, Martin; Lowther, Andrew; Fauchald, Per; Deehr Johannessen, John Elling; Martín López, Lucía Martina; Gkikopoulou, Kalliopi C.; Oosthuizen, W. Chris; Lindstrøm, Ulf (Frontiers in Marine Science, 2023)
Introduction: The Scotia Sea and Antarctic Peninsula are warming rapidly and changes in species distribution are expected. In predicting habitat shifts and considering appropriate management strategies for marine predators, a community-level understanding of how these predators are distributed is desirable. Acquiring such data, particularly in remote areas, is often problematic given the cost associated with the operation of research vessels. Here we use cruise vessels as sampling platforms to explore seabird distribution relative to habitat characteristics. Methods: Data on seabird at-sea distribution were collected using strip-transect counts throughout the Antarctic Peninsula and Scotia Sea in the austral summer of 2019-2020. Constrained correspondence analysis (CCA) and generalized additive models (GAM) were used to relate seabird community composition, density, and species richness to environmental covariates. Results: Species assemblages differed between oceanographic areas, with sea surface temperature and distance to coast being the most important predictors of seabird distribution. Our results further revealed a geographic separation of distinct communities rather than hotspot regions in the study area in summer. Discussion: These findings highlight the importance of large-scale environmental characteristics in shaping seabird community structure, presumably through underlying prey distribution and interspecific interactions. The present study contributes to the knowledge of seabird distribution and habitat use as well as the baseline for assessing the response of Antarctic seabird communities to climate warming. We argue that cruise vessels, when combined with structured research surveys, can provide a cost-effective additional tool for the monitoring of community and ecosystem level changes.
Keywords: Antarktis; Sørishavet; marin biologi; marin zoologi; marine økosystemer; sjøfugler

Antarctic iceberg distribution revealed through three decades of systematic ship-based observations in the SCAR International Iceberg Database - Orheim, Olav; Giles, A. Barry; Moholdt, Geir; (Jo) Jacka, T. H.; Bjørdal, Are (Journal of Glaciology, 2023)
In 1981, the Scientific Committee on Antarctic Research endorsed a program for ship-based collection of Antarctic iceberg data, to be coordinated by the Norwegian Polar Institute (NPI). From the austral summers 1982/1983 to 1997/1998, icebergs were recorded from most, and up to 2009/10 by fewer research vessels. The NPI database makes up 80% of the SCAR International Iceberg Database presented here, the remainder being Australian National Antarctic Research Expedition observations. The database contains positions of 374 142 icebergs resulting from 34 662 observations. Within these, 298 235 icebergs are classified into different size categories. The ship-based data are particularly useful because they include systematic observations of smaller icebergs not covered by current satellite-based datasets. Here, we assess regional and seasonal variations in iceberg density and total quantities, we identify drift patterns and exit zones from the continent, and we discuss iceberg dissolution rates and calving rates. There are significant differences in the extent of icebergs observed over the 30 plus years of observations, but much of these can be ascribed to differences in observation density and location. In the summer, Antarctic icebergs >10 m in length number ~130 000 of which 1000 are found north of the Southern Ocean boundary.
Keywords: Antarktis; Sørishavet; database; glasiologi; isfjell

Characteristics of Surface “Melt Potential” over Antarctic Ice Shelves based on Regional Atmospheric Model Simulations of Summer Air Temperature Extremes from 1979/80 to 2018/19 - Orr, Andrew; Deb, Pranab; Clem, Kyle R.; Gilbert, Ella; Bromwich, David H.; Boberg, Fredrik; Colwell, Steve; Hansen, Nicolaj; Lazzara, Matthew A.; Mooney, Priscilla A.; Mottram, Ruth; Niwano, Masashi; et al. (Journal of Climate, 2023)
We calculate a regional surface “melt potential” index (MPI) over Antarctic ice shelves that describes the frequency (MPI-freq; %) and intensity (MPI-int; K) of daily maximum summer temperatures exceeding a melt threshold of 273.15 K. This is used to determine which ice shelves are vulnerable to melt-induced hydrofracture and is calculated using near-surface temperature output for each summer from 1979/80 to 2018/19 from two high-resolution regional atmospheric model hindcasts (using the MetUM and HIRHAM5). MPI is highest for Antarctic Peninsula ice shelves (MPI-freq 23%–35%, MPI-int 1.2–2.1 K), lowest (2%–3%, <0 K) for the Ronne–Filchner and Ross ice shelves, and around 10%–24% and 0.6–1.7 K for the other West and East Antarctic ice shelves. Hotspots of MPI are apparent over many ice shelves, and they also show a decreasing trend in MPI-freq. The regional circulation patterns associated with high MPI values over West and East Antarctic ice shelves are remarkably consistent for their respective region but tied to different large-scale climate forcings. The West Antarctic circulation resembles the central Pacific El Niño pattern with a stationary Rossby wave and a strong anticyclone over the high-latitude South Pacific. By contrast, the East Antarctic circulation comprises a zonally symmetric negative Southern Annular Mode pattern with a strong regional anticyclone on the plateau and enhanced coastal easterlies/weakened Southern Ocean westerlies. Values of MPI are 3–4 times larger for a lower temperature/melt threshold of 271.15 K used in a sensitivity test, as melting can occur at temperatures lower than 273.15 K depending on snowpack properties.
Keywords: Antarktis; glasiologi; klima; smelting

The stability of present-day Antarctic grounding lines – Part 2: Onset of irreversible retreat of Amundsen Sea glaciers under current climate on centennial timescales cannot be excluded - Reese, R.; Garbe, J.; Hill, E. A.; Urruty, B.; Naughten, K. A.; Gagliardini, O.; Durand, G.; Gillet-Chaulet, F.; Gudmundsson, G. H.; Chandler, D.; Langebroek, P. M.; Winkelmann, R. (The Cryosphere, 2023)
Observations of ocean-driven grounding-line retreat in the Amundsen Sea Embayment in Antarctica raise the question of an imminent collapse of the West Antarctic Ice Sheet. Here we analyse the committed evolution of Antarctic grounding lines under the present-day climate. To this aim, we first calibrate a sub-shelf melt parameterization, which is derived from an ocean box model, with observed and modelled melt sensitivities to ocean temperature changes, making it suitable for present-day simulations and future sea level projections. Using the new calibration, we run an ensemble of historical simulations from 1850 to 2015 with a state-of-the-art ice sheet model to create model instances of possible present-day ice sheet configurations. Then, we extend the simulations for another 10 000 years to investigate their evolution under constant present-day climate forcing and bathymetry. We test for reversibility of grounding-line movement in the case that large-scale retreat occurs. In the Amundsen Sea Embayment we find irreversible retreat of the Thwaites Glacier for all our parameter combinations and irreversible retreat of the Pine Island Glacier for some admissible parameter combinations. Importantly, an irreversible collapse in the Amundsen Sea Embayment sector is initiated at the earliest between 300 and 500 years in our simulations and is not inevitable yet – as also shown in our companion paper (Part 1, Hill et al., 2023). In other words, the region has not tipped yet. With the assumption of constant present-day climate, the collapse evolves on millennial timescales, with a maximum rate of 0.9 mm a−1 sea-level-equivalent ice volume loss. The contribution to sea level by 2300 is limited to 8 cm with a maximum rate of 0.4 mm a−1 sea-level-equivalent ice volume loss. Furthermore, when allowing ice shelves to regrow to their present geometry, we find that large-scale grounding-line retreat into marine basins upstream of the Filchner–Ronne Ice Shelf and the western Siple Coast is reversible. Other grounding lines remain close to their current positions in all configurations under present-day climate.
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Antarctic permafrost degassing in Taylor Valley by extensive soil gas investigation - Ruggiero, L.; Sciarra, A.; Mazzini, A.; Florindo, F.; Wilson, G.; Tartarello, M.C.; Mazzoli, C.; Anderson, J.T.H.; Romano, V.; Worthington, R.; Bigi, S.; Sassi, R.; et al. (Science of The Total Environment, 2023)
Ongoing studies conducted in northern polar regions reveal that permafrost stability plays a key role in the modern carbon cycle as it potentially stores considerable quantities of greenhouse gases. Rapid and recent warming of the Arctic permafrost is resulting in significant greenhouse gas emissions, both from physical and microbial processes. The potential impact of greenhouse gas release from the Antarctic region has not, to date, been investigated. In Antarctica, the McMurdo Dry Valleys comprise 10 % of the ice-free soil surface areas in Antarctica and like the northern polar regions are also warming albeit at a slower rate. The work presented herein examines a comprehensive sample suite of soil gas (e.g., CO2, CH4 and He) concentrations and CO2 flux measurements conducted in Taylor Valley during austral summer 2019/2020. Analytical results reveal the presence of significant concentrations of CO2, CH4 and He (up to 3.44 vol%, 18,447 ppmv and 6.49 ppmv, respectively) at the base of the active layer. When compared with the few previously obtained measurements, we observe increased CO2 flux rates (estimated CO2 emissions in the study area of 21.6 km2 ≈ 15 tons day−1). We suggest that the gas source is connected with the deep brines migrating from inland (potentially from beneath the Antarctic Ice Sheet) towards the coast beneath the permafrost layer. These data provide a baseline for future investigations aimed at monitoring the changing rate of greenhouse gas emissions from Antarctic permafrost, and the potential origin of gases, as the southern polar region warms.
Keywords: Antarktis; drivhusgasser; geofysikk; geologi; geostatistikk; isbreer; permafrost

Insights into the vulnerability of Antarctic glaciers from the ISMIP6 ice sheet model ensemble and associated uncertainty - Seroussi, H.; Verjans, V.; Nowicki, S.; Payne, A. J.; Goelzer, H.; Lipscomb, W. H.; Abe-Ouchi, A.; Agosta, C.; Albrecht, T.; Asay-Davis, X.; Barthel, A.; Calov, R.; et al. (The Cryosphere, 2023)
The Antarctic Ice Sheet represents the largest source of uncertainty in future sea level rise projections, with a contribution to sea level by 2100 ranging from −5 to 43 cm of sea level equivalent under high carbon emission scenarios estimated by the recent Ice Sheet Model Intercomparison for CMIP6 (ISMIP6). ISMIP6 highlighted the different behaviors of the East and West Antarctic ice sheets, as well as the possible role of increased surface mass balance in offsetting the dynamic ice loss in response to changing oceanic conditions in ice shelf cavities. However, the detailed contribution of individual glaciers, as well as the partitioning of uncertainty associated with this ensemble, have not yet been investigated. Here, we analyze the ISMIP6 results for high carbon emission scenarios, focusing on key glaciers around the Antarctic Ice Sheet, and we quantify their projected dynamic mass loss, defined here as mass loss through increased ice discharge into the ocean in response to changing oceanic conditions. We highlight glaciers contributing the most to sea level rise, as well as their vulnerability to changes in oceanic conditions. We then investigate the different sources of uncertainty and their relative role in projections, for the entire continent and for key individual glaciers. We show that, in addition to Thwaites and Pine Island glaciers in West Antarctica, Totten and Moscow University glaciers in East Antarctica present comparable future dynamic mass loss and high sensitivity to ice shelf basal melt. The overall uncertainty in additional dynamic mass loss in response to changing oceanic conditions, compared to a scenario with constant oceanic conditions, is dominated by the choice of ice sheet model, accounting for 52 % of the total uncertainty of the Antarctic dynamic mass loss in 2100. Its relative role for the most dynamic glaciers varies between 14 % for MacAyeal and Whillans ice streams and 56 % for Pine Island Glacier at the end of the century. The uncertainty associated with the choice of climate model increases over time and reaches 13 % of the uncertainty by 2100 for the Antarctic Ice Sheet but varies between 4 % for Thwaites Glacier and 53 % for Whillans Ice Stream. The uncertainty associated with the ice–climate interaction, which captures different treatments of oceanic forcings such as the choice of melt parameterization, its calibration, and simulated ice shelf geometries, accounts for 22 % of the uncertainty at the ice sheet scale but reaches 36 % and 39 % for Institute Ice Stream and Thwaites Glacier, respectively, by 2100. Overall, this study helps inform future research by highlighting the sectors of the ice sheet most vulnerable to oceanic warming over the 21st century and by quantifying the main sources of uncertainty.
Keywords: Antarktis; glasiologi; isbreer; klimamodeller; smelting

New cold-adapted bacteria for efficient hydrolysis of feather waste at low temperature - Smirnova, Margarita; Losada, Cristian Bolaño; Akulava, Volha; Zimmermann, Boris; Kohler, Achim; Miamin, Uladzislau; Oostindjer, Marije; Shapaval, Volha (Bioresource Technology Reports, 2023)
A novel cold-adapted bacteria Arthrobacter oryzae BIM B-1663 isolated from Antarctic green snow showed keratinase activity and efficient poultry feather degradation. A. oryzae strain degraded more than 80 % of chicken feathers within 7 days of cultivation at 25 °C. The optimal keratinase activity for A. oryzae BIM B-1663 was observed at 50 °C, both for α-keratin (44.86 U/mL) and for β-keratin (94 mU/mL). The obtained results from sulfite and thiol groups tests and Fourier transform infrared spectroscopy (FTIR) showed that A. oryzae strain has a different keratin degradation mechanism than the reference strain Bacillus licheniformis CCM 2145T. FTIR fingerprinting can be used for monitoring of feather hydrolysis as it showed distinct chemical differences in feather meal hydrolysates, retentate and permeate from A. oryzae and B. licheniformis strains.
Keywords: Antarktis; bakterier; biokjemi; kjemi; mikrobiologi

The Antarctic Peninsula: Argentina and Chile in the era of global change - Vidal, Florian (The Polar Journal, 2023)
While Argentine-Chilean relations have long been swayed between cooperation and confrontation since their independence in the 19th century and a long-standing presence in Antarctica, the stretch between Tierra del Fuego to the Antarctic Peninsula stands as the closest lane (i.e. about 1,000 km) to any other continent. Despite their territorial dispute over islands on the fractured southern tip of South America and territorial claims on the Antarctic, their common diplo-matic ground successfully defuses any potential geopolitical instability. Along with Chile and Argentina, British claims overlap in the Antarctic Peninsula, which establishes unique geopolitical conditions in the whole of Antarctica. In this context, scientific missions and growing tourist activities could transform the region into the Antarctic gateway. From potential mineral resources exploitation to the United States- China global competition, the South Atlantic area could become a strategic bridgehead in light of the brewing geopolitical shift during the 21st century. Considering that climate change and geostrategic conditions evolve somewhat quickly to transform the Western Antarctic area, this article aims to assess and comprehend how these external drivers may affect the two South American countries. Given the fact that Antarctica is part of their respective national narrative, how do Argentina and Chile intend to maintain their presence and protect their interest in these shifting conditions? What are the vectors for partnering with the world’s great powers, such as China? Ultimately, could this space become a choke point through the 21st century?
Keywords: Antarktis; geopolitikk; politikk; ressurser

Threat management priorities for conserving Antarctic biodiversity - Lee, Jasmine R.; Terauds, Aleks; Carwardine, Josie; Shaw, Justine D.; Fuller, Richard A.; Possingham, Hugh P.; Chown, Steven L.; Convey, Peter; Gilbert, Neil; Hughes, Kevin A.; McIvor, Ewan; Robinson, Sharon A.; et al. (PLOS Biology, 2022)
Antarctic terrestrial biodiversity faces multiple threats, from invasive species to climate change. Yet no large-scale assessments of threat management strategies exist. Applying a structured participatory approach, we demonstrate that existing conservation efforts are insufficient in a changing world, estimating that 65% (at best 37%, at worst 97%) of native terrestrial taxa and land-associated seabirds are likely to decline by 2100 under current trajectories. Emperor penguins are identified as the most vulnerable taxon, followed by other seabirds and dry soil nematodes. We find that implementing 10 key threat management strategies in parallel, at an estimated present-day equivalent annual cost of US$23 million, could benefit up to 84% of Antarctic taxa. Climate change is identified as the most pervasive threat to Antarctic biodiversity and influencing global policy to effectively limit climate change is the most beneficial conservation strategy. However, minimising impacts of human activities and improved planning and management of new infrastructure projects are cost-effective and will help to minimise regional threats. Simultaneous global and regional efforts are critical to secure Antarctic biodiversity for future generations.
Keywords: Antarktis; biodiversitet; forvaltning; pingviner

Regional sea-level highstand triggered Holocene ice sheet thinning across coastal Dronning Maud Land, East Antarctica - Suganuma, Yusuke; Kaneda, Heitaro; Mas e Braga, Martim; Ishiwa, Takeshige; Koyama, Takushi; Newall, Jennifer C.; Okuno, Jun’ichi; Obase, Takashi; Saito, Fuyuki; Rogozhina, Irina; Andersen, Jane Lund; Kawamata, Moto; et al. (Communications Earth & Environment, 2022)
The East Antarctic Ice Sheet stores a vast amount of freshwater, which makes it the single largest potential contributor to future sea-level rise. However, the lack of well-constrained geological records of past ice sheet changes impedes model validation, hampers mass balance estimates, and inhibits examination of ice loss mechanisms. Here we identify rapid ice-sheet thinning in coastal Dronning Maud Land from Early to Middle Holocene (9000–5000 years ago) using a deglacial chronology based on in situ cosmogenic nuclide surface exposure dates from central Dronning Maud Land, in concert with numerical simulations of regional and continental ice-sheet evolution. Regional sea-level changes reproduced from our refined ice-load history show a highstand at 9000–8000 years ago. We propose that sea-level rise and a concomitant influx of warmer Circumpolar Deep Water triggered ice shelf breakup via the marine ice sheet instability mechanism, which led to rapid thinning of upstream coastal ice sheet sectors.
Keywords: Antarktis; Sørishavet; glasiologi; havis; havnivå; isshelf

The foraging behavior of nonbreeding Adélie penguins in the western Antarctic Peninsula during the breeding season - Oosthuizen, W. Chris; Pistorius, Pierre A.; Korczak-Abshire, Malgorzata; Hinke, Jefferson T.; Santos, Mercedes; Lowther, Andrew D. (Ecosphere, 2022)
Abstract Information on marine predator at-sea distributions is key to understanding ecosystem and community dynamics and an important component of spatial management frameworks that aim to identify regions important for conservation. Tracking data from seabirds are widely used to define priority areas for conservation, but such data are often restricted to the breeding population. This also applies to penguins in Antarctica, where identification of important habitat for nonbreeders has received limited attention. Nonbreeding penguins are expected to have larger foraging distributions than breeding conspecifics, which may alter their interactions with physical environmental factors, conspecifics, other marine predators, and threats. We studied the movement behavior of nonbreeding Adélie penguins tracked during the 2016/2017 breeding season at King George Island in the South Shetland Islands, Antarctica. We quantify how nonbreeding penguins' horizontal moment behavior varies in relation to environmental conditions and assess the extent of spatial overlap in the foraging ranges of nonbreeders and breeders, which were tracked over several years. Nonbreeders increased their prey search and area-restricted foraging behavior as sea surface temperature and bottom depths decreased, and in response to increasing sea ice concentration. Nonbreeders tended to transit (high directional movement) over the relatively deep Central Basin of the Bransfield Strait. The majority of foraging behavior occurred within the colder, Weddell Sea?sourced water of the Antarctic Coastal Current (incubation) and in the Weddell Sea (crèche). The utilization distributions of breeders and nonbreeders overlapped in the central Bransfield Strait. Spatial segregation was greater during the crèche stage of breeding compared to incubation and brood, because chick provisioning still constrained the foraging range of breeders to a scale of a few tens of kilometers, while nonbreeders commenced with premolt foraging trips into the Weddell Sea. Our results show that breeding and nonbreeding penguins may not be impacted similarly by local environmental variability, given that their spatial and temporal scales of foraging differ during some part of the austral summer. Our study highlights the need to account for different life history stages when characterizing foraging behavior of marine predator populations. This is particularly important for ?sentinel? species monitored as part of marine conservation and ecosystem-based management programs.
Keywords: Antarktis; ornitologi; pingviner; sjøfugler; økologi

South American claims in Antarctica: colonial, malgre tout - Mancilla, A (POLAR JOURNAL, 2022)
Argentina and Chile, known in the world of Antarctic politics as the 'South American claimants', have shown themselves since the inception of their interests in the White Continent as standing alone and in opposition to the advances of the colonial powers of the North - especially the United Kingdom. As Shirley Scott has suggested, while the UK was busy staking claims over Antarctica and treating it as terra nullius, Argentina and Chile ascertained what they took to be their historical rights to the continent, inherited from the time when they were Spanish colonies. In this article, I support Argentina's and Chile's contention that the attitude and procedure followed by the other claimants to the continent was unequivocally colonial, but I reject their contention that theirs was not. I examine four sites where their colonial spirit is revealed: their use of the geographic doctrines of continuity and contiguity, and of the sector principle; the appeal to historic rights inherited from the time when they were Spanish colonies; their expansion to Antarctica through the establishment of military settlements, and their underlying economic and strategic interests, no different from their 'Northern' counterparts. I then point to some specific and general implications of reinterpreting their story in this light.
Keywords: Antarktis; politikk

Isolation, Physiological Characterization, and Antibiotic Susceptibility Testing of Fast-Growing Bacteria from the Sea-Affected Temporary Meltwater Ponds in the Thala Hills Oasis (Enderby Land, East Antarctica) - Akulava, Volha; Miamin, Uladzislau; Akhremchuk, Katsiaryna; Valentovich, Leonid; Dolgikh, Andrey; Shapaval, Volha (Biology, 2022)
In this study, for the first time, we report the identification and characterization of culturable fast-growing bacteria isolated from the sea-affected temporary meltwater ponds (MPs) in the East Antarctica area of the Vecherny region (−67.656317, 46.175058) of the Thala Hills Oasis, Enderby Land. Water samples from the studied MPs showed alkaline pH (from 8.0 to 10.1) and highly varied total dissolved solids (86–94,000 mg/L). In total, twenty-nine bacterial isolates were retrieved from the studied MPs. The phylogenetic analysis based on 16S rRNA gene sequence similarities showed that the isolated bacteria belong to the phyla Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes and the twelve genera Pseudomonas, Shewanella, Acinetobacter, Sporosarcina, Facklamia, Carnobacterium, Arthrobacter, Brachybacterium, Micrococcus, Agrococcus, Leifsonia, and Flavobacterium. Most of the isolated bacteria were psychrotrophs and showed the production of one or more extracellular enzymes. Lipolytic and proteolytic activities were more prevalent among the isolates. Five isolates from the Actinobacteria phylum and one isolate from the Bacteroidetes phylum had strong pigmentation. Antibiotic susceptibility testing revealed that most of the isolates are resistant to at least one antibiotic, and seven isolates showed multi-resistance.
Keywords: Antarktis; bakterier; biokjemi

Bioaccumulation of Per and Polyfluoroalkyl Substances in Antarctic Breeding South Polar Skuas (Catharacta maccormicki) and Their Prey - Alfaro Garcia, Laura Andrea; Descamps, Sébastien; Herzke, Dorte; Chastel, Olivier; Carravieri, Alice; Cherel, Yves; Labadie, Pierre; Budzinski, Hélène; Munoz, Gabriel; Bustamante, Paco; Polder, Anuschka; Gabrielsen, Geir Wing; et al. (Frontiers in Marine Science, 2022)
Per and polyfluoroalkyl substances (PFASs) are found in Antarctic wildlife, with high levels in the avian top predator south polar skua (Catharacta maccormicki). As increasing PFAS concentrations were found in the south polar skua during the breeding season in Antarctica, we hypothesised that available prey during the breeding period contributes significantly to the PFAS contamination in skuas. To test this, we compared PFAS in south polar skuas and their main prey from two breeding sites on opposite sides of the Antarctic continent: Antarctic petrel (Thalassoica antarctica) stomach content, eggs, chicks, and adults from Svarthamaren in Dronning Maud Land and Adélie penguin chicks (Pygoscelis adeliae) from Dumont d’Urville in Adélie Land. Of the 22 PFAS analysed, seven were present in the majority of samples, except petrel stomach content [only perfluoroundecanoate (PFUnA) present] and Adélie penguins (only four compounds present), with increasing concentrations from the prey to the skuas. The biomagnification factors (BMFs) were higher at Dumont d’Urville than Svarthamaren. When adjusted to reflect one trophic level difference, the BMFs at Svarthamaren remained the same, whereas the ones at Dumont d’Urville doubled. At both the colonies, the skua PFAS pattern was dominated by perfluorooctanesulfonic acid (PFOS), followed by PFUnA, but differed with the presence of branched PFOS and perfluorotetradecanoate (PFTeA) and lack of perfluorononanoate (PFNA) and perfluorodecanoate (PFDA) at Dumont d’Urville. At Svarthamaren, the pattern in the prey was comparable to the skuas, but with a higher relative contribution of PFTeA in prey. At Dumont d’Urville, the pattern in the prey differed from the skuas, with the domination of PFUnA and the general lack of PFOS in prey. Even though the PFAS levels are low in Antarctic year-round resident prey, the three lines of evidence (pattern, BMF difference, and BMF adjusted to one trophic level) suggest that the Antarctic petrel are the significant source of PFAS in the Svarthamaren skuas, whereas the skuas in Dumont d’Urville have other important sources to PFAS than Adélie penguin, either in the continent or external on the inter-breeding foraging grounds far from Antarctica.
Keywords: Antarktis; fugler; miljøgifter; økotoksikologi

Bioaccumulation of Per and Polyfluoroalkyl Substances in Antarctic Breeding South Polar Skuas (Catharacta maccormicki) and Their Prey - Alfaro Garcia, Laura Andrea; Descamps, Sébastien; Herzke, Dorte; Chastel, Olivier; Carravieri, Alice; Cherel, Yves; Labadie, Pierre; Budzinski, Hélène; Munoz, Gabriel; Bustamante, Paco; Polder, Anuschka; Gabrielsen, Geir Wing; et al. (Frontiers in Marine Science, 2022)
Per and polyfluoroalkyl substances (PFASs) are found in Antarctic wildlife, with high levels in the avian top predator south polar skua (Catharacta maccormicki). As increasing PFAS concentrations were found in the south polar skua during the breeding season in Antarctica, we hypothesised that available prey during the breeding period contributes significantly to the PFAS contamination in skuas. To test this, we compared PFAS in south polar skuas and their main prey from two breeding sites on opposite sides of the Antarctic continent: Antarctic petrel (Thalassoica antarctica) stomach content, eggs, chicks, and adults from Svarthamaren in Dronning Maud Land and Adélie penguin chicks (Pygoscelis adeliae) from Dumont d’Urville in Adélie Land. Of the 22 PFAS analysed, seven were present in the majority of samples, except petrel stomach content [only perfluoroundecanoate (PFUnA) present] and Adélie penguins (only four compounds present), with increasing concentrations from the prey to the skuas. The biomagnification factors (BMFs) were higher at Dumont d’Urville than Svarthamaren. When adjusted to reflect one trophic level difference, the BMFs at Svarthamaren remained the same, whereas the ones at Dumont d’Urville doubled. At both the colonies, the skua PFAS pattern was dominated by perfluorooctanesulfonic acid (PFOS), followed by PFUnA, but differed with the presence of branched PFOS and perfluorotetradecanoate (PFTeA) and lack of perfluorononanoate (PFNA) and perfluorodecanoate (PFDA) at Dumont d’Urville. At Svarthamaren, the pattern in the prey was comparable to the skuas, but with a higher relative contribution of PFTeA in prey. At Dumont d’Urville, the pattern in the prey differed from the skuas, with the domination of PFUnA and the general lack of PFOS in prey. Even though the PFAS levels are low in Antarctic year-round resident prey, the three lines of evidence (pattern, BMF difference, and BMF adjusted to one trophic level) suggest that the Antarctic petrel are the significant source of PFAS in the Svarthamaren skuas, whereas the skuas in Dumont d’Urville have other important sources to PFAS than Adélie penguin, either in the continent or external on the inter-breeding foraging grounds far from Antarctica.
Keywords: Antarktis; Dronning Maud Land; biologi; ornitologi; petreller; sjøfugler

Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation’: a new SCAR Scientific Research Programme - Hughes, Kevin A.; Santos, Mercedes; Caccavo, Jilda A.; Chignell, Stephen M.; Gardiner, Natasha B.; Gilbert, Neil; Howkins, Adrian; Van Vuuren, Bettine Jansen; Lee, Jasmine R.; Liggett, Daniela; Lowther, Andrew; Lynch, Heather; et al. (Antarctic Science, 2022)
Antarctic and Southern Ocean environments are facing increasing pressure from multiple threats. The Antarctic Treaty System regularly looks to the Scientific Committee on Antarctic Research (SCAR) for the provision of independent and objective advice based on the best available science to support decision-making, policy development and effective environmental management. The recently approved SCAR Scientific Research Programme Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation‘ - facilitates and coordinates high-quality transdisciplinary research to inform the conservation and management of Antarctica, the Southern Ocean and the sub-Antarctic in the context of current and future impacts. The work of Ant-ICON focuses on three research themes examining 1) the current state and future projections of Antarctic systems, species and functions, 2) human impacts and sustainability and 3) socio-ecological approaches to Antarctic and Southern Ocean conservation, and one synthesis theme that seeks to facilitate the provision of timely scientific advice to support effective Antarctic conservation. Research outputs will address the most pressing environmental challenges facing Antarctica and offer high-quality science to policy and advisory bodies including the Antarctic Treaty Consultative Meeting, the Committee for Environmental Protection and the Scientific Committee of the Commission for the Conservation of Antarctic Marine Living Resources.
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forvaltning; human impact; miljøvern

The influence of energetic particle precipitation on Antarctic stratospheric chlorine and ozone over the 20th century - Maliniemi, V.; Arsenovic, P.; Seppälä, A.; Nesse Tyssøy, H. (Atmospheric Chemistry and Physics, 2022)
Keywords: Antarktis; kjemi; ozon; stratosfæren

Experimental warming increases fungal alpha diversity in an oligotrophic maritime Antarctic soil - Newsham, Kevin K.; Misiak, Marta; Goodall-Copestake, William P.; Dahl, Malin Stapnes; Boddy, Lynne; Hopkins, David W.; Davey, Marie L. (Frontiers in Microbiology, 2022)
The climate of maritime Antarctica has altered since the 1950s. However, the effects of increased temperature, precipitation and organic carbon and nitrogen availability on the fungal communities inhabiting the barren and oligotrophic fellfield soils that are widespread across the region are poorly understood. Here, we test how warming with open top chambers (OTCs), irrigation and the organic substrates glucose, glycine and tryptone soy broth (TSB) influence a fungal community inhabiting an oligotrophic maritime Antarctic fellfield soil. In contrast with studies in vegetated soils at lower latitudes, OTCs increased fungal community alpha diversity (Simpson’s index and evenness) by 102–142% in unamended soil after 5 years. Conversely, OTCs had few effects on diversity in substrate-amended soils, with their only main effects, in glycine-amended soils, being attributable to an abundance of Pseudogymnoascus. The substrates reduced alpha and beta diversity metrics by 18–63%, altered community composition and elevated soil fungal DNA concentrations by 1–2 orders of magnitude after 5 years. In glycine-amended soil, OTCs decreased DNA concentrations by 57% and increased the relative abundance of the yeast Vishniacozyma by 45-fold. The relative abundance of the yeast Gelidatrema declined by 78% in chambered soil and increased by 1.9-fold in irrigated soil. Fungal DNA concentrations were also halved by irrigation in TSB-amended soils. In support of regional- and continental-scale studies across climatic gradients, the observations indicate that soil fungal alpha diversity in maritime Antarctica will increase as the region warms, but suggest that the accumulation of organic carbon and nitrogen compounds in fellfield soils arising from expanding plant populations are likely, in time, to attenuate the positive effects of warming on diversity.
Keywords: Antarktis; kjemi; klimaendringer; mikrobiologi; sopper

Evaluation of Temperature-Dependent Complex Refractive Indices of Supercooled Liquid Water Using Downwelling Radiance and In-Situ Cloud Measurements at South Pole - Rowe, Penny M; Walden, Von P; Brandt, Richard E; Town, Michael S; Hudson, Stephen R; Neshyba, Steven (Journal of Geophysical Research: Atmospheres, 2022)
Clouds have a large effect on the radiation budget and represent a major source of uncertainty in climate models. Supercooled liquid clouds can exist at temperatures as low as 235 K, and the radiative effect of these clouds depends on the complex refractive index (CRI) of liquid water. Laboratory measurements have demonstrated that the liquid-water CRI is temperature-dependent, but corroboration with field measurements is difficult. Here we present measurements of the downwelling infrared radiance and in-situ measurements of supercooled liquid water in a cloud at temperatures as low as 240 K, made at South Pole Station in 2001. These results demonstrate that including the temperature dependence of the liquid-water CRI is essential for accurate calculations of radiative transfer through supercooled liquid clouds. Furthermore, we show that when cloud properties are retrieved from infrared radiances (using the spectral range 500–1,200 cm−1) spurious ice may be retrieved if the 300 K CRI is used for cold liquid clouds (∼240 K). These results have implications for radiative transfer in climate models as well as for retrievals of cloud properties from infrared radiance spectra.
Keywords: Antarktis; Sydpolen; atmosfæren; geofysikk; klimamodeller

Temperature- and Nutrients-Induced Phenotypic Changes of Antarctic Green Snow Bacteria Probed by High-Throughput FTIR Spectroscopy - Smirnova, Margarita; Tafintseva, Valeria; Kohler, Achim; Miamin, Uladzislau; Shapaval, Volha (Biology, 2022)
Temperature fluctuations and nutrient composition are the main parameters influencing green snow microbiome. In this study we investigated the influence of temperature and nutrient conditions on the growth and cellular chemical profile of bacteria isolated from green snow. Chemical profiling of the green snow bacteria was done by high-throughput FTIR spectroscopy combined with multivariate data analysis. We showed that temperature and nutrients fluctuations strongly affect growth ability and chemical profile of the green snow bacteria. The size of colonies for green snow bacteria grown at higher (25 °C) and lower (4 °C and 10 °C) than optimal temperature (18 °C) was smaller. All isolates grew on rich medium, and only 19 isolates were able to grow on synthetic minimal media. Lipid and mixed spectral regions showed to be phylogeny related. FTIR fingerprinting indicates that lipids are often affected by the temperature fluctuations. Growth on different media resulted in the change of the whole chemical profile, where lipids showed to be more affected than proteins and polysaccharides. Correlation analysis showed that nutrient composition is clearly strongly influencing chemical changes in the cells, followed by temperature.
Keywords: Antarktis; bakterier; kjemi; mikrobiologi; multivariate data analysis

Spatial and interspecific variation of accumulated highly toxic trace elements between fifteen bird species feathers from Antarctic, Arctic and China - Sun, Yayue; Lu, Zhibo; Xiao, Kaiyan; Zeng, Lingyun; Wang, Juan; Zhang, Yanyun; Gabrielsen, Geir Wing (Environmental Technology & Innovation, 2022)
To assess the impact of human activities and other factors on the levels of highly toxic trace elements in the environment, the contents of eight highly toxic trace elements (arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb) and zinc (Zn)) in feathers of 15 bird species from the Prydz Bay region in the Antarctic, Ny-Alsund region in the Arctic, and eastern China were evaluated in this study. Results showed that feathers collected from the Antarctic showed the highest As, Cu, and Hg contents (1.65–2.85, 9.58–18.56, and 4.77–8.76 μg/g dw, respectively) of the different study areas, whereas Arctic feathers exhibited the highest mean Pb levels (1.82–3.19 μg/g dw), and feathers from China showed significantly lower accumulations of Cr, Ni, Pb, and Zn compared with the other two areas. Overall, most of the studied highly toxic trace element contents in bird feathers from the densely populated and polluted area of eastern China were lower than those from remote polar regions, which are negligibly affected by human activities. In addition, feathers from the Arctic did not show higher highly toxic trace element contents than those of the more remote Antarctic. These results are thus inferred to reflect differences in the dietary structure of birds in the different habitats, as well as historical climate change. Carbon (δ13C) and nitrogen (δ15N) stable isotope ratios of feathers were also measured to evaluate the relationship between diet and highly toxic trace elements. Results showed that highly toxic trace element contents did not increase with increasing trophic levels. Moreover, the methylmercury content accounted for 87.57%–98.59% of the total mercury in all feather samples, regardless of location and species, confirming that most of the mercury entering the feathers is methylated. This finding suggests that the form of mercury changes during the process of transference from internal tissues to feathers, which improves our understanding of the mechanism by which feathers excrete mercury, this behavior greatly reduces the harm to bird health caused by mercury. This study confirms that measuring contaminants in feathers is a long-term and effective method for monitoring highly toxic trace elements pollution in particular environments, making future monitoring of highly toxic trace elements pollution in the polar regions, as well as more typical environments, more convenient.
Keywords: Antarktis; miljøgifter; polarområdene; sjøfugler; økotoksikologi

Aerosol optical properties calculated from size distributions, filter samples and absorption photometer data at Dome C, Antarctica, and their relationships with seasonal cycles of sources - Virkkula, A.; Grythe, H.; Backman, J.; Petäjä, T.; Busetto, M.; Lanconelli, C.; Lupi, A.; Becagli, S.; Traversi, R.; Severi, M.; Vitale, V.; Sheridan, P.; et al. (Atmospheric Chemistry and Physics, 2022)
Keywords: Antarktis; atmosfæren; forurensning

Evaluation of an emergent feature of sub-shelf melt oscillations from an idealized coupled ice sheet–ocean model using FISOC (v1.1) – ROMSIceShelf (v1.0) – Elmer/Ice (v9.0) - Zhao, Chen; Gladstone, Rupert; Galton-Fenzi, Benjamin Keith; Gwyther, David; Hattermann, Tore (Geosci. Model Dev., 2022)
Changes in ocean-driven basal melting have a key influence on the stability of ice shelves, the mass loss from the ice sheet, ocean circulation, and global sea level rise. Coupled ice sheet–ocean models play a critical role in understanding future ice sheet evolution and examining the processes governing ice sheet responses to basal melting. However, as a new approach, coupled ice sheet–ocean systems come with new challenges, and the impacts of solutions implemented to date have not been investigated. An emergent feature in several contributing coupled models to the 1st Marine Ice Sheet–Ocean Model Intercomparison Project (MISOMIP1) was a time-varying oscillation in basal melt rates. Here, we use a recently developed coupling framework, FISOC (v1.1), to connect the modified ocean model ROMSIceShelf (v1.0) and ice sheet model Elmer/Ice (v9.0), to investigate the origin and implications of the feature and, more generally, the impact of coupled modeling strategies on the simulated basal melt in an idealized ice shelf cavity based on the MISOMIP setup. We found the spatial-averaged basal melt rates (3.56 m yr−1) oscillated with an amplitude ∼0.7 m yr−1 and approximate period of ∼6 years between year 30 and 100 depending on the experimental design. The melt oscillations emerged in the coupled system and the standalone ocean model using a prescribed change of cavity geometry. We found that the oscillation feature is closely related to the discretized ungrounding of the ice sheet, exposing new ocean, and is likely strengthened by a combination of positive buoyancy–melt feedback and/or melt–geometry feedback near the grounding line, and the frequent coupling of ice geometry and ocean evolution. Sensitivity tests demonstrate that the oscillation feature is always present, regardless of the choice of coupling interval, vertical resolution in the ocean model, tracer properties of cells ungrounded by the retreating ice sheet, or the dependency of friction velocities to the vertical resolution. However, the amplitude, phase, and sub-cycle variability of the oscillation varied significantly across the different configurations. We were unable to ultimately determine whether the feature arises purely due to numerical issues (related to discretization) or a compounding of multiple physical processes amplifying a numerical artifact. We suggest a pathway and choices of physical parameters to help other efforts understand the coupled ice sheet–ocean system using numerical models.
Keywords: Antarktis; Sørishavet; glasiologi; havnivåstigning; innlandsis; oseanografi

Observed interannual changes beneath Filchner-Ronne Ice Shelf linked to large-scale atmospheric circulation - Hattermann, Tore; Nicholls, Keith W.; Hellmer, Hartmut H.; Davis, Peter E. D.; Janout, Markus A.; Østerhus, Svein; Schlosser, Elisabeth; Rohardt, Gerd; Kanzow, Torsten (Nature Communications, 2021)
Floating ice shelves are the Achilles’ heel of the Antarctic Ice Sheet. They limit Antarctica’s contribution to global sea level rise, yet they can be rapidly melted from beneath by a warming ocean. At Filchner-Ronne Ice Shelf, a decline in sea ice formation may increase basal melt rates and accelerate marine ice sheet mass loss within this century. However, the understanding of this tipping-point behavior largely relies on numerical models. Our new multi-annual observations from five hot-water drilled boreholes through Filchner-Ronne Ice Shelf show that since 2015 there has been an intensification of the density-driven ice shelf cavity-wide circulation in response to reinforced wind-driven sea ice formation in the Ronne polynya. Enhanced southerly winds over Ronne Ice Shelf coincide with westward displacements of the Amundsen Sea Low position, connecting the cavity circulation with changes in large-scale atmospheric circulation patterns as a new aspect of the atmosphere-ocean-ice shelf system.
Keywords: Antarktis; Sørishavet; glasiologi; isshelf; meteorologi; oseanografi

The effectiveness of Virkon® S disinfectant against an invasive insect and implications for Antarctic biosecurity practices - Bartlett, Jesamine C; Radcliffe, Richard James; Convey, Pete; Hughes, Kevin A; Hayward, Scott A L (Antarctic Science, 2021)
The flightless midge Eretmoptera murphyi is thought to be continuing its invasion of Signy Island via the treads of personnel boots. Current boot-wash biosecurity protocols in the Antarctic region rely on microbial biocides, primarily Virkon® S. As pesticides have limited approval for use in the Antarctic Treaty area, we investigated the efficacy of Virkon® S in controlling the spread of E. murphyi using boot-wash simulations and maximum threshold exposures. We found that E. murphyi tolerates over 8 h of submergence in 1% Virkon® S. Higher concentrations increased effectiveness, but larvae still exhibited > 50% survival after 5 h in 10% Virkon® S. Salt and hot water treatments (without Virkon® S) were explored as possible alternatives. Salt water proved ineffective, with mortality only in first-instar larvae across multi-day exposures. Larvae experienced 100% mortality when exposed for 10 s to 50°C water, but they showed complete survival at 45°C. Given that current boot-wash protocols alone are an ineffective control of this invasive insect, we advocate hot water (> 50°C) to remove soil, followed by Virkon® S as a microbial biocide on ‘clean’ boots. Implications for the spread of invasive invertebrates as a result of increased human activity in the Antarctic region are discussed.
Keywords: Antarktis; biologi; biosikkerhet; fjærmygg; forurensning; klimaendringer; miljøpåvirkning; økologi; økosystemer

First discrete iron(II) records from Dome C (Antarctica) and the Holtedahlfonna glacier (Svalbard) - Burgay, François; Barbaro, Elena; Cappelletti, David; Turetta, Clara; Gallet, Jean-Charles; Isaksson, Elisabeth; Stenni, Barbara; Dreossi, Giuliano; Scoto, Federico; Barbante, Carlo; Spolaor, Andrea (Chemosphere, 2021)
Fe(II) is more soluble and bioavailable than Fe(III) species, therefore the investigation of their relative abundance and redox processes is relevant to better assess the supply of bioavailable iron to the ocean and its impact on marine productivity. In this context, we present a discrete chemiluminescence-based method for the determination of Fe(II) in firn matrices. The method was applied on discrete samples from a snow pit collected at Dome C (DC, Antarctica) and on a shallow firn core from the Holtedahlfonna glacier (HDF, Svalbard), providing the first Fe(II) record from both Antarctica and Svalbard. The method showed low detection limits (0.006 ng g−1 for DC and 0.003 ng g−1 for the HDF) and a precision ranging from 3% to 20% RSD. Fe(II) concentrations ranged between the LoD and 0.077 ng g−1 and between the LoD and 0.300 ng g−1 for the Antarctic and Arctic samples, respectively. The Fe(II) contribution with respect to the total dissolved Fe was comparable in both sites accounting, on average, for 5% and 3%, respectively. We found that Fe(II) correctly identified the Pinatubo/Cerro Hudson eruption in the DC record, demonstrating its reliability as volcanic tracer, while, on the HDF core, we provided the first preliminary insight on the processes that might influence Fe speciation in firn matrices (i.e. organic ligands and pH influences).
Keywords: Antarktis; glasiologi; kjemi; polarområdene

Interactive effects of body mass changes and species-specific morphology on flight behavior of chick-rearing Antarctic fulmarine petrels under diurnal wind patterns - Dehnhard, Nina; Klekociuk, Andrew R; Emmerson, Louise (Ecology and Evolution, 2021)
For procellariiform seabirds, wind and morphology are crucial determinants of flight costs and flight speeds. During chick-rearing, parental seabirds commute frequently to provision their chicks, and their body mass typically changes between outbound and return legs. In Antarctica, the characteristic diurnal katabatic winds, which blow stronger in the mornings, form a natural experimental setup to investigate flight behaviors of commuting seabirds in response to wind conditions. We GPS-tracked three closely related species of sympatrically breeding Antarctic fulmarine petrels, which differ in wing loading and aspect ratio, and investigated their flight behavior in response to wind and changes in body mass. Such information is critical for understanding how species may respond to climate change. All three species reached higher ground speeds (i.e., the speed over ground) under stronger tailwinds, especially on return legs from foraging. Ground speeds decreased under stronger headwinds. Antarctic petrels (Thalassoica antarctica; intermediate body mass, highest wing loading, and aspect ratio) responded stronger to changes in wind speed and direction than cape petrels (Daption capense; lowest body mass, wing loading, and aspect ratio) or southern fulmars (Fulmarus glacialoides; highest body mass, intermediate wing loading, and aspect ratio). Birds did not adjust their flight direction in relation to wind direction nor the maximum distance from their nests when encountering headwinds on outbound commutes. However, birds appeared to adjust the timing of commutes to benefit from strong katabatic winds as tailwinds on outbound legs and avoid strong katabatic winds as headwinds on return legs. Despite these adaptations to the predictable diurnal wind conditions, birds frequently encountered unfavorably strong headwinds, possibly as a result of weather systems disrupting the katabatics. How the predicted decrease in Antarctic near-coastal wind speeds over the remainder of the century will affect flight costs and breeding success and ultimately population trajectories remains to be seen.
Keywords: Antarktis; fôring; klimaendringer; ornitologi; petreller; zoologi; økofysiologi; økologi

Projected land ice contributions to twenty-first-century sea level rise - Edwards, Tamsin L; Nowicki, Sophie; Marzeion, Ben; Hock, Regine; Goelzer, Heiko; Seroussi, Hélène; Jourdain, Nicolas C; Slater, Donald A; Turner, Fiona E; Smith, Christopher J; McKenna, Christine M; Simon, Erika; et al. (Nature, 2021)
The land ice contribution to global mean sea level rise has not yet been predicted using ice sheet and glacier models for the latest set of socio-economic scenarios, nor using coordinated exploration of uncertainties arising from the various computer models involved. Two recent international projects generated a large suite of projections using multiple models, but primarily used previous-generation scenarios and climate models, and could not fully explore known uncertainties. Here we estimate probability distributions for these projections under the new scenarios using statistical emulation of the ice sheet and glacier models. We find that limiting global warming to 1.5 degrees Celsius would halve the land ice contribution to twenty-first-century sea level rise, relative to current emissions pledges. The median decreases from 25 to 13 centimetres sea level equivalent (SLE) by 2100, with glaciers responsible for half the sea level contribution. The projected Antarctic contribution does not show a clear response to the emissions scenario, owing to uncertainties in the competing processes of increasing ice loss and snowfall accumulation in a warming climate. However, under risk-averse (pessimistic) assumptions, Antarctic ice loss could be five times higher, increasing the median land ice contribution to 42 centimetres SLE under current policies and pledges, with the 95th percentile projection exceeding half a metre even under 1.5 degrees Celsius warming. This would severely limit the possibility of mitigating future coastal flooding. Given this large range (between 13 centimetres SLE using the main projections under 1.5 degrees Celsius warming and 42 centimetres SLE using risk-averse projections under current pledges), adaptation planning for twenty-first-century sea level rise must account for a factor-of-three uncertainty in the land ice contribution until climate policies and the Antarctic response are further constrained.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action - Handley, Jonathan; Rouyer, Marie-Morgane; Pearmain, Elizabeth J; Warwick-Evans, Victoria; Teschke, Katharina; Hinke, Jefferson T; Lynch, Heather; Emmerson, Louise; Southwell, Colin; Griffith, Gary; Cárdenas, César A; Franco, Aldina M A; et al. (Frontiers in Marine Science, 2021)
Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional high quality areas could benefit from a proposed network of MPAs. Penguins offer a particular opportunity to identify high quality areas because these birds, as highly visible central-place foragers, are considered indicator species whose populations reflect the state of the surrounding marine environment. We compiled a comprehensive dataset of the location of penguin colonies and their associated abundance estimates in Antarctica. We then estimated the at-sea distribution of birds based on information derived from tracking data and through the application of a modified foraging radius approach with a density decay function to identify some of the most important marine areas for chick-rearing adult penguins throughout waters surrounding Antarctica following the Important Bird and Biodiversity Area (IBA) framework. Additionally, we assessed how marine IBAs overlapped with the currently adopted and proposed network of key management areas (primarily MPAs), and how the krill fishery likely overlapped with marine IBAs over the past five decades. We identified 63 marine IBAs throughout Antarctic waters and found that were the proposed MPAs to be adopted, the permanent conservation of high quality areas for penguin species would increase by between 49 and 100% depending on the species. Furthermore, our data show that, despite a generally contracting range of operation by the krill fishery in Antarctica over the past five decades, a consistently disproportionate amount of krill is being harvested within marine IBAs compared to the total area in which the fishery operates. Our results support the designation of the proposed MPA network and offer additional guidance as to where decision-makers should act before further perturbation occurs in the Antarctic marine ecosystem.
Keywords: Antarktis; Sørishavet; biodiversitet; klimaendringer; marin biologi; miljøvern

Evidence for a grounding line fan at the onset of a basal channel under the ice shelf of Support Force Glacier, Antarctica, revealed by reflection seismics - Hofstede, Coen; Beyer, Sebastian; Corr, Hugh; Eisen, Olaf; Hattermann, Tore; Helm, Veit; Neckel, Niklas; Smith, Emma C; Steinhage, Daniel; Zeising, Ole; Humbert, Angelika (The Cryosphere, 2021)
Curvilinear channels on the surface of an ice shelf indicate the presence of large channels at the base. Modelling studies have shown that where these surface expressions intersect the grounding line, they coincide with the likely outflow of subglacial water. An understanding of the initiation and the ice–ocean evolution of the basal channels is required to understand the present behaviour and future dynamics of ice sheets and ice shelves. Here, we present focused active seismic and radar surveys of a basal channel, ∼950 m wide and ∼200 m high, and its upstream continuation beneath Support Force Glacier, which feeds into the Filchner Ice Shelf, West Antarctica. Immediately seaward from the grounding line, below the basal channel, the seismic profiles show an ∼6.75 km long, 3.2 km wide and 200 m thick sedimentary sequence with chaotic to weakly stratified reflections we interpret as a grounding line fan deposited by a subglacial drainage channel directly upstream of the basal channel. Further downstream the seabed has a different character; it consists of harder, stratified consolidated sediments, deposited under different glaciological circumstances, or possibly bedrock. In contrast to the standard perception of a rapid change in ice shelf thickness just downstream of the grounding line, we find a flat topography of the ice shelf base with an almost constant ice thickness gradient along-flow, indicating only little basal melting, but an initial widening of the basal channel, which we ascribe to melting along its flanks. Our findings provide a detailed view of a more complex interaction between the ocean and subglacial hydrology to form basal channels in ice shelves.
Keywords: Antarktis; geovitenskap; glasiologi; isshelf

Norway's path to the Antarctic Treaty - Jølle, Harald Dag (Fram forum, 2021)
Keywords: Antarktis; Antarktistraktaten 1959; Norge; ekspedisjoner; historie; hvalfangst; internasjonal; jus; politikk

Subglacial discharge weakens the stability of the Ross Ice Shelf around the grounding line - Li, Yan; Shi, Hongling; Lu, Yang; Zhang, Zizhan; Xi, Hui (Polar Research, 2021)
In this paper, we examine potential impact of discharge in Subglacial Lake Engelhardt, West Antarctica, on the stability of the Ross Ice Shelf around the grounding line by combining satellite altimetry and remote sensing images. According to satellite altimetry data from the Ice, Cloud and Land Elevation Satellite (ICESat; 2003–06), Subglacial Lake Engelhardt (SLE) discharged ca. 1.91 ± 0.04 km3 of water into the downstream region. The ice-surface record derived from ICESat (2006–09) and CryoSat-2 (2011–17) data shows that the lake gained ca. 2.09 ± 0.05 km3 of water during the refilling event following the drainage event, taking three times as much time to reach the previous water level before the discharge; the calculation demonstrates that water input from an upstream lake is unable to sustain water increase in SLE, indicating that the subglacial, hydrologic system and groundwater flow could have contributed to water increase in SLE via hydrologic networks. Satellite images captured surface depressions and crevasses at the drainage outlet point of hydrologic networks around the grounding line; satellite altimetry data show that the ice surface there is still depressing even though the subglacial discharge has finished, potentially reflecting the long-term impact of subglacial discharge on the stability of the immediate Ross Ice Shelf around the grounding line. Keywords: Antarctic subglacial lakes; water storage change; satellite altimetry; remote sensing; hydraulic potential method.
Keywords: Antarktis; geodesi; hydrologi; isbreer; satellitt bilder; subglasial innsjø

Case Study of Blowing Snow Impacts on the Antarctic Peninsula Lower Atmosphere and Surface Simulated With a Snow/Ice Enhanced WRF Model - Luo, Liping; Zhang, Jing; Hock, Regine; Yao, Yao (Journal of Geophysical Research: Atmospheres, 2021)
To better capture the air-snow-ice interaction, a snow/ice enhanced Weather Research and Forecasting (WRF-ice) model has been developed. This study examines the performance of WRF-ice and its blowing snow component during a strong cyclone event from October 23 to 27, 2017 over the Antarctic Peninsula, which is characterized by a synoptic cyclone crossing the northern part of the Peninsula and an embodied mesoscale cyclone over the Weddell Sea. Evolution of the cyclone is accurately reproduced in the 5-km resolution WRF-ice simulation, and the simulated near-surface conditions agree well with station and satellite observations. Numerical simulations show that the process of blowing snow sublimation can be prominent within the lower atmosphere when the air is dry, and produces moistening and cooling effects. Over relatively warm and humid areas, cloud enhancement by blowing snow can lead to either colder or warmer surfaces because of competing effects of longwave and shortwave cloud radiative forcings. In particular, additional moisture from blowing snow sublimation can slightly intensify precipitation over the mountains. Surface energy budget analysis indicates that absorbed shortwave (Sa), incoming longwave (Ld), and outgoing longwave (Lu) are dominant components of surface energy budget. When increases in Ld, Lu, and sensible heat flux are combined with decreases in Sa and latent heat flux due to blowing snow effects, a negative surface net heat flux (∼0.5 W/m2) occurs during daytime. A positive domain-total surface mass balance (∼0.43 Gt) is generated during the simulated cyclone event due to increases in precipitation, decreases in runoff, and decreases in sublimation.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; geovitenskap; is; meteorologi; polarområdene; satellite; snø

Quantarctica, an integrated mapping environment for Antarctica, the Southern Ocean, and sub-Antarctic islands - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; de Pomereu, Jean; Griffiths, Huw; Headland, Robert; Herried, Brad; Katsumata, Katsuro; Le Brocq, Anne; Licht, Kathy; Morgan, Fraser; Neff, Peter D; et al. (Environmental Modelling & Software, 2021)
Quantarctica (https://www.npolar.no/quantarctica) is a geospatial data package, analysis environment, and visualization platform for the Antarctic Continent, Southern Ocean (>40oS), and sub-Antarctic islands. Quantarctica works with the free, cross-platform Geographical Information System (GIS) software QGIS and can run without an Internet connection, making it a viable tool for fieldwork in remote areas. The data package includes basemaps, satellite imagery, terrain models, and scientific data in nine disciplines, including physical and biological sciences, environmental management, and social science. To provide a clear and responsive user experience, cartography and rendering settings are carefully prepared using colour sets that work well for typical data combinations and with consideration of users with common colour vision deficiencies. Metadata included in each dataset provides brief abstracts for non-specialists and references to the original data sources. Thus, Quantarctica provides an integrated environment to view and analyse multiple Antarctic datasets together conveniently and with a low entry barrier.
Keywords: Antarktis; Sørishavet; geografi; kartografi; polarområdene

Hemispheric black carbon increase after the 13th-century Māori arrival in New Zealand - McConnell, Joseph R; Chellman, Nathan J; Mulvaney, Robert; Eckhardt, Sabine; Stohl, Andreas; Plunkett, Gill; Kipfstuhl, Sepp; Freitag, Johannes; Isaksson, Elisabeth; Gleason, Kelly E; Brugger, Sandra O; McWethy, David B; et al. (Nature, 2021)
New Zealand was among the last habitable places on earth to be colonized by humans. Charcoal records indicate that wildfires were rare prior to colonization and widespread following the 13th- to 14th-century Māori settlement, but the precise timing and magnitude of associated biomass-burning emissions are unknown, as are effects on light-absorbing black carbon aerosol concentrations over the pristine Southern Ocean and Antarctica. Here we used an array of well-dated Antarctic ice-core records to show that while black carbon deposition rates were stable over continental Antarctica during the past two millennia, they were approximately threefold higher over the northern Antarctic Peninsula during the past 700 years. Aerosol modelling demonstrates that the observed deposition could result only from increased emissions poleward of 40° S—implicating fires in Tasmania, New Zealand and Patagonia—but only New Zealand palaeofire records indicate coincident increases. Rapid deposition increases started in 1297 (±30 s.d.) in the northern Antarctic Peninsula, consistent with the late 13th-century Māori settlement and New Zealand black carbon emissions of 36 (±21 2 s.d.) Gg y−1 during peak deposition in the 16th century. While charcoal and pollen records suggest earlier, climate-modulated burning in Tasmania and southern Patagonia, deposition in Antarctica shows that black carbon emissions from burning in New Zealand dwarfed other preindustrial emissions in these regions during the past 2,000 years, providing clear evidence of large-scale environmental effects associated with early human activities across the remote Southern Hemisphere.
Keywords: Antarktis; iskjerner; miljø; paleoklimatologi

Future sea level change under CMIP5 and CMIP6 scenarios from the Greenland and Antarctic ice sheets - Payne, Antony J; Nowicki, Sophie; Abe-Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay-Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J; Calov, Reinhard; Chambers, Christopher; et al. (Geophysical Research Letters, 2021)
Projections of the sea level contribution from the Greenland and Antarctic ice sheets rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous CMIP5 effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Hvordan vet vi det vi vet om global oppvarming? - Seip, Knut Lehre (Naturen, 2021)
Hvordan vet vi det vi vet om global oppvarming? Denne artikkelen diskuterer grunnlaget for det vi vet med stor sikkerhet. I artikkelen diskuterer vi 12 temaer, og velger ut én eller to metoder som illustrerer hvordan kunnskap er skaffet til veie for hvert av temaene.
Keywords: Antarktis; global oppvarming; klimaendringer; klimatologi; polarområdene

Linking Sub-Tropical Evaporation and Extreme Precipitation Over East Antarctica: An Atmospheric River Case Study - Terpstra, Annick; Gorodetskaya, Irina V; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2021)
We investigate an intense snowfall event between 15 and 18 February 2011 over the East Antarctic coastal region which contributed to roughly 24% of the annual snow accumulation. The event was previously associated with an atmospheric river, and here we use both Eulerian and Lagrangian analysis to gain an understanding of the processes contributing to the atmospheric river signature. The planetary-scale configuration during the event consisted of a persistent blocking situation resulting in a sustained meridional flow from the sub-tropics to the Antarctic ice sheet between 20 and 50°E. Within this configuration, synoptic-scale cyclogenesis contributed to slantwise ascent of moisture loaded air parcels toward Antarctica. Landfall of this cyclone’s warm sector coincided with the onset of Antarctic precipitation. Subsequently, a secondary cyclone developed along a pre-existing baroclinic zone. The rapid intensification and propagation speed of this mesoscale cyclone alongside the warm, moist air mass resulted in strong moisture flux convergence ahead of the cyclone, providing additional poleward moisture transport. The poleward progression of warm moist air and a corresponding decrease of sea-surface temperatures implied downward surface sensible and latent heat fluxes throughout the region of intense poleward moisture, roughly between 40 and 60°S. Hence, moisture uptake via surface evaporation was suppressed between the sub-tropics and the polar continent, favoring long-range transport. Identification of the surface moisture uptake region by tracing changes in moisture in air parcels confirmed the limited uptake of moisture during the poleward transport in this case study, with the primary moisture source for Antarctic precipitation located in the sub-tropics.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; meteorologi; nedbør; snøfall

Surface Mass Balance Controlled by Local Surface Slope in Inland Antarctica: Implications for Ice-Sheet Mass Balance and Oldest Ice Delineation in Dome Fuji - Van Liefferinge, Brice; Taylor, Drew; Tsutaki, Shun; Fujita, Shuji; Gogineni, Prasad; Kawamura, Kenji; Matsuoka, Kenichi; Moholdt, Geir; Oyabu, Ikumi; Abe-Ouchi, Ayako; Awasthi, Abhishek; Buizert, Christo; et al. (Geophysical Research Letters, 2021)
The limited number of surface mass balance (SMB) observations in the Antarctic inland hampers estimates of ice-sheet contribution to global sea level and locations with million-year-old ice. We present finely resolved SMB over the past three centuries in a low-accumulation region with significant depth hoar formation on Dome Fuji derived from ∼1,100 km of microwave radar stratigraphy dated with a firn core. The regional-mean SMB over the past 264 years is estimated to ∼22.5 ± 3.3 kg m−2 a−1, but with large local variability of up to 30%. We found that local SMB is negatively correlated with surface slope at scales of a few hundred meters, resulting in anomalous zones of low SMB which represent as much as 8–10% of the total SMB on the inland plateau if the SMB-slope relationship is more widely valid. This impact should be investigated further to improve estimates of Antarctic mass balance and sea-level contribution.
Keywords: Antarktis; glasiologi

Legitimacy of the Antarctic Treaty System: is it time for a reform? - Yermakova, Yelena (The Polar Journal, 2021)
The Antarctic Treaty System (ATS) has governed the Antarctic for the last six decades ensuring it to be a place of peace and scientific cooperation. Like any institution, the ATS exists in order to solve collective action problems through coordination and the creation of norms. But how do we know if a particular institution is the right one to solve a specific problem or address issues regarding the governance of a region? And when is it time to replace or reform such an institution? To answer these questions, we need an account of institutional legitimacy. An assessment of the legitimacy of the ATS is necessary in order to determine whether it is worthy of being empowered through support, or if it is time to reform some aspects of it. Building on the account of legitimacy of global governance institutions proposed by Buchanan and Keohane, the paper assesses the legitimacy of the ATS and argues that it is time to reform some components of it. Specifically, the paper assesses the legitimacy of the ATS based on the following criteria: minimal moral acceptability; comparative benefit; institutional integrity; and accountability. The paper highlights the ATS? shortcomings based on these criteria and suggests reforms that will strengthen the legitimacy of the ATS
Keywords: Antarktis; Antarktistraktaten

Antarktis jubilerer (Polarboken, 2020)
Keywords: Antarktis; historie

Solar UV radiation measurements in Marambio, Antarctica, during years 2017–2019 - Aun, Margit; Lakkala, Kaisa; Sanchez, Ricardo; Asmi, Eija; Nollas, Fernando; Meinander, Outi; Sogacheva, Larisa; De Bock, Veerle; Arola, Antti; de Leeuw, Gerrit; Aaltonen, Veijo; Bolsee, David; et al. (Atmospheric Chemistry and Physics (Print), 2020)
In March 2017, measurements of downward global irradiance of ultraviolet (UV) radiation were started with a multichannel GUV-2511 radiometer in Marambio, Antarctica (64.23∘ S; 56.62∘ W), by the Finnish Meteorological Institute (FMI) in collaboration with the Servicio Meteorológico Nacional (SMN). These measurements were analysed and the results were compared to previous measurements performed at the same site with the radiometer of the Antarctic NILU-UV network during 2000–2008 and to data from five stations across Antarctica. In 2017/2018 the monthly-average erythemal daily doses from October to January were lower than those averaged over 2000–2008 with differences from 2.3 % to 25.5 %. In 2017/2018 the average daily erythemal dose from September to March was 1.88 kJ m−2, while in 2018/2019 it was 23 % larger (2.37 kJ m−2). Also at several other stations in Antarctica the UV radiation levels in 2017/2018 were below average. The maximum UV indices (UVI) in Marambio were 6.2 and 9.5 in 2017/2018 and 2018/2019, respectively, whereas during years 2000–2008 the maximum was 12. Cloud cover, the strength of the polar vortex and the stratospheric ozone depletion are the primary factors that influence the surface UV radiation levels in Marambio. The lower UV irradiance values in 2017/2018 are explained by the high ozone concentrations in November, February and for a large part of October. The role of cloud cover was clearly seen in December, and to a lesser extent in October and November, when cloud cover qualitatively explains changes which could not be ascribed to changes in total ozone column (TOC). In this study, the roles of aerosols and albedo are of minor influence because the variation of these factors in Marambio was small from one year to the other. The largest variations of UV irradiance occur during spring and early summer when noon solar zenith angle (SZA) is low and the stratospheric ozone concentration is at a minimum (the so-called ozone hole). In 2017/2018, coincident low total ozone column and low cloudiness near solar noon did not occur, and no extreme UV indices were measured.
Keywords: Antarktis; forskningsstasjoner; meteorologi; målinger; ozonlaget; ultrafiolett stråling

Surviving the Antarctic Winter—Life Stage Cold Tolerance and Ice Entrapment Survival in The Invasive Chironomid Midge Eretmoptera murphyi - Bartlett, Jesamine C; Convey, Peter; Hayward, Scott A L (Insects, 2020)
Keywords: Antarktis; fjærmygg; insektfysiologi; invasjonsbiologi; kuldeeksponering; kuldetoleranse; mikroklima; overvintring; termiske terskler; zoologi

The ice flux to the Lambert Glacier and Amery Ice Shelf along the Chinese inland traverse and implications for mass balance of the drainage basins, East Antarctica - Cui, Xiangbin; Du, Wenjia; Xie, Huan; Sun, Bo (Polar Research, 2020)
Study of the mass balance of the Antarctic Ice Sheet is critical to estimate its potential contribution to global sea-level rise in the future. As the largest drainage system, the Lambert Glacier–Amery Ice Shelf drainage system plays an important role in the mass balance of the Antarctic Ice Sheet. In this study, the ice thickness measured by airborne ice-penetrating radar with high spatial resolution and accuracy and accurate ice velocity measured by in situ GPS stations along the route of the Chinese National Antarctic Research Expedition inland traverse were used to calculate the ice flux with unprecedented accuracy. This transverse is from Zhongshan Station to Dome A, passing through the east side of the Lambert Glacier and the smaller coastal glacier in the C-Cp basin. The results show that the ice flux across the entire traverse is 24.7 ± 2.8 Gt a−1, along which the section in drainage basin B–C (Lambert Glacier) has an ice flux of 20.9 ± 1.9 Gt a−1 and the section in drainage basin C–Cp (basin adjacent to Lambert Glacier) contributed 3.8 ± 0.4 Gt a−1. The ice flux values in both regions are coincident with the mass balance calculated from the Ice, Cloud, and Land Elevation Satellite, Earth Observing System. Meanwhile, the C–Cp basin shows an ice flux value of 6.6 ± 0.8 Gt a−1 across the grounding line.
Keywords: Antarktis; havnivåstigning; innlandsis; klimaendringer; målinger

High inter- and intraspecific niche overlap among three sympatrically breeding, closely related seabird species: Generalist foraging as an adaptation to a highly variable environment? - Dehnhard, Nina; Achurch, Helen; Clarke, Judy; Michel, Loïc N; Southwell, Colin; Sumner, Michael D; Eens, Marcel; Emmerson, Louise (Journal of Animal Ecology, 2020)
Ecological niche theory predicts sympatric species to show segregation in their spatio-temporal habitat utilization or diet as a strategy to avoid competition. Similarly, within species individuals may specialize on specific dietary resources or foraging habitats. Such individual specialization seems to occur particularly in environments with predictable resource distribution and limited environmental variability. Still, little is known about how seasonal environmental variability affects segregation of resources within species and between closely related sympatric species. The aim of the study was to investigate the foraging behaviour of three closely related and sympatrically breeding fulmarine petrels (Antarctic petrels Thalassoica antarctica, cape petrels Daption capense and southern fulmars Fulmarus glacialoides) in a seasonally highly variable environment (Prydz Bay, Antarctica) with the aim of assessing inter- and intraspecific overlap in utilized habitat, timing of foraging and diet and to identify foraging habitat preferences. We used GPS loggers with wet/dry sensors to assess spatial habitat utilization over the entire breeding season. Trophic overlap was investigated using stable isotope analysis based on blood, feathers and egg membranes. Foraging locations were identified using wet/dry data recorded by the GPS loggers and expectation-maximization binary clustering. Foraging habitat preferences were modelled using generalized additive models and model cross-validation. During incubation and chick-rearing, the utilization distribution of all three species overlapped significantly and species also overlapped in the timing of foraging during the day—partly during incubation and completely during chick-rearing. Isotopic centroids showed no significant segregation between at least two species for feathers and egg membranes, and among all species during incubation (reflected by blood). Within species, there was no individual specialization in foraging sites or environmental space. Furthermore, no single environmental covariate predicted foraging activity along trip trajectories. Instead, best-explanatory environmental covariates varied within and between individuals even across short temporal scales, reflecting a highly generalist behaviour of birds. Our results may be explained by optimal foraging theory. In the highly productive but spatio-temporally variable Antarctic environment, being a generalist may be key to finding mobile prey—even though this increases the potential for competition within and among sympatric species.
Keywords: Antarktis; biologging; klimaendringer; observasjoner; ornitologi; overvåking; sjøfugler; stabile isotoper; zoologi; økologi; økosystemer

Prolonged high-grade metamorphism of supracrustal gneisses from Mühlig-Hofmannfjella, central Dronning Maud Land (East Antarctica) - Elvevold, Synnøve; Engvik, Ane K.; Abu-Alam, Tamer S.; Myhre, Per Inge; Corfu, Fernando (Precambrian Research, 2020)
The bedrock of Mühlig-Hofmannfjella, central Dronning Maud Land in eastern Antarctica, is part of the high-grade Maud Belt and comprises a deep-seated metamorphic-plutonic complex. The P-T-t evolution of anatectic supracrustal gneisses has been recovered through a study of mineral assemblages, textural relationships and U-Pb ID TIMS geochronology on zircon and monazite followed by pseudosection modelling. Peak conditions reached granulite facies conditions (T ≥ 810–820 °C) at moderate crustal depths (P = ca. 8 kbar) and resulted in partial melting. Peak-pressure conditions were followed by isothermal decompression at elevated temperatures. After exhumation to crustal levels of about 4–5 kbar, the area underwent a final near-isobaric cooling, which is documented by a secondary growth of garnet. Zircons indicate a period of growth at 570–566 Ma, whereas monazite ages range from 610 to 525 Ma. A likely heat source for the granulite facies metamorphism is decay of radioactive heat-producing elements in the core of the orogen. The combined geochronology and metamorphic data indicate a prolonged, clockwise P-T path, which reflects collision and formation of a long-lived orogenic plateau.
Keywords: Antarktis; Dronning Maud Land; geologi

Characteristics of ice rises and ice rumples in Dronning Maud Land and Enderby Land, Antarctica - Goel, Vikram; Matsuoka, Kenichi; Berger, Cesar Deschamps; Lee, Ian; Dall, Jørgen; Forsberg, René (Journal of Glaciology, 2020)
Ice rises and rumples, locally grounded features adjacent to ice shelves, are relatively small yet play significant roles in Antarctic ice dynamics. Their roles generally depend upon their location within the ice shelf and the stage of the ice-sheet retreat or advance. Large, long-stable ice rises can be excellent sites for deep ice coring and paleoclimate study of the Antarctic coast and the Southern Ocean, while small ice rises tend to respond more promptly and can be used to reveal recent changes in regional mass balance. The coasts of Dronning Maud Land (DML) and Enderby Land in East Antarctica are abundant with these features. Here we review existing knowledge, presenting an up-to-date status of research in these regions with focus on ice rises and rumples. We use regional datasets (satellite imagery, surface mass balance and ice thickness) to analyze the extent and surface morphology of ice shelves and characteristic timescales of ice rises. We find that large parts of DML have been changing over the past several millennia. Based on our findings, we highlight ice rises suitable for drilling ice cores for paleoclimate studies as well as ice rises suitable for deciphering ice dynamics and evolution in the region.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; glasiologi; isshelf

Networks of international co-authorship in journal articles about Antarctic research, 1998–2015 - Jang, Duckhee; Doh, Soogwan; Choi, Yongjin (Polar Research, 2020)
This study seeks insight into the social structure of Antarctic research from 1998 to 2015 by examining peer-reviewed journal articles listed in the Science Citation Index of the Web of Science database. This study identifies leading countries in peer-reviewed journal article output and applies social network analysis methods to identify countries where authors are collaborating with those affiliated with organizations in different countries. The results show that the number of publications on Antarctica and the proportion of international research collaboration increased from 23.0 to 33.2% during the period of time being considered. The number of articles published by authors affiliated with institutions in emerging countries such as China, Turkey, Brazil and South Korea rose, whereas the proportion of articles published by authors affiliated with institutions in the United States decreased. The largest proportion of academic publications pertaining to Antarctic research was within the natural sciences. Within this broad field, the majority of publications fell within Earth and related environmental sciences and the biological sciences. Social network analysis shows that Antarctic research moved towards a network, in which researchers are internationally more connected than ever before, with countries such as the United States, the United Kingdom, Germany, France and Australia in central positions. Sweden, Belgium and the Netherlands did not account for a high percentage of academic contributions but were still notable for their multinational collaborative research.
Keywords: Antarktis; forskning; publikasjoner; vitenskap

Interhemispheric Asymmetry of Large-Scale Electron Density Gradients in the Polar Cap Ionosphere: UT and Seasonal Variations - Jin, Yaqi; Xiong, Chao (Journal of Geophysical Research: Space Physics, 2020)
The high-latitude ionosphere is highly dynamical with significant irregularities and density gradients. However, the spatial and temporal distributions of density gradients and irregularities are very different between the Arctic and Antarctic. In this report, we study the interhemispheric asymmetry of the large-scale (100 km) density gradients in both polar caps. Our results show that density gradients in the Arctic are enhanced during local winter (December solstice) with a peak around 19 UT. The UT and spatial distributions in the Antarctic local winter (June solstice) are similar to the Arctic except that they are reversed by 12 hr, which indicates a mirror symmetry between hemispheres. The 12-hr difference in the peak density gradients can be explained by the displacements between the geographic and geomagnetic poles. The only asymmetry (anomaly) is the persistence of strong density gradients in the southern polar cap during local summer (December solstice).
Keywords: Antarktis; fysikk; geovitenskap; ionosfæren; polarområdene

Militærpsykologisk forskning i felt: En case-studie av biologiske markører under solokryssing av Antarktisk - Johnsen, Bjørn Helge; Gjeldnes, Rune; Neteland, Hans Olav Monsen; Thayer, Julian F; Phillips, Terry M (Necesse, 2020)
Tradisjonelt har registrering av blodparametere i militærpsykologisk og medisinsk forskning krevd betydelige logistiske, økonomiske og faglige ressurser. Dette har vanskeliggjort bruken av slike parametere. Imidlertid er det utviklet alternative metoder og denne case-studien undersøker anvendeligheten av «Dried Blood Spots» (DBS) under polare forhold. Det første målet med studien er en utprøving av anvendbarheten av DBS (registrering, lagring og ekstrahering av variabler), ana- lysert ved hjelp av “recycling immunoaffinity chromotography», under ekstreme polare feltmessige forhold. Det andre målet med studien var å undersøke om stress og immunparametere målt ved DBS gjenspeiler subjektive evalueringer av belastning under skimarsjen. Det tredje målet var å beskrive hormonelle og immun-responser under ekstreme polare belastninger. Metoden som ble benyttet var DBS registrert under en 90 dagers solo-ekspedisjon uten etterforsyninger, gjennomført over syd- polområdet. Ekspedisjonen var verdens lengste skitur. Resultatene viste at alle 16 planlagte parametere ble ekstrahert med suksess ni måneder etter ekspedisjonen. For å undersøke samvariasjonen mellom subjektive opplevelser og biologiske markører på belastning ble kortisolnivå og pro- og anti-inflammatoriske markører (IL-6 og IL- 10) sammenlignet med polfarerens dagbok. Basert på dagboken ble seks faser med ulik belastning identifisert. Resultatene viste at kortisol og IL-6 responser samvarierte med disse fasene. Resultatene viste også ekstreme kortisol og IL-6 responser under mestring av ekspedisjonen. DBS viste seg dermed som en relevant metode for bruk i felt, under polare betingelser.
Keywords: Antarktis; ekspedisjoner; medisin; psykofysiologi; psykologi

Formation and evolution of an extensive blue ice moraine in central Transantarctic Mountains, Antarctica - Kassab, Christine M; Licht, Kathy J; Petersson, Rickard; Lindbäck, Katrin; Graly, Joseph A; R, Kaplan. Michael (Journal of Glaciology, 2020)
Mount Achernar moraine is a terrestrial sediment archive that preserves a record of ice-sheet dynamics and climate over multiple glacial cycles. Similar records exist in other blue ice moraines elsewhere on the continent, but an understanding of how these moraines form is limited. We propose a model to explain the formation of extensive, coherent blue ice moraine sequences based on the integration of ground-penetrating radar (GPR) data with ice velocity and surface exposure ages. GPR transects (100 and 25 MHz) both perpendicular and parallel to moraine ridges at Mount Achernar reveal an internal structure defined by alternating relatively clean ice and steeply dipping debris bands extending to depth, and where visible, to the underlying bedrock surface. Sediment is carried to the surface from depth along these debris bands, and sublimates out of the ice, accumulating over time (>300 ka). The internal pattern of dipping reflectors, combined with increasing surface exposure ages, suggest sequential exposure of the sediment where ice and debris accretes laterally to form the moraine. Subsurface structure varies across the moraine and can be linked to changes in basal entrainment conditions. We speculate that higher concentrations of debris may have been entrained in the ice during colder glacial periods or entrained more proximal to the moraine sequence.
Keywords: Antarktis; glasiologi; radar observasjoner

Growth-related changes in salt gland mass in gentoo and chinstrap penguin chicks - Kim, Youmin; Jeong, Min-Su; Seo, Hae-Min; Kim, Hankyu; Lee, Woo-Shin; Choi, Chang-Yong (Polar Research, 2020)
The salt gland is a well-developed osmoregulation organ in marine birds, and its relative size often reflects an individual’s feeding environment and osmoregulation capability. The development and functions of salt glands have been described for the Adélie penguin (Pygoscelis adeliae), but this information has been poorly documented in the other two pygoscelid species: gentoo (P. papua) and chinstrap penguins (P. antarcticus). To describe the growth-related changes in salt gland masses in relation to chick growth, we measured the wet mass of the salt glands collected from dead gentoo and chinstrap chicks during the early breeding period. The mass of the salt glands was linearly proportional to their body measurements, especially to body mass, in both species, and no significant difference was detected between the two species. Penguins are obligate marine dwellers throughout their life cycle, and the development of the salt gland in penguin chicks suggests that their ability to regulate dietary osmotic stress begins at an early stage of development after hatching. Furthermore, the linear relationship between the gland mass and body mass also suggests that the osmoregulation capability may continue to develop as penguin chicks grow. This descriptive note provides novel and quantitative information on the early developmental pattern of salt glands in gentoo and chinstrap penguins.
Keywords: Antarktis; marine økosystemer; ornitologi; osmoregulering; osmotisk stress; pingviner; saltkjertel; zoologi

Validation of the TROPOspheric Monitoring Instrument (TROPOMI) surface UV radiation product - Lakkala, Kaisa; Kujanpää, Jukka; Brogniez, Colette; Henriot, Nicolas; Arola, Antti; Aun, Margit; Auriol, Frédérique; Bais, Alkiviadis F; Bernhard, Germar; De Bock, Veerle; Catalfamo, Maxime; Deroo, Christine; et al. (Atmos. Meas. Tech., 2020)
The TROPOspheric Monitoring Instrument (TROPOMI) onboard the Sentinel-5 Precursor (S5P) satellite was launched on 13 October 2017 to provide the atmospheric composition for atmosphere and climate research. The S5P is a Sun-synchronous polar-orbiting satellite providing global daily coverage. The TROPOMI swath is 2600 km wide, and the ground resolution for most data products is 7.2×3.5 km2 (5.6×3.5 km2 since 6 August 2019) at nadir. The Finnish Meteorological Institute (FMI) is responsible for the development of the TROPOMI UV algorithm and the processing of the TROPOMI surface ultraviolet (UV) radiation product which includes 36 UV parameters in total. Ground-based data from 25 sites located in arctic, subarctic, temperate, equatorial and Antarctic areas were used for validation of the TROPOMI overpass irradiance at 305, 310, 324 and 380 nm, overpass erythemally weighted dose rate/UV index, and erythemally weighted daily dose for the period from 1 January 2018 to 31 August 2019. The validation results showed that for most sites 60 %–80 % of TROPOMI data was within ±20 % of ground-based data for snow-free surface conditions. The median relative differences to ground-based measurements of TROPOMI snow-free surface daily doses were within ±10 % and ±5 % at two-thirds and at half of the sites, respectively. At several sites more than 90 % of cloud-free TROPOMI data was within ±20 % of ground-based measurements. Generally median relative differences between TROPOMI data and ground-based measurements were a little biased towards negative values (i.e. satellite data < ground-based measurement), but at high latitudes where non-homogeneous topography and albedo or snow conditions occurred, the negative bias was exceptionally high: from −30 % to −65 %. Positive biases of 10 %–15 % were also found for mountainous sites due to challenging topography. The TROPOMI surface UV radiation product includes quality flags to detect increased uncertainties in the data due to heterogeneous surface albedo and rough terrain, which can be used to filter the data retrieved under challenging conditions.
Keywords: Antarktis; atmosfæren; klimatologi; meteorologi; ultrafiolett stråling

CloudSat-Inferred Vertical Structure of Snowfall Over the Antarctic Continent - Lemonnier, Florentin; Madeleine, Jean-Baptiste; Claud, Chantal; Palerme, Cyril; Genthon, Christophe; L'Ecuyer, Tristan; Wood, Norman B (Journal of Geophysical Research: Atmospheres, 2020)
Current global warming is causing significant changes in snowfall in polar regions, directly impacting the mass balance of the ice caps. The only water supply in Antarctica, precipitation, is poorly estimated from surface measurements. The onboard cloud-profiling radar of the CloudSat satellite provided the first real opportunity to estimate solid precipitation at continental scale. Based on CloudSat observations, we propose to explore the vertical structure of precipitation in Antarctica over the 2007–2010 period. A first division of this data set following a topographical approach (continent vs. peripheral regions, with a 2,250 m topographical criterion) shows a high snowfall rate (275 mm yr at 1,200 m above ground level) with low relative seasonal variation ( ) over the peripheral areas. Over the plateau, the snowfall rate is low (34 mm yr at 1,200 m above ground level) with a much larger relative seasonal variation ( ). A second study that follows a geographical division highlights the average vertical structure of precipitation and temperature depending on the regions and their interactions with topography. In particular, over ice shelves, we see a strong dependence of the distribution of snowfall on the sea ice coverage. Finally, the relationship between precipitation and temperature is analyzed and compared with a simple analytical relationship. This study highlights that precipitation is largely dependent on the advection of air masses along the topographic slopes with an average vertical wind of 0.02 m s . This provides new diagnostics to evaluate climate models with a three-dimensional approach of the atmospheric structure of precipitation.
Keywords: Antarktis; global oppvarming; klimamodeller; klimatologi; meteorologi; nedbør; polarområdene; snøfall

Will Climate Change Impact Polar NOx Produced by Energetic Particle Precipitation? - Maliniemi, Ville; Marsh R., Daniel; Tyssøy, Hilde Nesse; Smith-Johnsen, Christine (Geophysical Research Letters, 2020)
Energetic electron precipitation (EEP) is an important source of polar nitrogen oxides (NOx) in the upper atmosphere. During winter, mesospheric NOx has a long chemical lifetime and is transported to the stratosphere by the mean meridional circulation. Climate change is expected to accelerate this circulation and therefore increase polar mesospheric descent rates. We investigate the Southern Hemispheric polar NOx distribution during the 21st century under a variety of future scenarios using simulations of the Whole Atmosphere Community Climate Model (WACCM). We simulate stronger polar mesospheric descent in all future scenarios that increase the atmospheric radiative forcing. Polar NOx in the upper stratosphere is significantly enhanced in two future scenarios with the largest increase in radiative forcing. This indicates that the ozone depleting NOx cycle will become more important in the future, especially if stratospheric chlorine species decline. Thus, EEP-related atmospheric effects may become more prominent in the future.
Keywords: Antarktis; geofysikk; klimaendringer; klimatologi; ozonlaget; polarområdene; romvitenskap

Four principles to justify claims to jurisdiction and to natural resources in Antarctica - Mancilla, Alejandra (Yearbook of Polar Law, 2020)
Global pressure over Antarctic resources will mount in the course of the coming decades. Three factors are likely to motivate states to claim jurisdictional rights or rights to natural resources in Antarctica: climate change, dwindling natural resources in the rest of the world, and the fact that – by virtue of Article IV of the Antarctic Treaty – the question of sovereignty remains unresolved. It is high time to think about the moral dimensions that should shape Antarctic claims in the future. Is there any state or group of states more entitled than others to make such claims? What does sound management of natural resources require? How should environmental concerns factor into decisions about jurisdictional control and appropriation of natural resources? With these broad questions in the background, in this article I examine four principles of justice that figure prominently in current theories of territorial rights and rights over natural resources in political philosophy: connection, capacity, fair distribution, and need. I show how these principles have been used by states, alone or in tandem, to justify claims to jurisdiction and claims to natural resources in Antarctica. After pointing to their main strengths and weaknesses, I suggest that they may be necessary, but insufficient to build a just framework for jurisdiction and appropriation of resources in the White Continent.
Keywords: Antarktis; jus; politikk; ressurser

Deep glacial troughs and stabilizing ridges unveiled beneath the margins of the Antarctic ice sheet - Morlighem, Mathieu; Rignot, Eric; Binder, Tobias; Blankenship, Donald; Drews, Reinhard; Eagles, Graeme; Eisen, Olaf; Ferraccioli, Fausto; Forsberg, René; Fretwell, Peter; Goel, Vikram; Greenbaum, Jamin S; et al. (Nature Geoscience, 2020)
The Antarctic ice sheet has been losing mass over past decades through the accelerated flow of its glaciers, conditioned by ocean temperature and bed topography. Glaciers retreating along retrograde slopes (that is, the bed elevation drops in the inland direction) are potentially unstable, while subglacial ridges slow down the glacial retreat. Despite major advances in the mapping of subglacial bed topography, significant sectors of Antarctica remain poorly resolved and critical spatial details are missing. Here we present a novel, high-resolution and physically based description of Antarctic bed topography using mass conservation. Our results reveal previously unknown basal features with major implications for glacier response to climate change. For example, glaciers flowing across the Transantarctic Mountains are protected by broad, stabilizing ridges. Conversely, in the marine basin of Wilkes Land, East Antarctica, we find retrograde slopes along Ninnis and Denman glaciers, with stabilizing slopes beneath Moscow University, Totten and Lambert glacier system, despite corrections in bed elevation of up to 1 km for the latter. This transformative description of bed topography redefines the high- and lower-risk sectors for rapid sea level rise from Antarctica; it will also significantly impact model projections of sea level rise from Antarctica in the coming centuries.
Keywords: Antarktis; glasiologi; innlandsis; klimaendringer

Post-depositional loss of nitrate and chloride in Antarctic snow by photolysis and sublimation: a field investigation - Noro, Kazushi; Takenaka, Norimichi (Polar Research, 2020)
Nitrate in snow is subject to post-depositional processing, which leads to a net loss and redistribution within the snowpack. The relative importance of post-depositional loss processes such as the volatilization of nitric acid (HNO3) and photolysis of nitrate has long been debated. Changes in nitrate and chloride concentrations in the snowpack were investigated at H128 (69°23.584’S, 41°33.712’E), an Antarctic coastal site approximately 100 km from Syowa Station in East Antarctica from December 2015 to February 2016. Results indicate that chloride migrated to deeper sites within the snowpack under the influence of water vapour movement. Moreover, 50% of the nitrate on surface snow was lost to photolysis, and approximately 20% of the nitrate was absent at a depth of 40 cm. To enhance our knowledge of the Antarctic geochemical cycle, this study is the first to suggest chloride ion movement in snowpacks or significant nitrate loss for any Antarctic coastal site.
Keywords: Antarktis; geokjemi; kromatografi; observasjoner; ozon; snø; temperatur

New Antarctic clawed lobster species (Crustacea: Decapoda: Nephropidae) from the Upper Cretaceous of James Ross Island - Pinheiro, Allysson P; Saraiva, Antônio Álamo Feitosa; Santana, William; Sayão, Juliana Manso; Figueiredo, Rodrigo Giesta; Rodrigues, Taissa; Weinschütz, Luiz Carlos; Ponciano, Luiza Corral Martins de Oliveira; Kellner, Alexander Wilhelm Armin (Polar Research, 2020)
A new species of nephropid lobster, Hoploparia echinata sp. nov., from the James Ross Island in the Antarctic Peninsula is here described and illustrated. The material was collected in the Santa Marta Formation (Santonian–-Campanian), the basal unit of the Marambio Group, Larsen Basin, located in the western portion of the Antarctic Peninsula. Hoploparia echinata sp. nov. can easily be differentiated from its congeners by the presence of distinct short spines on dorsal and ventral margins on the third maxillipeds, merus of the chelipeds and pereopods; these are the characters not described in other Hoploparia species so far.
Keywords: Antarktis; fossiler; geologi; langhalekreps; paleobiologi; paleogeografi; paleontologi; zoologi

Discovery of a large population of Hygrolembidium isophyllum (Lepidoziaceae, Marchantiophyta) in the South Shetland Islands, Antarctica - Putzke, Jair; Ramos Ferrari, Flávia; Schaefer, Carlos E. G. R. (Polar Research, 2020)
In February 2019, during fieldwork at Harmony Point, Nelson Island, South Shetland Islands, Antarctica, a large population of the rare liverwort Hygrolembidium isophyllum (Lepidoziaceae) was discovered. The occurrence of this rare species reinforces the need to preserve Antarctic Specially Protected Area 133.
Keywords: Antarktis; biologi; levermoser; miljøvern; planter

A Mobile, Multichannel, UWB Radar for Potential Ice Core Drill Site Identification in East Antarctica: Development and First Results - Rodriguez-Morales, Fernando; Braaten, David; Trong Mai, Hoang; Paden, John; Gogineni, Prasad; Yan, Jie-Bang; Abe-Ouchi, Ayako; Fujita, Shuji; Kawamura, Kenji; Tsutaki, Shun; Liefferinge, Brice Van; Matsuoka, Kenichi; et al. (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2020)
We developed a high-performance, multichannel, ultra-wideband radar system for measurements of the base and interior of the East Antarctic Ice Sheet. We designed the radar to be of high power (4000-W peak) yet portable and to be able to operate with 60-MHz bandwidth at a center frequency of 200 MHz, providing high sensitivity and fine vertical resolution relative to current technology. We used the radar to perform extensive measurements as a part of a multinational collaboration. We collected data onboard a tracked vehicle outfitted with an array of high-gain antennas. We sounded 2- to 3-km thick ice near Dome Fuji. Preliminary ice thickness data match those obtained via semicoincident measurements performed with a different surface-based pulse modulated radar system operated during the same field campaign, as well as previous airborne measurements. In addition, we mapped internal reflection horizons with fine vertical resolution from 300 m below the ice surface to ∼100 m above the bed. In this article, we provide a detailed overview of the radar instrument design, implementation, and field measurement setup. We present sample data to illustrate its capabilities and discuss how the data collected with it will be valuable for the assessment of promising drilling sites to recover ice cores that are 0.9–1.5 million years old.
Keywords: Antarktis; glasiologi; innlandsis; iskjerner

The retrospective analysis of Antarctic tracking data project - Ropert-Coudert, Yan; Van de Putte, Anton P; Reisinger, Ryan R; Bornemann, Horst; Charrassin, Jean-Benoît; Costa, Daniel P; Danis, Bruno; Hückstädt, Luis A; Jonsen, Ian D; Lea, Mary-Anne; Thompson, David; Torres, Leigh G; et al. (Scientific Data, 2020)
The Retrospective Analysis of Antarctic Tracking Data (RAATD) is a Scientific Committee for Antarctic Research project led jointly by the Expert Groups on Birds and Marine Mammals and Antarctic Biodiversity Informatics, and endorsed by the Commission for the Conservation of Antarctic Marine Living Resources. RAATD consolidated tracking data for multiple species of Antarctic meso- and top-predators to identify Areas of Ecological Significance. These datasets and accompanying syntheses provide a greater understanding of fundamental ecosystem processes in the Southern Ocean, support modelling of predator distributions under future climate scenarios and create inputs that can be incorporated into decision making processes by management authorities. In this data paper, we present the compiled tracking data from research groups that have worked in the Antarctic since the 1990s. The data are publicly available through biodiversity.aq and the Ocean Biogeographic Information System. The archive includes tracking data from over 70 contributors across 12 national Antarctic programs, and includes data from 17 predator species, 4060 individual animals, and over 2.9 million observed locations.
Keywords: Antarktis; Sørishavet; biologi; økologi; økosystem

Snowfall and Water Stable Isotope Variability in East Antarctica Controlled by Warm Synoptic Events - Servettaz, Aymeric P M; Orsi, Anais J; Curran, Mark A J; Moy, Andrew D; Landais, Amaelle; Agosta, Cécile; Winton, V Holly L; Touzeau, Alexandra; McConnell, Joseph R; Werner, Martin; Baroni, Mélanie (Journal of Geophysical Research: Atmospheres, 2020)
Understanding climate proxy records that preserve physical characteristics of past climate is a prerequisite to reconstruct long-term climatic conditions. Water stable isotope ratios (δ18O) constitute a widely used proxy in ice cores to reconstruct temperature and climate. However, the original climate signal is altered between the formation of precipitation and the ice, especially in low-accumulation areas such as the East Antarctic Plateau. Atmospheric conditions under which the isotopic signal is acquired at Aurora Basin North (ABN), East Antarctica, are characterized with the regional atmospheric model Modèle Atmosphérique Régional (MAR). The model shows that 50% of the snow is accumulated in less than 24 days year−1. Snowfall occurs throughout the year and intensifies during winter, with 64% of total accumulation between April and September, leading to a cold bias of −0.86°C in temperatures above inversion compared to the annual mean of −29.7°C. Large snowfall events are associated with high-pressure systems forcing warm oceanic air masses toward the Antarctic interior, which causes a warm bias of +2.83°C. The temperature-δ18O relationship, assessed with the global atmospheric model ECHAM5-wiso, is primarily constrained by the winter variability, but the observed slope is valid year-round. Three snow δ18O records covering 2004–2014 indicate that the anomalies recorded in the ice core are attributable to the occurrence of warm winter storms bringing precipitation to ABN and support the interpretation of δ18O in this region as a marker of temperature changes related to large-scale atmospheric conditions, particularly blocking events and variations in the Southern Annular Mode.
Keywords: Antarktis; iskjerner; meteorologi; nedbør; paleoklimatologi; vannstabile isotoper

Ice front blocking of ocean heat transport to an Antarctic ice shelf - Wåhlin, Anna K; Steiger, Nadine; Darelius, Elin; Assmann, Karen M; Glessmer, Mirjam; Ha, Ho Kyung; Herraiz-Borreguero, Laura; Heuzé, Céline; Jenkins, Adrian; Kim, Tae-Wan; Mazur, Aleksandra K; Sommeria, Joël; et al. (Nature, 2020)
Mass loss from the Antarctic Ice Sheet to the ocean has increased in recent decades, largely because the thinning of its floating ice shelves has allowed the outflow of grounded ice to accelerate. Enhanced basal melting of the ice shelves is thought to be the ultimate driver of change, motivating a recent focus on the processes that control ocean heat transport onto and across the seabed of the Antarctic continental shelf towards the ice. However, the shoreward heat flux typically far exceeds that required to match observed melt rates, suggesting that other critical controls exist. Here we show that the depth-independent (barotropic) component of the heat flow towards an ice shelf is blocked by the marked step shape of the ice front, and that only the depth-varying (baroclinic) component, which is typically much smaller, can enter the sub-ice cavity. Our results arise from direct observations of the Getz Ice Shelf system and laboratory experiments on a rotating platform. A similar blocking of the barotropic component may occur in other areas with comparable ice–bathymetry configurations, which may explain why changes in the density structure of the water column have been found to be a better indicator of basal melt rate variability than the heat transported onto the continental shelf. Representing the step topography of the ice front accurately in models is thus important for simulating ocean heat fluxes and induced melt rates.
Keywords: Antarktis; glasiologi; global oppvarming; innlandsis; issmelting; klimaendringer

High-precision ice-flow velocities from ground observations on Dalk Glacier, Antarctica - Ai, Songtao; Wang, Shansi; Li, Yuansheng; Moholdt, Geir; Zhou, Chunxia; Liu, Leibao; Yang, Yuande (Polar Science, 2019)
Dalk Glacier, which has been monitored by CHINARE since 2007, is a calving outlet glacier near the Chinese Zhongshan Station in East Antarctica. Using in situ observational azimuthal data from 2007 to 2012, 67 high-precision spatial intersection points were calculated. Consequently, the ice-flow features of the tongue of Dalk Glacier were explored via ground measurements. The maximum observed ice-flow velocity (IV) was 192.72 m/a, at stake P9. The velocities then decreased with the distance from the central flow line on both sides of the glacier in a cross section. Further analysis showed the following: the velocities of each stake increased annually; the closer to the terminus, the faster the ice flowed; and the ascent ratio of the IVs was approximately 10.67 m/a2 in the main flow area. We also observed seasonal variations in the ice-flow velocities, including a speed-up in January 2009 preceding an ice-calving event. The elevation change measurements at the stakes showed fluctuations along the central flow line, which indicates ice-shelf grounding over a seamount that had not been previously identified.
Keywords: Antarktis; glasiologi

What and who is an Antarctic ambassador? - Alexander, Karen A.; Liggett, Daniela; Leane, Elizabeth; Nielsen, Hanne E. F.; Bailey, Jennifer L.; Brasier, Madeline J.; Haward, Marcus (Polar Record, 2019)
The term “Antarctic ambassadorship” is increasingly used to represent an individual’s connection to Antarctica and their subsequent advocacy. However, there is little clarity regarding the concept. To address this, we combined a literature review with an expert elicitation workshop. We argue that (i) the concept of Antarctic ambassador has been understood in myriad ways; (ii) Antarctic ambassadors have a connection to, knowledge of and passion for Antarctica; (iii) they also have a commitment to defending and advancing Antarctic values and (iv) Antarctic ambassadorship is about more than advocacy. We propose the first comprehensive definition of Antarctic ambassadorship. We hope this will provide a cornerstone upon which future research, and a more informed governance of Antarctic tourism, can be built.
Keywords: Antarktis; samfunnsfag

Warm Circumpolar Deep Water at the Western Getz Ice Shelf Front, Antarctica - Assmann, Karen; Darelius, Elin Maria K; Wåhlin, Anna K; Kim, Tae Wan; Lee, Sang Hoon (Geophysical Research Letters, 2019)
The Getz Ice Shelf is one of the largest sources of fresh water from ice shelf basal melt in Antarctica. We present new observations from three moorings west of Siple Island 2016–2018. All moorings show a persistent flow of modified Circumpolar Deep Water toward the western Getz Ice Shelf. Unmodified Circumpolar Deep Water with temperatures up to 1.5 °C reaches the ice shelf front in frequent episodes. These represent the warmest water observed at any ice shelf front in the Amundsen Sea. Mean currents within the warm bottom layer of 18–20 cm/s imply an advection time scale of 7 days from shelf break to ice shelf front. Zonal wind stress at the shelf break affects heat content at the ice shelf front on weekly to monthly time scales. Our 2-year mooring records also evince that upwelling over the shelf break controls thermocline depth on subannual to annual time scales.
Keywords: Antarktis; geofysikk; glasiologi; isbrem; isshelf; observasjoner

Chr. Christensen and C. A. Larsen: A comparative analysis of two whaling entrepreneurs - Basberg, Bjørn L (International Journal of Maritime History, 2019)
Keywords: Antarktis; historie; hvalfangere; hvalfangst

The Four Ladies of Prydz Bay: notes on the naming of a submarine formation in Australian Antarctic Territory - Bathie, Carol; Pett, Janet (The Victorian Naturalist, 2019)
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Nitrogen isotope fractionation explains the 15N enrichment of Antarctic cryptogams by volatilized ammonia from penguin and seal colonies - Bokhorst, Stef; van Logtestijn, Richard; Convey, Peter; Aerts, Rien (Polar Research, 2019)
Vegetation near bird and seal rookeries typically has high δ15N signatures and these high values are linked to the enriched δ15N values of rookery soils. However, Antarctic cryptogams are mostly dependent on atmospheric ammonia (NH3) and volatized NH3 from rookeries is severely depleted in δ15N-NH3. So there is an apparent discrepancy between the isotopically depleted source (NH3) and δ15N-enriched vegetation. In this article, we aim to resolve this discrepancy to better understand the mechanisms and processes involved in isotopic changes during nitrogen transfer between Antarctic marine and terrestrial ecosystems. Under laboratory conditions, we quantified whether volatized NH3 affects the isotopic signature of cryptogams. NH3 volatilizing from penguin guano and elephant seal dung was depleted (44–49‰) in δ15N when captured on acidified filters, compared to the source itself. Cryptogams exposed to the volatized NH3 were enriched (18.8–23.9‰) in δ15N. The moss Andreaea regularis gained more nitrogen (0.9%) than the lichen Usnea antarctica (0.4%) from volatilized NH3, indicating a potential difference in atmospheric NH3 acquisition that is consistent with existing field differences in nitrogen concentrations and δ15N between mosses and lichens in general. This study clarifies the δ15N enrichment of cryptogams resulting from one of the most important nitrogen pathways for Antarctic vegetation.
Keywords: Antarktis; fugler; kjemiske analyser; kryptogamer; lav; moser; planter; seler; økologi

Patchy Lakes and Topographic Origin for Fast Flow in the Recovery Glacier System, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Jordan, Tom A; Kohler, Jack; Ferraccioli, Fausto; Corr, Hugh F; Olesen, Arne V; Forsberg, René; Casal, Tania G (Journal of Geophysical Research: Earth Surface, 2019)
The Recovery subglacial basin, with its largest glacier Recovery Glacier, has been identified as potentially the biggest contributor to future sea level rise from East Antarctica. Subglacial lakes along the main trunk have been detected from satellite data, with four giant lakes (Recovery Lakes A, B, C, and D) located at the onset of the fast ice flow (≥15 m/yr) and multiple smaller lakes along the glacier. The presence of subglacial water potentially plays a key role in the control of fast ice flow of Recovery Glacier. We present new insights on the Recovery Lakes from airborne radar data collected in 2013 and 2015. Using an adjusted classification scheme, we show that a single large area consisting of smaller lakes connected by likely saturated sediment, referred to as Lake AB, exists in the originally proposed area of the Recovery Lakes A and B. We estimate that the current size of Lake AB is ∼4,320 km2. Water likely leaks from the western shore of Lake AB lubricating the bed initiating fast ice flow at this location. The difference in the outlines of Lake AB and the Lakes A and B previously derived from surface features suggested that a larger paleolake existed here in the past. From our data, we find Recovery Lake C to be dry; we attribute fast ice flow originating from this area to be due to a topographic step and thus an increase in ice thickness rather than enhanced lubrication at the bed.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; radar observasjoner; satellite bilder; subglasial innsjø; topografi

Variability of Sediment Accumulation Rates in an Antarctic Fjord - Eidam, Emily F.; Nittrouer, Charles; Lundesgaard, Øyvind; Homolka, Khadijah; Smith, Craig (Geophysical Research Letters, 2019)
Fjords on the West Antarctic Peninsula (WAP) serve as sediment traps, preserving histories of glacial sediment supply. Regional warming trends are expected to change sediment supplies, altering water quality, depositional history, and ecosystem drivers. Our ability to assess magnitudes of these changes is limited by sparse data on modern sediment accumulation. Twelve new cores and four existing cores from Andvord Bay were used to characterize variability in sediment accumulation rates. These range from 1.5 to 7.9 mm/year (0.12 to 0.56 g·cm−2·year−1). Spatial differences and a weak down-fjord gradient in rates suggest diverse sediment sources, including from outside the fjord. This data set provides a comprehensive assessment of sedimentation during the past century, indicating little change in rates due to recent WAP warming, and sets a benchmark for assessing climate-related changes in sediment delivery and ecosystem drivers (e.g., burial disturbance) in the fjord over coming decades.
Keywords: Antarktis; akkumulasjon; bentiske organismer; biodiversitet; fjord; glasiologi; sedimenter; sedimentologi; tidevannsbreen

A continent of and for whiteness?: “White” colonialism and the 1959 Antarctic Treaty - Mancilla, Alejandra (Polar Record, 2019)
There are at least four ways in which Antarctic colonialism was white: it was paradigmatically performed by white men; it consisted in the taking of vast, white expanses of land; it was carried out with a carte blanche (literally, “blank card”) attitude; and it was presented to the world as a white, innocent adventure. While the first, racial whiteness has been amply problematised, I suggest that the last three illuminate yet other moral wrongs of the Antarctic colonial project. Moreover, they might be constitutive of a larger class of “white” colonialisms beyond the White Continent.
Keywords: Antarktis; historie; politikk; samfunnsfag

Quantarctica 3 released - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; Melvær, Yngve; Tronstad, Stein (Fram forum, 2019)
Keywords: Antarktis; geofysikk; geografi; glasiologi; innlandsis; kartografi; satellite bilder

A note on digital elevation model smoothing and driving stresses - McCormack, Felicity S; Roberts, Jason L; Jong, Lenneke M; Young, Duncan A; Beem, Lucas H (Polar Research, 2019)
Ice-flow fields, including the driving stress, provide important information on the current state and evolution of Antarctic and Greenland ice-sheet dynamics. However, computation of flow fields from continent-scale DEMs requires the use of smoothing functions and scales, the choice of which can be ad hoc. This study evaluates smoothing functions and scales for robust calculations of driving stress from Antarctic DEMs. Our approach compares a variety of filters and scales for their capacity to minimize the residual between predicted and observed flow direction fields. We find that a spatially varying triangular filter with a width of 8–10 ice thicknesses provides the closest match between the observed and predicted flow direction fields. We use the predicted flow direction fields to highlight artefacts in observed Antarctic velocities, demonstrating that comparison of multiple observational data sets has utility for quality control of continent-scale data sets.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis; isbreer; istykkelse

Review of The life of José María Sobral: scientist, diarist, and pioneer in Antarctica, by Mary R. Tahan (2018). Cham, Switzerland: Springer International Publishing. 336 pp. ISBN 978-3-319-67267-0 - Millar, Pat (Polar Research, 2019)
Keywords: Antarktis; Otto Nordenskjöld; bokanmeldelser; dagbøker; ekspedisjoner; geodesi; magnetisme; meteorologi; oppdagelsesreiser

First evidence of a tetrapod footprint from the Triassic of northern Victoria Land, Antarctica - Mörs, Thomas; Niedźwiedzki, Grzegorz; Crispini, Laura; Läufer, Andreas; Bomfleur, Benjamin (Polar Research, 2019)
Here, we report on a tetrapod footprint from the Transantarctic Basin in the far north of Victoria Land, which marks the first record of terrestrial vertebrates for this region. The single specimen derives from a previously unknown lithological unit of Middle or Late Triassic age of the Beacon Supergroup in the Helliwell Hills in the central Rennick Glacier area. It differs in both size and morphology clearly from Middle Triassic trackway types from the upper Fremouw Formation of the Queen Alexandra Range in southern Victoria Land, and likely represents a primitive amniote, procolophonid or therapsid. The footprint is the third evidence of fossil vertebrate trackways in Antarctica.
Keywords: Antarktis; fossiler; paleobiologi; paleontologi; terrestriske virveldyr

Very Strong Atmospheric Methane Growth in the 4 Years 2014–2017: Implications for the Paris Agreement - Nisbet, Euan G; Manning, Martin; Dlugokencky, Ed; Fisher, Rebecca; Lowry, Dave; Michel, Sylvia; Myhre, Cathrine Lund; Platt, Stephen Matthew; Allen, Grant; Bousquet, Philippe; Brownlow, Rebecca; Cain, Michelle; et al. (Global Biogeochemical Cycles, 2019)
Atmospheric methane grew very rapidly in 2014 (12.7 ± 0.5 ppb/year), 2015 (10.1 ± 0.7 ppb/year), 2016 (7.0 ± 0.7 ppb/year), and 2017 (7.7 ± 0.7 ppb/year), at rates not observed since the 1980s. The increase in the methane burden began in 2007, with the mean global mole fraction in remote surface background air rising from about 1,775 ppb in 2006 to 1,850 ppb in 2017. Simultaneously the 13C/12C isotopic ratio (expressed as δ13CCH4) has shifted, now trending negative for more than a decade. The causes of methane's recent mole fraction increase are therefore either a change in the relative proportions (and totals) of emissions from biogenic and thermogenic and pyrogenic sources, especially in the tropics and subtropics, or a decline in the atmospheric sink of methane, or both. Unfortunately, with limited measurement data sets, it is not currently possible to be more definitive. The climate warming impact of the observed methane increase over the past decade, if continued at >5 ppb/year in the coming decades, is sufficient to challenge the Paris Agreement, which requires sharp cuts in the atmospheric methane burden. However, anthropogenic methane emissions are relatively very large and thus offer attractive targets for rapid reduction, which are essential if the Paris Agreement aims are to be attained.
Keywords: Antarktis; atmosfæren; atmosfærisk metan; fossilt brensel; global klimamodell; global oppvarming; klimaendringer; klimagasser; metanisotoper; metanutslipp; meteorologi; polarområdene

Influence of Summer Sublimation on δD, δ18O, and δ17O in Precipitation, East Antarctica, and Implications for Climate Reconstruction From Ice Cores - Pang, Hongxi; Hou, Shugui; Landais, Amaelle; Masson-Delmotte, Valérie; Jouzel, Jean; Steen-Larsen, Hans Christian; Risi, Camille; Zhang, Wangbin; Wu, Shuangye; Li, Yuansheng; An, Chunlei; Wang, Yetang; et al. (Journal of Geophysical Research: Atmospheres, 2019)
In central Antarctica, where accumulation rates are very low, summer sublimation of surface snow is a key element of the surface mass balance, but its fingerprint in isotopic composition of water (δD, δ18O, and δ17O) remains unclear. In this study, we examined the influence of summer sublimation on δD, δ18O, and δ17O in precipitation using data sets of isotopic composition of precipitation at various sites on the inland East Antarctica. We found unexpectedly low δ18O values in the summer precipitation, decoupled from surface air temperatures. This feature can be explained by the combined effects of weak or nonexistent temperature inversion and moisture recycling associated with sublimation-condensation processes in summer. Isotopic fractionation during the moisture-recycling process also explains the observed high values of d-excess and 17O-excess in summer precipitation. Our results suggest that the local cycle of sublimation-condensation in summer is an important process for the isotopic composition of surface snow, water vapor, and consequently precipitation on inland East Antarctica.
Keywords: Antarktis; geofysikk; iskjerner; paleoklimatologi; stabile isotoper

Subglacial Geology and Geomorphology of the Pensacola-Pole Basin, East Antarctica - Paxman, Guy J G; Jamieson, Stewart S R; Ferraccioli, Fausto; Jordan, Tom A; Bentley, Michael J; Ross, Neil; Forsberg, René; Matsuoka, Kenichi; Steinhage, Daniel; Eagles, Graeme; Casal, Tania G (Geochemistry, Geophysics, Geosystems, 2019)
The East Antarctic Ice Sheet (EAIS) is underlain by a series of low-lying subglacial sedimentary basins. The extent, geology, and basal topography of these sedimentary basins are important boundary conditions governing the dynamics of the overlying ice sheet. This is particularly pertinent for basins close to the grounding line wherein the EAIS is grounded below sea level and therefore potentially vulnerable to rapid retreat. Here we analyze newly acquired airborne geophysical data over the Pensacola-Pole Basin (PPB), a previously unexplored sector of the EAIS. Using a combination of gravity and magnetic and ice-penetrating radar data, we present the first detailed subglacial sedimentary basin model for the PPB. Radar data reveal that the PPB is defined by a topographic depression situated ~500 m below sea level. Gravity and magnetic depth-to-source modeling indicate that the southern part of the basin is underlain by a sedimentary succession 2–3 km thick. This is interpreted as an equivalent of the Beacon Supergroup and associated Ferrar dolerites that are exposed along the margin of East Antarctica. However, we find that similar rocks appear to be largely absent from the northern part of the basin, close to the present-day grounding line. In addition, the eastern margin of the basin is characterized by a major geological boundary and a system of overdeepened subglacial troughs. We suggest that these characteristics of the basin may reflect the behavior of past ice sheets and/or exert an influence on the present-day dynamics of the overlying EAIS.
Keywords: Antarktis; Sydpolen; Sørpolen; geofysikk; geomorfologi; glasiologi; innlandsis; subglasial geologi; subglasial topografi

Comparison of elastic moduli from seismic diving-wave and ice-core microstructure analysis in Antarctic polar firn - Schlegel, Rebecca; Diez, Anja; Löwe, Henning; Mayer, Christoph; Lambrecht, Astrid; Freitag, Johannes; Miller, Heinrich; Hofstede, Coen; Eisen, Olaf (Annals of Glaciology, 2019)
We compared elastic moduli in polar firn derived from diving wave refraction seismic velocity analysis, firn-core density measurements and microstructure modelling based on firn-core data. The seismic data were obtained with a small electrodynamic vibrator source near Kohnen Station, East Antarctica. The analysis of diving waves resulted in velocity–depth profiles for different wave types (P-, SH- and SV-waves). Dynamic elastic moduli of firn were derived by combining P- and S-wave velocities and densities obtained from firn-core measurements. The structural finite-element method (FEM) was used to calculate the components of the elastic tensor from firn microstructure derived from X-ray tomography of firn-core samples at depths of 10, 42, 71 and 99 m, providing static elastic moduli. Shear and bulk moduli range from 0.39 to 2.42 GPa and 0.68 to 2.42 GPa, respectively. The elastic moduli from seismic observations and the structural FEM agree within 8.5% for the deepest achieved values at a depth of 71 m, and are within the uncertainty range. Our observations demonstrate that the elastic moduli of the firn can be consistently obtained from two independent methods which are based on dynamic (seismic) and static (tomography and FEM) observations, respectively, for deeper layers in the firn below ~10 m depth.
Keywords: Antarktis; glasiologi; seismologi

Project and Community Management in Polar Sciences – Challenges and Opportunities - Werner, Kirstin; Zaika, Yulia; Pavlov, Alexey K; Lidström, Sven; Pope, Allen; Badhe, Renuka; Brückner, Marlen; Cristini, Luisa (Adv. Geosci., 2019)
Because geoscientific research often occurs via community-instigated bursts of activity with multi-investigator collaborations variously labelled as e.g., years (The International Polar Year IPY), experiments (World Ocean Circulation Experiment WOCE), programs (International Ocean Discovery Program), missions (CRYOSAT spacecraft), or decades (The International Decade of Ocean Exploration IDOE), successful attainment of research goals generally requires skilful scientific project management. In addition to the usual challenges of matching scientific ambitions to limited resources, on-going coordination and specifically project management, planning and implementation of polar science projects often involve many uncertainties caused by, for example, unpredictable weather or ocean and sea ice conditions, large-scale logistical juggling; and often these collaborations are spatially distributed and take place virtually. Large amounts of funding are needed to procure the considerable infrastructure and technical equipment required for polar expeditions; permissions to enter certain regions must be requested; and potential risks for expedition members as well as technical issues in extreme environments need to be considered. All these aspects are challenging for polar science projects, which therefore need a well thought-through program including a realistic alternative “plan B” and possibly also a “plan C” and “plan D”. The four most challenging overarching themes in polar science project management have been identified: international cooperation, interdisciplinarity, infrastructure, and community management. In this paper, we address ongoing challenges and opportunities in polar science project management based on a survey among 199 project and community managers and an additional of 85 project team members active in the field of polar sciences. Case studies and survey results are discussed with the conclusive goal to provide recommendations on how to fully reach the potential of polar sciences project and community management.
Keywords: Antarktis; geovitenskap; internasjonal samarbeid; klimaendringer; miljøendringer; polarområdene

A nematode in the mist: Scottnema lindsayae is the only soil metazoan in remote Antarctic deserts, at greater densities with altitude - Zawierucha, Krzysztof; Marshall, Craig J; Wharton, David; Janko, Karel (Polar Research, 2019)
A decrease in biodiversity and density of terrestrial organisms with increasing altitude and latitude is a well-known ecogeographical pattern. However, studies of these trends are often taxonomically-biased toward well-known organisms and especially those with relatively large bodies, and environmental variability at the local scale may perturb these general effects. Here, we focus on understudied organisms—soil invertebrates—in Antarctic deserts, which are among the driest and coldest places on Earth. We sampled two remote Antarctic sites in the Darwin Glacier area and established an altitudinal gradient running from 210 to 836 m a.s.l. We measured soil geochemistry and organic matter content and linked these parameters with the presence of soil invertebrates. We found three general outcomes, two of which are consistent with general assumptions: (a) the hostile climatic condition of the Darwin Glacier region supports an extremely low diversity of soil metazoans represented by a single nematode species—Scottnema lindsayae; (b) soil geochemistry is the main factor influencing distribution of nematodes at the local scale. Contrary to our expectations, a positive correlation was found between nematode density and altitude. This last observation could be explained by an additional effect of soil moisture as we found this increased with altitude and may be caused by orographic clouds, which are present in this region. To the best of our knowledge such effects have been described in tropical and temperate regions. Potential effect of orographic clouds on soil properties in polar deserts may be a fruitful area of ecological research on soil fauna.
Keywords: Antarktis; biodiversitet; geokjemi; jord; metazoan; rundormer; økogeografi; økosystemer

Verification and Improvement of the Ability of CFSv2 to Predict the Antarctic Oscillation in Boreal Spring - Zhang, Dapeng; Huang, Yanyan; Sun, Bo; Li, Fei; Wang, Huijun (Advances in Atmospheric Sciences, 2019)
The boreal spring Antarctic Oscillation (AAO) has a significant impact on the spring and summer climate in China. This study evaluates the capability of the NCEP’s Climate Forecast System, version 2 (CFSv2), in predicting the boreal spring AAO for the period 1983–2015. The results indicate that CFSv2 has poor skill in predicting the spring AAO, failing to predict the zonally symmetric spatial pattern of the AAO, with an insignificant correlation of 0.02 between the predicted and observed AAO Index (AAOI). Considering the interannual increment approach can amplify the prediction signals, we firstly establish a dynamical–statistical model to improve the interannual increment of the AAOI (DY AAOI), with two predictors of CFSv2-forecasted concurrent spring sea surface temperatures and observed preceding autumn sea ice. This dynamical–statistical model demonstrates good capability in predicting DY AAOI, with a significant correlation coefficient of 0.58 between the observation and prediction during 1983–2015 in the two-year-out cross-validation. Then, we obtain an improved AAOI by adding the improved DY AAOI to the preceding observed AAOI. The improved AAOI shows a significant correlation coefficient of 0.45 with the observed AAOI during 1983–2015. Moreover, the unrealistic atmospheric response to March–April–May sea ice in CFSv2 may be the possible cause for the failure of CFSv2 to predict the AAO. This study gives new clues regarding AAO prediction and short-term climate prediction.
Keywords: Antarktis; atmosfæren; klimatologi; meteorologi

Polarårboken Glacier (Polarboken, 2018)
Keywords: Antarktis; geografi; glasiologi

SuperDARN Radar-Derived HF Radio Attenuation During the September 2017 Solar Proton Events - Bland, Emma C; Heino, Erkka; Kosch, Michael J; Partamies, Noora (Space Weather, 2018)
Two solar proton events in September 2017 had a significant impact on the operation of the Super Dual Auroral Radar Network (SuperDARN), a global network of high-frequency (HF) radars designed for observing F region ionospheric plasma convection. Strong polar cap absorption caused near-total loss of radar backscatter, which prevented the primary SuperDARN data products from being determined for a period of several days. During this interval, the high-latitude and polar cap radars measured unusually low levels of background atmospheric radio noise. We demonstrate that these background noise measurements can be used to observe the spatial and temporal evolution of the polar cap absorption region, using an approach similar to riometry. We find that the temporal evolution of the SuperDARN radar-derived HF attenuation closely follows that of the cosmic noise absorption measured by a riometer. Attenuation of the atmospheric noise up to 10 dB at 12 MHz is measured within the northern polar cap, and up to 14 dB in the southern polar cap, which is consistent with the observed backscatter loss. Additionally, periods of enhanced attenuation lasting 2–4 hr are detected by the midlatitude radars in response to M- and X-class solar flares. Our results demonstrate that SuperDARN's routine measurements of atmospheric radio noise can be used to monitor 8- to 20-MHz radio attenuation from middle to polar latitudes, which may be used to supplement riometer data and also to investigate the causes of SuperDARN backscatter loss during space weather events.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; ionosfæren; polarområdene; radiostøy

Contextualizing the 1997 warm event observed at Patriot Hills in the interior of West Antarctica - Carrasco, Jorge F (Polar Research, 2018)
Between 5 and 8 December 1997, the surface air temperature increased up to 3°C in the interior of West Antarctica, at Patriot Hills (PH), located at about 80°08’S, 81°16ʹ W, at an elevation of 855 m a.s.l. This was about 15°C warmer than the mean air temperature (−12°C) for this location at this time of the year. The ice surface field along the hills used as a runway for large aircraft melted, forming small ponds at the foot of the slope. This warm event was associated with a passing mid-tropospheric ridge that reached the interior of West Antarctica, whose anticyclonic circulation advected warm air towards the PH area. The foehn effect of the descending airflow on the northern slope of PH did not significantly contribute to the warming. The El Niño–Southern Oscillation (ENSO) was reaching its mature phase during the last quarter of 1997 and the warming/melting episode may be related to large-scale circulation associated with ENSO occurrence. However, warm events in the interior of West Antarctica may occur during any phase of ENSO. In contrast, the negative phase of the Antarctic Oscillation seems to support the development of the mid-tropospheric ridges that can advect warm maritime air towards the interior of West Antarctica. The 3°C registered at PH may be one of the highest near-surface air temperatures measured below 2500 m a.s.l. in the far interior coastal area of West Antarctica. This suggests a new subregion for determining air temperature records in Antarctica may need to be considered.
Keywords: Antarktis; føhn; føn; lufttemperatur; meteorologi; oppvarming; smelting; snø; sørlig oscillasjon

On the long-ignored scientific achievements of the Belgica expedition 1897–1899 - De Deckker, Patrick (Polar Research, 2018)
The Belgica expedition, which left Belgium in August 1897, was the first to spend 13 months continuously in Antarctic waters, before returning in late 1899. This was not only an exploratory venture, as new lands and oceans were charted, but more importantly it was an exceptional and successful scientific voyage. After the return of the expedition, a vast array of scientific data was processed and eventually 92 publications in some nine volumes funded by the Belgica Commission appeared over 40 years as a series called Résultats du voyage de la Belgica en 1897–99 sous le commandement de A. de Gerlache de Gomery – rapports scientifiques. Disappointingly, those significant results have been mostly ignored in the scientific literature and the paper here aims to inform scientists of the achievements of the Belgica expedition and where to obtain the information. Many of the climatological and oceanographic data obtained by the expeditioners ought to be examined in line with the changes that are occurring today in the Antarctic Peninsula region as a result of global warming. Some of the Belgica data form an important database to critically assess environmental changes over 120 years in the region of the Antarctic Peninsula.
Keywords: Antarktis; Belgica ekspedisjon; glasiologi; global oppvarming; klimaendringer; klimatologi; meteorologi; miljøendringer; oppdagelsesreiser; oseanografi; vitenskap

Basal Settings Control Fast Ice Flow in the Recovery/Slessor/Bailey Region, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F; Kohler, Jack; Olesen, Arne V; Forsberg, René (Geophysical Research Letters, 2018)
The region of Recovery Glacier, Slessor Glacier, and Bailey Ice Stream, East Antarctica, has remained poorly explored, despite representing the largest potential contributor to future global sea level rise on a centennial to millennial time scale. Here we use new airborne radar data to improve knowledge about the bed topography and investigate controls of fast ice flow. Recovery Glacier is underlain by an 800 km long trough. Its fast flow is controlled by subglacial water in its upstream and topography in its downstream region. Fast flow of Slessor Glacier is controlled by the presence of subglacial water on a rough crystalline bed. Past ice flow of adjacent Recovery and Slessor Glaciers was likely connected via the newly discovered Recovery-Slessor Gate. Changes in direction and speed of past fast flow likely occurred for upstream parts of Recovery Glacier and between Slessor Glacier and Bailey Ice Stream. Similar changes could also reoccur here in the future.
Keywords: Antarktis; geofysikk; geologi; glasiologi; havnivåstigning; isbre; isstrøm

I Roald Amundsens fotspor til Sydpolen med besøk på Bettytoppen - Furholt, Astrid (Polarboken, 2018)
Keywords: Antarktis; ekspedisjoner; historie

A preliminary survey of the terrestrial arthropods of the Rosenthal Islands, Antarctica - Gantz, J D; Spacht, Drew E; Lee, Richard E (Polar Research, 2018)
The Rosenthal Islands lie along the western edge of the Antarctic Peninsula. They are largely inaccessible and the few research projects in the area have focused on seabird colonies, so nothing has been known about the arthropod fauna on these islands. We conducted a preliminary survey of the arthropods associated with large penguin colonies. We identified two species of Collembola (Cryptopygus antarcticus and Friesea grisea), four species of mites (Alaskozetes antarcticus, Hydrogamasellus racovitzai, Tectopenthalodes villosus and Rhagidia sp.) and one insect (Belgica antarctica). The mite A. antarcticus and the collembolan C. antarcticus were common in large aggregations at our collecting sites and were occasionally observed on the surface of penguin guano without vegetative cover. The insect, a chironomid midge, was less common and found only in vegetated areas.
Keywords: Antarktis; biologi; fauna; leddyr; midder; pingviner; zoologi

Facing the climate change conundrum at the South Pole: actors’ perspectives on the implications of global warming for Chilean Antarctic governance - Gladkova, Ekaterina; Blanco-Wells, Gustavo; Nahuelhual, Laura (Polar Research, 2018)
Antarctica is recognized as being geopolitically and scientifically important, and as one of the regions with the greatest potential to affect and be affected by global climate change. Still, little is known in practice about how climate change will be handled within the main governance framework of the continent: the Antarctic Treaty System (ATS). Using qualitative interviews, participant observations and policy document analysis, this paper explores the perspectives of Chilean scientific, political and non-governmental actors regarding the implications of climate change for the current Antarctic governance framework. Results corroborate a misalignment of the climate change agenda and the ATS, stemming from the divergent views displayed by a wide network of actors. From the interviews, two predominant visions emerge: (i) climate change as an opportunity, where actors recognize the role of Antarctica in regulating global climate and stress greater opportunities to conduct Antarctic-based climate change research, the need for strategic international collaboration, and the reinforcement of Chile’s position in Antarctica through science; (ii) climate change as a burden where actors acknowledge climate change as a global problem, largely external to Antarctica, express disbelief regarding the effectiveness of local actions to tackle climate change and do not associate with climate change governance. The study concludes that climate change may become a dividing, rather than a unifying, field of action in Chilean Antarctic governance, reinforcing previously existing geopolitical tendencies.
Keywords: Antarktis; Antarktistraktaten; geopolitikk; klimaendringer; vitenskap

Provenance, transport and diagenesis of sediment in polar areas: a case study in Profound Lake, King George Island, Antarctica - Hernández, Ana C; Bastias, Joaquin; Matus, Daniela; Mahaney, William C (Polar Research, 2018)
Detailed scanning electron microscopy (SEM) micro-texture and mineralogical analysis of lacustrine sediment recovered from Profound Lake (also known as Uruguay Lake), Antarctica, was conducted in the foreland area of the Collins Glacier, King George Island. Very coarse and coarse sand grade size fractions (2 mm – 600 μm) were examined with SEM/ energy dispersive spectrometry, while the total sand fraction and fines (silt + clay) were examined using x-ray diffraction to determine relationships to source rock, weathering and transport history and long-term clay mineral weathering, all of which are poorly understood in polar areas. The mineralogy of these sediments was compared with petrographical information of the country rock to identify potential detrital sources. The association of recovered detrital minerals, sometimes strongly pre-weathered, supports release from source rock of basaltic and andesitic compositions. The micro-texture analysis of quartz, magnetite and various plagioclase grains show micro-features that reveal a complex weathering–diagenesis history tentatively extending into the Paleogene. The bedrock was eroded mostly by glacial processes and mechanical action presumed to result from glacial crushing. Alteration minerals, likely the product of pre-weathering, are probably sourced from weathered bedrock during contact with the sub-aerial atmosphere prior to entrainment. However, amorphous silica precipitation indicates weathering subsequent to glacial erosion from the source bedrock. Cracks of variable dimensions are mostly characteristic of either frost weathering or glacial transport, and involve mechanical and chemical processes.
Keywords: Antarktis; geologi; mineralogi; petrografi; polarområdene; sedimentologi

Antarctic environmental protection: strengthening the links between science and governance - Hughes, Kevin A; Constable, Andrew; Frenot, Yves; López-Martinez, Jerónimo; McIvor, Ewan; Njåstad, Birgit; Terauds, Aleks; Liggett, Daniela; Roldan, Gabriela; Wilmotte, Annick; Xavier, José C (Environmental Science & Policy, 2018)
The Antarctic has significant environmental, scientific, historic, and intrinsic values, all of which are worth protecting into the future. Nevertheless, the area is subject to an increasing level and diversity of human activities that may impact these values within marine, terrestrial and cryosphere environments. Threats to the Antarctic environment, and to the aforementioned values, include climate change, pollution, habitat destruction, wildlife disturbance and non-native species introductions. Over time, a suite of legally binding international agreements, which form part of the Antarctic Treaty System (ATS), has been established to help safeguard the Antarctic environment and provide a framework for addressing the challenges arising from these threats. Foremost among these agreements are the Protocol on Environmental Protection to the Antarctic Treaty and the Convention on the Conservation of Antarctic Marine Living Resources. Many scientists working in Antarctica undertake research that is relevant to Antarctic environmental policy development. More effective two-way interaction between scientists and those responsible for policy development would further strengthen the governance framework, including by (a) better communication of policy makers’ priorities and identification of related science requirements and (b) better provision by scientists of ‘policy-ready’ information on existing priorities, emerging issues and scientific/technological advances relevant to environmental protection. The Scientific Committee on Antarctic Research (SCAR) has a long and successful record of summarizing policy-relevant scientific knowledge to policy makers, such as through its Group of Specialists on Environmental Affairs and Conservation (GOSEAC) up to 2002, currently the SCAR Standing Committee on the Antarctic Treaty System (SCATS) and recently through its involvement in the Antarctic Environments Portal. Improvements to science-policy communication mechanisms, combined with purposeful consideration of funding opportunities for policy-relevant science, would greatly enhance international policy development and protection of the Antarctic environment.
Keywords: Antarktis; miljøvern

Current logistical capacity is sufficient to deliver the implementation and management of a representative Antarctic protected area system - Hughes, Kevin A; Grant, Susie M (Polar Research, 2018)
Antarctica’s terrestrial ecosystems are vulnerable to impacts resulting from climate change and local human activities. The Antarctic Treaty System (ATS) provides for the designation of protected areas through the Protocol on Environmental Protection to the Antarctic Treaty. Unsystematic use of agreed management tools, including Antarctic Specially Protected Areas (ASPAs), has resulted in a protected area system lacking representation across the full range of Antarctic terrestrial ecosystems and Antarctic Conservation Biogeographic Regions (ACBRs). Systematic Conservation Planning (SCP) methods provide established mechanisms to fulfil ATS protected area designation goals. However, how would a continent-wide ASPA system be delivered should appropriate sites be identified using SCP or other methods? Although the rate of area protection has slowed recently, we show that newer Consultative Parties to the Antarctic Treaty are increasingly active as ASPA proponents and may have scope for further engagement with protected area management activities. Furthermore, all 16 ACBRs were found to be within the operational footprint of at least two Parties, indicating that this current logistical footprint could support the implementation and management of a continent-wide ASPA system. Effective management of a representative Antarctic protected areas system could be delivered through greater participation by those Parties with currently more limited protected area management responsibilities and greater use of remote-sensing technologies for protected area monitoring, where appropriate. Crucially, political will to implement an ASPA system identified through SCP approaches may be greater once a pragmatic means of delivery and effective management has been identified.
Keywords: Antarktis; Antarktistraktaten; biodiversitet; forvaltning; klimaendringer; menneskelig påvirkning; miljøvern; områdevern; økosystemer

Deriving micro- to macro-scale seismic velocities from ice-core c axis orientations - Kerch, Johanna; Diez, Anja; Weikusat, Ilka; Eisen, Olaf (The Cryosphere, 2018)
One of the great challenges in glaciology is the ability to estimate the bulk ice anisotropy in ice sheets and glaciers, which is needed to improve our understanding of ice-sheet dynamics. We investigate the effect of crystal anisotropy on seismic velocities in glacier ice and revisit the framework which is based on fabric eigenvalues to derive approximate seismic velocities by exploiting the assumed symmetry. In contrast to previous studies, we calculate the seismic velocities using the exact c axis angles describing the orientations of the crystal ensemble in an ice-core sample. We apply this approach to fabric data sets from an alpine and a polar ice core. Our results provide a quantitative evaluation of the earlier approximative eigenvalue framework. For near-vertical incidence our results differ by up to 135 m s−1 for P-wave and 200 m s−1 for S-wave velocity compared to the earlier framework (estimated 1 % difference in average P-wave velocity at the bedrock for the short alpine ice core). We quantify the influence of shear-wave splitting at the bedrock as 45 m s−1 for the alpine ice core and 59 m s−1 for the polar ice core. At non-vertical incidence we obtain differences of up to 185 m s−1 for P-wave and 280 m s−1 for S-wave velocities. Additionally, our findings highlight the variation in seismic velocity at non-vertical incidence as a function of the horizontal azimuth of the seismic plane, which can be significant for non-symmetric orientation distributions and results in a strong azimuth-dependent shear-wave splitting of max. 281 m s−1 at some depths. For a given incidence angle and depth we estimated changes in phase velocity of almost 200 m s−1 for P wave and more than 200 m s−1 for S wave and shear-wave splitting under a rotating seismic plane. We assess for the first time the change in seismic anisotropy that can be expected on a short spatial (vertical) scale in a glacier due to strong variability in crystal-orientation fabric (±50 m s−1 per 10 cm). Our investigation of seismic anisotropy based on ice-core data contributes to advancing the interpretation of seismic data, with respect to extracting bulk information about crystal anisotropy, without having to drill an ice core and with special regard to future applications employing ultrasonic sounding.
Keywords: Antarktis; glasiologi

Mapping glacier-related research in polar regions: a bibliometric analysis of research output from 1987 to 2016 - Liang, Qi; Peng, Sha; Niu, Beibei; Zhou, Chunxia; Wang, Zhen (Polar Research, 2018)
We carried out a bibliometric analysis of literature related to glaciers in polar regions from the period 1987–2016 indexed in the Science Citation Index Expanded database. A comprehensive review was performed by analysing the research output trends, publication categories, main journals, leading countries and their collaborations, leading scientists, author keywords and Keywords Plus. The results indicated that the number of publications related to glaciers in polar regions has increased rapidly. The USA and several European countries, including the UK, France, Germany and Switzerland, are the leaders in the field of glacial studies, as reflected both in the productivity measures and in the distribution of core scientists. Quaternary Science Reviews, the Journal of Glaciology, and Geophysical Research Letters were the most productive journals for glacial studies. The synthesized analysis of the keywords demonstrated the current research emphases and hinted at future research trends. Reconstructing past climate changes through studies of ice-core records is one of the most important research subjects. Numerical modelling has become a commonly used tool in polar region glacial research. A better understanding of the responses of glaciers to widespread climatic warming is needed now and in the future.
Keywords: Antarktis; bibliometri; glasiologi; isbreer; klimaendringer; litteratur; miljøendringer; polarområdene

The moral limits of territorial claims in Antarctica - Mancilla, Alejandra (Ethics & International Affairs, 2018)
By virtue of the Antarctic Treaty, signed in 1959, the territorial claims to Antarctica of seven of the original signatories were held in abeyance or “frozen.” Considered by many as an exemplar of international law, the Antarctic Treaty System has come to be increasingly questioned, however, in a very much changed global scenario that presents new challenges to the governance of the White Continent. In this context, it is necessary to gain a clearer understanding of the moral weight of those initial claims, which stand (despite being frozen) as a cornerstone of the treaty. The aim of this article is to offer an appraisal of such claims, which may be divided into two main kinds: those grounded on some relevant link to the territory, and those grounded on official documents and geographical doctrines. After pointing to the limitations and challenges that they face, I conclude with some remarks about how this assessment ought to serve as a starting point to rethink the territorial status of Antarctica.
Keywords: Antarktis; historie; jus; politikk; ressurser

Mesospheric Nitric Acid Enhancements During Energetic Electron Precipitation Events Simulated by WACCM-D - Orsolini, Yvan J.; Smith-Johnsen, Christine; Marsh, Daniel R.; Stordal, Frode; Rodger, Craig J.; Verronen, Pekka T.; Clilverd, Mark A. (Journal of Geophysical Research: Atmospheres, 2018)
While observed mesospheric polar nitric acid enhancements have been attributed to energetic particle precipitation through ion cluster chemistry in the past, this phenomenon is not reproduced in current whole-atmosphere chemistry-climate models. We investigate such nitric acid enhancements resulting from energetic electron precipitation events using a recently developed variant of the Whole Atmosphere Community Climate Model (WACCM) that includes a sophisticated ion chemistry tailored for the D-layer of the ionosphere (50–90 km), namely, WACCM-D. Using the specified dynamics mode, that is, nudging dynamics in the troposphere and stratosphere to meteorological reanalyses, we perform a 1-year-long simulation (July 2009–June 2010) and contrast WACCM-D with the standard WACCM. Both WACCM and WACCM-D simulations are performed with and without forcing from medium-to-high energy electron precipitation, allowing a better representation of the energetic electrons penetrating into the mesosphere. We demonstrate the effects of the strong particle precipitation events which occurred during April and May 2010 on nitric acid and on key ion cluster species, as well as other relevant species of the nitrogen family. The 1-year-long simulation allows the event-related changes in neutral and ionic species to be placed in the context of their annual cycle. We especially highlight the role played by medium-to-high energy electrons in triggering ion cluster chemistry and ion-ion recombinations in the mesosphere and lower thermosphere during the precipitation event, leading to enhanced production of nitric acid and raising its abundance by 2 orders of magnitude from 10−4 to a few 10−2 ppb.
Keywords: Antarktis; elektroner; energiske partikler; geomagnetiske stormer; geovitenskap; ionosfæren; klimamodeller; meteorologi; polarområdene; salpetersyre; stratosfæren

Psoroma antarcticum, a new lichen species from Antarctica and neighbouring areas - Park, Chae Haeng; Hong, Soon Gyu; Elvebakk, Arve (Polar Biology, 2018)
Keywords: Antarktis; biodiversitet; botanikk; lav; moser; planter

Influence of meteorological parameters on atmospheric CO2 at Bharati, the Indian Antarctic research station - Pathakoti, Mahesh; Gaddamidi, Sreenivas; Gharai, Biswadip; Sudhakaran Syamala, Prijith; Venkata Narasimha Rao, Pamaraju; Choudhury, Saroj Bandh; Venkata Raghavendra, Kaila; Dadhwal, Vinay Kumar (Polar Research, 2018)
During the 35th Indian Scientific Expedition to Antarctica, measurements of atmospheric carbon dioxide (CO 2 ) were carried out using a Li-Cor CO 2 /H 2 O analyser at Bharati, the Indian Antarctic research station. This study examines the short-term variability of atmospheric CO 2 during the austral summer (January–February) of 2016. An average of 396.25 ± 4.20 ppm was observed during the study period. Meteorological parameters such as relative humidity, precipitation, wind speed, air temperature and atmospheric boundary layer height in conjunction with photosynthetically active radiation, the biological activity indicator which modulates atmospheric CO 2 concentration have been investigated. High wind speed (>20 m s −1 ) combined with precipitation scavenges CO 2 in the atmosphere, resulting in low concentrations at the study site. The lowest CO 2 concentration of 385 ppm coincided with heavy precipitation of 15 mm during study period. Statistical analysis of the data shows that precipitation and relative humidity independently correlated 55% (r = −0.55) and 32% (r = −0.32), respectively, with the variability of CO 2 mixing in the atmosphere at the study site. Atmospheric CO 2 was significantly correlated with precipitation alone with a p value of 0.003. Further, multiple regression analysis was performed to test the significant relation between variability of atmospheric CO 2 and meteorological parameters. Long-range air-mass transport analysis depicted that the majority of the air masses are reaching the study site through the oceanic region.
Keywords: Antarktis; atmosfæren; drivhuseffekt; drivhusgasser; forskning; karbondioksid; klimagasser; luftmassetransport; meteorologi; nedbør; polarområdene

Interhemispheric Survey of Polar Cap Aurora - Reidy, Jade; Fear, Robert; Whiter, Daniel; Lanchester, Betty; Kavanagh, Andrew John; Milan, Steve; Carter, Jennifer; Paxton, Larry; Zhang, Yongliang (Journal of Geophysical Research: Space Physics, 2018)
This study investigates the interhemispheric nature of polar cap auroras via ultraviolet imaging, combined with particle data, to determine whether they occur on open or closed field lines. Data from the SSUSI (Special Sensor Ultraviolet Spectrographic Imager) instrument on board the DMSP (Defence Meteorological Satellite Program) spacecraft are examined. The DMSP spacecraft are in 90-min orbits; hence, images of each hemisphere are separated by 45 min providing a good opportunity for interhemispheric study. 21 polar cap arc (PCA) events are recorded in December 2015 which have particle data from the SSJ/4 particle spectrometer associated with an arc in at least one hemisphere. Nine events are found to contain 'arcs' consistent with a closed field line mechanism, that is, arcs associated with an ion signature present in both hemispheres. Six events contained arcs that were consistent with an 'open field line' mechanism, that is, they were associated with electron-only precipitation. Events containing arcs that were not consistent with either of these expectations are also explored, including an example of a 'non-conjugate' theta aurora and an interesting example of auroral morphology similar to a PCA which is associated with a geomagnetic storm. Seasonal effects are also investigated through a statistical analysis of PCAs over 4 months in 2015. It is found that PCAs are visible in the SSUSI data at least 20% of the time and that it is likely some are missed due to the spacecraft field of view and poor sensitivity in the summer hemisphere due to increased solar illumination.
Keywords: Antarktis; astronomi; energiske partikler; geomagnetiske stormer; meteorologi; polarlys; polarområdene; solvind

Psychological Hibernation in Antarctica - Sandal, Gro Mjeldheim; van deVijver, Fons J. R.; Smith, Nathan (Frontiers in Psychology, 2018)
Human activity in Antarctica has increased sharply in recent years. In particular during the winter months, people are exposed to long periods of isolation and confinement and an extreme physical environment that poses risks to health, well-being and performance. The present study aimed to gain a better understanding of processes contributing to psychological resilience in this context. Specifically, the study examined how the use of coping strategies changed over time, and the extent to which changes coincided with alterations in mood and sleep. Two crews (N = 27) spending approximately 10 months at the Concordia station completed the Utrecht Coping List, the Positive and Negative Affect Schedule (PANAS), and a structured sleep diary at regular intervals (x 9). The results showed that several variables reached a minimum value during the midwinter period, which corresponded to the third quarter of the expedition. The effect was particularly noticeable for coping strategies (i.e., active problem solving, palliative reactions, avoidance, and comforting cognitions). The pattern of results could indicate that participants during Antarctic over-wintering enter a state of psychological hibernation as a stress coping mechanism.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Description of plant communities on Half Moon Island, Antarctica - Schmitz, Daniela; Putzke, Jair; Pereira de Albuquerque, Margéli; Schünemann, Adriano Luis; Costa Beber Vieira, Frederico; de Carvalho Victoria, Filipe de Carvalho Victoria; Batista Pereira, Antônio (Polar Research, 2018)
During February–March of the austral summers of 2013/14 and 2014/2015, fieldwork was performed on Half Moon Island, South Shetland Archipelago, Antarctica, to evaluate the distribution and abundance of mosses and lichens, as well as to describe and map the plant communities there. The quadrat (20 × 20 cm) sampling method was employed in a phytosociological study that aimed to describe these communities. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The number of species totalled 38 bryophytes, 59 lichens, only one flowering plant (Deschampsia antarctica Desv.), and two macroscopic terrestrial algae. Five types of plant communities were identified on the island, as follows: (1) fruticose lichen and moss cushion, (2) moss carpet, (3) muscicolous lichen, (4) crustose lichen and (5) moss turf.
Keywords: Antarktis; botanikk; bryozoa; flora; fytososiologi; lav; moser; planter; økologi

A continent-wide search for Antarctic petrel breeding sites with satellite remote sensing - Schwaller, Mathew R; Lynch, Heather J; Tarroux, Arnaud; Prehn, Brandon (Remote Sensing of Environment, 2018)
The Antarctic petrel (Thalassoica antarctica) has been identified as a key species for monitoring the status and health of the Southern Ocean and Antarctic ecosystems. Breeding colonies of the Antarctic petrel are often found on isolated nunataks far from inhabited stations, some up to hundreds of kilometers from the shoreline. It is difficult therefore to monitor and census known colonies, and it is believed that undiscovered breeding locations remain to be found. We developed an algorithm that can detect Antarctic petrel colonies and used it to complete a continent-wide survey using Landsat-8 Operational Line Imager (OLI) imagery in Antarctica up to the southernmost extent of Landsat's orbital view at 82.68°S. Our survey successfully identified 8 known Antarctic petrel colonies containing 86% of the known population of Antarctic petrels. The survey also identified what appears to be a significant population of breeding birds in areas not known to host breeding Antarctic petrel colonies. Our survey suggests that the breeding population at Mt. Biscoe (66°13′S 51°21′E), currently reported to be in the 1000s, may actually be on the order of 400,000 breeding pairs, which would make it the largest known Antarctic petrel breeding colony in the world. The algorithm represents a first-ever attempt to apply satellite remote sensing to assess the distribution and abundance of the Antarctic petrel on a continent-wide basis. As such, we note several algorithm shortcomings and identify research topics for algorithm improvement. Even with these caveats, our algorithm for identifying Antarctic petrel colonies with Landsat imagery demonstrates the feasibility of monitoring their populations using satellite remote sensing and identifies breeding locations, including Mt. Biscoe, that should be considered high priorities for validation with directed field surveys.
Keywords: Antarktis; hekkekoloni; jordobservasjon; ornitologi; petreller; sjøfugler; zoologi

Nighttime mesospheric ozone enhancements during the 2002 southern hemispheric major stratospheric warming - Smith-Johnsen, Christine; Orsolini, Yvan; Stordal, Frode; Limpasuvan, Varavut; Pérot, Kristell (Journal of Atmospheric and Solar-Terrestrial Physics, 2018)
Sudden Stratospheric Warmings (SSW) affect the chemistry and dynamics of the middle atmosphere. Major warmings occur roughly every second winter in the Northern Hemisphere (NH), but has only been observed once in the Southern Hemisphere (SH), during the Antarctic winter of 2002. Observations by the Global Ozone Monitoring by Occultation of Stars (GOMOS, an instrument on board Envisat) during this rare event, show a 40% increase of ozone in the nighttime secondary ozone layer at subpolar latitudes compared to non-SSW years. This study investigates the cause of the mesospheric nighttime ozone increase, using the National Center for Atmospheric Research (NCAR) Whole Atmosphere Community Climate Model with specified dynamics (SD-WACCM). The 2002 SH winter was characterized by several reductions of the strength of the polar night jet in the upper stratosphere before the jet reversed completely, marking the onset of the major SSW. At the time of these wind reductions, corresponding episodic increases can be seen in the modelled nighttime secondary ozone layer. This ozone increase is attributed largely to enhanced upwelling and the associated cooling of the altitude region in conjunction with the wind reversal. This is in correspondence to similar studies of SSW induced ozone enhancements in NH. But unlike its NH counterpart, the SH secondary ozone layer appeared to be impacted less by episodic variations in atomic hydrogen. Seasonally decreasing atomic hydrogen plays however a larger role in SH compared to NH.
Keywords: Antarktis; atmosfæren; geovitenskap; ozonlaget

Revisiting perceptions and evolving culture: a community dialogue on women in polar research - Starkweather, Sandra; Seag, M; Lee, O; Pope, A (Polar Research, 2018)
Women have made outstanding contributions to polar research in recent decades, though full engagement may be hindered by persistent inequities, including notably the prevalence of workplace harassment. Remote field settings, such as those pervasive in polar research, have been identified as particularly susceptible to cultures of harassment. It was therefore timely at the Polar 2018 Open Science Conference in Davos, Switzerland, to convene a discussion focused on women’s perspectives and experiences. A panel discussion—“From Entering the Field to Taking the Helm: Perspectives of Women in Polar Research”—took place on 20 June 2018 and featured five women undertaking work from marine biotechnology to organizational leadership, across career levels. Over 300 conference attendees joined the lunchtime panel. The panellists’ perspectives on historical barriers, current challenges and future prospects revealed that while challenges persist, experiences vary greatly. Audience engagement underscored the need to sustain dialogue at polar meetings, to bring visibility to the statistics related to workplace harassment and to encourage polar science organizations to assume leadership on promoting equitable workplace culture.
Keywords: Antarktis; arbeidsmiljø; kjønn; kultur; likestilling; polarforskning; sosiologi; trakassering; vitenskap

Precipitation instruments at Rothera Station, Antarctic Peninsula: a comparative study - Tang, Malcolm S Y; Nettukandy Chenoli, Sheeba; Colwell, Steve; Grant, Rosey; Simms, Mairi; Law, John; Abu Samaha, Azizan (Polar Research, 2018)
Direct measurement of precipitation in the Antarctic using ground-based instruments is important to validate the results from climate models, reanalyses and satellite observations. Quantifying precipitation in Antarctica faces many unique challenges such as wind and other technical difficulties due to the harsh environment. This study compares a variety of precipitation measurements in Antarctica, including satellite data and reanalysis fields at Rothera Station, Antarctica Peninsula. The tipping bucket gauges (TBGs) were less sensitive than laserbased sensors (LBSs). The most sensitive LBS (Visibility and Present Weather Sensor, VPF-730) registered 276 precipitation days, while the most sensitive TBG (Universal Precipitation Gauge, UPG-1000) detected 152 precipitation days. Case studies of the precipitation and seasonal accumulation results show the VPF-730 to be the most reliable precipitation sensor of the evaluated instruments. The precipitation amounts given by the reanalyses were positively correlated with wind speed. The precipitation from the Japanese 55-year Reanalysis was most affected by wind speed. Case studies also show that during low wind periods, precipitation measurements from the instruments were very close to the precipitation measurement given by the Global Precipitation Climatology Project (GPCP) 1-degreedaily (1DD) data. During strong wind events, the GPCP 1DD did not fully capture the effect of wind, accounting for the relatively small precipitation amount. The Laser Precipitation Monitor (LPM) and Campbell Scientific-700 (CS700H) experienced instrumental errors during the study, which caused the precipitation readings to become exceedingly high and low, respectively. Installing multiple LBSs in different locations (in close proximity) can help identify inconsistency in the readings.
Keywords: Antarktis; analyser; klimatologi; meteorologi; nedbør; satellitt observasjoner

Temporal variation in trophic relationships among three congeneric penguin species breeding in sympatry - Tarroux, Arnaud; Lydersen, Christian; Trathan, Philip N; Kovacs, Kit M. (Ecology and Evolution, 2018)
Penguins are a monophyletic group in which many species are found breeding sympatrically, raising questions regarding how these species coexist successfully. Here, the isotopic niche of three sympatric pygoscelid penguin species was investigated at Powell Island, South Orkney Islands, during two breeding seasons (austral summers 2013–2014 and 2015–2016). Measurements of carbon (δ13C) and nitrogen (δ15N) stable isotope ratios were obtained from blood (adults) or feather (chicks) samples collected from Adélie Pygoscelis adeliae, chinstrap P. antarctica, and gentoo P. papua penguins. Isotopic niche regions (a proxy for the realized trophic niches) were computed to provide estimates of the trophic niche width of the studied species during the breeding season. The isotopic niche regions of adults of all three species were similar, but gentoo chicks had noticeably wider isotopic niches than the chicks of the other two species. Moderate to strong overlap in isotopic niche among species was found during each breeding season and for both age groups, suggesting that the potential for competition for shared food sources was similar during the two study years, although the actual level of competition could not be determined owing to the lack of data on resource abundance. Clear interannual shifts in isotopic niche were seen in all three species, though of lower amplitude for adult chinstrap penguins. These shifts were due to variation in carbon, but not nitrogen, isotopic ratios, which could indicate either a change in isotopic signature of their prey or a switch to an alternative food web. The main conclusions of this study are that (1) there is a partial overlap in the isotopic niches of these three congeneric species and that (2) they responded similarly to changes that likely occurred at the base of their food chain between the 2 years of the study.
Keywords: Antarktis; fôring; hekkekoloni; klimaendringer; krill; miljøendringer; pingviner; plankton; stabile isotoper; zoologi

Investigation of Babesia sp. in pygoscelid penguins at the South Shetland Islands - Thijl Vanstreels, Ralph Eric; Ferreira Junior, Francisco C; de Angeli Dutra, Daniela; Epiphanio, Sabrina; Braga, Érika M; Pistorius, Pierre A; Catão-Dias, José Luiz (Polar Research, 2018)
Babesia spp. are tick-borne parasites, and 16 avian-infecting species have been described to date, including one species ( Babesia peircei ) that infects penguins. Considering the results of a recent study reporting Babesia sp. in penguins on Deception Island, South Shetland Islands, we re-examined the samples obtained in a previous investigation on the occurrence of blood parasites in adult Adélie ( Pygoscelis adeliae ), chinstrap ( Pygoscelis antarcticus ) and gentoo penguins ( Pygoscelis papua ) on King George and Elephant islands, South Shetland Islands. Notwithstanding a comprehensive re-examination of the blood smears, Babesia sp. was not detected. When we employed two nested PCR tests targeting the 18S rRNA gene of Babesia , a considerable proportion of the samples produced positive results; however, gene sequencing revealed these were due to cross-amplification of non-target organisms. We therefore did not detect Babesia sp. infection in penguins on King George and Elephant islands. Additional studies will be valuable to clarify the distribution and epidemiology of tick-borne pathogens in sub-Antarctic and Antarctic seabirds.
Keywords: Antarktis; biologi; epidemiologi; ornitologi; parasitter; pingviner; sjøfugler; zoologi

Topographic Steering of Enhanced Ice Flow at the Bottleneck Between East and West Antarctica - Winter, Kate; Ross, Neil; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F J; Forsberg, René; Matsuoka, Kenichi; Olesen, Arne V; Casal, Tania G (Geophysical Research Letters, 2018)
Hypothesized drawdown of the East Antarctic Ice Sheet through the “bottleneck” zone between East and West Antarctica would have significant impacts for a large proportion of the Antarctic Ice Sheet. Earth observation satellite orbits and a sparseness of radio echo sounding data have restricted investigations of basal boundary controls on ice flow in this region until now. New airborne radio echo sounding surveys reveal complex topography of high relief beneath the southernmost Weddell/Ross ice divide, with three subglacial troughs connecting interior Antarctica to the Foundation and Patuxent Ice Streams and Siple Coast ice streams. These troughs route enhanced ice flow through the interior of Antarctica but limit potential drawdown of the East Antarctic Ice Sheet through the bottleneck zone. In a thinning or retreating scenario, these topographically controlled corridors of enhanced flow could however drive ice divide migration and increase mass discharge from interior West Antarctica to the Southern Ocean.
Keywords: Antarktis; glasiologi; innlandsis; isgjennomtrengende; isstrøm; radarundersøkelser

Global Cooling Contributed to the Establishment of a Modern-Like East Asian Monsoon Climate by the Early Miocene - Zhang, Ran; Zhang, Zhongshi; Jiang, Dabang (Geophysical Research Letters, 2018)
The establishment of a modern-like monsoon climate in East Asia by the early Miocene was a complex process forced by several factors, and previous studies paid less attention to global cooling. Here we investigate this process using climate modeling by considering changes in topography and global cooling under the early Miocene boundary conditions. Using early Miocene paleogeography and an atmospheric CO2 concentration of 560 ppmv, our model results indicate that a nonzonal climate pattern has appeared in East China but that this climate exhibits weak precipitation and wind seasonality. Such seasonality strengthens as the concentration of atmospheric CO2 decreases from 560 to 420 ppmv and resembles the modern-like condition after the growth of the Antarctic ice sheet. Although the development of East Asian topography can further strengthen this seasonality, our results indicate that global cooling is also pivotal for the establishment of a modern-like monsoon climate in East Asia.
Keywords: Antarktis; innlandsis; klimamodeller; klimatologi; nedbør; paleogeografi

Persistent Organic Pollutants in the East Antarctic Atmosphere: Inter-Annual Observations from 2010 to 2015 Using High-Flow-Through Passive Sampling - Bengtson Nash, Susan M; Wild, Sean J; Hawker, Darryl W; Cropp, Roger A; Hung, Hayley; Wania, Frank; Xiao, Hang; Bohlin-Nizzetto, Pernilla; Bignert, Anders; Broomhall, Sara (Environmental Science & Technology, 2017)
In the first multiyear sampling effort for POPs in the eastern Antarctic atmosphere, 32 PCBs and 38 organochlorine pesticides were targeted in air collected with a high-flow-through passive sampler. Agricultural chemicals were found to dominate atmospheric profiles, in particular HCB and endosulfan-I, with average concentrations of 12 600 and 550 fg/m3, respectively. HCB showed higher concentrations in the austral summer, indicative of local, temperature-dependent volatilisation, while endosulfan-I appeared to show fresh, late-austral-summer input followed by temporally decreasing levels throughout the year. The current-use herbicide, trifluralin, and the legacy pesticides mirex and toxaphene, were detected in Antarctic air for the first time. Trifluralin was observed at low but increasing levels over the five-year period. Its detection in the Antarctic atmosphere provides evidence of its persistence and long-range environmental transport capability. While a time frame of five years exceeds the duration of most Antarctic air monitoring efforts, it is projected that continuous monitoring at the decadal scale is required to detect an annual 10% change in atmospheric concentrations of key analytes. This finding emphasizes the importance of continuous, long-term monitoring efforts in polar regions, that serve a special role as sentinel environments of hemispheric chemical usage trends.
Keywords: Antarktis; atmosfæren; forurensning; kjemiske analyser; miljøgifter

Fracture propagation and stability of ice shelves governed by ice shelf heterogeneity - Borstad, Chris; McGrath, Daniel; Pope, Allen (Geophysical Research Letters, 2017)
Tabular iceberg calving and ice shelf retreat occurs after full-thickness fractures, known as rifts, propagate across an ice shelf. A quickly evolving rift signals a threat to the stability of Larsen C, the Antarctic Peninsula's largest ice shelf. Here we reveal the influence of ice shelf heterogeneity on the growth of this rift, with implications that challenge existing notions of ice shelf stability. Most of the rift extension has occurred in bursts after overcoming the resistance of suture zones that bind together neighboring glacier inflows. We model the stresses in the ice shelf to determine potential rift trajectories. Calving perturbations to ice flow will likely reach the grounding line. The stability of Larsen C may hinge on a single suture zone that stabilizes numerous upstream rifts. Elevated fracture toughness of suture zones may be the most important property that allows ice shelves to modulate Antarctica's contribution to sea level rise.
Keywords: Antarktis; geofysikk; glasiologi; havnivåstigning; is; isberg; isbrem; isfjell; isshelf; kalv; kalving

Patterns of fungal–algal symbiont association in Usnea aurantiaco-atra reveal the succession of lichen–moss communities in Fildes Peninsula, Antarctica - Cao, Shunan; Peng, Fang; Zheng, Hongyuan; Liu, Chuanpeng; Zhou, Qiming (Polar Research, 2017)
Usnea aurantiaco-atra is the most widespread flora in Fildes Peninsula. There are two growth types of U. aurantiaco-atra: the erect form on rocks and the prostrate form associated with mosses. Phylogenetic analysis showed that individuals of the two growth forms share genotypes. Moreover, haploid disequilibrium testing indicated no significant genetic difference for the two growth forms when fungal and algal internal transcribed spacer rDNA were treated as two alleles of one lichen individual. The two growth forms of U. aurantiaco-atra appear to reflect different stages of lichen–moss community succession. A mode is proposed for demonstrating the occurrence of this succession.
Keywords: Antarktis; botanikk; flora; fylogenetikk; lav; moser; planter

Microbes influence the biogeochemical and optical properties of maritime Antarctic snow - Hodson, Andrew; Nowak, Aga; Cook, Joseph; Sabacka, Marie; Wharfe, Emma S; Pearce, David Anthony; Convey, Peter; Vieira, Gonçalo (Journal of Geophysical Research: Biogeosciences, 2017)
Snowmelt in the Antarctic Peninsula region has increased significantly in recent decades, leading to greater liquid water availability across a more expansive area. As a consequence, changes in the biological activity within wet Antarctic snow require consideration if we are to better understand terrestrial carbon cycling on Earth's coldest continent. This paper therefore examines the relationship between microbial communities and the chemical and physical environment of wet snow habitats on Livingston Island of the maritime Antarctic. In so doing, we reveal a strong reduction in bacterial diversity and autotrophic biomass within a short (<1 km) distance from the coast. Coastal snowpacks, fertilized by greater amounts of nutrients from rock debris and marine fauna, develop obvious, pigmented snow algal communities that control the absorption of visible light to a far greater extent than with the inland glacial snowpacks. Absorption by carotenoid pigments is most influential at the surface, while chlorophyll is most influential beneath it. The coastal snowpacks also indicate higher concentrations of dissolved inorganic carbon and CO2 in interstitial air, as well as a close relationship between chlorophyll and dissolved organic carbon (DOC). As a consequence, the DOC resource available in coastal snow can support a more diverse bacterial community that includes microorganisms from a range of nearby terrestrial and marine habitats. Therefore, since further expansion of the melt zone will influence glacial snowpacks more than coastal ones, care must be taken when considering the types of communities that may be expected to evolve there.
Keywords: Antarktis; biogeokjemi; mikrobiologi; mikroorganismer; snøalger; snøpakke; snøsmelting

An enigmatic fossil penguin from the Eocene of Antarctica - Jadwiszczaka, Piotr; Mörs, Thomas (Polar Research, 2017)
Tarsometatarsi are key skeletal elements in penguin palaeontology. They constitute, among others, type specimens of all 10 widely accepted species of fossil penguins from the Eocene La Meseta Formation on Seymour Island (Graham Land, Antarctic Peninsula). Here, we report on a recently collected large-sized tarsometatarsus from this formation that represents a new morphotype. We are convinced that the morphotype corresponds to a new species, but the material is too scarce for a taxonomic act. Undoubtedly, the bone discussed here is a valuable addition to our knowledge on diversity of early penguins.
Keywords: Antarktis; fossiler; paleobiologi; paleontologi; pingviner

Antarctic ice rises: small in size but big on impact - Matsuoka, Kenichi (Fram forum, 2017)
Ice discharge from the Antarctic Ice Sheet directly impacts global sea level, making ice sheet dynamics a central topic in antarctic research. Glaciologists are studying a poorly understood but potentially important phenomenon that looks like a little hill of ice. They call these hills “ice rises”.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf

Occurrence and average behavior of pulsating aurora - Partamies, Noora; Whiter, Daniel; Kadokura, Akira; Kauristie, Kirsti; Nesse Tyssøy, Hilde; Massetti, Stefano; Stauning, Peter; Raita, Tero (Journal of Geophysical Research: Space Physics, 2017)
Motivated by recent event studies and modeling efforts on pulsating aurora, which conclude that the precipitation energy during these events is high enough to cause significant chemical changes in the mesosphere, this study looks for the bulk behavior of auroral pulsations. Based on about 400 pulsating aurora events, we outline the typical duration, geomagnetic conditions, and change in the peak emission height for the events. We show that the auroral peak emission height for both green and blue emission decreases by about 8 km at the start of the pulsating aurora interval. This brings the hardest 10% of the electrons down to about 90 km altitude. The median duration of pulsating aurora is about 1.4 h. This value is a conservative estimate since in many cases the end of event is limited by the end of auroral imaging for the night or the aurora drifting out of the camera field of view. The longest durations of auroral pulsations are observed during events which start within the substorm recovery phases. As a result, the geomagnetic indices are not able to describe pulsating aurora. Simultaneous Antarctic auroral images were found for 10 pulsating aurora events. In eight cases auroral pulsations were seen in the southern hemispheric data as well, suggesting an equatorial precipitation source and a frequent interhemispheric occurrence. The long lifetimes of pulsating aurora, their interhemispheric occurrence, and the relatively high-precipitation energies make this type of aurora an effective energy deposition process which is easy to identify from the ground-based image data.
Keywords: Antarktis; astronomi; atmosfæren; geofysikk; geomagnetiske stormer; mesosfæren; meteorologi; polarlys

Benchmarks: February 5, 1931 and February 20, 1935: Antarctic firsts for women - Zalzal, Kate S (Earth, 2017)
Keywords: Antarktis; Nordmenn; ekspedisjoner; kvinner; oppdagelsesreiser

Geomorphic and shallow-acoustic investigation of an Antarctic Peninsula fjord system using high-resolution ROV and shipboard geophysical observations: Ice dynamics and behaviour since the Last Glacial Maximum - García, Marga; Dowdeswell, J.A.; Noormets, R.; Hogan, K.A.; Evans, J.; Ó Cofaigh, C.; Larter, R.D. (Quaternary Science Reviews, 2016)
Detailed bathymetric and sub-bottom acoustic observations in Bourgeois Fjord (Marguerite Bay, Antarctic Peninsula) provide evidence on sedimentary processes and glacier dynamics during the last glacial cycle. Submarine landforms observed in the 50 km-long fjord, from the margins of modern tidewater glaciers to the now ice-distal Marguerite Bay, are described and interpreted. The landforms are grouped into four morpho-sedimentary systems: (i) glacial advance and full-glacial; (ii) subglacial and ice-marginal meltwater; (iii) glacial retreat and neoglaciation; and (iv) Holocene mass-wasting. These morpho-sedimentary systems have been integrated with morphological studies of the Marguerite Bay continental shelf and analysed in terms of the specific sedimentary processes and/or stages of the glacial cycle. They demonstrate the action of an ice-sheet outlet glacier that produced drumlins and crag-and-tail features in the main and outer fjord. Meltwater processes eroded bedrock channels and ponds infilled by fine-grained sediments. Following the last deglaciation of the fjord at about 9000 yr BP, subsequent Holocene neoglacial activity involved minor readvances of a tidewater glacier terminus in Blind Bay. Recent stillstands and/or minor readvances are inferred from the presence of a major transverse moraine that indicates grounded ice stabilization, probably during the Little Ice Age, and a series of smaller landforms that reveal intermittent minor readvances. Mass-wasting processes also affected the walls of the fjord and produced scars and fan-shaped deposits during the Holocene. Glacier-terminus changes during the last six decades, derived from satellite images and aerial photographs, reveal variable behaviour of adjacent tidewater glaciers. The smaller glaciers show the most marked recent retreat, influenced by regional physiography and catchment-area size.
Keywords: Antarctic Peninsula; Antarktis; Fjord systems; Geomorphology; Glacial sedimentary processes; Last Glacial Maximum; ROV-Derived bathymetry; Sørishavet; batymetri; geomorfologi

Naturen 1916 Roald Amundsens sydpolsfærd og dens videnskabelige resultater (Naturen, 2016)
Efterat kaptein James Ross i 1841 hadde opdaget det sydpolare eller antarktiske fastland og den store isbarriere under sin seilas i det hav som efter ham har faat navn av Ross-Havet, blev den øvrige del av dette fastland fremdeles ukjendt indtil 1898. Fra dette aar av har en række ekspeditioner med større og mindre held forsøkt at finde beliggenheten av det antarktiske fastlands kyster, og av disse har nogen opnaadd at trænge ind i det indre, endog like til sydpolen. Imidlertid er der endnu store strækninger hvor havisen har stængt seilasen og gjort det umulig at naa ind til det faste land.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; historie; oppdagelsesreiser; vitenskap

Den nyttige taperen - Scotts plass i norske nyhetsmediers fortellinger om erobringen av Sørpolen - Alnæs, Jørgen; Simonsen, Anne Hege (Norsk medietidsskrift, 2016)
Hundre år etter at Roald Amundsen nådde Sørpolen, ble han behørig feiret både av det offisielle Norge og av norske nyhetsmedier. Robert F. Scott, som nådde polen om lag en måned seinere, var en del av omtalen. Han fikk rollen som motstander og taper, og slik ble han en nyttig brikke når forestillingene om Norge som en rettmessig stormakt i Antarktis skulle etableres. Det er imidlertid mange måter å framstille Scott på, og norske aviser har ikke alltid hatt det samme synet på ham.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; ekspedisjoner; historie; kappløpet; mediefortelling; oppdagelsesreiser

On Roald Amundsen’s scientific achievements - Blix, Arnoldus Schytte (Polar Research, 2016)
This paper describes the significant direct and indirect contributions to science made by the Norwegian polar explorer Roald Amundsen in the period 1897–1924. It documents that his expeditions through the North-west Passage (1903–06) with Gjøa, to the South Pole (1910–12) with Fram and through the North-east Passage (1918–1920) and the Chukchi and East Siberian seas (1921–25) with Maud yielded vast amounts of published scientific material on meteorology, terrestrial magnetism, geology, palaeontology, oceanography, ethnography, zoology and botany, which, though celebrated at the time, have since received scant recognition in more recent assessments of Amundsen’s achievements. Keywords: Fridtjof Nansen; polar exploration; South Pole; North-west Passage; North-east Passage; H.U. Sverdrup.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; forskning; geologi; meteorologi; oseanografi

Algal biomass and pigments along a latitudinal gradient in Victoria Land lakes, East Antarctica - Borghini, Francesca; Colacevich, Andrea; Caruso, Tancredi; Bargagli, Roberto (Polar Research, 2016)
It is generally accepted that Antarctic terrestrial diversity decreases as latitude increases, but latitudinal patterns of several organisms are not always as clear as expected. The Victoria Land region is rich in lakes and ponds and spans 8 degrees of latitude that encompasses gradients in factors such as solar radiation, temperature, ice cover and day length. An understanding of the links between latitudinally driven environmental and biodiversity changes is essential to the understanding of the ecology and evolution of Antarctic biota and the formulation of hypotheses about likely future changes in biodiversity. As several studies have demonstrated that photosynthetic pigments are an excellent, although underused, tool for the study of lacustrine algal communities, the aim of the present study was to investigate variations in algal biomass and biodiversity across the latitudinal gradient of Victoria Land using sedimentary pigments. We test the hypothesis that the biodiversity of freshwater environments decreases as latitude increases. On the basis of our results, we propose using the number of sedimentary pigments as a proxy for algal diversity and the sum of chlorophyll a and bacteriochlorophyll a with their degradation derivatives as an index of biomass. Overall, our data show that biomass and diversity decrease as latitude increases but local environmental conditions, in particular, natural levels of eutrophy, can affect both productivity and diversity. Keywords: Biodiversity; photosynthetic pigments; proxy; continental Antarctica; sediments; biogeography.
Keywords: Antarktis; alger; biodiversitet; biogeografi; biomasse; ferskvann; fotosyntese; innsjø; sedimenter; økologi

A constitutive framework for predicting weakening and reduced buttressing of ice shelves based on observations of the progressive deterioration of the remnant Larsen B Ice Shelf - Borstad, Chris; Khazendar, Ala; Scheuchl, Bernd; Morlighem, Mathieu; Larour, Eric; Rignot, Eric (Geophysical Research Letters, 2016)
The increasing contribution of the Antarctic Ice Sheet to sea level rise is linked to reductions in ice shelf buttressing, driven in large part by basal melting of ice shelves. These ocean-driven buttressing losses are being compounded as ice shelves weaken and fracture. To date, model projections of ice sheet evolution have not accounted for weakening ice shelves. Here we present the first constitutive framework for ice deformation that explicitly includes mechanical weakening, based on observations of the progressive degradation of the remnant Larsen B Ice Shelf from 2000 to 2015. We implement this framework in an ice sheet model and are able to reproduce most of the observed weakening of the ice shelf. In addition to predicting ice shelf weakening and reduced buttressing, this new framework opens the door for improved understanding and predictions of iceberg calving, meltwater routing and hydrofracture, and ice shelf collapse.
Keywords: Antarktis; glasiologi; global oppvarming; havnivåstigning; innlandsis; isbrem; isshelf; smelting

Observed vulnerability of Filchner-Ronne Ice Shelf to wind-driven inflow of warm deep water - Darelius, Elin Maria K; Fer, Ilker; Nicholls, Keith William (Nature Communications, 2016)
Keywords: Antarktis; Weddellhavet; isshelf; oseanografi; sjøvann

Tourism and Arctic Observation Systems: exploring the relationships - de la Barre, Suzanne; Maher, Patrick; Dawson, Jackie; Hillmer-Pegram, Kevin; Huijbens, Edward; Lamers, Machiel; Liggett, Daniela; Müller, Dieter; Pashkevich, Albina; Stewart, Emma (Polar Research, 2016)
The Arctic is affected by global environmental change and also by diverse interests from many economic sectors and industries. Over the last decade, various actors have attempted to explore the options for setting up integrated and comprehensive trans-boundary systems for monitoring and observing these impacts. These Arctic Observation Systems (AOS) contribute to the planning, implementation, monitoring and evaluation of environmental change and responsible social and economic development in the Arctic. The aim of this article is to identify the two-way relationship between AOS and tourism. On the one hand, tourism activities account for diverse changes across a broad spectrum of impact fields. On the other hand, due to its multiple and diverse agents and far-reaching activities, tourism is also well-positioned to collect observational data and participate as an actor in monitoring activities. To accomplish our goals, we provide an inventory of tourism-embedded issues and concerns of interest to AOS from a range of destinations in the circumpolar Arctic region, including Alaska, Arctic Canada, Iceland, Svalbard, the mainland European Arctic and Russia. The article also draws comparisons with the situation in Antarctica. On the basis of a collective analysis provided by members of the International Polar Tourism Research Network from across the polar regions, we conclude that the potential role for tourism in the development and implementation of AOS is significant and has been overlooked. Keywords: Arctic; Antarctic; citizen science; observation systems; tourism; IPTRN
Keywords: Antarktis; klimaendringer; miljøendringer; polarområdene; turisme

Gastrointestinal helminths of Adélie penguins (Pygoscelis adeliae) from Antarctica - Diaz, Julia Inés; Fusaro, Bruno; Longarzo, Lucrecia; Coria, Néstor Rubén; Vidal, Virginia; D'Amico, Verónica; Barbosa, Andrés (Polar Research, 2016)
Knowledge about parasitic organisms in Antarctica is scarce and fragmentary. The study reported here adds to the knowledge of gastrointestinal parasites of the Adélie penguin (Pygoscelis adeliae) (Sphenisciformes), from 25 de Mayo/King George Island (South Shetlands), Bahia Esperanza (Hope Bay) and Avian Island (Antarctica). Thirty-five freshly dead specimens (20 chicks and 15 adults) were collected from December 2007 to December 2014 and examined for internal macroparasites. Three adult parasite species were found: one Cestoda, Parorchites zederi, and two Nematoda, Stegophorus macronectes and Tetrameres sp. Immature Tetrabothrius sp. were found in hosts from Avian Island. Helminth communities are known to be related to host feeding behaviours. Low parasite richness observed in Adélie penguins could be related to the stenophagic and pelagic diet of this host species, which feeds almost exclusively on krill. Keywords: Parorchites zederi; Stegophorus macronectes; Tetrameres sp.; parasites; ecosystem health.
Keywords: Antarktis; krill; parasitter; pingviner; plankton; zoologi; økosystemer

Re-assessment of recent (2008 - 2013) surface mass balance over Dome Argus, Antarctica - Ding, Minghu; Xiao, Cunde; Yang, Yuande; Wang, Yetang; Li, Chuanjin; Yuan, Naiming; Shi, Guitao; Sun, Weijun; Ming, Jing (Polar Research, 2016)
At Dome Argus, East Antarctica, the surface mass balance (SMB) from 2008 to 2013 was evaluated using 49 stakes installed across a 30×30 km area. Spatial analysis showed that at least 12 and 20 stakes are needed to obtain reliable estimates of SMB at local scales (a few hundred square metres) and regional scales (tens of square kilometres), respectively. The estimated annual mean SMB was 22.9±5.9 kg m−2 yr−1, including a net loss by sublimation of −2.22±0.02 kg m−2 yr−1 and a mass gain by deposition of 1.37±0.01 kg m−2 yr−1. Therefore, ca. 14.3% of precipitation was modified after deposition, which should be considered when interpreting snow or ice core records produced by future drilling projects. The surface snow density and SMB in the western portion of Dome Argus are higher than in other areas, and these differences are likely related to the katabatic wind, which is strengthened by topography in this sector. A new digital elevation model (DEM) of Dome Argus was generated, confirming that both peaks of the dome can be considered as the summit of the East Antarctic Ice Sheet. Findings from this study should be valuable for validating SMB estimates obtained from regional climate models and DEMs established using remote-sensing data. Keywords: Snow accumulation; Kunlun Station; CHINARE; digital elevation model; deep ice core sites; East Antarctic Ice Sheet.
Keywords: Antarktis; glasiologi; innlandsis; meteorologi; snø akkumulasjon; topografi

Tilt signals at Mount Melbourne, Antarctica: evidence of a shallow volcanic source - Gambino, Salvatore; Aloisi, Marco; Falzone, Giuseppe; Ferro, Angelo (Polar Research, 2016)
Mount Melbourne (74°21′ S, 164°43′ E) is a quiescent volcano located in northern Victoria Land, Antarctica. Tilt signals have been recorded on Mount Melbourne since early 1989 by a permanent shallow borehole tiltmeter network comprising five stations. An overall picture of tilt, air and permafrost temperatures over 15 years of continuous recording data is reported. We focused our observations on long-term tilt trends that at the end of 1997 showed coherent changes at the three highest altitude stations, suggesting the presence of a ground deformation source whose effects are restricted to the summit area of Mount Melbourne. We inverted these data using a finite spherical body source, thereby obtaining a shallow deflation volume source located under the summit area. The ground deformation observed corroborates the hypothesis that the volcanic edifice of Mount Melbourne is active and should be monitored multidisciplinarily.Keywords: Tilt monitoring; volcanic dynamics; physics volcanology; ground deformation; Victoria Land.
Keywords: Antarktis; geofysikk; tektonikk; vulkaner

In memory of Torgny Vinje - a genuine polar scientist - Isaksson, Elisabeth; Gerland, Sebastian; Divine, Dmitry (Polar Research, 2016)
Keywords: Antarktis; Norsk Polarinstitutt; biografi; forskning; geofysikk; geologi; glasiologi; meteorologi; polarområdene

Delivering 21st century Antarctic and Southern Ocean science - Kennicutt, Mahlon C I I; Kim, Yeadong; Rogan-Finnemore, Michelle; Anandakrishnan, Sridhar; Chown, Steven L; Colwell, Steven (Antarctic Science, 2016)
The Antarctic Roadmap Challenges (ARC) project identified critical requirements to deliver high priority Antarctic research in the 21st century. The ARC project addressed the challenges of enabling technologies, facilitating access, providing logistics and infrastructure, and capitalizing on international co-operation. Technological requirements include: i) innovative automated in situ observing systems, sensors and interoperable platforms (including power demands), ii) realistic and holistic numerical models, iii) enhanced remote sensing and sensors, iv) expanded sample collection and retrieval technologies, and v) greater cyber-infrastructure to process ‘big data’ collection, transmission and analyses while promoting data accessibility. These technologies must be widely available, performance and reliability must be improved and technologies used elsewhere must be applied to the Antarctic. Considerable Antarctic research is field-based, making access to vital geographical targets essential. Future research will require continent- and ocean-wide environmentally responsible access to coastal and interior Antarctica and the Southern Ocean. Year-round access is indispensable. The cost of future Antarctic science is great but there are opportunities for all to participate commensurate with national resources, expertise and interests. The scope of future Antarctic research will necessitate enhanced and inventive interdisciplinary and international collaborations. The full promise of Antarctic science will only be realized if nations act together.
Keywords: Antarktis; forskning; vitenskap

Regurgitation of the koilin layer in chinstrap penguins (Pygoscelis antarcticus) and its association with gastric parasites - Kim, Han-Kyu; Choi, Chang-Yong; Jeong, Min-Su; Kang, Hwa-Yeon; Lee, Woo-Shin (Polar Research, 2016)
The koilin membrane, formed by the secretions of the ventricular and pyloric glands, functions as a protective layer in the gizzards of most bird species. However, the ecological functions of koilin have never been studied in free-ranging penguins. During the two austral summers from 2012 to 2014, we observed the regurgitated koilins of chinstrap penguins (Pygoscelis antarcticus) at Narębski Point on King George Island, South Shetland Islands, and we detected a significant difference in the daily accumulation of regurgitated koilins between the pre-hatching and post-hatching periods in the rookery. We also found 233 gastrointestinal parasites, all Stegophorus macronectes (Nematoda, Acuariidae), from 26 out of 45 koilins freshly regurgitated by chinstrap penguins. We suggest that the regurgitation of koilins may benefit adult chinstrap penguins in the wild by reducing parasitic loads when they fast during incubation; it may also help decrease the risk of parasite transmission to chicks. Our results present the first observations of regurgitated koilins among breeding chinstrap penguins. How koilin regurgitation functions in penguins requires further study. Among the gentoo penguins (P. papua) co-occurring at the study site, we observed no regurgitated koilin layers. Keywords: Cuticula gastris; host-parasite interaction; nematodes; parasitic load; regurgitation; Stegophorus macronectes.
Keywords: Antarktis; biologi; gastrointestinale parasitter; ornitologi; pingviner; zoologi

The impact of sunlight on high-latitude equivalent currents - Laundal, Karl M; Gjerloev, Jesper; Østgaard, Nikolai; Reistad, Jone Peter; Haaland, Stein; Snekvik, Kristian; Tenfjord, Paul; Ohtani, Shin-ichi; Milan, Steve (Journal of Geophysical Research: Space Physics, 2016)
Ground magnetic field measurements can be mathematically related to an overhead ionospheric equivalent current. In this study we look in detail at how the global equivalent current, calculated using more than 30 years of SuperMAG magnetometer data, changes with sunlight conditions. The calculations are done using spherical harmonic analysis in quasi-dipole coordinates, a technique which leads to improved accuracy compared to previous studies. Sorting the data according to the location of the sunlight terminator and orientation of the interplanetary magnetic field (IMF), we find that the equivalent current resembles ionospheric convection patterns on the sunlit side of the terminator but not on the dark side. On the dark side, with southward IMF, the current is strongly dominated by a dawn cell and the current across the polar cap has a strong dawnward component. The contrast between the sunlit and dark side increases with increasing values of the F10.7 index, showing that increasing solar EUV flux changes not only the magnitude but also the morphology of the equivalent current system. The results are consistent with a recent study showing that Birkeland currents indirectly determine the equivalent current in darkness and that Hall currents dominate in sunlight. This has implication for the interpretation of ground magnetic field measurements and suggests that the magnetic disturbances at conjugate points will be asymmetrical when the solar illumination is different.
Keywords: Antarktis; geomagnetiske stormer; ionosfæren; ionosfæriske strømmer; polarlys; polarområdene; sollys; solvind

Adjustment of pigment composition in Desmarestia (Desmarestiaceae) species along a sub-Antarctic to Antarctic latitudinal gradient - Mansilla, Andrés; Méndez, Fabio; Murcia, Silvia; Rodriguez, Juan Pablo; Marambio, Johanna; Rosenfeld, Sebastián; Yokoya, Nair; Bischof, Kai (Polar Research, 2016)
Photosynthesis at high latitudes demands efficient strategies of light utilization to maintain algal fitness and performance. The fitness, and physiological adaptation, of a plant or algae species depends in part on the abundance and efficiency of the pigments it can produce to utilize the light resource from its environment. We quantified pigment composition and concentration in six species of the brown macroalgal genus Desmarestia, collected from sub-Antarctic sites (Strait of Magellan, Beagle Channel–Cape Horn Province) and sites on the Antarctic Peninsula and adjacent islands. Sub-Antarctic Desmarestia species exhibited lower concentrations of chlorophyll a, chlorophyll c and fucoxanthin than endemic Antarctic species. Antarctic samples of D. menziesii and D. antarctica collected along a decreasing latitudinal gradient showed spatial and interspecific differences in light-harvesting pigment composition. Our results suggest distinct physiological adjustments in Desmarestia species in response to heterogeneous abiotic environmental conditions. The marine sub-Antarctic and Antarctic ecosystems are characterized by harsh environments (e.g., extreme irradiance, photoperiod, temperature, salinity) to which the physiology of macroalgal species must adapt. Keywords: Macroalgae; Phaeophyceae; photosynthesis; physiology; environmental heterogeneity; Chile.
Keywords: Antarktis; alger; fotosyntese; fysiologi; planter

Gåten om Roald Amundsens varde på Bettyfjellet i Antarktis - Mehlum, Fridtjof (Polarboken, 2016)
Keywords: Antarktis; ekspedisjoner; historie

Polheim: teltet på Sydpolen - Melgård, Anne (Polarboken, 2016)
Keywords: Antarktis; ekspedisjoner; historie

Local controls on sediment accumulation and distribution in a fjord in the West Antarctic Peninsula: implications for palaeoenvironmental interpretations - Munoz, Yuribia P.; Wellner, Julia S. (Polar Research, 2016)
We analyse surface sediment and its distribution in Flandres Bay, West Antarctic Peninsula, in order to understand modern day sediment dispersal patterns in a fjord with retreating, tidewater glaciers. The surface sediment descriptions of 41 cores are included in this study. The sediment facies described include muddy diatomaceous ooze, diatomaceous mud, pebbly mud, sandy mud and mud, with scattered pebbles present in most samples. In contrast to a traditional conceptual model of glacial sediment distribution in fjords, grain size in Flandres Bay generally coarsens from the inner to outer bay. The smallest grain size sediments were found in the bay head and are interpreted as fine-grained deposits resulting from meltwater plumes and sediment gravity flows occurring close to the glacier front. The middle of the bay is characterized by a high silt percentage, which correlates to diatom-rich sediments. Sediments in the outer bay have a high component of coarse material, which is interpreted as being the result of winnowing from currents moving from the Bellingshausen Sea into the Gerlache Strait. Palaeoenvironmental reconstructions of glacial environments often use grain size as an indicator of proximity to the ice margin. After a detailed analysis of a large number of cores collected in the study area, our findings highlight the variability in sedimentation patterns within a fjord and provide a valuable evidence of the complexity that may occur in the sedimentary record. Keywords: Flandres Bay; Antarctic Peninsula; sediment distribution; grain size.
Keywords: Antarktis; havbunnen; isbreer; miljøvitenskap; sedimenter; sedimentologi; topografi

Magnetotelluric investigation of the Vestfold Hills and Rauer Group, East Antarctica - Peacock, Jared; Selway, Kate (Journal of Geophysical Research: Solid Earth, 2016)
The Vestfold Hills and Rauer Group in East Antarctica have contrasting Archean to Neoproterozoic geological histories and are believed to be juxtaposed along a suture zone that now lies beneath the Sørsdal Glacier. Exact location and age of this suture zone are unknown, as is its relationship to regional deformation associated with the amalgamation of East Gondwana. To image the suture zone, magnetotelluric (MT) data were collected in Prydz Bay, East Antarctica, mainly along a profile crossing the Sørsdal Glacier and regions inland of the Vestfold Hills and Rauer Group islands. Time-frequency analysis of the MT time series yielded three important observations: (1) Wind speeds in excess of ∼8 m/s reduce coherence between electric and magnetic fields due to charged wind-blown particles of ice and snow. (2) Estimation of the MT transfer function is best between 1000 and 1400 UT when ionospheric Hall currents enhance the magnetic source field. (3) Nonplanar source field effects were minimal but detectable and removed from estimation of the MT transfer function. Inversions of MT data in 2-D and 3-D produce similar resistivity models, where structures in the preferred 3-D resistivity model correlate strongly with regional magnetic data. The electrically conductive Rauer Group is separated from the less conductive Vestfold Hills by a resistive zone under the Sørsdal Glacier, which is interpreted to be caused by oxidation during suturing. Though a suture zone has been imaged, no time constrains on suturing can be made from the MT data.
Keywords: Antarktis; geofysikk; geologi; magnetotelluriske målinger

Animals as instruments of Norwegian imperial authority in the interwar Arctic - Roberts, Peder; Jørgensen, Dolly (Journal for the History of Environment and Society, 2016)
During the first half of the twentieth century a number of individuals in Norway participated in the transfer of animals from both the Arctic to the Antarctic regions and vice versa. These projects may be conceptualized as a form of imperial acclimatization, following in the footsteps of earlier attempts to transplant both plants and animals from their indigenous ranges to new geographic locations for both practical and recreational purposes. Reindeer were introduced to the island of South Georgia before World War I as Norwegian whalers turned a space previously uninhabited by humans into the operational hub of a booming Antarctic whaling industry. The successful transplantation of reindeer was followed by less successful attempts to transfer muskoxen from Greenland to Svalbard and the Scandinavian mainland, penguins from the Antarctic to the coast of Norway, and dreams of transferring fur seals from south to north. We argue that these attempts constituted both practical attempts to “enrich” the fauna of discrete habitats, but also expressions of Norwegian authority over the polar regions at a time when imperial ambitions in both the Arctic and Antarctic had significant traction within Norway. The transplanted animals may thus be conceived as geopolitical instruments – mastery over fauna as being a means of expressing mastery over space.
Keywords: Antarktis; Bouvetøya; Norge; geopolitikk; hvalfangst; polarområdene

Den langsomme polare vippen - Sorokina, Svetlana (Naturen, 2016)
De siste 20 årene har vært de varmeste siden globale temperaturmålinger startet i 1880 (Figur 1). FNs klimapanel konkluderer med at hovedårsaken til den observerte temperaturøkningen er menneskeskapte utslipp av klimagasser. I nordområdene har temperaturen økt nesten dobbelt så raskt som i resten av verden. Isdekket er nær halvert og isvolumet er redusert til en tredjedel. Men på den andre siden av jorden, altså i Antarktis, er situasjonen en helt annen. Temperaturen har vært fallende de siste årene og isdekket har vært rekordstort. Dette paradokset brukes ofte som et argument mot menneskeskapte endring av klima. For hvordan kan det ha seg at temperaturen i Antarktis faller når klimagassutslippene øker?
Keywords: Antarktis; global oppvarming; klimaendringer; klimagasser; polarområdene

The canine explorers – the sled dogs who helped Roald Amundsen reach the South Pole - Tahan, Mary R (Journal of Antarctic Affairs, 2016)
One hundred Greenland dogs were purchased by Roald Amundsen from the Royal Greenland Trading Company in September 1909 ostensibly for a North Pole expedition, but secretly to use to reach the South Pole. Amundsen considered the dogs “equipment”. He was a complicated character in a very different time. And he compulsively pursued his mission. His actions perhaps are seen differently from the 21st century perspective and in light of our evolving attitude toward animals, especially dogs. This paper presents the facts of what happened concerning the sled dogs, using Amundsen’s own statements in his books, diaries, and letters, as well as the expedition members’ journal entries and personal letters. It focuses on the dogs who made Amundsen’s exploration possible, and who helped humankind discover the final undiscovered part of our world. Amundsen began his Norwegian expedition with 97 sturdy canine souls, who were taken on board the Fram near the coast of Kristiansand in August 1910. Through births and deaths on the ship during their five-month journey south, the dogs’ number swelled to 116 upon arrival in Antarctica. Adults and puppies alike withstood the roller-coaster ride of the Fram on the ocean waters, the heat of the tropics near the equator, and the freezing winter of Antarctica. Taking into account the birth of puppies on the ship and at their Antarctic home Framheim, the actual number of dogs involved in this significant moment in history doubles to over two hundred. But, after initially nurturing and protecting the dogs, Amundsen proceeded to cull them throughout the expedition, slaughtering those he deemed unnecessary or weak, and destroying those who had served their purpose. Amundsen began his South Pole trek in October 1911 with 52 brave canines, and returned with 11, as a result of unnatural, forced attrition. The dogs were nearly starved; at times when they were fed, it was the flesh of their fallen comrades they were given to line their empty stomachs. And yet the dogs all performed their roles brilliantly, even when death was their reward. The sled dogs were the heart and power of the South Pole expedition. The intent of this article is to shine a light on the dogs’ population, accomplishments, and sacrifices, and to give them their due recognition and place in history.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Investigating uncertainty in the simulation of the Antarctic ice sheet during the mid-Piacenzian - Yan, Qing; Zhang, Zhongshi; Wang, Huijun (Journal of Geophysical Research: Atmospheres, 2016)
The mid-Piacenzian (~3 Ma) represents the most recent warm period in Earth's history on a geological time scale; it is characterized by a significant rise of global sea level. The simulation of the size and location of the ice sheets and the investigation of the uncertainty in the simulations are potentially helpful for constraining reconstructed sea level changes. In this study, we focus on the behavior of the Antarctic ice sheet (AIS) in the mid-Piacenzian. We investigate the influence of topography correction, model parameters, climate forcings, and model resolution on the modeled AIS and explore the isolated role of atmospheric and oceanic forcings. Forced by the simulated climate changes with the Norwegian Earth System Model, the Parallel Ice Sheet Model (15 km × 15 km) produces a nearly collapsed West AIS (WAIS) in the mid-Piacenzian, with no significant retreat of the East AIS (EAIS). The role of increased air temperature plays a key role in the mass loss of the mid-Piacenzian AIS, while its role is comparable to the role of ocean warming on the melting of the WAIS. In terms of the range of sea level changes, the largest source of uncertainty in the modeled AIS is derived from ice sheet model parameters and climate forcings. Although the employed model parameters, topography correction factors, and model resolution affect the simulated AIS in the mid-Piacenzian, large-scale deglaciation of the EAIS in our sensitivity experiments may only be possible with additional warming.
Keywords: Antarktis; atmosfæren; geologi; havnivåstigning; innlandsis; klimaendringer; paleontologi

The impact of energetic electron precipitation on mesospheric hydroxyl during a year of solar minimum - Zawedde, Annet Eva; Nesse Tyssøy, Hilde; Hibbins, Robert; Espy, Patrick J; Ødegaard, Linn-Kristine Glesnes; Sandanger, Marit Irene; Stadsnes, Johan (Journal of Geophysical Research: Space Physics, 2016)
In 2008 a sequence of geomagnetic storms occurred triggered by high-speed solar wind streams from coronal holes. Improved estimates of precipitating fluxes of energetic electrons are derived from measurements on board the NOAA/POES 18 satellite using a new analysis technique. These fluxes are used to quantify the direct impact of energetic electron precipitation (EEP) during solar minimum on middle atmospheric hydroxyl (OH) measured from the Aura satellite. During winter, localized longitudinal density enhancements in the OH are observed over northern Russia and North America at corrected geomagnetic latitudes poleward of 55°. Although the northern Russia OH enhancement is closely associated with increased EEP at these longitudes, the strength and location of the North America enhancement appear to be unrelated to EEP. This OH density enhancement is likely due to vertical motion induced by atmospheric wave dynamics that transports air rich in atomic oxygen and atomic hydrogen downward into the middle atmosphere, where it plays a role in the formation of OH. In the Southern Hemisphere, localized enhancements of the OH density over West Antarctica can be explained by a combination of enhanced EEP due to the local minimum in Earth's magnetic field strength and atmospheric dynamics. Our findings suggest that even during solar minimum, there is substantial EEP-driven OH production. However, to quantify this effect, a detailed knowledge of where and when the precipitation occurs is required in the context of the background atmospheric dynamics.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; geomagnetiske stormer; planetbølger; solvind

On-site and in situ remediation technologies applicable to petroleum hydrocarbon contaminated sites in the Antarctic and Arctic - Camenzuli, Danielle; Freidman, Benjamin L (Polar Research, 2015)
Petroleum hydrocarbon contaminated sites, associated with the contemporary and legacy effects of human activities, remain a serious environmental problem in the Antarctic and Arctic. The management of contaminated sites in these regions is often confounded by the logistical, environmental, legislative and financial challenges associated with operating in polar environments. In response to the need for efficient and safe methods for managing contaminated sites, several technologies have been adapted for on-site or in situ application in these regions. This article reviews six technologies which are currently being adapted or developed for the remediation of petroleum hydrocarbon contaminated sites in the Antarctic and Arctic. Bioremediation, landfarming, biopiles, phytoremediation, electrokinetic remediation and permeable reactive barriers are reviewed and discussed with respect to their advantages, limitations and potential for the long-term management of soil and groundwater contaminated with petroleum hydrocarbons in the Antarctic and Arctic. Although these technologies demonstrate potential for application in the Antarctic and Arctic, their effectiveness is dependent on site-specific factors including terrain, soil moisture and temperature, freeze–thaw processes and the indigenous microbial population. The importance of detailed site assessment prior to on-site or in situ implementation is emphasized, and it is argued that coupling of technologies represents one strategy for effective, long-term management of petroleum hydrocarbon contaminated sites in the Antarctic and Arctic. Keywords: Petroleum hydrocarbons; remediation; Antarctica; Arctic; cold regions; contaminated site.
Keywords: Antarktis; forurensning; hydrokarboner; miljøvern; petroleum; polarområdene

Mapping lichen distribution on the Antarctic Peninsula using remote sensing, lichen spectra and photographic documentation by citizen scientists - Casanovas, Paula; Black, Martin; Fretwell, Peter; Convey, Peter (Polar Research, 2015)
On the Antarctic Peninsula, lichens are the most diverse botanical component of the terrestrial ecosystem. However, detailed information on the distribution of lichens on the Antarctic Peninsula region is scarce, and the data available exhibit significant heterogeneity in sampling frequency and effort. Satellite remote sensing, in particular the use of the Normalized Difference Vegetation Index (NDVI), has facilitated determination of vegetation richness and cover distribution in some remote and otherwise inaccessible environments. However, it is known that using NDVI for the detection of vegetation can overlook the presence of lichens even if their land cover is extensive. We tested the use of known spectra of lichens in a matched filtering technique for the detection and mapping of lichen-covered land from remote sensing imagery on the Antarctic Peninsula, using data on lichen presence collected by citizen scientists and other non-specialists as ground truthing. Our results confirm that the use of this approach allows for the detection of lichen flora on the Antarctic Peninsula, showing an improvement over the use of NDVI alone for the mapping of flora in this area. Keywords: Antarctica; NDVI; matched filtering; Landsat; remote sensing.
Keywords: Antarktis; botanikk; flora; lav; satellitt bilder; økosystemer

Van Allen probes, NOAA, GOES, and ground observations of an intense EMIC wave event extending over 12 h in magnetic local time - Engebretson, Mark J; Posch, J L; Wygant, J R; Kletzing, Craig A; Lessard, M R; Huang, C.-L.; Spence, Harlan; Smith, C W; Singer, H J; Omura, Yoshiharu; Horne, R B; Reeves, Geoffrey; et al. (Journal of Geophysical Research: Space Physics, 2015)
Although most studies of the effects of electromagnetic ion cyclotron (EMIC) waves on Earth's outer radiation belt have focused on events in the afternoon sector in the outer plasmasphere or plume region, strong magnetospheric compressions provide an additional stimulus for EMIC wave generation across a large range of local times and L shells. We present here observations of the effects of a wave event on 23 February 2014 that extended over 8 h in UT and over 12 h in local time, stimulated by a gradual 4 h rise and subsequent sharp increases in solar wind pressure. Large-amplitude linearly polarized hydrogen band EMIC waves (up to 25 nT p-p) appeared for over 4 h at both Van Allen Probes, from late morning through local noon, when these spacecraft were outside the plasmapause, with densities ~5–20 cm−3. Waves were also observed by ground-based induction magnetometers in Antarctica (near dawn), Finland (near local noon), Russia (in the afternoon), and in Canada (from dusk to midnight). Ten passes of NOAA-POES and METOP satellites near the northern foot point of the Van Allen Probes observed 30–80 keV subauroral proton precipitation, often over extended L shell ranges; other passes identified a narrow L shell region of precipitation over Canada. Observations of relativistic electrons by the Van Allen Probes showed that the fluxes of more field-aligned and more energetic radiation belt electrons were reduced in response to both the emission over Canada and the more spatially extended emission associated with the compression, confirming the effectiveness of EMIC-induced loss processes for this event.
Keywords: Antarktis; astronomi; elektromagnetiske ionesyklotronbølger; fysikk; magnetosfæriske kompresjoner; strålingsbelter

Interhemispheric differences in ionospheric convection: Cluster EDI observations revisited - Förster, Matthias; Haaland, Stein (Journal of Geophysical Research: Space Physics, 2015)
The interaction between the interplanetary magnetic field and the geomagnetic field sets up a large-scale circulation in the magnetosphere. This circulation is also reflected in the magnetically connected ionosphere. In this paper, we present a study of ionospheric convection based on Cluster Electron Drift Instrument (EDI) satellite measurements covering both hemispheres and obtained over a full solar cycle. The results from this study show that average flow patterns and polar cap potentials for a given orientation of the interplanetary magnetic field can be very different in the two hemispheres. In particular during southward directed interplanetary magnetic field conditions, and thus enhanced energy input from the solar wind, the measurements show that the southern polar cap has a higher cross polar cap potential. There are persistent north-south asymmetries, which cannot easily be explained by the influence of external drivers. These persistent asymmetries are primarily a result of the significant differences in the strength and configuration of the geomagnetic field between the Northern and Southern Hemispheres. Since the ionosphere is magnetically connected to the magnetosphere, this difference will also be reflected in the magnetosphere in the form of different feedback from the two hemispheres. Consequently, local ionospheric conditions and the geomagnetic field configuration are important for north-south asymmetries in large regions of geospace.
Keywords: Antarktis; astrofysikk; geovitenskap; ionosfæren; magnetosfæren; polarområdene; solvind

Haematological values of three Antarctic penguins: gentoo (Pygoscelis papua), Adélie (P. adeliae) and chinstrap (P. antarcticus) - Ibañez, Andrés E; Najle, Roberto; Larsen, Karen; Pari, Marcela; Figueroa, Amalia; Montalti, Diego (Polar Research, 2015)
It is established that haematological and biochemical parameters provide important data to assess the physiological condition and health status of wild birds. To undertake conservation physiology or ecophysiology work, it is therefore essential to establish baseline physiological parameters and how these parameters change with age and life history events. In this work, we determined and compared baseline haematology and serum biochemistry between adults and chicks of three Antarctic penguin species of the genus Pygoscelis: gentoo (P. papua), Adélie (P. adeliae) and chinstrap (P. antarcticus). Differences in adults among species were observed in haemoglobin and biochemical parameters such as total proteins, glucose and alkaline phosphatase activity. In addition, differences between adults and chicks in haematocrit, haemoglobin, total proteins and glucose concentration were determined. Moreover, we evaluated the electrophoretic protein profiles between adults and chicks of the genus Pygoscelis, and a conserved protein pattern was observed among species and ages in the genus. Altogether, the results suggest that biochemical and haematological differences among pygoscelids may be related to the nutritional status and energetic expenditure during breeding as well as their feeding habits and development stage. Keywords: Antarctic; haematology; physiology; Pygoscelis; penguins; serum biochemistry.
Keywords: Antarktis; biokjemi; biologi; fysiologi; hematologi; pingviner; zoologi

A roadmap for Antarctic and Southern Ocean science for the next two decades and beyond - Kennicutt, M.C.; Chown, S.L.; Cassano, J.J.; Liggett, D.; Peck, L.S.; Massom, R.; Rintoul, S.R.; Storey, J.; Vaughan, D.G.; Wilson, T.J.; Allison, I.; Ayton, J.; et al. (Antarctic Science, 2015)
Antarctic and Southern Ocean science is vital to understanding natural variability, the processes that govern global change and the role of humans in the Earth and climate system. The potential for new knowledge to be gained from future Antarctic science is substantial. Therefore, the international Antarctic community came together to ‘scan the horizon’ to identify the highest priority scientific questions that researchers should aspire to answer in the next two decades and beyond. Wide consultation was a fundamental principle for the development of a collective, international view of the most important future directions in Antarctic science. From the many possibilities, the horizon scan identified 80 key scientific questions through structured debate, discussion, revision and voting. Questions were clustered into seven topics: i) Antarctic atmosphere and global connections, ii) Southern Ocean and sea ice in a warming world, iii) ice sheet and sea level, iv) the dynamic Earth, v) life on the precipice, vi) near-Earth space and beyond, and vii) human presence in Antarctica. Answering the questions identified by the horizon scan will require innovative experimental designs, novel applications of technology, invention of next-generation field and laboratory approaches, and expanded observing systems and networks. Unbiased, non-contaminating procedures will be required to retrieve the requisite air, biota, sediment, rock, ice and water samples. Sustained year-round access to Antarctica and the Southern Ocean will be essential to increase winter-time measurements. Improved models are needed that represent Antarctica and the Southern Ocean in the Earth System, and provide predictions at spatial and temporal resolutions useful for decision making. A co-ordinated portfolio of cross-disciplinary science, based on new models of international collaboration, will be essential as no scientist, programme or nation can realize these aspirations alone.
Keywords: Antarktis; Sørishavet; forskning; teknologi

The significant inputs of trace elements and rare earth elements from melting glaciers in Antarctic coastal waters - Kim, Intae; Kim, Guebuem; Choy, Eun Jung (Polar Research, 2015)
To evaluate the impact of modern glacier melting on the chemical enrichment of Antarctic coastal waters, we measured trace elements, including dissolved iron (Fe) and rare earth elements (REEs), together with dissolved inorganic nitrogen, phosphorous, silicate and dissolved organic carbon (DOC) in ice, snow and coastal seawater of Marian Cove in the northernmost part of Antarctica (62°S). There was an increase in the concentrations of Fe and other trace elements (Al, Mn, Cr, Ni, Co, Pb and REEs) between the bay mouth and the glacier valleys. Good correlations between salinity and these chemical elements indicate that the trend was mainly due to the influence of glacier meltwater (GMW). When the effect of GMW was quantified based on plots of its presence (average 5.7%) in the surface water of the cove, the concentrations of trace elements in seawater increased 18-fold for Fe, eight- to 10-fold for Al and Mn and up to four-fold for Cr, Ni, Co, Pb and REEs by GMW. However, the contribution of GMW to inorganic nutrients and DOC was negligible. The significance of GMW-borne REE contribution in this cove was further evidenced by middle REE enrichment in cove water. Our results suggest that the currently increasing glacier melting in Antarctica has a significant influence on the level of trace elements, particularly Fe, in cove water, which in turn may have a significant impact on the biogeochemistry of coastal seawater in Antarctica. Keywords: Iron; trace elements; rare earth elements; glacier melting; Antarctica; Marian Cove.
Keywords: Antarktis; biogeokjemi; isbreer; kjemiske analyser; sjøvann; smelting

Birkeland current effects on high-latitude ground magnetic field perturbations - Laundal, Karl M; Haaland, Stein; Lehtinen, N; Gjerloev, Jesper; Østgaard, Nikolai; Tenfjord, Paul; Reistad, Jone Peter; Snekvik, Kristian; Milan, Steve; Ohtani, Shin-ichi; Anderson, B J (Geophysical Research Letters, 2015)
Magnetic perturbations on ground at high latitudes are directly associated only with the divergence-free component of the height-integrated horizontal ionospheric current, J⊥,df. Here we show how J⊥,df can be expressed as the total horizontal current J⊥ minus its curl-free component, the latter being completely determined by the global Birkeland current pattern. Thus, in regions where J⊥=0, the global Birkeland current distribution alone determines the local magnetic perturbation. We show with observations from ground and space that in the polar cap, the ground magnetic field perturbations tend to align with the Birkeland current contribution in darkness but not in sunlight. We also show that in sunlight, the magnetic perturbations are typically such that the equivalent overhead current is antiparallel to the convection, indicating that the Hall current system dominates. Thus, the ground magnetic field in the polar cap relates to different current systems in sunlight and in darkness.
Keywords: Antarktis; Birkelandstrømmer; ionosfæren; ionosfæriske strømmer; polarområdene; sollys

The great white silence : den offisielle filmen om Robert Falcon Scotts sydpolekspedisjon og en vurdering av ekspedisjonen - Lund, Vidar (Maritimt Magasin Historie, 2015)
Keywords: Antarktis; Robert Falcon Scott; Sydpolsekspedisjonen; oppdagelsesreiser

Antarctic ice rises and rumples: their properties and significance for ice-sheet dynamics and evolution - Matsuoka, Kenichi; Hindmarsh, Richard C A; Moholdt, Geir; Bentley, Michael J; Pritchard, Hamish D; Brown, Joel; Conway, Howard; Drews, Reinhard; Durand, Gaël; Goldberg, Daniel; Hattermann, Tore; Kingslake, Jonathan; et al. (Earth-Science Reviews, 2015)
Locally grounded features in ice shelves, called ice rises and rumples, play a key role buttressing discharge from the Antarctic Ice Sheet and regulating its contribution to sea level. Ice rises typically rise several hundreds of meters above the surrounding ice shelf; shelf flow is diverted around them. On the other hand, shelf ice flows across ice rumples, which typically rise only a few tens of meters above the ice shelf. Ice rises contain rich histories of deglaciation and climate that extend back over timescales ranging from a few millennia to beyond the last glacial maximum. Numerical model results have shown that the buttressing effects of ice rises and rumples are significant, but details of processes and how they evolve remain poorly understood. Fundamental information about the conditions and processes that cause transitions between floating ice shelves, ice rises and ice rumples is needed in order to assess their impact on ice-sheet behavior. Targeted high-resolution observational data are needed to evaluate and improve prognostic numerical models and parameterizations of the effects of small-scale pinning points on grounding-zone dynamics.
Keywords: Antarktis; Sørishavet; glasiologi; havis

Observational evidence of the influence of Antarctic stratospheric ozone variability on middle atmosphere dynamics - Narukull, Venkateswara Rao; Espy, Patrick Joseph; Hibbins, Robert; Fritts, David C; Kavanagh, Andrew John (Geophysical Research Letters, 2015)
Abstract Modeling results have suggested that the circulation of the stratosphere and mesosphere in spring is strongly affected by the perturbations in heating induced by the Antarctic ozone hole. Here using both mesospheric MF radar wind observations from Rothera Antarctica (67°S, 68°W) as well as stratospheric analysis data, we present observational evidence that the stratospheric and mesospheric wind strengths are highly anti-correlated, and show their largest variability in November. We find that these changes are related to the total amount of ozone loss that occurs during the Antarctic spring ozone hole and particularly with the ozone gradients that develop between 57.5°S and 77.5°S. The results show that with increasing ozone loss during spring, winter conditions in the stratosphere and mesosphere persist longer into the summer. These results are discussed in the light of observations of the onset and duration of the Antarctic polar mesospheric cloud season.
Keywords: Antarktis; klimatologi; meteorologi; ozonhull; ozonlaget

Methane and nitrous oxide fluxes in relation to vegetation covers and bird activity in ice-free soils of Rip Point, Nelson Island, Antarctica - Neufeld, Ângela Denise Hubert; de Godoi, Stefânia Guedes; Pereira, Antônio Batista; Bayer, Cimélio; Schünemann, Andriano Luis; de Carvalho Victoria, Filipe; de Albuquerque, Margéli Pereira; Camargo, Estefânia; Vieira, Frederico Costa Beber (Polar Research, 2015)
This study aimed to quantify the nitrous oxide (N2O) and methane (CH4) fluxes at sites with different vegetation covers and where bird activity was present or absent using the static chamber method, on Rip Point, Nelson Island, maritime Antarctic. The sites were soils covered by Sanionia uncinata, lichens, Prasiola crispa, Deschampsia antarctica and bare soil. Seabirds used the P. crispa and D. antarctica sites as nesting areas. Soil mineral N contents, air and soil temperature and water-filled pore space were measured, and the content of total organic C and particulate organic C, total N, bulk density and texture were determined to identify controlling variables of the gas emissions. The N2O and CH4 flux rates were low for all sampling events. Mean N2O flux rates ranged from 0.11±1.93 up to 21.25±22.14 µg N2O m−2 h−1 for the soils under lichen and P. crispa cover, respectively. For the CH4 fluxes, only the P. crispa site showed a low positive mean (0.47±3.61 µg CH4 m−2 h−1). The bare soil showed the greatest absorption of CH4 (−11.92±5.7 µg CH4 m−2 h−1), probably favoured by the coarse soil texture. Bare soil and S. uncinata sites had N2O accumulated emissions close to zero. Net CH4 accumulated emission was observed only at the P. crispa site, which was correlated with (p<0.001). These results indicate that seabird activity influences N2O and CH4 soil fluxes, while vegetation has little influence, and bare soil areas in maritime Antarctica could be greenhouse gas sinks. Keywords: Soil greenhouse gases; seabirds; vegetal cover; maritime Antarctica.
Keywords: Antarktis; biogeokjemi; drivhuseffekt; drivhusgasser; flora; global oppvarming; klimaendringer; klimagasser; planter; sjøfugler; økosystemer

Polychlorinated biphenyl exposure and corticosterone levels in seven polar seabird species - Tartu, Sabrina; Angelier, Frédéric; Bustnes, Jan-Ove; Moe, Børge; Hanssen, Sven Are; Herzke, Dorte; Gabrielsen, Geir Wing; Verboven, Nanette; Verreault, J; Labadie, Pierre; Budzinski, Helene; Wingfield, John C; et al. (Environmental Pollution, 2015)
The role of polychlorinated biphenyls (PCBs) on exposure-related endocrine effects has been poorly investigated in wild birds. This is the case for stress hormones including corticosterone (CORT). Some studies have suggested that environmental exposure to PCBs and altered CORT secretion might be associated. Here we investigated the relationships between blood PCB concentrations and circulating CORT levels in seven free-ranging polar seabird species occupying different trophic positions, and hence covering a wide range of PCB exposure. Blood ∑7PCB concentrations (range: 61–115,632 ng/g lw) were positively associated to baseline or stress-induced CORT levels in three species and negatively associated to stress-induced CORT levels in one species. Global analysis suggests that in males, baseline CORT levels generally increase with increasing blood ∑7PCB concentrations, whereas stress-induced CORT levels decrease when reaching high blood ∑7PCB concentrations. This study suggests that the nature of the PCB-CORT relationships may depend on the level of PCB exposure.
Keywords: Antarktis; forurensning; miljø; nevrobiologi; ornitologi; polarområdene; sjøfugler; stresshormoner; zoologi

Corticosterone, prolactin and egg neglect behavior in relation to mercury and legacy POPs in a long-lived Antarctic bird - Tartu, Sabrina; Angelier, Frédéric; Wingfield, John C; Bustamante, Paco; Labadie, Pierre; Budzinski, Helene; Weimerskirch, Henri; Bustnes, Jan-Ove; Chastel, Olivier (Science of the Total Environment, 2015)
Seabirds often have high loads of contaminants. These contaminants have endocrine disrupting properties but their relationships with some endocrine mechanisms are still poorly investigated in free-living organisms. This is the case for the stress response which shifts energy investment away from reproduction and redirects it towards survival. In birds, this stress response is achieved through a release of corticosterone and is also accompanied by a decrease in circulating prolactin, an anterior pituitary hormone widely involved in regulating parental cares. We measured blood concentrations of some legacy persistent organic pollutants (POPs) and mercury (Hg) and examined their relationships with the corticosterone and prolactin responses of known-age (9–46years old) incubating snow petrels (Pagodroma nivea) to a standardized capture/handling stress protocol. In this Antarctic seabird, we also investigated whether high contaminant burden correlates with a higher occurrence of egg neglect, a frequently observed behavior in snow petrels. POPs and Hg were unrelated to age. Stress-induced corticosterone concentrations were positively related to POPs in both sexes, and stress-induced prolactin concentrations were negatively related to Hg in males. Egg-neglect behavior was not related to POPs burden, but males with higher Hg concentrations were more likely to neglect their egg. This suggests that in birds, relationships between age and contaminants are complex and that even low to moderate concentrations of POPs and Hg are significantly related to hormonal secretion. In this Antarctic species, exposure to legacy POPs and Hg could make individuals more susceptible to environmental stressors such as ongoing disturbances in Polar Regions.
Keywords: Antarktis; forurensning; miljø; nevrobiologi; ornitologi; petreller; polarområdene; reproduksjon; sjøfugler; zoologi

Investigating the recent apparent hiatus in surface temperature increases: 2. Comparison of model ensembles to observational estimates - Thorne, Peter; Outten, Stephen; Bethke, Ingo; Seland, Øyvind (Journal of Geophysical Research: Atmospheres, 2015)
To assess published hypotheses surrounding the recent slowdown in surface warming (hiatus), we compare five available global observational surface temperature estimates to two 30-member ensembles from the Norwegian Earth System Model (NorESM). Model ensembles are initialized in 1980 from the transient historical runs and driven with forcings used in the CMIP5 experiments and updated forcings based upon current observational understanding, described in Part 1. The ensembles' surface temperature trends are statistically indistinguishable over 1998–2012 despite differences in the prescribed forcings. There is thus no evidence that forcing errors play a significant role in explaining the hiatus according to NorESM. The observations fall either toward the lower portion of the ensembles or, for some observational estimates and regions, outside. The exception is the Arctic where the observations fall toward the upper ensemble bounds. Observational data set choices can make a large difference to findings of consistency or otherwise. Those NorESM ensemble members that exhibit Nino3.4 Sea Surface Temperature (SST) trends similar to observed also exhibit comparable tropical and to some extent global mean trends, supporting a role for El Nino Southern Oscillation in explaining the hiatus. Several ensemble members capture the marked seasonality observed in Northern Hemisphere midlatitude trends, with cooling in the wintertime and warming in the remaining seasons. Overall, we find that we cannot falsify NorESM as being capable of explaining the observed hiatus behavior. Importantly, this is not equivalent to concluding NorESM could simultaneously capture all important facets of the hiatus. Similar experiments with further, distinct, Earth System Models are required to verify our findings.
Keywords: Antarktis; atmosfæren; fjernmåling; geofysikk; klimaendringer; klimatologi; meteorologi; observasjoner; polarområdene; temperatur

Comment on “Unexpected Occurrence of Volatile Dimethylsiloxanes in Antarctic Soils, Vegetation, Phytoplankton, and Krill” - Warner, Nicholas A; Krogseth, Ingjerd S; Whelan, Mick J (Environmental Science & Technology, 2015)
Sanchís et al. (2015) recently reported the occurrence of volatile methyl siloxanes (VMS) in soil, vegetation, phytoplankton, and krill samples from Antarctica. As the paper’s title suggests, findings of these chemicals in such a remote region is unexpected and of significant concern. However, our experience with the analysis of these compounds at trace concentrations suggests that the observations reported may have been influenced by artifacts. Here we present our concerns based upon known emissions, physicochemical properties and on apparent quality control measures including treatment of blank samples and detection limits.
Keywords: Antarktis; forurensning; miljøgifter

An Antarctic Research Station as a Source of Brominated and Perfluorinated Persistent Organic Pollutants to the Local Environment - Wild, Seanan; McLagan, David; Schlabach, Martin; Bossi, Rossana; Hawker, Darryl; Cropp, Roger; King, Catherine K; Stark, Jonathan S; Mondon, Julie; Nash, Susan Bengtson (Environmental Science & Technology, 2015)
This study investigated the role of a permanently manned Australian Antarctic research station (Casey Station) as a source of contemporary persistent organic pollutants (POPs) to the local environment. Polybrominated diphenyl ethers (PBDEs) and poly- and perfluoroalkylated substances (PFASs) were found in indoor dust and treated wastewater effluent of the station. PBDE (e.g., BDE-209 26–820 ng g–1 dry weight (dw)) and PFAS levels (e.g., PFOS 3.8–2400 ng g–1 (dw)) in dust were consistent with those previously reported in homes and offices from Australia, reflecting consumer products and materials of the host nation. The levels of PBDEs and PFASs in wastewater (e.g., BDE-209 71–400 ng L–1) were in the upper range of concentrations reported for secondary treatment plants in other parts of the world. The chemical profiles of some PFAS samples were, however, different from domestic profiles. Dispersal of chemicals into the immediate marine and terrestrial environments was investigated by analysis of abiotic and biotic matrices. Analytes showed decreasing concentrations with increasing distance from the station. This study provides the first evidence of PFAS input to Polar regions via local research stations and demonstrates the introduction of POPs recently listed under the Stockholm Convention into the Antarctic environment through local human activities.
Keywords: Antarktis; forskningsstasjoner; forurensning; menneskelig påvirkning; miljøgifter

HFC-43-10mee atmospheric abundances and global emission estimates - Arnold, Tim; Ivy, Diane J; Harth, Christina M; Vollmer, Martin K; Mühle, Jens; Salameh, Peter K; Paul Steele, L; Krummel, Paul B; Wang, Ray H J; Young, Dickon; Lunder, Chris R; Hermansen, Ove; et al. (Geophysical Research Letters, 2014)
We report in situ atmospheric measurements of hydrofluorocarbon HFC-43-10mee (C5H2F10; 1,1,1,2,2,3,4,5,5,5-decafluoropentane) from seven observatories at various latitudes, together with measurements of archived air samples and recent Antarctic flask air samples. The global mean tropospheric abundance was 0.21 ± 0.05 ppt (parts per trillion, dry air mole fraction) in 2012, rising from 0.04 ± 0.03 ppt in 2000. We combine the measurements with a model and an inverse method to estimate rising global emissions—from 0.43 ± 0.34 Gg yr−1 in 2000 to 1.13 ± 0.31 Gg yr−1 in 2012 (~1.9 Tg CO2-eq yr−1 based on a 100 year global warming potential of 1660). HFC-43-10mee—a cleaning solvent used in the electronics industry—is currently a minor contributor to global radiative forcing relative to total HFCs; however, our calculated emissions highlight a significant difference from the available reported figures and projected estimates.
Keywords: Antarktis; atmosfæren; forurensning; massespektrometri; meteorologi; målinger; utslipp

Late Holocene climate change recorded in proxy records from a Bransfield Basin sediment core, Antarctic Peninsula - Barnard, Alex; Wellner, Julia S; Anderson, John B (Polar Research, 2014)
The glacimarine environment of the Antarctic Peninsula region is one of the fastest warming places on Earth today, but details of changes in the recent past remain unknown. Large distances and widespread variability separate late Holocene palaeoclimate reconstructions in this region. This study focuses on a marine sediment core collected from ca. 2000 m below sea level in the Central Bransfield Strait that serves as a key for understanding changes in this region. The core yielded a high sedimentation rate and therefore provides an exceptional high-resolution sedimentary record composed of hemipelagic sediment, with some turbidites. An age model has been created using radiocarbon dates that span the Late Holocene: 3560 cal yr BP to present. This chronostratigraphic framework was used to establish five units, which are grouped into two super-units: a lower super-unit (3560–1600 cal yr BP) and an upper super-unit (1600 cal yr BP–present), based on facies descriptions, laser particle size analysis, x-ray analysis, multi-sensor core logger data, weight percentages and isotopic values of total organic carbon and nitrogen. We interpret the signal contained within the upper super-unit as an increase in surface water irradiance and/or shortening of the sea-ice season and the five units are broadly synchronous with climatic intervals across the Antarctic Peninsula region. While the general trends of regional climatic periods are represented in the Bransfield Basin core we have examined, each additional record that is obtained adds variability to the known history of the Antarctic Peninsula, rather than clarifying specific trends. Keywords: Antarctic Peninsula; palaeoclimate; Holocene; marine; isotopes.
Keywords: Antarktis; geofysikk; geokjemi; paleoklimatologi; sedimentologi

Inspeksjonsordningen under Antarktistraktaten - Bech, Jon (Polarboken, 2014)
Keywords: Antarktis; jus; politikk

A community-based geological reconstruction of Antarctic Ice Sheet deglaciation since the Last Glacial Maximum - Bentley, Michael J.; Ó Cofaigh, Colm; Anderson, John B.; Conway, Howard; Davies, Bethan; Graham, Alastair G.C.; Hillenbrand, Claus-Dieter; Hodgson, Dominic A.; Jamieson, Stewart S.R.; Larter, Robert D.; Mackintosh, Andrew; Smith, James A.; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
A robust understanding of Antarctic Ice Sheet deglacial history since the Last Glacial Maximum is important in order to constrain ice sheet and glacial-isostatic adjustment models, and to explore the forcing mechanisms responsible for ice sheet retreat. Such understanding can be derived from a broad range of geological and glaciological datasets and recent decades have seen an upsurge in such data gathering around the continent and Sub-Antarctic islands. Here, we report a new synthesis of those datasets, based on an accompanying series of reviews of the geological data, organised by sector. We present a series of timeslice maps for 20 ka, 15 ka, 10 ka and 5 ka, including grounding line position and ice sheet thickness changes, along with a clear assessment of levels of confidence. The reconstruction shows that the Antarctic Ice sheet did not everywhere reach the continental shelf edge at its maximum, that initial retreat was asynchronous, and that the spatial pattern of deglaciation was highly variable, particularly on the inner shelf. The deglacial reconstruction is consistent with a moderate overall excess ice volume and with a relatively small Antarctic contribution to meltwater pulse 1a. We discuss key areas of uncertainty both around the continent and by time interval, and we highlight potential priorities for future work. The synthesis is intended to be a resource for the modelling and glacial geological community.
Keywords: Antarktis; Modelling; deglasiasjon; geologi; glasiologi; innlandsis

Svartelisting i isødet - Christensen, Stig H (LO-Aktuelt, 2014)
Hvalfangst-eventyret i Antarktis fra 1905 kostet menneskeliv og blodslit. Hvalfangernes forsøk på å organisere seg ble møtt med svartelisting, utestengelse og arrestasjoner.
Keywords: Antarktis; Sørishavet; arbeidsforhold; fagforbund; hvalfangere; hvalfangst; pelagisk; sjøfolk

Contrasting strategies of resistance vs. tolerance to desiccation in two polar dipterans - Everatt, M J; Convey, P; Worland, M R; Bale, J S; Hayward, S A L (Polar Research, 2014)
Low water availability is one of the principal stressors for terrestrial invertebrates in the polar regions, determining the survival of individuals, the success of species and the composition of communities. The Arctic and Antarctic dipterans Heleomyza borealis and Eretmoptera murphyi spend the majority of their biennial life cycles as larvae, and so are exposed to the full range of environmental conditions, including low water availability, over the annual cycle. In the current study, the desiccation resistance and desiccation tolerance of larvae were investigated, as well as their capacity for cross-tolerance to temperature stress. Larvae of H. borealis showed high levels of desiccation resistance, only losing 6.9% of their body water after 12 days at 98.2% relative humidity (RH). In contrast, larvae of E. murphyi lost 46.7% of their body water after 12 days at the same RH. Survival of E. murphyi larvae remained high in spite of this loss (>80% survival). Following exposure to 98.2% RH, larvae of E. murphyi showed enhanced survival at −18°C for 2 h. The supercooling point of larvae of both species was also lowered following prior treatment at 98.2% RH. Cross-tolerance to high temperatures (37 or 38.5°C) was not noted following desiccation in E. murphyi, and survival even fell at 37°C following a 12-day pre-treatment. The current study demonstrates two different strategies of responding to low water availability in the polar regions and indicates the potential for cross-tolerance, a capacity which is likely to be beneficial in the ever-changing polar climate. Keywords: Acclimation; dipteran; supercooling point; temperature; cross-tolerance.
Keywords: Antarktis; diptera; polarområdene; temperatur; tovinger; uttørking; virvelløse dyr

Counteracting the climate effects of volcanic eruptions using short-lived greenhouse gases - Fuglestvedt, Jan S.; Samset, Bjørn H.; Shine, Keith P. (Geophysical Research Letters, 2014)
A large volcanic eruption might constitute a climate emergency, significantly altering global temperature and precipitation for several years. Major future eruptions will occur, but their size or timing cannot be predicted. We show, for the first time, that it may be possible to counteract these climate effects through deliberate emissions of short-lived greenhouse gases, dampening the abrupt impact of an eruption. We estimate an emission pathway countering a hypothetical eruption 3 times the size of Mount Pinatubo in 1991. We use a global climate model to evaluate global and regional responses to the eruption, with and without counteremissions. We then raise practical, financial, and ethical questions related to such a strategy. Unlike the more commonly discussed geoengineering to mitigate warming from long-lived greenhouse gases, designed emissions to counter temporary cooling would not have the disadvantage of needing to be sustained over long periods. Nevertheless, implementation would still face significant challenges.
Keywords: Antarktis; drivhusgasser; global klimamodell; global oppvarming; klimatologi; nedbør; polarområdene; vulkaner

Commercial fishing vessel as research vessels in the Antarctic – Requirements and solutions exemplified with a new vessel - Godø, Olav; Reiss, Christian; Siegel, V; Watkins, Jonathan (CCAMLR science journal of the Scientific Committee and the Commission for the Conservation of Antarctic Marine Living Resources, 2014)
Keywords: Antarktis; fiskefartøy; forskning; forskningsfartøy; klimaendringer; oseanografi; økosystem

Alien invasions in Antarctica - is anyone liable? - Hughes, Kevin A; Convey, Peter (Polar Research, 2014)
The introduction of non-native species to Antarctica in association with human activities is a major threat to indigenous biodiversity and the region's unique ecosystems, as has been well-demonstrated in other ecosystems globally. Existing legislation contained in the Protocol on Environmental Protection to the Antarctic Treaty does not specifically make the eradication of non-native species mandatory, although it is implicit that human-assisted introductions should not take place. Furthermore, to date, eradications of non-native species in the Treaty area have been infrequent and slow to progress. In 2005 an additional Annex (VI) to the Protocol was agreed concerning “Liability arising from environmental emergencies.” This annex focusses on prevention of environmental emergencies, contingency planning and reclaiming costs incurred when responding to an environmental emergency caused by another operator within the Antarctic Treaty area. However, the types of environmental emergencies covered by the annex are not defined. In this paper we highlight potential difficulties with the application of Annex VI in the context of non-native species control and eradication, including, for example, whether a non-native species introduction would be classified as an “environmental emergency” and therefore be considered under the terms of the annex. Even if this were the case, we conclude that the slow pace of approval of the annex by Antarctic Treaty Parties may prevent it coming into force for many years and, once in force, in its current form it is unlikely to be useful for reclaiming costs associated with the eradication or management of a non-native species.
Keywords: Antarktis; biodiversitet; internasjonal; miljøvern; politikk; samarbeid; økosystemer

At the root of the early penguin neck: a study of the only two cervicodorsal spines recovered from the Eocene of Antarctica - Jadwiszczak, Piotr (Polar Research, 2014)
The spinal column of early Antarctic penguins is poorly known, mainly due to the scarcity of articulated vertebrae in the fossil record. One of the most interesting segments of this part of the skeleton is the transitional series located at the root of the neck. Here, two such cervicodorsal series, comprising reinterpreted known material and a new specimen from the Eocene of Seymour Island (Antarctic Peninsula), were investigated and contrasted with those of modern penguins and some fossil bones. The new specimen is smaller than the counterpart elements in recent king penguins, whereas the second series belonged to a large-bodied penguin from the genus Palaeeudyptes. It had been assigned by earlier researchers to P. gunnari (a species of “giant” penguins) and a Bayesian analysis—a Bayes factor approach based on size of an associated tarsometatarsus—strongly supported such an assignment. Morphological and functional studies revealed that mobility within the aforementioned segment probably did not differ substantially between extant and studied fossil penguins. There were, however, intriguing morphological differences between the smaller fossil specimen and the comparative material related to the condition of the lateral excavation in the first cervicodorsal vertebra and the extremely small size of the intervertebral foramen located just prior to the first “true” thoracic vertebra. The former feature could have resulted from discrepancy in severity of external pneumatization. Both fossils provided valuable insights into the morphology and functioning of the axial skeleton in early penguins. Keywords: Antarctic Peninsula; La Meseta Formation; Palaeogene; early Sphenisciformes; cervicodorsal vertebrae.
Keywords: Antarktis; biologi; fossiler; morfologi; paleogen; pingviner

Comparative study on PCDD/F pollution in soil from the Antarctic, Arctic and Tibetan Plateau - Jia, Shenglan; Wang, Qiang; Li, Li; Fang, Xuekun; Shi, Yehong; Xu, Weiguang; Hu, Jianxin (Science of the Total Environment, 2014)
The concentrations of polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) in 35 soil samples collected from Fildes Peninsula in the Antarctic, Ny-Ålesund in the Arctic, and Zhangmu-Nyalam in the Tibetan Plateau were reported in this study. A comparison of the total concentration and TEQ of PCDD/Fs at the Three Poles was conducted. Both the total concentration and TEQ of PCDD/Fs demonstrates a decreasing trend in the order of Zhangmu-Nyalam (mean: 26.22 pg/g, 0.37 pg I-TEQ/g)>Ny-Ålesund (mean: 9.97 pg/g, 0.33 pg I-TEQ/g)>Fildes Peninsula (mean: 2.18 pg/g, 0.015 pg I-TEQ/g) (p<0.05). In all samples, the congener and homologue profiles dominated with higher (seven and eight) chlorinated PCDD/Fs (more than 85% of the total mass percentage of PCDD/Fs) at the Three Poles. Finally, a FLEXPART backward simulation was used to preliminarily identify the potential local and regional anthropogenic sources of PCDD/Fs. The results imply that the air masses passing over surrounding regions with significant PCDD/F emissions might contribute to the occurrence of PCDD/Fs in both the Arctic and Tibetan Plateau.
Keywords: Antarktis; menneskelig påvirkning; miljøgifter; miljøovervåking; polarområdene

Et besøk på Bettyfjellet - Kristensen, Monica; McIntyre, Neil (Polarboken, 2014)
Keywords: Antarktis; ekspedisjoner; historie

Reassembling Gondwana: A new high quality constraint from vibroseis exploration of the sub-ice shelf geology of the East Antarctic continental margin - Kristoffersen, Yngve; Hofstede, Coen; Diez, Anja; Blenkner, Richard; Lambrecht, Astrid; Mayer, Christoph; Eisen, Olaf (Journal of Geophysical Research: Solid Earth, 2014)
The breakup of Gondwana is manifested by coeval early Jurassic Karoo magmatism in South Africa and East Antarctica. In South Africa, the large volumes of volcanic rocks of the adjoining Lebombo and Mwenetzi-Save monoclines represent a volcanic rift margin, and in East Antarctica, a corresponding feature, the Explora Wedge is buried below sediments and floating ice shelves on the continental margin of Dronning Maud Land. We use the seismic vibrator source to explore the sub-ice geology in Antarctica, and the new seismic reflection and available regional aeromagnetic data enable us to outline a dogleg landward extent of the Explora Wedge in Dronning Maud Land. The congruent inboard wedge geometries on the two continents define a high quality constraint, which facilitate for the first time, a geologically consistent and tight reconstruction of Africa relative to East Antarctica within Gondwana. The uncertainties in correlations of major geological features (mobile belts) from one continent to the other may now be of the order of ten's of kilometers rather than hundreds of kilometers.
Keywords: Antarktis; geofysikk; geologi; kontinentalmargin; seismologi; stratigrafi

Complex network of channels beneath an Antarctic ice shelf - Langley, Kirsty; von Deschwanden, Angela; Kohler, Jack; Sinisalo, Anna; Matsuoka, Kenichi; Hattermann, Tore; Humbert, Angelika; Nøst, Ole Anders; Isaksson, Elisabeth (Geophysical Research Letters, 2014)
Ice shelves play an important role in stabilizing the interior grounded ice of the large ice sheets. The thinning of major ice shelves observed in recent years, possibly in connection to warmer ocean waters coming into contact with the ice-shelf base, has focused attention on the ice-ocean interface. Here we reveal a complex network of sub ice-shelf channels under the Fimbul Ice Shelf, Antarctica, mapped using ground-penetrating radar over a 100 km2 grid. The channels are 300–500 m wide and 50 m high, among the narrowest of any reported. Observing narrow channels beneath an ice shelf that is mainly surrounded by cold ocean waters, with temperatures close to the surface freezing point, shows that channelized basal melting is not restricted to rapidly melting ice shelves, indicating that spatial melt patterns around Antarctica are likely to vary on scales that are not yet incorporated in ice-ocean models.
Keywords: Antarktis; glasiologi; innlandsis; isshelf; satellite bilder; satellite mikrobølgesensorer

Assessing the importance of human activities for the establishment of the invasive Poa annua in Antarctica - Molina-Montenegro, Marco A; Carrasco-Urra, Fernando; Acuña-Rodriguez, Ian; Oses, Rómulo; Torres-Diaz, Cristian; Chwedorzewska, Katarzyna J (Polar Research, 2014)
Because of its harsh environmental conditions and remoteness, Antarctica is often considered to be at low risk of plant invasion. However, an increasing number of reports have shown the presence and spread of non-native plants in Antarctica; it is therefore important to study which factors control the invasion process in this ecosystem. Here, we assessed the role of different human activities on the presence and abundance of the invasive Poa annua. In addition, we performed a reciprocal transplant experiment in the field, and a manipulative experiment of germination with P. annua and the natives Colobanthus quitensis and Deschampsia antarctica, in order to unravel the effects of physical soil disturbance on the establishment and survival of P. annua. We found a positive correlation between abundance of P. annua and level of soil disturbance, and that survival of P. annua was 33% higher in sites with disturbed soil than non-disturbed. Finally, we found that disturbance conditions increased germination for P. annua, whereas for native species germination in experimentally disturbed soil was either unchanged or reduced compared to undisturbed soil. Our results indicate that human activities that modify abiotic soil characteristics could play an important role in the abundance of this invasive species. If the current patterns of human activities are maintained in Antarctica, the establishment success and spread of P. annua could increase, negatively affecting native flora. Keywords: Alien species; Colobanthus quitensis; Deschampsia antarctica; human disturbance; Poa annua; tourists.
Keywords: Antarktis; biodiversitet; flora; menneskelig påvirkning; planter; turisme; økosystemer

Selected elements in surface waters of Antarctica and their relations with the natural environment - Nędzarek, Arkadiusz; Tórz, Agnieszka; Drost, Arkadiusz (Polar Research, 2014)
The aim of the study was to specify the concentration of selected chemical elements in surface waters of King George Island, off the western coast of the Antarctic Peninsula. The research encompassed six streams, a lake and an artificial water reservoir located on the western coast of Admiralty Bay. Measured hydrochemical parameters included pH, conductivity, total dissolved solids (TDS), and total and dissolved forms elements such as Al, Co, Ni, Cu, Zn, Cd, Pb, Mn, Fe, As and Se. The values of pH, conductivity and TDS had the following ranges: 6.09–8.21, 6.0–875 µS cm−1 and 7.0–975 mg/L, respectively, and were typical for surface waters of Antarctica. Wide disparities were discovered regarding concentrations of the investigated elements, ranging from <0.01 µg/L for Cd to 510 µg/L for Fe, and differing from one water body to another. The investigated elements are discussed with reference to environmental conditions and anthropogenic factors. Concentrations of total and dissolved forms of elements are considered in connection with the composition of soil in their surroundings and with atmospheric deposition, mostly such as that took place locally. The increased levels of Pb and Zn concentrations in the immediate proximity of a research station suggested anthropogenic contamination. Keywords: Antarctic surface waters; total and dissolved elements; baseline elements values; anthropogenic metal contamination.
Keywords: Antarktis; biologi; geokjemi; hydrokjemi; kjemiske analyser; overflatevann

Deterrent activities in the crude lipophilic fractions of Antarctic benthic organisms: chemical defences against keystone predators - Núñez-Pons, Laura; Avila, Conxita (Polar Research, 2014)
Generalist predation constitutes a driving force for the evolution of chemical defences. In the Antarctic benthos, asteroids and omnivore amphipods are keystone opportunistic predators. Sessile organisms are therefore expected to develop defensive mechanisms mainly against such consumers. However, the different habits characterizing each predator may promote variable responses in prey. Feeding-deterrence experiments were performed with the circumpolar asteroid macropredator Odontaster validus to evaluate the presence of defences within the apolar lipophilic fraction of Antarctic invertebrates and macroalgae. A total of 51% of the extracts were repellent, yielding a proportion of 17 defended species out of the 31 assessed. These results are compared with a previous study in which the same fractions were offered to the abundant circum-Antarctic amphipod Cheirimedon femoratus. Overall, less deterrence was reported towards asteroids (51%) than against amphipods (80.8%), principally in sponge and algal extracts. Generalist amphipods, which establish casual host–prey sedentary associations with biosubstrata (preferentially sponges and macroalgae), may exert more localized predation pressure than sea stars on certain sessile prey, which would partly explain these results. The nutritional quality of prey may interact with feeding deterrents, whose production is presumed to be metabolically expensive. Although optimal defence theory posits that chemical defences are managed and distributed as to guarantee protection at the lowest cost, we found that only a few organisms localized feeding deterrents towards most exposed and/or valuable body regions. Lipophilic defensive metabolites are broadly produced in Antarctic communities to deter opportunistic predators, although several species combine different defensive traits. Keywords: Antarctic invertebrates; Antarctic algae; chemical ecology; sea star Odontaster validus; amphipod Cheirimedon femoratus; chemical defence.
Keywords: Antarktis; alger; kjemisk økologi; virvelløse dyr

Å filme de dypfrosne hemmelighetene til en aktiv vulkan - Roberts, Jason (Polarboken, 2014)
Keywords: Antarktis; film; geofysikk; vulkaner

Recent climate tendencies on an East Antarctic ice shelf inferred from a shallow firn core network - Schlosser, Elisabeth; Anschütz, Helgard; Divine, Dmitry; Martma, Tõnu; Sinisalo, Anna; Altnau, Sebastian; Isaksson, Elisabeth (Journal of Geophysical Research: Atmospheres, 2014)
Nearly three decades of stable isotope ratios and surface mass balance (SMB) data from eight shallow firn cores retrieved at Fimbul Ice Shelf, East Antarctica, in the Austral summers 2009–2011 have been investigated. An additional longer core drilled in 2000/2001 extends the series back to the early eighteenth century. Isotope ratios and SMB from the stacked record of all cores were also related to instrumental temperature data from Neumayer Station on Ekström Ice Shelf. Since the second half of the twentieth century, the SMB shows a statistically significant negative trend, whereas the δ18O of the cores shows a significant positive trend. No trend is found in air temperature at the nearest suitable weather station, Neumayer (available since 1981). This does not correspond to the statistically significant positive trend in Southern Annular Mode (SAM) index, which is usually associated with a cooling of East Antarctica. SAM index and SMB are negatively correlated, which might be explained by a decrease in meridional exchange of energy and moisture leading to lower precipitation amounts. Future monitoring of climate change on the sensitive Antarctic ice shelves is necessary to assess its consequences for sea level change.
Keywords: Antarktis; brehylle; geofysikk; geologi; glasiologi; havnivåstigning; isbrem; isshelf; klimaendringer; meteorologi; stabile isotoper

Age-Related Mercury Contamination and Relationship with Luteinizing Hormone in a Long-Lived Antarctic Bird - Tartu, Sabrina; Bustamante, Paco; Goutte, Aurélie; Cherel, Yves; Weimerskirch, Henri; Bustnes, Jan Ove; Chastel, Olivier (PloS One, 2014)
Seabirds, as long-lived top predators, accumulate contaminants such as mercury (Hg), an established endocrine disruptor. In long lived species hormonal secretion varies with age; therefore, Hg-induced endocrine disruption may be exacerbated in some age classes. Here we investigated relationships between blood total Hg and luteinizing hormone (LH, a key pituitary hormone for the onset of breeding), in pre-laying known-age (11–45 years old) snow petrels (Pagodroma nivea) from Adélie Land, Antarctica. We predicted that 1) blood Hg would increase with advancing age as a consequence of bio-accumulation; and that 2) increasing blood Hg would be related to decreased concentrations of LH in the most Hg-contaminated individuals. Hg concentrations were higher in females than in males (p<0.001), and contrary to our prediction, decreased with advancing age in males (p = 0.009) and tended to do so in females (p = 0.06). The analysis of stable isotopes (δ13C and δ15N) suggested that this unexpected pattern could originate from age and sex-related variations in trophic niche, and hence Hg exposure. Regarding LH, our prediction was only supported in young birds (≤23 years) where baseline LH was inversely correlated with Hg concentrations (p = 0.04). Hg burden did not predict baseline LH or GnRH-induced LH in birds that were more than 23 years old. These results show that age and contaminants may interfere with major endocrine mechanisms and, together with other recent studies, support the view that Hg could be connected to LH secretion and could then impair the fitness of long-lived birds.
Keywords: Antarktis; forurensning; kjemiske analyser; miljø; nevrobiologi; ornitologi; petreller; sjøfugler; stabile isotoper; zoologi; økologiske nisjer

Antarktis-isen: større og dypere - Bjermeland, Monica (Klima: norsk magasin for klimaforskning, 2013)
De siste tiårene har isen i Antarktis økt litt i utbredelse. Men ikke fordi det er blitt kaldere der.
Keywords: Antarktis; Sørishavet; glasiologi; havis; is; klima

On-site and in situ remediation technologies applicable to metal-contaminated sites in Antarctica and the Arctic: a review - Camenzuli, Danielle; Freidman, Benjamin L; Statham, Tom M; Mumford, Kathryn A; Gore, Damian B (Polar Research, 2013)
Effective management of contaminated land requires a sound understanding of site geology, chemistry and biology. This is particularly the case for Antarctica and the Arctic, which function using different legislative frame- works to those of industrialized, temperate environments and are logistically challenging environments to operate in. This paper reviews seven remediation technologies currently used, or demonstrating potential for on-site or in situ use at metal-contaminated sites in polar environments, namely permeable reactive barriers (PRB), chemical fixation, bioremediation, phytoremediation, electrokinetic separation, land capping, and pump and treat systems. The technologies reviewed are discussed in terms of their advantages, limitations and overall potential for the management of metal-contaminated sites in Antarctica and the Arctic. This review demonstrates that several of the reviewed technologies show potential for on-site or in situ usage in Antarctica and the Arctic. Of the reviewed technologies, chemical fixation and PRB are particularly promising technologies for metal-contaminated sites in polar environments. However, further research and relevant field trials are required before these technologies can be considered proven techniques. Keywords: Polar; heavy metals; remediation; contaminants; in situ
Keywords: Antarktis; biologi; forurensning; geologi; jord; kjemi; menneskelig påvirkning; polarområdene; tungmetaller

Reading and thinking about International Polar Years: five recent books - Carlson, Dave (Polar Research, 2013)
Within the polar science community the Polar (and Geophysical) Years represent signal events. We often read, largely within geoscience literature, that those events represented positive and dramatic steps forward in international science. From five recent books - two historical compilations and three personal narratives - augmented by interviews with a few key participants, a more cautious picture emerges, of remarkable successes but also of occasional or even persistent missteps and deficiencies. An improved understanding of the IPY concept and experience can provide useful guidance for future polar and global science. Keywords: International Polar Year; International Geophysical Year; international science; history of polar science.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); IPY; bokanmeldelser; internasjonal; politikk; samarbeid; vitenskap

Using visible reflectance spectroscopy to reconstruct historical changes in chlorophyll a concentration in East Antarctic ponds - Chen, Qianqian; Liu, Xiaodong; Nie, Yaguang; Sun, Liguang (Polar Research, 2013)
The visible reflectance spectroscopy (VRS) and chlorophyll a concentration were determined in three sediment profiles collected from East Antarctica to investigate the potential application of VRS in reconstructing historical changes in Antarctic lake primary productivity. The results showed that the appearance of a trough at 650–700 nm is an important marker for chlorophyll a concentration and can therefore be used to distinguish the sedimentary organic matter source from guano and algae. The measured chlorophyll a content had significant positive correlations with the trough area between 650 and 700 nm, and no distinct trough was found in the sediments with organic matter completely derived from guano. Modelling results showed that the spectra spectrally inferred chlorophyll a content, and the measured data exhibit consistent trends with depth, showing that the dimensionless trough area can serve as an independent proxy for reconstructing historical fluctuations in the primary production of Antarctic ponds. The correlation of phosphorus (P) with measured and inferred chlorophyll a contents in ornithogenic sediments near penguin colonies indicates that the change in primary productivity in the Antarctic ponds investigated was closely related to the amount of guano input from these birds. Keywords: Reflectance spectroscopy; ornithogenic sediments; chlorophyll a; Antarctic ponds; primary productivity; VRS.
Keywords: Antarktis; alger; biogeokjemi; fytoplankton; innsjø; pingviner; sedimenter; sjøfugler

Bedmap2: improved ice bed, surface and thickness datasets for Antarctica - Fretwell, Peter; Pritchard, Hamish; Vaughan, David; Bamber, Jonathan; Barrand, N; Bell, Robin; Bianchi, Cesidio; Bingham, R; Blankenship, D; Casassa, Gino; Catania, G; Callens, D; et al. (The Cryosphere, 2013)
We present Bedmap2, a new suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of the Antarctic south of 60° S. We derived these products using data from a variety of sources, including many substantial surveys completed since the original Bedmap compilation (Bedmap1) in 2001. In particular, the Bedmap2 ice thickness grid is made from 25 million measurements, over two orders of magnitude more than were used in Bedmap1. In most parts of Antarctica the subglacial landscape is visible in much greater detail than was previously available and the improved data-coverage has in many areas revealed the full scale of mountain ranges, valleys, basins and troughs, only fragments of which were previously indicated in local surveys. The derived statistics for Bedmap2 show that the volume of ice contained in the Antarctic ice sheet (27 million km3) and its potential contribution to sea-level rise (58 m) are similar to those of Bedmap1, but the mean thickness of the ice sheet is 4.6% greater, the mean depth of the bed beneath the grounded ice sheet is 72 m lower and the area of ice sheet grounded on bed below sea level is increased by 10%. The Bedmap2 compilation highlights several areas beneath the ice sheet where the bed elevation is substantially lower than the deepest bed indicated by Bedmap1. These products, along with grids of data coverage and uncertainty, provide new opportunities for detailed modelling of the past and future evolution of the Antarctic ice sheets.
Keywords: Antarktis; glasiologi

Abundance and breeding distribution of seabirds in the northern part of the Danco Coast, Antarctic Peninsula - González-Zevallos, Diego; Santos, M Mercedes; Rombolá, Emilce F; Juáres, Mariana A; Coria, Néstor R (Polar Research, 2013)
Seabird abundances and breeding distribution have the potential to serve as ecological indicators. The western Antarctic Peninsula is one of the three sites in the world with the greatest increases in local temperature during the last 50 years. The aim of this study was to monitor the distribution and abundance of breeding populations of seabirds in the northern sector of the Danco Coast, north-west of the Antarctic Peninsula, during the breeding season 2010/11. The birds were the Wilson's storm petrel (Oceanites oceanicus), South Polar skua (Stercorarius maccormicki), kelp gull (Larus dominicanus), Antarctic tern (Sterna vittata), snowy sheathbill (Chionis alba), chinstrap penguin (Pygoscelis antarctica), southern giant petrel (Macronectes giganteus), gentoo penguin (Pygoscelis papua), Cape petrel (Daption capense) and Antarctic shag (Phalacrocorax bransfieldensis). Annual breeding population growth increased in pygoscelids, southern giant petrel and sheathbill, and for the remaining species, breeding population trends were stable. Given that seabird populations can provide valuable information on the conditions of their feeding and nesting environments, this study highlights the need to maintain basics monitoring studies. Keywords: Seabird abundances; breeding distribution; Danco Coast; Antarctic Peninsula.
Keywords: Antarktis; klimaendringer; ornitologi; petreller; sjøfugler; temperatur

The impact of abrupt suspension of solar radiation management (termination effect) in experiment G2 of the Geoengineering Model Intercomparison Project (GeoMIP) - Jones, Andy; Haywood, Jim M; Alterskjær, Kari; Boucher, Olivier; Cole, Jason N S; Curry, Charles L; Irvine, Peter J; Ji, Duoying; Kravitz, Ben; Egill Kristjánsson, Jón; Moore, John C; Niemeier, Ulrike; et al. (Journal of Geophysical Research: Atmospheres, 2013)
We have examined changes in climate which result from the sudden termination of geoengineering after 50 years of offsetting a 1% per annum increase in CO2 concentrations by a reduction of solar radiation, as simulated by 11 different climate models in experiment G2 of the Geoengineering Model Intercomparison Project. The models agree on a rapid increase in global-mean temperature following termination accompanied by increases in global-mean precipitation rate and decreases in sea-ice cover. There is no agreement on the impact of geoengineering termination on the rate of change of global-mean plant net primary productivity. There is a considerable degree of consensus for the geographical distribution of temperature change following termination, with faster warming at high latitudes and over land. There is also considerable agreement regarding the distribution of reductions in Arctic sea-ice, but less so for the Antarctic. There is much less agreement regarding the patterns of change in precipitation and net primary productivity, with a greater degree of consensus at higher latitudes.
Keywords: Antarktis; global oppvarming; karbondioksid; klimaendringer; klimamodeller; klimatologi; polarområdene; solstråling

Better late than never? Interannual and seasonal variability in breeding chronology of gentoo penguins at Stranger Point, Antarctica - Juáres, Mariana A; Santos, M Mercedes; Negrete, Javier; Santos, M Rita; Mennucci, Jorge A; Rombolá, Emilce; Longarzo, Lucrecia; Coria, Néstor R; Carlini, Alejandro R (Polar Research, 2013)
Rapid climate change recorded in the western Antarctic Peninsula confronts species with less predictable conditions in the marine and terrestrial environments. We analysed the breeding chronology and nesting site selection of gentoo penguins (Pygoscelis papua) at King George Island (Isla 25 de Mayo), Antarctica, during four seasons in which differences in snow presence and persistence on the ground were observed. We recorded an overall delay as well as seasonal asynchrony at the beginning of reproduction for those years with higher snow deposition. A redistribution of breeding groups was also observed. Nevertheless, the population breeding success and chicks’ weight at fledging remained relatively constant, despite the delay in breeding chronology, the increased duration of foraging trips during the guard stage and the decreased weight of stomach contents during the crèche stage. We suggest that the plasticity of their trophic biology, along with the flexibility of their breeding phenology and relocation of breeding groups, may be complementary reasons why gentoo penguin populations in the region have remained stable in spite of the changing conditions currently registered. Keywords: Antarctica; breeding delay; breeding phenology; snow; Pygoscelis papua; Euphausia superba.
Keywords: Antarktis; klimaendringer; krill; observasjoner; pingviner; plankton; reproduksjon; snø; zoologi

Standardized algal growth potential and/or algal primary production rates of maritime Antarctic stream waters (King George Island, South Shetlands) - Kvíderová, Jana; Elster, Josef (Polar Research, 2013)
In addition to the chemical analyses providing total nutrient content, standardized water trophic status bioassays are useful in the determination of available nutrients for primary producers. The aim of the study was to determine the standardized values of algal growth potential (AGP) and algal primary productivity rate (APPR) of maritime Antarctic stream water using modified AGP/APPR protocols. The standardized values of AGP and the APPR of oligotrophic and mesotrophic water samples from snow-melt streams were measured, and possible nutrient limitation and heavy metal inhibition were evaluated at 5°C and 25°C using polar and temperate strains of Stichococcus bacillaris, respectively. The water samples were enriched for the nutrient limitation tests with 1000 mμ l-1 NO3- -N, 50 μg l-1 PO43- -P, and a mixture of 1000 μg l-1 NO3- -N + 50 μg l-1 PO43- -P, and for the heavy metal inhibition tests with 1000 mg l-1 Na2-ethylenediaminetetraacetic acid (EDTA). The AGP of oligotrophic samples was significantly lower than that of the mesotrophic ones at both temperatures. In addition, AGP was significantly higher at 5°C than at 25°C. Oligotrophic samples were identified as being nitrogen limited, while no nutrient limitation was observed in the mesotrophic samples. No statistically significant heavy metal inhibition was observed at either temperature. The positive correlation of AGP and water nutrient content indicates that the method used accurately and comprehensively monitors the changes in biological availability of mineral nutrients and can provide a standardized reference point for similar exploration of freshwater ecosystems across both polar regions. Keywords: Maritime Antarctic; microalgae; nutrient limitations; snow-melt stream water.
Keywords: Antarktis; alger; analyser; ferskvann; innsjø; kjemisk; klimaendringer; næringsstoff; polarområdene; snø; strøm; økosystemer

Automated ice-sheet snowmelt detection using microwave radiometer measurements - Liang, Lei; Guo, Huadong; Li, Xinwu; Cheng, Xiao (Polar Research, 2013)
Monitoring ice-sheet snowmelt is fundamental to understanding global climate change. A simple and automated snowmelt detection process is critical to the establishment of an ice-sheet snowmelt monitoring system. However, different ice-sheet snowmelt detection methods are based on a variety of thresholding schemes using different melt signals for dry and wet snow; these complicate the regular operation of an ice-sheet snowmelt monitoring. We propose an automated melt signal detection method developed using melt signals derived from the cross-gradient polarization ratio snowmelt detection method over Greenland and the wavelet transformation-based snowmelt detection method over Antarctica. Initial results indicate that the proposed method not only increases computational efficiency, practicability and operability but is also more accurate. Keywords: Ice sheet; snowmelt detection; radiometer; cross-gradient polarization ratio; wavelet transformation; generalized Gaussian model.
Keywords: Antarktis; innlandsis; klimaendringer; mikrobølge; målinger; polarområdene; radiometer; snøsmelting; statistisk analyse; temperatur måling

Observations of nitric oxide in the Antarctic middle atmosphere during recurrent geomagnetic storms - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Straub, Corinne; Holmén, Kim; Horne, Richard B (Journal of Geophysical Research: Space Physics, 2013)
We report ground-based measurements of the polar middle atmosphere made using a 230–250 GHz passive microwave radiometer deployed at Troll station (72°01′S 02°32′E, L shell of L = 4.8), Antarctica. Our observations show enhanced mesospheric nitric oxide (NO) volume mixing ratio (VMR) during a series of small recurrent geomagnetic storms in the 2008 austral winter, reaching 1.2 ppmv on day 200 (18 July). The Lomb normalized periodogram of the NO VMR time series averaged over 65-80 km for days 130 to 220 of 2008 (9 May to 7 August) shows a peak exceeding the 95% confidence limit at 25.8 days, close to the synodic rotation period for low-latitude solar coronal holes. The highest correlations between the radiometer NO VMR data and trapped and quasi-trapped electron count rates for L = 3.5-5.5 from the Polar Orbiting Environment Satellites 90° telescope are for the >30 keV (90e1) channel (rmax = 0.56, lag time of 5.1 days) and >100 keV (90e2) channel (rmax = 0.57, lag time of 4.4 days). Maximum correlation between NO VMR and the >700 keV (90P6) channel data is lower but lag times are close to zero. Superposed epoch analyses for the eight most significant geomagnetic storm periods and three Carrington rotations (2070-2072) within the 90 day observation period indicate that significant NO abundance observed at 65-80 km in the Antarctic mesosphere may be produced directly by >200 keV electron precipitation or originate from a source at higher altitudes, e.g., production by >30 keV electrons followed by downward transport.
Keywords: Antarktis; atmosfæren; fysikk; geomagnetiske stormer; meteorologi; polarområdene

New at-sea records of pelagic seabirds in the South Atlantic Ocean and Antarctica - Orgeira, José Luis; Scioscia, Gabriela; Torres, Mónica Anilía; Dellabianca, Natalia Andrea (Polar Research, 2013)
During ship-based seabird surveys in the south Atlantic and Antarctica in the austral summers of 1994/95, 2009, 2010, 2011 and 2012, we documented at-sea distributions of Buller’s albatross (Thalassarche bulleri), Atlantic petrel (Pterodroma incerta), soft-plumaged petrel (Pterodroma mollis), Kerguelen petrel (Lugensa brevirostris) and great-winged petrel (Pterodroma macroptera). In some cases, sightings were considered as extralimital, but for other species updating their distributions in the literature seems warranted. Atlantic petrel, for example, has been regularly observed in the Drake Passage and north of the Antarctic Peninsula for about 30 years, but the distribution of this species has not been updated in the literature. The observations reported here will contribute to update the at-sea distributions of these species and to changes in their distributions. Keywords: Seabirds; Antarctica; South Atlantic Ocean; distribution.
Keywords: Antarktis; Sørishavet; marin zoologi; observasjoner; ornitologi; petreller; sjøfugler

The first men on the last continent – Carsten Egeberg Borchgrevink and the Southern Cross expedition, 1898 -1900 - Smelror, Morten (Fram forum, 2013)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; første landgang; geologi; oppdagelsesreiser; overvintring

Trends in Antarctic ecological research in Latin America shown by publications in international journals - Stotz, Gisela C; Salgado-Luarte, Cristian; Rios, Rodrigo S; Acuña-Rodriguez, Ian S; Carrasco-Urra, Fernando; Molina-Montenegro, Marco A; Gianoli, Ernesto (Polar Research, 2013)
Antarctica is a highly interesting region for ecologists because of its extreme climatic conditions and the uniqueness of its species. In this article, we describe the trends in Antarctic ecological research participation by Latin American countries. In a survey of articles indexed by the ISI Web of Science, we searched under the categories ‘‘Ecology,’’ ‘‘Biodiversity Conservation’’ and ‘‘Evolutionary Biology’’ and found a total of 254 research articles published by Latin American countries. We classified these articles according to the country of affiliation, kingdom of the study species, level of biological organization and environment. Our main finding is that there is a steady increase in the relative contribution of Latin American countries to Antarctic ecological research. Within each category, we found that marine studies are more common than terrestrial studies. Between the different kingdoms, most studies focus on animals and most studies use a community approach. The leading countries in terms of productivity were Argentina, Chile and Brazil, with Argentina showing the highest rate of increase. Keywords: Antarctica; Argentina; Brazil; Chile; research trends; scientific productivity.
Keywords: Antarktis; biodiversitet; forskning; vitenskap; økologi

Characterization and mapping of plant communities at Hennequin Point, King George Island, Antarctica - Victoria, Filipe de C; de Albuquerque, Margéli P; Pereira, Antonio B; Simas, Felipe N B; Spielmann, Adriano A; Schaefer, Carlos E G R (Polar Research, 2013)
King George Island is the largest island and the principal area used for research bases in Antarctica. Argentina, Brazil, Chile, China, Poland, Russia, South Korea and Uruguay have permanent open bases on this island. Other countries have seasonal summer stations on different parts of this island, which demonstrates that human impact is strong on King George Island relative to other areas in the maritime and continental Antarctica. The objective of this work was to present a phytosociological approach for ice-free areas of Hennequin Point, eastern coast of Admiralty Bay, King George Island. The study started with the classification and description of the plant communities based primarily on phytosociological and biodiversity data. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The plant communities were described as follows: (1) lichen and moss cushion formation; (2) moss carpet formation; (3) fellfield formation; (4) grass and cushion chamaephyte formation; and (5) Deschampsia Antarctica–lichen formation. Characterizations and distributions of the plant communities are presented on a map at a scale of 1:5000. The plant communities found at Hennequin Point, in general, differ from those found in other areas of the Admiralty Bay region, probably because of the concentration of skua nests in the area and the relief singularities. We conclude by highlighting the importance of the study of plant species found in the ice-free areas of the Antarctic with respect to environmental monitoring and for evaluating global climate and environmental changes. Keywords: Plant communities mapping; lichens; mosses; flowering plants; Antarctic
Keywords: Antarktis; biodiversitet; fytososiologi; klimaendringer; lav; miljøendringer; moser; planter; plantesosiologi

Isolation and description of a globally distributed cryosphere cyanobacterium from Antarctica - Won Hong, Ji; Kim, Sung Hong; Choi, Han-Gu; Kang, Sung-Ho; Yoon, Ho-Sung (Polar Research, 2013)
A previously uncultured cyanobacterium, strain KNUA009, was axenically isolated from a meltwater stream on Barton Peninsula, King George Island, South Shetland Islands, Antarctica. Molecular evidences showed that the isolate belongs to groups of globally distributed cryosphere cyanobacterial clones and this new isolate represents the first laboratory culture to be assigned to these groups. Strain KNUA009 was able to thrive at low temperatures ranging between 5°C and 20°C, but did not survive at temperatures of 25°C and above. As the isolate morphologically resembled Oscillatoria species, it is suggested that this cyanobacterium may represent a new species clade with cold resistance within the genus Oscillatoria. Keywords: Barton Peninsular; cryosphere cyanobacteria; King George Island; uncultured Oscillatoria species.
Keywords: Antarktis; bakterier; biologi; ferskvann; fylogenetikk

Den japanske antarktisekspedisjonen i 1912 - Barr, Susan (Polarboken, 2012)
Keywords: Antarktis; ekspedisjoner; historie

Roald Amundsen: Forsker eller grobian? - Blix, Arnoldus Schytte (Nordisk tidskrift för vetenskap, konst och industri, 2012)
Roald Amundsens (1872-1928) liv og bedrifter er fremstilt i en rekke biografier, men det er oppdageren og eventyreren som blir tillagt mest vekt, mens vitenskapsmannen og forskeren tidvis underkjennes. Professor i arktisk biologi ved Universitetet i Tromsø, Arnoldus Schytte Blix, er kritisk til mye av det biografiske arbeidet som er gjort, og mener det er et åpent spørsmål om kontorhistorikere og journalister har noen reell mulighet til fullt ut å forstå Roald Amundsens situasjon og reaksjoner. Artikkelen er basert på et foredrag med en rekke illustrasjoner i Det Norske Videnskabs-Akademi, 17. november 2011.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; biografier; oppdagelsesreiser

Ecosystem response to climatic change: the importance of the cold season - Bokhorst, Stef; Bjerke, Jarle W; Tømmervik, Hans; Preece, Catherine; Phoenix, Gareth K (Ambio, 2012)
Winter climate and snow cover are the important drivers of plant community development in polar regions. However, the impacts of changing winter climate and associated changes in snow regime have received much less attention than changes during summer. Here, we synthesize the results from studies on the impacts of extreme winter weather events on polar heathland and lichen communities. Dwarf shrubs, mosses and soil arthropods were negatively impacted by extreme warming events while lichens showed variable responses to changes in extreme winter weather events. Snow mould formation underneath the snow may contribute to spatial heterogeneity in plant growth, arthropod communities and carbon cycling. Winter snow cover and depth will drive the reported impacts of winter climate change and add to spatial patterns in vegetation heterogeneity. The challenges ahead lie in obtaining better predictions on the snow patterns across the landscape and how these will be altered due to winter climate change.
Keywords: Antarktis; biologi; botanikk; dyr; klimaendringer; leddyr; planter; snø; sopper; zoologi; økosystemer

Environmental monitoring and management proposals for the Fildes Region, King George Island, Antarctica - Braun, Christina; Mustafa, Osama; Nordt, Anja; Pfeiffer, Simone; Peter, Hans-Ulrich (Polar Research, 2012)
The Antarctic terrestrial environment is under increasing pressure from human activities. The Fildes Region is characterized by high biodiversity, but is also a major logistic centre for the northern Antarctic Peninsula. Different interests, from scientific research, nature conservation, protection of geological and historical values, station operations, transport logistics and tourism, regularly overlap in space and time. This has led to increasing conflict among the multiple uses of the region and breaches of the legal requirements for environmental protection that apply in the area. The aim of this study was to assess the impacts of human activities in the Fildes Region by monitoring the distribution of bird and seal breeding sites and recording human activities and their associated environmental impacts. Data from an initial monitoring period 200306 were compared with data from 200810. We observed similar or increased levels of air, land and ship traffic, but fewer violations of overflight limits near Antarctic Specially Protected Area No. 150 Ardley Island. Open waste dumping and oil contamination are still major environmental impacts. Scientific and outdoor leisure activities undertaken by station personnel are more frequent than tourist activities and are likely to have a commensurate level of environmental impact. Despite the initial success of some existing management measures, it is essential that scientific and environmental values continue to be safeguarded, otherwise environmental impacts will increase and the habitat will be further degraded. We argue that the Fildes Region should be considered for designation as an Antarctic Specially Managed Area, a measure that has proven effective for environmental management of vulnerable areas of the Antarctic.
Keywords: Antarktis; biodiversitet; miljøvern

Aerosol-Mediated Transport and Deposition of Brominated Diphenyl Ethers to Antarctica - Dickhut, Rebecca M; Cincinelli, Alessandra; Cochran, Michele; Kylin, Henrik (Environmental Science & Technology, 2012)
Brominated diphenyl ethers (BDE47, 99, 100, and 209) were measured in air, snow and sea ice throughout western Antarctica between 2001 and 2007. BDEs in Antarctic air were predominantly associated with aerosols and were low compared to those in remote regions of the northern hemisphere, except in Marguerite Bay following the fire at Rothera research station in Sept 2001, indicating that this event was a local source of BDE209 to the Antarctic environment. Aerosol BDE47/100 reflects a mixture of commercial pentaBDE products; however, BDE99/100 is suggestive of photodegradation of BDE99 during long-range atmospheric transport (LRAT) in the austral summer. BDEs in snow were lower than predicted based on snow scavenging of aerosols indicating that atmospheric deposition events may be episodic. BDE47, -99, and -100 significantly declined in Antarctic sea ice between 2001 and 2007; however, BDE209 did not decline in Antarctic sea ice over the same time period. Significant losses of BDE99 and -100 from sea ice were recorded over a 19 day period in spring 2001 demonstrating that seasonal ice processes result in the preferential loss of some BDEs. BDE47/100 and BDE99/100 in sea ice samples reflect commercial pentaBDE products, suggesting that photodegradation of BDE99 is minimal during LRAT in the austral winter.
Keywords: Antarktis; Sørishavet; atmosfæren; forurensning; miljøgifter; polarområdene

Low genetic diversity in Antarctic populations of the lichenforming ascomycete Cetraria aculeata and its photobiont - Domaschke, Stephanie; Fernández-Mendoza, Fernando; Garcia, Miquel A; Martín, Maria P; Printzen, Christian (Polar Research, 2012)
Lichens, symbiotic associations of fungi (mycobionts) and green algae or cyanobacteria (photobionts), are poikilohydric organisms that are particularly well adapted to withstand adverse environmental conditions. Terrestrial ecosystems of the Antarctic are therefore largely dominated by lichens. The effects of global climate change are especially pronounced in the maritime Antarctic and it may be assumed that the lichen vegetation will profoundly change in the future. The genetic diversity of populations is closely correlated to their ability to adapt to changing environmental conditions and to their future evolutionary potential. In this study, we present evidence for low genetic diversity in Antarctic mycobiont and photobiont populations of the widespread lichen Cetraria aculeata. We compared between 110 and 219 DNA sequences from each of three gene loci for each symbiont. A total of 222 individuals from three Antarctic and nine antiboreal, temperate and Arctic populations were investigated. The mycobiont diversity is highest in Arctic populations, while the photobionts are most diverse in temperate regions. Photobiont diversity decreases significantly towards the Antarctic but less markedly towards the Arctic, indicating that ecological factors play a minor role in determining the diversity of Antarctic photobiont populations. Richness estimators calculated for the four geographical regions suggest that the low genetic diversity of Antarctic populations is not a sampling artefact. Cetraria aculeata appears to have diversified in the Arctic and subsequently expanded its range into the Southern Hemisphere. The reduced genetic diversity in the Antarctic is most likely due to founder effects during long-distance colonization. The environmental conditions of the Antarctic are among the most adverse on Earth and are generally characterized by low mean annual temperatures, high wind velocities, extreme drought and extended periods of darkness. The effects of global climate change are especially pronounced in parts of the Antarctic (Turner et al. 2005). Air temperature in the maritime Antarctic has steadily increased within the last years (Smith & Stammerjohn 1996; Turner et al. 2005). On the western Antarctic Peninsula a temperature increase of more than 2.5 K has been observed over the last 50 years. The overall effect of such a temperature increase on terrestrial Antarctic organisms could be beneficial. For example, glacial melting will increase the availability of terrestrial (page number not for citation purpose). Keywords Genetic diversity; lichens; Cetraria aculeata; Trebouxia jamesii; polar lichens; global change.
Keywords: Antarktis; alger; fotobiont; genetisk mangfold; klimaendringer; lav; sopper; økosystemer

Leadership in politics and science within the Antarctic Treaty - Dudeney, John R; Walton, David W H (Polar Research, 2012)
For over 50 years the Antarctic has been governed through the Antarctic Treaty, an international agreement now between 49 nations of whom 28 Consultative Parties (CPs) undertake the management role. Ostensibly, these Parties have qualified for their position on scientific grounds, though diplomacy also plays a major role. This paper uses counts of policy papers and science publications to assess the political and scientific outputs of all CPs over the last 18 years. We show that a subset of the original 12 Treaty signatories, consisting of the seven claimant nations, the USA and Russia, not only set the political agenda for the continent but also provide most of the science, with those CPs producing the most science generally having the greatest political influence. None of the later signatories to the Treaty appear to play a major role in managing Antarctica compared with this group, with half of all CPs collectively producing only 7% of the policy papers. Although acceptance as a CP requires demonstration of a substantial scientific programme, the Treaty has no formal mechanism to review whether a CP continues to meet this criterion. As a first step to addressing this deficiency, we encourage the CPs collectively to resolve to hold regular international peer reviews of their individual science programmes and to make the results available to the other CPs. Keywords: Governance; claimant states; Antarctic policy; scientific publications.
Keywords: Antarktis; Antarktistraktaten; forvaltning; politikk; vitenskap

Correlative and dynamic species distribution modelling for ecological predictions in the Antarctic: a cross-disciplinary concept - Gutt, Julian; Zurell, Damaris; Bracegridle, Thomas J; Cheung, William; Clark, Melody S; Convey, Peter; Danis, Bruno; David, Bruno; De Broyer, Claude; di Prisco, Guido; Griffiths, Huw; Laffont, Rémi; et al. (Polar Research, 2012)
Keywords: Antarktis; biodiversitet; biosfære; miljø; oseanografi; økologi; økosystemer

Review of Race for the South Pole: the expedition diaries of Scott and Amundsen, by Roland Huntford - Jølle, Harald Dag (Polar Research, 2012)
Roland Huntford is the grand old man among polar historians. After his classic Scott and Amundsen in 1979 (later editions were retitled, The last place on Earth), he wrote a series of books on Norwegian and British polar heroes as well as a thorough study of the history of skiing (2006). Huntford challenged the British admiration of Robert Falcon Scott’s scientific programme and great courage*and insisted that Roald Amundsen’s expedition was far better prepared and carried out. Huntford’s scathing criticism of Scott’s fatal choices and lack of competence dared to assault this cherished British polar icon in a manner that would be unthinkable for Norwegian authors.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; Sørpolen; bokanmeldelser; dagbøker; kappløpet; polarhistorie; polarområdene

The South Pole expedition of Roald Amundsen: how did he prepare for the expedition and what do his crewmembers' diaries tell us about it? / Geir O. Kløver. - Kløver, Geir Olav (Nimrod : the Journal of the Ernest Shackleton Autumn School, 2012)
Describes Amundsen's experience on de Gerlache's 1897-99 Belgica Antarctic expedition, scientific interests, lessons learned on his 1903-06 Gjøa Northwest Passage expedition, and experience on 1910-12 Fram Antarctic expedition. Gives details of crew members on Antarctic expedition with account of their diaries. Author is director of Fram Museum and editor of South Pole diaries of Amundsen and fourteen of his crew members.
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; dagbøker; polarhistorie

Perspective: Strategic challenges of tourism development and governance in Antarctica: taking stock and moving forward - Lamers, Machiel; Liggett, Daniela; Amelung, Bas (Polar Research, 2012)
Keywords: Antarktis; forvaltning; turisme

Spatial variation of englacial radar attenuation: Modeling approach and application to the Vostok flowline - MacGregor, Joseph A.; Matsuoka, Kenichi; Waddington, Edwin D.; Winebrenner, Dale P.; Pattyn, Frank (Journal of Geophysical Research: Earth Surface, 2012)
Constraining the spatial variation of englacial radar attenuation is critical for accurate inference of the spatial variation of the englacial and basal properties of ice sheets from radar returned power. Here we evaluate attenuation models that account for spatial variations in ice temperature and chemistry and test them along the flowline that passes through the Vostok ice core site, Antarctica. The simplest model, often used but rarely valid, assumes a uniform attenuation rate everywhere along the flowline, so that total attenuation is proportional to ice thickness. The next simplest model uses spatially varying temperatures predicted by an ice-flow model and assumes uniform chemistry. Additional models account for spatially varying chemistry using englacial stratigraphy. We find that the roundtrip attenuation to the bed can easily differ by 10 dB or more between the uniform attenuation-rate model and models that account for variable ice temperature. Such differences are sufficient to confound the delineation of dry and wet beds. Also including spatial variations in chemistry produces smaller differences (<10 dB), but the magnitude of these differences depends on the relative importance of dry and wet deposition of impurities in the past. Accounting for dry-deposited impurities requires ice-flow modeling and results in larger differences from all other models, which assume uniform chemistry or wet deposition only. These results indicate that modeling the spatial variation of attenuation requires a spatially varying temperature model in order to infer bed conditions from bed returned power accurately, and that both ice core data and radar stratigraphy are also strongly desirable.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis

Rapid development of anisotropic ice-crystal-alignment fabrics inferred from englacial radar polarimetry, central West Antarctica - Matsuoka, Kenichi; Power, Donovan; Fujita, Shuji; Raymond, Charles F (Journal of Geophysical Research: Earth Surface, 2012)
Anisotropy in englacial radar power was measured using 60-MHz and 179-MHz copolarized pulse-modulated radar at 19 sites in central West Antarctica. The study region is a 100 × 300 km2area near the West Antarctic Ice Sheet Divide that separates ice flow toward the Ross and Amundsen Embayments. The frequency dependence of the returned power indicates that most of the radar data are affected by vertical variations in the crystal-orientation fabric (COF), though the 60-MHz data are more affected by acidity contrasts in the top 1000 m. Significant polarimetric variations occur at most sites, likely due to effects of the anisotropic COF patterns. More anisotropic variations occur at sites with significant horizontal strain, whereas more isotropic variations occur at sites where vertical compression dominates. Azimuthal shifts with depth of the principal axes of COF were found in shallow ice near the current flow divide and at greater depths over locations of rough bed. The former indicates that the divide has differentially migrated, resulting in a rotation of the principal COF axes. Nevertheless, the regionally consistent radar signatures suggest that the first-order ice properties in this area have remained constant and that no major changes in the strain configuration or ice topography have occurred for the past five to eight thousand years. We conclude that shallow polarimetric features can be related to the current strain configurations, and that englacial polarimetric features can help constrain current ice rheology and evolution of the ice topography.
Keywords: Antarktis; glasiologi; innlandsis; iskrystaller; polarimetrisk radar; topografi

Review of A complete guide to Antarctic wildlife: birds and mammals of the Antarctic Continent and the Southern Ocean, by Hadoram Shirihai - Mehlum, Fridtjof (Polar Research, 2012)
This impressive book is an invaluable, fully illustrated, wildlife guide for tourists and scientists visiting the Southern Ocean and Antarctica.
Keywords: Antarktis; Sørishavet; bokanmeldelser; dyreliv; fugler; marin biologi; ornitologi; pattedyr; zoologi

The oldest elasmosaurs (Sauropterygia, Plesiosauria) from Antarctica, Santa Marta Formation (upper Coniacian? Santonian-upper Campanian) and Snow Hill Island Formation (upper Campanian-lower Maastrichtian), James Ross Island - O'Gorman, José P (Polar Research, 2012)
Elasmosaurs are recorded for the first time in the Lachman Crags Member (Beta Member) of the Santa Marta Formation (lower Campanian) and in the Herbert Sound Member of the Snow Hill Island Formation (upper Campanian). These are the first elasmosaurids from James Ross Island, Antarctic Peninsula. These records greatly improve our knowledge of the taxonomic diversity of plesiosaurs of the Santa Marta Formation and Herbert Sound Member of the Snow Hill Island Formation, and extend the lower limit of the record of Elasmosauridae in Antarctica to the lower Campanian, making this the oldest record of an Antarctic elasmosaur. Keywords: Elasmosauridae; Antarctica; Late Cretaceous.
Keywords: Antarktis; geologi; paleontologi

Being there: examining the behaviour of Antarctic tourists through their blogs - Roura, Ricardo M (Polar Research, 2012)
Most visitors to Antarctica today are commercial tourists. Over 150 000 tourists visited Antarctica between 2007 and 2010, making up more than 700 000 person/landings. Despite the scale of tourism in Antarctica, knowledge about its environmental impacts is generally inconclusive, and monitoring is limited. This article examines tourist behaviour regarding the environment using information available on travel weblogs (blogs) posted by tourists on the Internet. Fifty blogs describing Antarctic travel were analysed, mostly as part of organized tourism cruises, during the four Antarctic summer seasons between 2007 and 2010, both qualitatively and quantitatively. The blogs described the activities of 90 people who had visited Deception Island as part of their itinerary and who, overall, had undertaken at least 190 person/landings in Antarctica. Blog analysis highlighted the importance of wildlife as a tourist attraction. In the blogs it was apparent that touristwildlife interactions result in a range of behaviours from both individual tourists and animals. Tourism results in cultural traces and other environmental consequences, although some of these would not be judged as ‘‘impacts’’ under the current practice of implementing the Protocol on Environmental Protection to the Antarctic Treaty. Blogs showed many more instances of compliance than of noncompliance with environmental regulations. Tourist blogs illustrate the behavioural processes by which environmental impacts from tourism could occur, which are repeated through thousands of person-landings and other activities in Antarctica every season. Precautionary action may be a practical alternative to manage tourism at some sites until it is clearer how this activity affects the environment.
Keywords: Antarktis; miljøvern; polarområdene; turisme

Extent of low-accumulation 'wind glaze' areas on the East Antarctic plateau: implications for continental ice mass balance - Scambos, Ted A; Frezzotti, Massimo; Haran, T; Bohlander, J; Lenaerts, Jan T M; Van Den Broeke, M R; Jezek, K; Long, D; Urbini, S; Farness, K; Neumann., T; Albert, M; et al. (Journal of Glaciology, 2012)
Persistent katabatic winds form widely distributed localized areas of near-zero net surface accumulation on the East Antarctic ice sheet (EAIS) plateau. These areas have been called 'glaze' surfaces due to their polished appearance. They are typically 2-200 km2 in area and are found on leeward slopes of ice-sheet undulations and megadunes. Adjacent, leeward high-accumulation regions (isolated dunes) are generally smaller and do not compensate for the local low in surface mass balance (SMB). We use a combination of satellite remote sensing and field-gathered datasets to map the extent of wind glaze in the EAIS above 1500 m elevation. Mapping criteria are derived from distinctive surface and subsurface characteristics of glaze areas resulting from many years of intense annual temperature cycling without significant burial. Our results show that 11.2 ± 1.7%, or 950 ± 143 × 103km2, of the EAIS above 1500 m is wind glaze. Studies of SMB interpolate values across glaze regions, leading to overestimates of net mass input. Using our derived wind-glaze extent, we estimate this excess in three recent models of Antarctic SMB at 46-82 Gt. The lowest-input model appears to best match the mean in regions of extensive wind glaze.
Keywords: Antarktis; glasiologi

Sydpolen eller Sørpolen? - Skagestad, Odd Gunnar (Ordet: kvartalsskrift for riksmålsbevegelsen, 2012)
Keywords: Antarktis; språk; stedsnavn

The impact of human activities on wilderness and aesthetic values in Antarctica - Summerson, Rupert; Bishop, Ian D. (Polar Research, 2012)
There has been little progress in implementing protection of wilderness and aesthetic values in Antarctica since the coming into force of the Protocol on Environmental Protection to the Antarctic Treaty in 1998. This can in part be attributed to a lack of research defining these values and showing how they may be assessed. In 2009, a survey comprising 90 images of Antarctic landscapes was established on the Internet to canvass as wide a cross-section of people with an interest in Antarctica as possible on their perceptions of wilderness and their aesthetic preference. At the time of writing, over 337 respondents from 23 nationalities have taken part in the survey. Responses were analysed to determine the effect of human presence, both transient and as infrastructure, on perceptions of wilderness and aesthetic values. The analysis was in three parts: (1) all images combined; (2) images grouped by landscape type, derived from the Environmental Domains of Antarctica regionalization; and (3) 16 pairs of digitally manipulated images of which respondents were shown either an original image or one in which human presence had been either digitally removed or added. Responses to images grouped by landscape type show that coastal and ice-free areas are less valued both aesthetically and as wilderness than mountainous and ice-covered terrains. Signs of human presence were found to make images significantly less likely to be considered as wilderness and also reduced their aesthetic rating. This demonstrates that human impacts on these values are measureable. Keywords: Antarctica; Madrid Protocol; wilderness; aesthetic; values; photographs.
Keywords: Antarktis; Antarktistraktaten; estetikk; menneskelig påvirkning; miljøpåvirkning; miljøvern

Trampling on maritime Antarctica: can soil ecosystems be effectively protected through existing codes of conduct? - Tejedo, Pablo; Pertierra, Luis R; Benayas, Javier; Convey, Peter; Justel, Ana; Quesada, Antonio (Polar Research, 2012)
Soil trampling is one of the most obvious direct negative human impacts in Antarctica. Through a range of experiments and field studies based on quantitative physical (soil penetration resistance) and biological (collembolan abundance) indicators, we evaluate the current codes of conduct relating to the protection of Antarctic soils from the consequences of pedestrian impacts. These guidelines include using, where available, established paths that cross vegetation-free soils. However, the effectiveness of this strategy is highly dependent on context. Limited intensity use - below 100 foot passes per year - produces small changes at the soil surface that can recover relatively rapidly, suggesting that the dispersal of activity across wider corridors may be the most appropriate option. However, for paths with a higher use level and those located in steep-sloped sites, it is desirable to define a single track, following stony or bouldery surfaces wherever possible, to keep the disturbed area to a minimum. It is clear that both environmental conditions and expected use levels must be taken into account in determining when and where it is more appropriate to concentrate or disperse human activities. Even though they may have performed satisfactorily to date, the increasing pressure in terms of numbers of visits for certain sites may make it necessary to revise existing codes of conduct. Keywords: Trampling impacts; environmental monitoring; low impact practices; soil resilience; soil penetration resistance; collembolan abundance.
Keywords: Antarktis; jord; menneskelig påvirkning; miljøvern; økosystemer

Foreword: The complex business of managing human activities and protecting the environment of the polar regions - Tin, Tina; Liggett, Daniela; Maher, Patrick T (Polar Research, 2012)
The thematic cluster ‘‘Human impacts in the Arctic and Antarctic’’ in Polar Research has its origins in the International Polar Year (2007-09) Oslo Science Conference held in Oslo, Norway, from 8 to 12 June 2010. We were the co-convenors of the session ‘‘Human impacts in the Arctic and Antarctic: regulatory and management implications,’’ in which 27 talks and 21 posters were presented over the course of two days. We invited contributors to the conference session to explore all types of impacts of human activities and regional environmental change in the polar regions, with a special focus on highlighting the management priorities for the protection of the landscape (environment and people) of the polar regions in the face of increasing human activity. Exploring a wide range of topics ranging from human wildlife interactions to chemical contamination and from whaling to polar tourism, contributors provided examples of existing environmental management regimes that are working as well as those that are not.
Keywords: Antarktis; forurensning; menneskelig påvirkning; miljøvern; polarområdene; turisme; økosystemer

Chemical composition of tropospheric air masses encountered during high altitude flights (>11.5 km) during the 2009 fall Operation Ice Bridge field campaign - Yang, Mei Ying Melissa; Vay, Stephanie A; Stohl, Andreas; Choi, Yonghoon; Diskin, Glenn S; Sachse, Glen W; Blake, Donald R (Journal of Geophysical Research: Atmospheres, 2012)
As part of the 2009 Operation Ice Bridge campaign, the NASA DC-8 aircraft was used to fill the data-time gap in laser observation of the changes in ice sheets, glaciers and sea ice between ICESat-I (Ice, Cloud, and land Elevation Satellite) and ICESat-II. Complementing the cryospheric instrument payload were four in situ atmospheric sampling instruments integrated onboard to measure trace gas concentrations of CO2, CO, N2O, CH4, water vapor and various VOCs (Volatile Organic Compounds). This paper examines two plumes encountered at high altitude (12 km) during the campaign; one during a southbound transit flight (13°S) and the other at 86°S over Antarctica. The data presented are especially significant as the Southern Hemisphere is heavily under-sampled during the austral spring, with few if any high-resolution airborne observations of atmospheric gases made over Antarctica. Strong enhancements of CO, CH4, N2O, CHCl3, OCS, C2H6, C2H2 and C3H8 were observed in the two intercepted air masses that exhibited variations in VOC composition suggesting different sources. The transport model FLEXPART showed that the 13°S plume contained predominately biomass burning emissions originating from Southeast Asia and South Africa, while both anthropogenic and biomass burning emissions were observed at 86°S with South America and South Africa as indicated source regions. The data presented here show evidence that boundary layer pollution is transported from lower latitudes toward the upper troposphere above the South Pole, which may not have been observed in the past.
Keywords: Antarktis; atmosfæren; atmosfæriske gasser; forurensning; havis; innlandsis; isbreer; isbrem; kjemi; kjemiske analyser; menneskelig påvirkning; meteorologi; sjøis; sporgass

Variation of accumulation rates over the last eight centuries on the East Antarctic Plateau derived from volcanic signals in ice cores - Anschütz, Helgard; Sinisalo, Anna; Isaksson, Elisabeth; McConnell, Joseph R; Hamran, Svein Erik; Bisiaux, M M; Pasteris, Daniel R; Neumann, Thomas; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2011)
Volcanic signatures in ice-core records provide an excellent means to date the cores and obtain information about accumulation rates. From several ice cores it is thus possible to extract a spatio-temporal accumulation pattern. We show records of electrical conductivity and sulfur from 13 firn cores from the Norwegian-USA scientific traverse during the International Polar Year 2007–2009 (IPY) through East Antarctica. Major volcanic eruptions are identified and used to assess century-scale accumulation changes. The largest changes seem to occur in the most recent decades with accumulation over the period 1963–2007/08 being up to 25% different from the long-term record. There is no clear overall trend, some sites show an increase in accumulation over the period 1963 to present while others show a decrease. Almost all of the sites above 3200 m above sea level (asl) suggest a decrease. These sites also show a significantly lower accumulation value than large-scale assessments both for the period 1963 to present and for the long-term mean at the respective drill sites. The spatial accumulation distribution is influenced mainly by elevation and distance to the ocean (continentality), as expected. Ground-penetrating radar data around the drill sites show a spatial variability within 10–20% over several tens of kilometers, indicating that our drill sites are well representative for the area around them. Our results are important for large-scale assessments of Antarctic mass balance and model validation.
Keywords: Antarktis; akkumulasjon; geovitenskap; glasiologi; innlandsis; iskjerner; klimatologi

Implications of meltwater pulse events for soil biology and biogeochemical cycling in a polar desert - Ball, Becky A; Barrett, J E; Gooseff, Mike N; Virginia, Ross A; Wall, Diana H (Polar Research, 2011)
The McMurdo Dry Valleys are one of the most arid environments on Earth. Over the soil landscape for the majority of the year, biological and ecosystem processes in the dry valleys are constrained by the low temperatures and limited availability of water. The prevalence of these physical limitations in controlling biological and ecosystem processes makes the dry valleys a climatesensitive system, poised to experience substantial changes following projected future warming. Short-duration increases in summer temperatures are associated with pulses of water from melting ice reserves, including glaciers, snow and permafrost. Such pulses alter soil geochemistry by mobilizing and redistributing soil salts (via enhanced weathering, solubility and mobility), which can alter habitat suitability for soil organisms. Resulting changes in soil community composition or distribution may alter the biogeochemical processes in which they take part. Here, we review the potential impacts of meltwater pulses and present new field data documenting instances of meltwater pulse events that result from different water sources and hydrological patterns, and discuss their potential influence on soil biology and biogeochemistry. We use these examples to discuss the potential impacts of future climate change on the McMurdo Dry Valley soil ecosystem.Keywords: Water pulse; climate change; polar desert; International Polar Year; discrete warming events; soil biogeochemistry.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); IPY; biogeokjemi; biologi; jord; klimaendringer; polarørken

Some like it cold: microbial transformations of mercury in polar regions - Barkay, Tamar; Kroer, Niels; Poulain, Alexandre J (Polar Research, 2011)
The contamination of polar regions with mercury that is transported from lower latitudes as inorganic mercury has resulted in the accumulation of methylmercury (MeHg) in food chains, risking the health of humans and wildlife. While production of MeHg has been documented in polar marine and terrestrial environments, little is known about the responsible transformations and transport pathways and the processes that control them. We posit that as in temperate environments, microbial transformations play a key role in mercury geochemical cycling in polar regions by: (1) methylating mercury by one of four proposed pathways, some not previously described; (2) degrading MeHg by activities of mercury resistant and other bacteria; and (3) carrying out redox transformations that control the supply of the mercuric ion, the substrate of methylation reactions. Recent analyses have identified a high potential for mercury-resistant microbes that express the enzyme mercuric reductase to affect the production of gaseous elemental mercury when and where daylight is limited. The integration of microbially mediated processes in the paradigms that describe mercury geochemical cycling is therefore of high priority especially in light of concerns regarding the effect of global warming and permafrost thawing on input of MeHg to polar regions. Keywords: Microbiology; mercury biogeochemistry; redox transformations; polar regions; methylation
Keywords: Antarktis; biogeokjemi; forurensning; mikrobiologi; miljøvern; polarområdene; økosystemer

Review of Tourism and change in polar regions: climate, environment and experience and Cruise tourism in polar regions: promoting environmental and social sustainability? - Capelotti, P J (Polar Research, 2011)
These two edited volumes, which cover much of the same ground, both begin from a common premise: polar tourism, as its been experienced by wealthy travellers for over a century, has a very definite shelf life. With the acceleration of global climate change, the Arctic and Antarctic are being changed, changed rapidly, perhaps permanently and, if one pays attention to the news, seemingly by the day. When combined with popular documentaries and feature films like An inconvenient truth, March of the penguins and Happy feet potential polar tourists have been sensitized to see the polar regions not as implacably hostile wastes once challenged only by the likes of Nansen, Amundsen, Scott and Shackleton but as irreplaceably fragile zones that, once lost, will take some essential part of the planet with them.
Keywords: Antarktis; bokanmeldelser; cruiseturisme; global oppvarming; klimaendringer; miljøvern; polarområdene; turisme; økologi

Princess Elisabeth Antarctica: an International Polar Year outreach and media success story - Cheek, Joseph; Huyge, Ben; Pomereu, Jean de (Polar Research, 2011)
One of the priorities of the fourth International Polar Year (IPY) was to increase awareness of the polar regions and polar science among the general public through education, communication and other forms of outreach. This paper reports on the media coverage of Princess Elisabeth Antarctica (PEA), Belgium’s ‘‘zero-emission’’ Antarctic research station designed by the nonprofit International Polar Foundation (IPF) to run on wind and solar energy and to employ state-of-the-art forms of energy management and other ‘‘green’’ technology. This paper provides background information on PEA, a review of IPF’s media strategy for the project, a description of media coverage of the station and a discussion of the way in which the IPF’s main messages were reported in the media. IPF staff surveyed approximately 300 media reports released between February 2004, when the PEA project was announced to the general public, and June 2010, when the IPF presented their findings at the IPY conference in Oslo. PEA was featured 580 times in print and web media in Belgium, and 303 times outside Belgium. Major international agencies such as the Associated Press, Agence France Presse, the BBC, Al-Jazeera and Reuters covered the project. On television and radio, PEA was featured in news broadcasts from all four major television networks in Belgium, most major radio stations and 34 different television and radio news outlets outside Belgium. The paper concludes that the media coverage for PEA was significant and suggests reasons why the project was so widely reported. Keywords: Media and outreach; media strategy; Antarctic research stations; energy management system; renewable energy; reducing environmental footprint
Keywords: Antarktis; Det internasjonale polaråret; fornybar energi; forskningsstasjoner; fotavtrykk; mediadekning; miljø; polarområdene

Global southern limit of flowering plants and moss peat accumulation - Convey, Peter; Hopkins, David W; Roberts, Stephen J; Tyler, Andrew N (Polar Research, 2011)
The ecosystems of the western Antarctic Peninsula, experiencing amongst the most rapid trends of regional climate warming worldwide, are important “early warning” indicators for responses expected in more complex systems elsewhere. Central among responses attributed to this regional warming are widely reported population and range expansions of the two native Antarctic flowering plants, Deschampsia antarctica and Colobanthus quitensis. However, confirmation of the predictions of range expansion requires baseline knowledge of species distributions. We report a significant southwards and westwards extension of the known natural distributions of both plant species in this region, along with several range extensions in an unusual moss community, based on new survey work in a previously unexamined and un-named low altitude peninsula at 69º22.0’S 71º50.7’W in Lazarev Bay, north-west Alexander Island, southern Antarctic Peninsula. These plant species therefore have a significantly larger natural range in the Antarctic than previously thought. This site provides a potentially important monitoring location near the southern boundary of the region currently demonstrated to be under the influence of rapidly changing climate trends. Combined radiocarbon and lead isotope radiometric dating suggests that this location was most likely deglaciated sufficiently to allow peat to start accumulating towards the end of the 19th century, which we tentatively link to a phase of post-1870 climate amelioration. We conclude that the establishment of vegetation in this location is unlikely to be linked to the rapid regional warming trends recorded along the Antarctic Peninsula since the mid-20th century. Antarctic plants, distribution limits, peat accumulation, dating.
Keywords: Antarktis; hårgress; klimaendringer; perleurt; planter; økosystemer

Polythermal glacier hydrology: a review - Irvine-Fynn, Tristram D L; Hodson, Andrew J; Moorman, Brian J; Vatne, Geir; Hubbard, Alun L (Reviews of Geophysics, 2011)
The manner by which meltwater drains through a glacier is critical to ice dynamics, runoff characteristics, and water quality. However, much of the contemporary knowledge relating to glacier hydrology has been based upon, and conditioned by, understanding gleaned from temperate valley glaciers. Globally, a significant proportion of glaciers and ice sheets exhibit nontemperate thermal regimes. The recent, growing concern over the future response of polar glaciers and ice sheets to forecasts of a warming climate and lengthening summer melt season necessitates recognition of the hydrological processes in these nontemperate ice masses. It is therefore timely to present an accessible review of the scientific progress in glacial hydrology where nontemperate conditions are dominant. This review provides an appraisal of the glaciological literature from nontemperate glaciers, examining supraglacial, englacial, and subglacial environments in sequence and their role in hydrological processes within glacierized catchments. In particular, the variability and complexity in glacier thermal regimes are discussed, illustrating how a unified model of drainage architecture is likely to remain elusive due to structural controls on the presence of water. Cold ice near glacier surfaces may reduce meltwater flux into the glacier interior, but observations suggest that the transient thermal layer of near surface ice holds a hydrological role as a depth-limited aquifer. Englacial flowpaths may arise from the deep incision of supraglacial streams or the propagation of hydrofractures, forms which are readily able to handle varied meltwater discharge or act as locations for water storage, and result in spatially discrete delivery of water to the subglacial environment. The influence of such drainage routes on seasonal meltwater release is explored, with reference to summer season upwellings and winter icing formation. Moreover, clear analogies emerge between nontemperate valley glacier and ice sheet hydrology, the discussion of which indicates how persistent reassessment of our conceptualization of glacier drainage systems is required. There is a clear emphasis that continued, integrated endeavors focused on process glaciology at nontemperate glaciers are a scientific imperative to augmenting the existing body of research centered on ice mass hydrology.
Keywords: Antarktis; geografi; glasiologi; global oppvarming; hydrologi; innlandsis; isbreer; isbrem; polarområdene

Low-ozone events in the southern polar summer as indicated by Met Office ozone analyses - Jackson, David; Orsolini, Yvan Joseph; Engelsen, Ola (Journal of Geophysical Research: Atmospheres, 2011)
Southern summer low-ozone events (LOEs) are examined using Met Office ozone analyses for 2005–2007. At 31 hPa, tongues of low-ozone air are pulled out of the polar region and extend to lower latitudes. Low tongues are also seen at 100 hPa, but there the low ozone is transported from low to high latitudes. These low tongues are frequently superimposed on one another, meaning that there are often also reductions in total ozone. What is striking is that at high latitudes, summer total ozone is typically lower over the Weddell Sea than at other longitudes. The low-ozone tongues at 31 and 100 hPa are consistent with transport associated with planetary waves. Daily geopotential height fields show a poleward and westward wave tilt with height, indicating the presence of baroclinic waves. The tilt enables the superimposition of the low-ozone tongues at 100 and 31 hPa. Filtered geopotential height anomalies reveal the presence of waves reported in other studies and indicate the connection between tropospheric and stratospheric wave dynamics in driving the LOEs. There is also a high connection between the LOEs and ultraviolet (UV) Index. The Weddell Sea region gets up to 20–30% more UV than the zonal mean, and the tip of South America gets about 10–25% more. There have been numerous studies of the impacts of increased UV on the Antarctic marine ecosystem during the springtime ozone hole, and our results indicate there is a case for these studies being extended to the summer LOEs.
Keywords: Antarktis; UV-stråling; Weddellhavet; ozonlaget; polarområdene; stratosfæren; ultrafiolett stråling

The oldest plesiosaur (Reptilia, Sauropterygia) from Antarctica - Kellner, Alexander Wilhelm Armin; Simões, Tiago Rodrigues; Riff, Douglas; Grillo, Orlando; Romano, Pedro; Paula, Helder de; Ramos, Renato; Carvalho, Marcelo; Sayão, Juliana; Oliveira, Gustavo; Rodrigues, Taissa (Polar Research, 2011)
Antarctic plesiosaurs are known from the Upper Cretaceous López de Bertodano and Snow Hill Island formations (Campanian to upper Maastrichtian), which crop out within the James Ross Basin region of the Antarctic Peninsula. Here we describe the first plesiosaur fossils from the Lachman Crags Member of the Santa Marta Formation, north-western James Ross Island. This material constitutes the stratigraphically oldest plesiosaur occurrence presently known from Antarctica, extending the occurrence of plesiosaurians in this continent back to Santonian times (86.3-83.5 Mya). Furthermore, MN 7163-V represents the first plesiosaur from this region not referable to the Elasmosauridae nor Aristonectes, indicating a greater diversity of this group of aquatic reptiles in Antarctica than previously suspected. Keywords: James Ross Island; Antarctica; plesiosauria; Late Cretaceous; Museu Nacional.
Keywords: Antarktis; geologi; paleontologi; svaneøgler

Meteoritten som vitnet om liv på Mars - Knutsen, Henning; Matland, Aleksander (Naturen, 2011)
Har livet på Jorda blitt ført hit fra tidligere liv på planeten Mars? I 1996 hevdet en gruppe forskere at en meteoritt fra Mars faktisk inneholdt spor etter organisk liv. Hvis dette virkelig var tilfelle, ville det medføre en revolusjon for vårt syn på verden og det univers vi befinner oss i. Men vitenskapsfolk besitter sunn skepsis, og hos dem kommer ikke tvilen tiltalte til gode. Nå mener de fleste ekspertene at funnet var for godt til å være sant.
Keywords: Antarktis; astrofysikk; mikrobiologi

Recovery Lakes, East Antarctica: Radar assessment of sub-glacial water extent - Langley, Kirsty; Kohler, Jack; Matsuoka, Kenichi; Sinisalo, Anna; Scambos, Ted; Neumann, Thomas; Muto, Atsuhiro; Winther, Jan-Gunnar; Albert, Mary (Geophysical Research Letters, 2011)
A fast-flowing tributary of Recovery ice stream penetrates more than 500 km into the interior of East Antarctica. Recent satellite-based studies found surface features in the onset area of this tributary that indicate a significant subglacial hydraulic system, including four large smooth basins, the typical surface expression of large subglacial lakes, as well as eleven smaller areas over which ice-sheet surface elevations rapidly changed by discharge/filling of subglacial water. Here we present the first ice-penetrating radar evidence of subglacial conditions in this area. We identified a distinct ice-water interface only over a limited area within the boundaries of the investigated large smooth basins, previously hypothesized to be water-filled lakes. The radar characteristics in some areas are similar to those of a drained lake, indicating that parts of the bed are wet, but not a typical lake. We also find evidence for discrete water bodies outside of the lake boundaries. The lines of evidence indicate that the northern most two Recovery Lakes have recently drained.
Keywords: Antarktis; geofysikk; glasiologi; isbre; isstrøm; radar observasjoner; subglasial innsjø

A comparison of the present and last interglacial periods in six Antarctic ice cores - Masson-Delmotte, Valerie; Buiron, Daphné; Ekaykin, Alexey Anatolievich; Frezzotti, M; Gallée, Hubert; Jouzel, Jean; Krinner, Gerhard; Landais, Amaelle; Motoyama, Hideaki; Oerter, Hans; Pol, K; Pollard, D; et al. (Clim. Past, 2011)
We compare the present and last interglacial periods as recorded in Antarctic water stable isotope records now available at various temporal resolutions from six East Antarctic ice cores: Vostok, Taylor Dome, EPICA Dome C (EDC), EPICA Dronning Maud Land (EDML), Dome Fuji and the recent TALDICE ice core from Talos Dome. We first review the different modern site characteristics in terms of ice flow, meteorological conditions, precipitation intermittency and moisture origin, as depicted by meteorological data, atmospheric reanalyses and Lagrangian moisture source diagnostics. These different factors can indeed alter the relationships between temperature and water stable isotopes. Using five records with sufficient resolution on the EDC3 age scale, common features are quantified through principal component analyses. Consistent with instrumental records and atmospheric model results, the ice core data depict rather coherent and homogenous patterns in East Antarctica during the last two interglacials. Across the East Antarctic plateau, regional differences, with respect to the common East Antarctic signal, appear to have similar patterns during the current and last interglacials. We identify two abrupt shifts in isotopic records during the glacial inception at TALDICE and EDML, likely caused by regional sea ice expansion. These regional differences are discussed in terms of moisture origin and in terms of past changes in local elevation histories, which are compared to ice sheet model results. Our results suggest that elevation changes may contribute significantly to inter-site differences. These elevation changes may be underestimated by current ice sheet models.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; atmosfæren; glasiologi; iskjerner; klimatologi; meteorologi; stabile isotoper

Pitfalls in radar diagnosis of ice-sheet bed conditions: Lessons from englacial attenuation models - Matsuoka, Kenichi (Geophysical Research Letters, 2011)
Radar power returned from ice-sheet beds has been widely accepted as an indicator of bed conditions. However, the bed returned power also depends on englacial attenuation, which is primarily a function of ice temperature. Here, using a one-dimensional attenuation model, it is demonstrated that, in most cases, variations in bed returned power are dominated by variations in englacial attenuation, rather than bed reflectivity. Both accumulation rate and geothermal flux anomalies can interfere with the interpretation. With the consequence, analytical radar algorithms that have been widely accepted likely yield false delineations of wet/dry beds. More careful consideration is needed when diagnosing bed conditions. Spatial patterns of shallow englacial radar reflectors can be used as a proxy for accumulation rates, which affect ice temperature and thus returned power. I argue that it is necessary to simultaneously interpret the returned power and englacial-reflector patterns to improve the bed diagnosis.
Keywords: Antarktis; geotermisk strømning; glasiologi; innlandsis; istykkelse; overflateakkumulering; polarområdene

The present location of the tent that Roald Amundsen left behind at the South Pole in December 1911 - Orheim, Olav (Polar Record, 2011)
Determining the present precise location of Amundsen's tent is a function of 1) the precision of Amundsen's navigation in 1911, 2) the flow of ice since then, and 3) the amount of burial by intervening snow fall. These factors are discussed and it is concluded that the best location that can be given for the tent in December 2011 is 89° 58′ 51″ S, 46° 14′ E, and lying 17 m below the present snow surface. The uncertainty in the position is 0.3 km, and is mainly related to uncertainties in the original positioning. It can be concluded with high certainty that the tent lies between 1.8 and 2.5 km from the South Pole.
Keywords: Antarktis; ekspedisjoner; glasiologi; historie

Hva er en helt? Kjønn i antarktislitteraturen - Ryall, Anka (Fortid : historiestudentenes tidsskrift, UiO, 2011)
Menneskenes historie i Antarktis er ikke mer enn noen hundre år gammel. De viktigste kildene til denne historien er ekspedisjonsberetningene – en omfangsrik litteratur som kan leses på mange måter, også fra et kjønnsperspektiv.
Keywords: Antarktis; ekspedisjoner; litteratur; polarhistorie

Spatial modelling of wetness for the Antarctic Dry Valleys - Stichbury, Glen; Brabyn, Lars; Green, T G Allan; Cary, Craig (Polar Research, 2011)
This paper describes a method used to model relative wetness for part of the Antarctic Dry Valleys using Geographic Information Systems (GIS) and remote sensing. The model produces a relative index of liquid water availability using variables that influence the volume and distribution of water. Remote sensing using Moderate Resolution Imaging Spectroradiometer (MODIS) images collected over four years is used to calculate an average index of snow cover and this is combined with other water sources such as glaciers and lakes. This water source model is then used to weight a hydrological flow accumulation model that uses slope derived from Light Detection and Ranging (LIDAR) elevation data. The resulting wetness index is validated using three-dimensional visualization and a comparison with a high-resolution Advanced Land Observing Satellite image that shows drainage channels. This research demonstrates that it is possible to produce a wetness model of Antarctica using data that are becoming widely available. Keywords: GIS; water; Antarctica; remote sensing.
Keywords: Antarktis; geografi; hydrologi; innsjø; isbreer; satellitt bilder; snø; vann; økosystemer

Using transport diagnostics to understand chemistry climate model ozone simulations - Strahan, Susan; Douglass, A R; Stolarski, R S; Akiyoshi, Hideharu; Bekki, Slimane; Braesicke, P; Butchart, N; Chipperfield, Martyn; Cugnet, David; Dhomse, Sandip; Frith, Stacey; Gettelman, Andrew; et al. (Journal of Geophysical Research: Atmospheres, 2011)
We use observations of N2O and mean age to identify realistic transport in models in order to explain their ozone predictions. The results are applied to 15 chemistry climate models (CCMs) participating in the 2010 World Meteorological Organization ozone assessment. Comparison of the observed and simulated N2O, mean age and their compact correlation identifies models with fast or slow circulations and reveals details of model ascent and tropical isolation. This process-oriented diagnostic is more useful than mean age alone because it identifies models with compensating transport deficiencies that produce fortuitous agreement with mean age. The diagnosed model transport behavior is related to a model's ability to produce realistic lower stratosphere (LS) O3 profiles. Models with the greatest tropical transport problems compare poorly with O3 observations. Models with the most realistic LS transport agree more closely with LS observations and each other. We incorporate the results of the chemistry evaluations in the Stratospheric Processes and their Role in Climate (SPARC) CCMVal Report to explain the range of CCM predictions for the return-to-1980 dates for global (60°S–60°N) and Antarctic column ozone. Antarctic O3 return dates are generally correlated with vortex Cly levels, and vortex Cly is generally correlated with the model's circulation, although model Cl chemistry and conservation problems also have a significant effect on return date. In both regions, models with good LS transport and chemistry produce a smaller range of predictions for the return-to-1980 ozone values. This study suggests that the current range of predicted return dates is unnecessarily broad due to identifiable model deficiencies.
Keywords: Antarktis; drivhusgasser; fysikk; geovitenskap; klimamodeller; meteorologi; ozonlaget; stratosfæren

Amundsens omstridte forløper ; Innsjøen under isen - Thuesen, Nils Petter (Vi menn vitenskap & historie, 2011)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Vostoksjøen; ekspedisjoner; glasiologi; subglasial innsjø

Colonization and demographic structure of Deschampsia antarctica and Colobanthus quitensis along an altitudinal gradient on Livingston Island, South Shetland Islands, Antarctica - Vera, María Luisa (Polar Research, 2011)
The colonization capacity and demographic structure of populations of Deschampsia antarctica and Colobanthus quitensis were studied in different microhabitats between 10 and 147 m a.s.l. on Livingston Island, South Shetland Islands, near the Spanish Antarctic base Juan Carlos I, in February 2002. At the highest site (147 m a.s.l.), mean temperatures were about 1 ºC lower than at sea level. Both species are less common in inland areas and at the highest altitudes only occur at restricted sites that are frequently snow-free in the early austral summer. The diameters of the largest plants (C. quitensis cushions 7-8 cm ; D. antarctica tufts 10-11 cm) in the populations growing at the highest altitudes (110 and 147 m a.s.l.) suggest that these populations were established about 24-28 years ago. The largest diameter plants (Deschampsia 20 cm; Colobanthus 18 cm) were found at the lowest altitudes on deep soil. The presence of numerous seedlings and young individuals on the periphery of populations established several years ago or at recently colonized sites suggests an active process of expansion. There were more emerged seedlings of C. quitensis than of D. antarctica, but the density of established individuals was higher for D. antarctica, suggesting these species have different demographic strategies. Keywords: Antarctic vascular plants; altitude and habitat effect; colonization; population structure.
Keywords: Antarktis; biologi; flora; planter

Mesospheric wind semidiurnal tides within the Canadian Middle Atmosphere Model Data Assimilation System - Xu, Xiaoyong; Manson, Alan H; Meek, Christopher; Jacobi, Christoph; Hall, Chris; Drummond, James (Journal of Geophysical Research: Atmospheres, 2011)
The horizontal wind data from the standard version of Canadian Middle Atmosphere Model Data Assimilation System (CMAM-DAS) for the years 2006–2008 are analyzed to obtain the global structure and seasonal variability of the semidiurnal tide (SDT) in the mesosphere. The modeled amplitudes and phases of the SDTs at single stations from middle/high northern latitudes are quite similar to those observed by radars. The primary nonmigrating tides identified in both the meridional wind and zonal wind semidiurnal spectra at 88 km include the westward propagating wave numbers s = 1 (SW1), 3 (SW3), 4 (SW4), 6 (SW6), the standing s = 0 (S0), and the eastward propagating s = 2 (SE2). The migrating SDT (SW2) amplitude maxima usually occur at 40°N–60°N during December–February and August–September, and also at 40°S–60°S in April–May, with the dominance of (2, 4) during October–April and (2, 3) and (2, 5) dominance for other months. The CMAM-DAS is quite successful in reproducing the dominance of SW1 in the Antarctic summer mesosphere. The modeled SW1 shows very good overall agreement in both amplitude and phase with wind measurements from UARS High Resolution Doppler Imager and Wind Imaging Interferometer (UARS-HRDI/WINDII) and from TIMED Doppler Interferometer (TIDI). The CMAM-DAS analyses for SW3, SW4, SW6, and S0 are also in reasonable agreement with those determined from the HRDI/WINDII or TIDI wind measurements. This work provides further evidence for the tidal forcing from below.
Keywords: Antarktis; atmosfæren; atmosfærisk tidevann; geofysikk; meteorologi

The intraseasonal variability of winter semester surface air temperature in Antarctica - Yu, Lejiang; Zhang, Zhanhai; Zhou, Mingyu; Zhong, Shiyuan; Sun, Bo; Hsu, Hsiaoming; Gao, Zhiqiu; Wu, Huiding; Ban, Junmei (Polar Research, 2011)
This study investigates systematically the intraseasonal variability of surface air temperature over Antarctica by applying empirical orthogonal function (EOF) analysis to the National Centers for Environmental Prediction, US Department of Energy, Reanalysis 2 data set for the period of 1979 through 2007. The results reveal the existence of two major intraseasonal oscillations of surface temperature with periods of 26 - 30 days and 14 days during the Antarctic winter season in the region south of 60°S. The first EOF mode shows a nearly uniform spatial pattern in Antarctica and the Southern Ocean associated with the Antarctic Oscillation. The mode-1 intraseasonal variability of the surface temperature leads that of upper atmosphere by one day with the largest correlation at 300-hPa level geopotential heights. The intraseasonal variability of the mode-1 EOF is closely related to the variations of surface net longwave radiation the total cloud cover over Antarctica. The other major EOF modes reveal the existence of eastward propagating phases over the Southern Ocean and marginal region in Antarctica. The leading two propagating modes respond to Pacific-South American modes. Meridional winds induced by the wave train from the tropics have a direct influence on the surface air temperature over the Southern Ocean and the marginal region of the Antarctic continent. Keywords: Antarctic climate, surface air temperature, intraseasonal variability, Antarctic Oscillation.
Keywords: Antarktis; forskning; klima; lufttemperatur

East Antarctic snow accumulation changes - Anschütz, Helgard; Isaksson, Elisabeth; Müller, Karsten; Winther, Jan-Gunnar; Albert, Mary (Ice and climate news, 2010)
Keywords: Antarktis; glasiologi

Patterns of variation of serum oxidative stress markers in two seabird species - Costantini, David; Bonadonna, Francesco (Polar Research, 2010)
Variation in oxidative stress markers in natural populations may provide a useful background for understanding variation in life history strategies. In this study, we seek to evaluate patterns of variation in levels of reactive oxygen metabolites (markers of oxidative damage), serum antioxidant capacity, and serum concentration of thiols (antioxidants endogenously synthesized) in nestling and breeding blue petrels (Halobaena caerulea) and in breeding Antarctic prions (Pachyptila desolata). Male and female prions and nestling petrels did not differ in any of the oxidative stress markers. The serum antioxidant capacity positively correlated with the sample time in nestling blue petrels. Breeding petrels with higher body condition index had higher serum antioxidant capacity and circulating thiols. Finally, both seabird species showed lower levels of reactive oxygen metabolites and higher levels of serum antioxidant capacity than previously studied bird species.
Keywords: Antarktis; marin biologi; ornitologi; petreller; reproduksjon; sjøfugler; zoologi; økologi

Holocene Antarctic climate variability from ice and marine sediment cores: insights on ocean-atmosphere interaction - Divine, Dmitry; Koç, Nalân; Isaksson, Elisabeth; Nielsen, Simon H; Crosta, Xavier; Godtliebsen, Fred (Quaternary Science Reviews, 2010)
Holocene climate variability in the southeast Atlantic sector of the Southern Ocean and Antarctic is assessed and quantified through integration of available marine sediment core and Antarctic ice core data. We use summer sea surface temperature (SSST) and sea ice presence (SIP) reconstructions from two marine sediment cores recovered north (50 °S) and south (53.2 °S) of the present day Antarctic Polar Front (APF), as well as an atmospheric temperature and sea ice proxy from the EPICA ice core from Dronning Maud Land (EDML). We find reasonably good agreement in the timing of climate evolution in the analyzed series. Almost all records show a gradual glacial-to-Holocene climate transition, interrupted by the Antarctic cold reversal around 13 000 cal yr BP, and early Holocene climatic optimum (HCO) at about 11 000 cal yr BP. During the early HCO, the seasonal ice cover retreats to south of 53 °S; it then readvances in the course of the mid- to late Holocene. The maximum winter sea ice edge position during the recent 10 000 years varied mainly within 51–53 °S, with sporadic growth to north of 50 °S, a position similar to that during the last glacial. The onset of the Neoglacial period after ca 4000 yr BP is associated with a steepening of the SSST gradient between the marine core sites, strengthening of the westerlies and cooling in the inland ice sheet. The agreement in timing between elevated SSST during the early HCO and decreased deuterium excess in EDML and other ice cores from different locations in the East Antarctic suggests that the retreat of sea ice during the early HCO and weakening of the APF was a general feature of the East Antarctic climate during that time.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; glasiologi; holocene; iskjerner; klimaendringer; oseanografi; paleoklimatologi

Guest editorial—the 1959 Antarctic Treaty: reflecting on the 50th anniversary of a landmark agreement - Dodds, Klaus (Polar Research, 2010)
Commemorating a particular anniversary is always an arbitrary affair, an act of whimsy. After all, why acknowledge the 50th anniversary of someone or some event as opposed to the 48th? In terms of birthdays, we tend to celebrate each year as another rite of human passage. However, when it comes to events such as wars and diplomatic encounters, the media and political commentators like more substantial blocks of time: 10th, 25th, 50th, 75th and 100th anniversaries are particularly noteworthy. The year 2009 has proven no different in terms of representing a temporal marker for the 50th anniversary of the signing of the 1959 Antarctic Treaty. In December 2009 a so-called Antarctic Treaty Summit was held in Washington, D.C. to take advantage of not only such a milestone, but also “to highlight lessons learned about international governance ‘with the interests of science and the progress of all mankind’ ” (Antarctic Treaty Summit 2009, emphasis added).
Keywords: Antarktis; Antarktistraktaten; historie; internasjonal samarbeid; politikk

Review of Legacies and change in polar sciences: historical, legal and political reflections on the International Polar Year, edited by JM Shadian & M Tennberg - Dodds, Klaus (Polar Research, 2010)
The International Polar Year (IPY) of 2007–09 was an international scientific enterprise that encompassed all polar regions, and built on the legacies bequeathed by earlier endeavours stretching back to the late 19th century. The first such venture was initiated in 1882–83, the second was in 1932–33 and the last, the International Geophysical Year (IGY), occurred in 1957–58, and involved thousands of scientists working inter alia in the polar continent. Activity in the Arctic, for geopolitical reasons, was rather more limited, and was certainly not epitomized by free and unfettered scientific investigation. Sponsored by the International Council for Science, the most recent IPY was noteworthy for its explicit bi-polar focus, and its integration of the humanities and social sciences with the physical and environmental sciences. The role of indigenous communities was also notable in Arctic-based projects, a development that would have been inconceivable during the IGY. As with the IGY, however, a spectacular event in one of the theatres of scientific interest grabbed world headlines: in 1957 it was Sputnik orbiting the Earth, and in 2007 it was a Russian submersible planting a flag on the bottom of the central Arctic Ocean basin.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); bokanmeldelser; forskning; geopolitikk; internasjonal; polarområdene; samarbeid; vitenskap

A New Approach for Exploring Ice Sheets and Sub-Ice Geology - Eisen, Olaf; Hofstede, Coen; Miller, Heinrich; Kristoffersen, Yngve; Blenkner, Rick; Lambrecht, Astrid; Mayer, Christoph (Eos Transactions American Geophysical Union, 2010)
Keywords: Antarktis; geofysikk; geologi; innlandsis; seismologi

Neogene biochronology of Antarctic diatoms: A comparison between two quantitative approaches, CONOP and UAgraph - Galster, Federico; Guex, Jean; Hammer, Oyvind (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
A quantitative biochronological study by Cody et al. (2008) integrates comprehensive diatom biostratigraphy, magnetostratigraphy, and tephrostratigraphy from 32 Neogene sections around the Southern Ocean and Antarctic continental margin. A recent method, known as Constrained Optimization (CONOP), which can be viewed as a multidimensional version of graphic correlation, is applied to that very interesting database. The goal of the present paper is to discuss some theoretical aspects of quantitative biochronology and to compare the constrained optimization with the deterministic method called Unitary Associations (UAM), a graph theoretical model. We illustrate the fact that the UAM is an extremely powerful and unique theory allowing an in-depth analysis of the internal conflicting inter-taxon stratigraphic relationships, inherent to any complex biostratigraphical database.
Keywords: Antarktis; Sørishavet; biokronologi; diatomeer; paleogeografi; paleoklimatologi; paleontologi; paleoøkologi

Polarskipet Antarctics stolte historie. Del 2 - Goldberg, Fred (Polarboken, 2010)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; logistikk

Evaluating CERES angular distribution models for snow using surface reflectance observations from the East Antarctic Plateau - Hudson, Stephen R; Kato, Seiji; Warren, Stephen G (Journal of Geophysical Research: Atmospheres, 2010)
Clouds and the Earth's radiant energy system (CERES) is a satellite-based remote sensing system designed to monitor the Earth's radiation budget. In this paper we examine uncertainties in the angular distribution models (ADMs) used by CERES over permanently snow covered surfaces with clear skies. These ADMs are a key part of the CERES data processing algorithms, used to convert the observed upwelling radiance to an estimate of the upwelling hemispheric flux. We model top-of-atmosphere anisotropic reflectance factors using an atmospheric radiative transfer model with a lower boundary condition based on extensive reflectance observations made at Dome C, Antarctica. The model results and subsequent analysis show that the CERES operational clear-sky permanent-snow ADMs are appropriate for use over Dome C, with differences of less than 5% between the model results and the ADMs at most geometries used by CERES operationally. We show that the uncertainty introduced into the flux estimates through the use of the modeled radiances used in the ADM development is small when the fluxes are averaged over time and space. Finally, we show that variations in the angular distribution of radiance at the top of the atmosphere due to atmospheric variability over permanently snow covered regions are in most cases unlikely to mask the real variations in flux caused by these atmospheric variations.
Keywords: Antarktis; atmosfæren; fjernmåling; klima; meteorologi; observasjoner; snø; solstråling

A comparison of shortwave reflectance over the East Antarctic Plateau observed by CERES to that estimated from surface reflectance observations - Hudson, Stephen R; Warren, Stephen G; Kato, Seiji (Journal of Geophysical Research: Atmospheres, 2010)
Spectral albedo and bidirectional reflectance of snow were measured at Dome C on the East Antarctic Plateau for wavelengths of 350–2400 nm and solar zenith angles of 52°–87°. A parameterization of bidirectional reflectance, based on those measurements, is used as the lower boundary condition in the atmospheric radiation model SBDART to calculate radiance and flux at the top of the atmosphere (TOA). The model's atmospheric profile is based on radiosoundings at Dome C and ozonesoundings at the South Pole. Computed TOA radiances are integrated over wavelength for comparison with the Clouds and the Earth's Radiant Energy System (CERES) shortwave channel. CERES radiance observations and flux estimates from four clear days in January 2004 and January 2005 from within 200 km of Dome C are compared with the TOA radiances and fluxes computed for the same solar zenith angle and viewing geometry, providing 11,000 comparisons. The measured radiance and flux are lower than the computed values. The median difference is about 7% for CERES on Terra, and 9% on Aqua. Sources of uncertainty in the model and observations are examined in detail and suggest that the measured values should be less than the computed values, but only by 1.7% ± 4%. The source of the discrepancy of about 6% cannot be identified here; however, the modeled values do agree with observations from another satellite instrument (Multiangle Imaging Spectroradiometer), suggesting that the CERES calibration must be considered a possible source of the discrepancy.
Keywords: Antarktis; atmosfæren; fjernmåling; meteorologi; observasjoner; solstråling

Heat conservation during cold exposure in birds (vasomotor and respiratory implications) - Johansen, Kjell; Bech, Claus (Polar Research, 2010)
The mechanisms by :vhich peripheral circulation and respiration serve in maintaining thermal homeostasis in birds living in cold climates are reviewed. Three types of arteriovenous heat exchanger (an elaborate rete, asimple rete, and a venue comirantes system) are found in the legs of birds. The anatomical differences between the different types of A-V associations are described, and the regulation of peripheral blood flow, in respect to maximal heat conservation and prevention of tissue damage, is discussed. A nasal temporal counter current heat exchanger, lowering the temperature of the expired air to values considerably below the body temperature, is the most important mechanism for minimizing the respiratory heat and water loss. In addition, a decreased ventilatory requirement, caused by a changed respiratory pattern and an increased parabronchial oxygen extraction, lowers the amount of air ventilated relative to the amount of oxygen uptake. Thus, the relative loss of heat and water is reduced.
Keywords: Antarktis; fugler; kuldeeksponering; kuldetoleranse; ornitologi; zoofysiologi; zoologi

Antarctic clouds - Lachlan-Cope, Tom (Polar Research, 2010)
Sensitivity studies with global climate models show that, by their influence on the radiation balance, Antarctic clouds play a major role in the climate system, both directly at high southern latitudes and indirectly globally, as the local circulation changes lead to global teleconnections. Unfortunately, observations of cloud distribution in the Antarctic are limited and often of low quality because of the practical difficulty in observing clouds in the harsh Antarctic environment. The best surface observations suggest that the fractional cloud cover at the South Pole is around 50–60% in all seasons, whereas the cloud cover rises to around 80–90% close to the coast of the continent. Microphysical observations of cloud parameters are also very sparse in the Antarctic. However, the few measurements that do exist show predominantly ice-crystal clouds across the interior, with mixed-phase clouds close to the coasts. Crystal sizes vary from 5 to 30 mm (effective radius) in the interior to somewhat larger ice crystals and water drops near the coast. A wide range of crystal shapes is observed at all sites. This review considers the available cloud observations and highlights the importance of Antarctic clouds and the need for better observations in the future.
Keywords: Antarktis; klimatologi; meteorologi; observasjoner; satellitt bilder; skyer

An 860 km surface mass-balance profile on the East Antarctic plateau derived by GPR - Müller, Karsten; Sinisalo, Anna; Anschütz, Helgard; Hamran, Svein-Erik; Hagen, Jon-Ove; McConnell, Joseph R; Pasteris, Daniel R (Annals of Glaciology, 2010)
Snow accumulation and its variability on the East Antarctic plateau are poorly understood due to sparse and regionally confined measurements. We present a 5.3 GHz (C-band) ground-penetrating radar (GPR) profile with a total length of 860 km recovered during the joint Norwegian–US International Polar Year traverse 2007/08. Mean surface mass balance (SMB) over the last 200 years was derived from the GPR data by identifying the volcanic deposition of the Tambora eruption in 1815. It varies between 9.1 and 37.7 kg m−2 a−1 over the profile, with a mean of 23.7 kg m−2 a−1 and a standard deviation of 4.7 kg m−2 a−1. The 200 year SMB estimated is significantly lower than most of the SMB estimates over shorter time periods in this region. This can be partly explained by a SMB minimum in the vicinity of the ice divide. However, it is more likely that a recent increase in SMB observed by several studies is largely responsible for the observed discrepancy.
Keywords: Antarktis; Dronning Maud Land; glasiologi

Glacier advance in southern middle-latitudes during the Antarctic Cold Reversal - Putnam, Aaron E.; Denton, George H.; Schaefer, Joerg M.; Barrell, David J. A.; Andersen, Bjørn G.; Finkel, Robert C.; Schwartz, Roseanne; Doughty, Alice M.; Kaplan, Michael R.; Schlüchter, Christian (Nature Geoscience, 2010)
The geographic extent of cooling associated with the Antarctic Cold Reversal is unclear. Dating of glacial moraines in New Zealand suggests that the cooling extended into the southern mid-latitudes, possibly as a result of the northward migration of the southern subtropical front.
Keywords: Antarktis; deglasiasjon; holocene; kryosfæren; paleoglasiologi; paleoklimatologi

Land and sea-ice properties in Antarctica: bridging the gap between the ground and satellite measurements in the western Ross Sea region - Rack, Wolfgang; Langhorne, Pat; Haas, Christian; Clavano, Wendy; Gough, Alex; Kruetzmann, Nikolai; Pinchin, James; Riger-Kusk, Mette (Ice and climate news, 2010)
Keywords: Antarktis; Sørishavet; glasiologi; havis; isshelf

Antarktistraktatens effekt på norsk politikk 1959-2009: fra polarimperium på sparebluss til nye utfordringer - og ny giv? - Skagestad, Odd Gunnar (Norsk militært tidsskrift, 2010)
Keywords: Antarktis; politikk

Characteristics of atmospheric transport into the Antarctic troposphere - Stohl, Andreas; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2010)
We have developed a 5.5 year climatology of atmospheric transport into the Antarctic troposphere, which uses the same data set and methods as described in a recent study for the Arctic. This allows direct comparisons of transport properties for the two polar regions. The climatology is based on a simulation with the Lagrangian particle dispersion model FLEXPART, where the model atmosphere was globally filled with particles. Transport characteristics as well as emission sensitivities were derived from 6 hourly particle positions. We found that the probability for near-surface air to originate from the stratosphere on a time scale of 10 days is an order of magnitude higher near the South Pole than near the North Pole, a result of higher topography and descent that partly compensates for the flow of air down the Antarctic Plateau with the katabatic winds. The stratospheric influence is largest in fall, which is opposite to the seasonality in the Arctic. Stratospheric influence is much smaller over the shelf ice regions and in a band around Antarctica. The average time for which air near the surface has been exposed to continuous darkness in July (continuous light in January) is longest over the Ronne Ice Shelf and Ross Ice Shelf at ∼11 days (20 days). We calculated how sensitive Antarctic air masses are to emission input up to 30 days before arriving in Antarctica if removal processes are ignored. The emission sensitivity shows strong meridional gradients and, as a result, is generally low over South America, Africa, and Australia. For a 10 day time scale, the largest emission sensitivities over these continents are 1–2 orders of magnitude smaller than over Eurasia for transport to the Arctic, showing that foreign continents have a much smaller potential to pollute the Antarctic than the Arctic troposphere. Emission sensitivities and derived black carbon (BC) source contributions over South America, Africa, and Australia are substantially (a factor 10 for Africa) larger in winter than in summer. In winter, biomass burning contributes more BC than anthropogenic sources. For typical aerosol lifetimes of 5–10 days, ship emissions south of 60°S account for half of the total BC concentrations in the lowest 1000 m of the atmosphere south of 70°S in December. The increasing number of tourists visiting Antarctica and fishing vessels operating close to Antarctica are, therefore, a matter of concern.
Keywords: Antarktis; cruiseturisme; forurensning; klimatologi; polarområdene; stratosfæren; utslipp

A consistent data set of Antarctic ice sheet topography, cavity geometry, and global bathymetry - Timmermann, Ralph; Le Brocq, Anne M; Deen, Tara J; Domack, Eugene W; Dutrieux, Pierre; Galton-Fenzi, Benjamin K; Hellmer, Hartmut H; Humbert, Angelika; Jansen, Daniela; Jenkins, Adrian; Lambrecht, Astrid; Makinson, Keith; et al. (Earth Syst. Sci. Data, 2010)
Sub-ice shelf circulation and freezing/melting rates in ocean general circulation models depend critically on an accurate and consistent representation of cavity geometry. Existing global or pan-Antarctic data sets have turned out to contain various inconsistencies and inaccuracies. The goal of this work is to compile in- dependent regional fields into a global data set. We use the S-2004 global 1-minute bathymetry as the backbone and add an improved version of the BEDMAP topography (ALBMAP bedrock topography) for an area that roughly coincides with the Antarctic continental shelf. The position of the merging line is individually chosen in different sectors in order to get the best out of each data set. High resolution gridded data for upper and lower ice surface topographies and cavity geometry of the Amery, Fimbul, Filchner-Ronne, Larsen C and George VI Ice Shelves, and for Pine Island Glacier are carefully merged into the ambient ice and ocean topographies. Multibeam survey data for bathymetry in the former Larsen B cavity and the southeastern Bellingshausen Sea have been obtained from the data centers of Alfred Wegener Institute (AWI), British Antarctic Survey (BAS) and Lamont-Doherty Earth Observatory (LDEO), gridded, and blended into the existing bathymetry map. The resulting global 1-minute topography data set (RTopo-1) contains maps for upper and lower ice surface heights, bedrock bathymetry, and consistent masks for open ocean, grounded ice, floating ice, and bare land surface.
Keywords: Antarktis; Sørishavet; batymetri; glasiologi; havbunnen; topografi

Biogeochemical weathering under ice: Size matters - Wadham, Jemma L; Tranter, Martyn; Skidmore, Mark; Hodson, Andy; Priscu, John C; Lyons, W Berry; Sharp, Martin; Wynn, Peter; Jackson, Miriam (Global Biogeochemical Cycles, 2010)
The basal regions of continental ice sheets are gaps in our current understanding of the Earth's biosphere and biogeochemical cycles. We draw on existing and new chemical data sets for subglacial meltwaters to provide the first comprehensive assessment of sub-ice sheet biogeochemical weathering. We show that size of the ice mass is a critical control on the balance of chemical weathering processes and that microbial activity is ubiquitous in driving dissolution. Carbonate dissolution fueled by sulfide oxidation and microbial CO2 dominate beneath small valley glaciers. Prolonged meltwater residence times and greater isolation characteristic of ice sheets lead to the development of anoxia and enhanced silicate dissolution due to calcite saturation. We show that sub-ice sheet environments are highly geochemically reactive and should be considered in regional and global solute budgets. For example, calculated solute fluxes from Antarctica (72–130 t yr−1) are the same order of magnitude as those from some of the world's largest rivers and rates of chemical weathering (10–17 t km−2 yr−1) are high for the annual specific discharge (2.3–4.1 × 10−3 m). Our model of chemical weathering dynamics provides important information on subglacial biodiversity and global biogeochemical cycles and may be used to design strategies for the first sampling of Antarctic Subglacial Lakes and other sub-ice sheet environments for the next decade.
Keywords: Antarktis; biogeokjemi; biosfære; brehylle; glasiologi; innlandsis; isbrem; isshelf; subglasial biodiversitet; subglasial innsjø

Seismic and radar investigations of Fourcade Glacier on King George Island, Antarctica - Young Kim, Ki; Lee, Joohan; Ho Hong, Myung; Kuk Hong, Jong; Keun Jin, Young; Shon, Howong (Polar Research, 2010)
To determine P- and S-wave velocities, elastic properties and subglacial topography of the polythermal Fourcade Glacier, surface seismic and radar surveys were conducted along a 470-m profile in November 2006. P- and S-wave velocity structures were determined by travel-time tomography and inversion of Rayleigh wave dispersion curves, respectively. The average P- and S-wave velocities of ice are 3466 and 1839 m s-1, respectively. Radar velocities were obtained by migration velocity analysis of 112 diffraction events. An estimate of 920 kg m-3 for the bulk density of wet ice corresponds to water contents of 5.1 and 3.2%, which were derived from the average P-wave and radar velocities, respectively. Using this density and the average P- and S-wave velocities, we estimate that the corresponding incompressibility and rigidity of the ice are 6.925 and 3.119 GPa, respectively. Synergistic interpretation of the radar profile and P- and S-wave velocities indicates the presence of a fracture zone above a subglacial high. Here, the P- and S-wave velocities are approximately 5 and 3% less than in the ice above a subglacial valley, respectively. The S-wave velocities indicate that warmer and less rigid ice underlies 10–15 m of colder ice near the surface of the glacier. Such layering is characteristic of polythermal glaciers. As a relatively simple non-invasive approach, integration of P-wave tomography, Rayleigh wave inversion and ground-towed radar is effective for various glaciological studies, including the elastic properties of englacial and subglacial materials, cold/warm ice interfaces, topography of a glacier bed and location of fracture zones.
Keywords: Antarktis; geofysikk; glasiologi; isbre; radarundersøkelse; seismisk undersøkelse; subglasial; tomografi; topografi

Isostatic stability of the East Antarctic station Dumont d’Urville from long-term geodetic observations and geophysical models - Amalvict, Martine; Willis, Pascal; Wöppelmann, Guy; Ivins, Erik R.; Bouin, Marie-Noëlle; Testut, Laurent; Hinderer, Jacques (Polar Research, 2009)
Geodetic measurements of the vertical crustal displacement collocated with absolute gravity changes provide a discriminatory measurement of present-day glacial changes, versus more deeply seated rock motions caused by glacial isostatic adjustment (GIA). At the East Antarctic station of Dumont d’Urville, we compare the displacements derived from continuous DORIS (1993.0– 2006.0) and Global Positioning System (GPS) (1999.0–2005.7) data, and observed changes in absolute gravity (2000–2006), with the predicted vertical displacement and change in gravity from GIA modelling. The geodetic results have mutual self-consistency, suggest station stability and provide upper bounds on both GIA and secular ice mass changes. The GIA models tend to predict amplitudes of rock motion larger than those observed, and we conclude that this part of Antarctica is probably experiencing a slight gain in ice mass, in contrast to West Antarctica.
Keywords: Antarktis; breendringer; geodesi; geofysikk; innlandsis; tidevannsmålinger

East Antarctic snow accumulation changes - Anschütz, Helgard; Isaksson, Elisabeth; Winther, Jan-Gunnar; Müller, Karsten; Albert, Mary (Polar Research in Tromsø, 2009)
Keywords: Antarktis; glasiologi

Ice-ocean processes over the continental shelf of the southern Weddell Sea, Antarctica: A review - Nicholls, Keith W.; Østerhus, Svein; Makinson, Keith; Gammelsrød, Tor; Fahrbach, Eberhard (Reviews of Geophysics, 2009)
Interactions between the Southern Ocean and the Weddell Sea ice shelves are important both to the Antarctic Ice Sheet and to the production of globally significant water masses. Here we review the interaction between the Filchner-Ronne Ice Shelf and the shelf sea in which it floats. The continental shelf processes leading to the production of Weddell Sea deep and bottom waters from the original off-shelf source waters are discussed, and a new view is offered of the initial production of High-Salinity Shelf Water. Data from ship-based measurements at the ice front, from glaciological methods, and from measurements made within the sub–ice shelf cavity itself are used to describe the pattern of flows beneath the ice shelf. We also consider the variability observed within the cavity from tidal to interannual time scales and finish with a discussion of future research priorities in the region.
Keywords: AABW; Antarktis; Sørishavet; Weddellhavet; glasiologi; innlandsis; isfront; isshelf; oseanografi; vannmasser

Forutsetninger for Antarktistraktaten: hva var Norges linje? - Skagestad, Odd Gunnar (Norsk militært tidsskrift, 2009)
Keywords: Antarktis; politikk

Suverenitet, jurisdiksjon og samarbeid: Antarktistraktaten – forutsetninger og innhold - Skagestad, Odd Gunnar (Norsk statsvitenskapelig tidsskrift, 2009)
Keywords: Antarktis; jus; politikk

Asymmetries in the moisture origin of Antarctic precipitation - Sodemann, Harald; Stohl, Andreas (Geophysical Research Letters, 2009)
The seasonality of moisture sources for precipitation in Antarctica is studied with a Lagrangian moisture source diagnostic. Moisture origin for precipitation in Antarctica has strongly asymmetric properties, which are related to the Antarctic topography, seasonal sea ice coverage, and the land/ocean contrasts in the mid-latitudes of the southern hemisphere. The highest altitudes of the East Antarctic ice shield, where major ice cores have been drilled, have mean source latitudes of 45–40°S year-round. This finding contrasts to results from previous Lagrangian studies which detected a more southerly moisture origin due to too short trajectories. Now, results from Lagrangian moisture source diagnostics are consistent with findings from general circulation models with tagged tracers. Thus, both approaches can serve as a common benchmark for the interpretation of moisture source indicators based on stable isotopes, such as deuterium excess, in Antarctic ice cores.
Keywords: Antarktis; klimatologi; meteorologi; nedbør

Contrasting climate change in the two polar regions - Turner, John; Overland, Jim (Polar Research, 2009)
The two polar regions have experienced remarkably different climatic changes in recent decades. The Arctic has seen a marked reduction in sea-ice extent throughout the year, with a peak during the autumn. A new record minimum extent occurred in 2007, which was 40% below the long-term climatological mean. In contrast, the extent of Antarctic sea ice has increased, with the greatest growth being in the autumn. There has been a large-scale warming across much of the Arctic, with a resultant loss of permafrost and a reduction in snow cover. The bulk of the Antarctic has experienced little change in surface temperature over the last 50 years, although a slight cooling has been evident around the coast of East Antarctica since about 1980, and recent research has pointed to a warming across West Antarctica. The exception is the Antarctic Peninsula, where there has been a winter (summer) season warming on the western (eastern) side. Many of the different changes observed between the two polar regions can be attributed to topographic factors and land/sea distribution. The location of the Arctic Ocean at high latitude, with the consequently high level of solar radiation received in summer, allows the icealbedo feedback mechanism to operate effectively. The Antarctic ozone hole has had a profound effect on the circulations of the high latitude ocean and atmosphere, isolating the continent and increasing the westerly winds over the Southern Ocean, especially during the summer and winter.
Keywords: Antarktis; Sørishavet; havis; klimaendringer; klimatologi; ozonhull; ozonlaget; polarområdene; sjøis

Sedimentological, geochemical and palaeontological evidence for a neoglacial cold event during the late Holocene in the continental shelf of the northern South Shetland Islands, West Antarctica - Yoo, Kyu-Cheul; Yoon, Ho Il; Kim, Jin-Kyung; Khim, Boo-Keun (Polar Research, 2009)
Two sediment cores obtained from the continental shelf of the northern South Shetland Islands, West Antarctica, consist of: an upper unit of silty mud, bioturbated by a sluggish current, and a lower unit of well-sorted, laminated silty mud, attributed to an intensified Polar Slope Current. Geochemical and accelerator mass spectrometry 14C analyses yielded evidence for a late Holocene increase in sea-ice extent and a decrease in phytoplankton productivity, inferred from a reduction in the total organic carbon content and higher C : N ratios, at approximately 330 years B.P., corresponding to the Little Ice Age. Prior to this, the shelf experienced warmer marine conditions, with greater phytoplankton productivity, inferred from a higher organic carbon content and C : N ratios in the lower unit. The reduced abundance of Weddell Sea ice-edge bloom species (Chaetoceros resting spores, Fragilariopsis curta and Fragilariopsis cylindrus) and stratified cold-water species (Rhizosolenia antennata) in the upper unit was largely caused by the colder climate. During the cold period, the glacial restriction between the Weddell Sea and the shelf of the northern South Shetland Islands apparently hindered the influx of ice-edge bloom species from the Weddell Sea into the core site. The relative increases in the abundance of Actinocyclus actinochilus and Navicula glaciei, indigenous to the coastal zone of the South Shetland Islands, probably reflects a reduction in the dilution of native species, resulting from the diminished influx of the ice-edge species from the Weddell Sea. We also document the recent reduction of sea-ice cover in the study area in response to recent warming along the Antarctic Peninsula.
Keywords: Antarktis; Den lille istid; Vestantarktis; Weddellhavet; diatomeer; fytoplankton; geokjemi; havis; klimaendringer; klimatologi; kontinentalsokkel; marin biologi; mikropaleontologi; oseanografi; sedimenter; sedimentologi; sjøis

Self-scattering of a powerful HF radio wave on stimulated ionospheric turbulence - Zalizovski, Andriy; Kashcheyev, S B; Yampolski, Y M; Galushko, V G; Belyey, Vasyl; Isham, B; Rietveld, M T; La Hoz, C; Brekke, A; Blagoveshchenskaya, N F; Kornienko, V A (Radio Science, 2009)
An analysis is presented of high-frequency (HF) signals from the European Incoherent Scatter HF ionospheric modification transmitter received during 26–30 October 2002 at three sites, two in Europe and one in Antarctica. Two components with different characteristics (“mirror-reflected” and “scattered”) were observed in the signal spectra. The mirror-reflected component can be associated with radiation through the side lobes of the transmitting antenna thus bypassing the modified volume on its way to the receiving sites. In contrast, the scattered component was radiated through the main antenna beam and then scattered by pump-induced ionospheric irregularities above the heater. As a result, variations in the scattered component signal intensity and Doppler frequency shifts (DFS) recorded at the greatly separated sites showed a high level of correlation. It is shown that the Doppler frequency variations can be associated with variations in the plasma density and/or physical motion velocities of stimulated inhomogeneities within the volume common to all propagation paths. Analysis of Doppler frequency shifts at greatly separated sites would allow identifying the mechanism responsible for the self-scattering effect. In the case of DFSs due to motion of the pump-induced scatterers it would be also possible to reconstruct the full velocity vector of the inhomogeneities.
Keywords: Antarktis; astronomi; fysikk; ionosfæren; polarområdene

Review of Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition, by M.L. Paine - Baughman, Timothy H (Polar Research, 2008)
If the reader is looking for another rehashing of one of the adventures of the “Heroic Era” of Antarctic exploration, or another reshaping of the same old material about the three or four explorers from that period who get all the attention, M.L. Paine’s Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition is not the book for you. But if you are a serious Antarctic buff who wants to learn something new, and really get inside one of the early expeditions of the 20th century, Paine’s volume will be a compelling read.
Keywords: Antarktis; Richard Evelyn Byrd; Sydpolflyvningen; bokanmeldelser; dagbøker; ekspedisjoner; fly; luftfart; oppdagelsesreiser; polarflyving; turisme

Ground-based measurements of spatial and temporal variability of snow accumulation in East Antarctica - Eisen, Olaf; Frezzotti, Massimo; Genthon, Christophe; Isaksson, Elisabeth; Magand, Olivier; van den Broeke, Michiel R; Dixon, Daniel A; Ekaykin, Alexey; Holmlund, Per; Kameda, Takao; Karlöf, Lars; Kaspari, Susan; et al. (Reviews of Geophysics, 2008)
The East Antarctic Ice Sheet is the largest, highest, coldest, driest, and windiest ice sheet on Earth. Understanding of the surface mass balance (SMB) of Antarctica is necessary to determine the present state of the ice sheet, to make predictions of its potential contribution to sea level rise, and to determine its past history for paleoclimatic reconstructions. However, SMB values are poorly known because of logistic constraints in extreme polar environments, and they represent one of the biggest challenges of Antarctic science. Snow accumulation is the most important parameter for the SMB of ice sheets. SMB varies on a number of scales, from small-scale features (sastrugi) to ice-sheet-scale SMB patterns determined mainly by temperature, elevation, distance from the coast, and wind-driven processes. In situ measurements of SMB are performed at single points by stakes, ultrasonic sounders, snow pits, and firn and ice cores and laterally by continuous measurements using ground-penetrating radar. SMB for large regions can only be achieved practically by using remote sensing and/or numerical climate modeling. However, these techniques rely on ground truthing to improve the resolution and accuracy. The separation of spatial and temporal variations of SMB in transient regimes is necessary for accurate interpretation of ice core records. In this review we provide an overview of the various measurement techniques, related difficulties, and limitations of data interpretation; describe spatial characteristics of East Antarctic SMB and issues related to the spatial and temporal representativity of measurements; and provide recommendations on how to perform in situ measurements.
Keywords: Antarktis; akkumulasjon; fjernmåling; glasiologi; havnivåstigning; innlandsis; paleoklimatologi; snø

Apatite single-grain (U-Th)/He data from Heimefrontfjella, East Antarctica: Indications for differential exhumation related to glacial loading? - Emmel, Benjamin; Jacobs, Joachim; Crowhurst, P; Austegard, Atle; Schwarz-Schampera, Ulrich (Tectonics, 2008)
Single-grain (U-Th)/He ages from two profiles were used to reconstruct the post-Permian tectonic-thermal history of basement rocks in Heimefrontfjella, East Antarctica. The (U-Th)/He ages from one sample collected below the late Carboniferous/Early Permian sedimentary cover rocks indicate Jurassic–Early Cretaceous basement paleotemperatures of ∼40°–60°C due to post-Permian burial. Combined apatite fission track and (U-Th)/He analyses from samples of a profile in Sivorgfjella suggest a period of flexural-related tilting after ∼87 Ma. The timing was further constrained using forward and inverse models of the (U-Th)/He data. Model results indicate a Cenozoic phase of relatively rapid cooling from ∼40°C to surface temperatures. As the driving mechanism, we propose flexural isostatic rebound due to glacial load during the development of the intracontinental ice sheet in the hinterland of the Heimefrontfjella region.
Keywords: Antarktis; geologi; tektonikk; termokronologi

Predicting the fate of ice shelves - Galton-Fenzi, Benjamin K (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

From the editor: halfway through the IPY—halfway for an Antarctic traverse - Goldman, Helle V (Polar Research, 2008)
April is here and we have just passed the midpoint of the International Polar Year (IPY), which began on 1 March 2007 and will conclude on 1 March 2009. The “year” stretches over 24 months to accommodate two summer field seasons in both polar regions. The northern summer is fast approaching, and scientists who will undertake a second IPY summer season in the Arctic are making their final preparations. At the opposite end of the planet, summer is over and scientists have wrapped up the first IPY field season. Those whose projects will carry on for a second summer season will have to wait until late this year to resume work in Antarctica.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Antarctic ices shelves in a changing climate - Jenkins, Adrian (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

In situ measurements of snow surface roughness using a laser profiler - Lacroix, Pascal; Legrésy, B; Langley, Kirsty; Hamran, Svein Erik; Kohler, Jack; Roques, S; Rémy, F; Dechambre, M (Journal of Glaciology, 2008)
The snow surface roughness at centimetre and millimetre scales is an important parameter related to wind transport, snowdrifts, snowfall, snowmelt and snow grain size. Knowledge of the snow surface roughness is also of high interest for analyzing the signal from radar sensors such as SAR, altimeters and scatterometers. Unfortunately, this parameter has seldom been measured over snow surfaces. The techniques used to measure the roughness of other surfaces, such as agricultural or sand soils, are difficult to implement in polar regions because of the harsh climatic conditions. In this paper we develop a device based on a laser profiler coupled with a GPS receiver on board a snowmobile. This instrumentation was tested successfully in midre Lovénbreen, Svalbard, in April 2006. It allowed us to generate profiles of 3 km sections of the snow-covered glacier surface. Because of the motion of the snowmobile, the roughness signal is mixed with the snowmobile signal. We use a distance/frequency analysis (the empirical mode decomposition) to filter the signal. This method allows us to recover the snow surface structures of wavelengths between 4 and 50 cm with amplitudes of >1 mm. Finally, the roughness parameters of snow surfaces are retrieved. The snow surface roughness is found to be dependent on the scales of the observations. The retrieved RMS of the height distribution is found to vary between 0.5 and 9.2 mm, and the correlation length is found to be between 0.6 and 46 cm. This range of measurements is particularly well adapted to the analysis of GHz radar response on snow surfaces.
Keywords: Antarktis; glasiologi; teknologi

The use and abuse of dogs on Scott's and Amundsen's South Pole expeditions - Murray, Carl (Polar Record, 2008)
In the century since Roald Amundsen and Robert F. Scott led the first and second expeditions to reach the South Pole, commentators have frequently passed judgement on the different means of transport that the two explorers employed. In hindsight, and since he ‘won,’ they have consistently praised Amundsen for using dogs exclusively and criticised Scott for not doing the same. Surprisingly, however, almost no attention has been given to the experience of Amundsen's dogs, whose extreme suffering seems to have vanished into a collective blind spot. Here, with the aim of restoring balance to one part of the vexed historiography of the two explorers, that record is set straight. Amundsen's troubled and contradictory attitude towards his animals is also explored and common misconceptions about Scott's views on the use of dogs for transport are confuted.
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie; sledehunder

Land-fast ice variation during the past five decades: Lützow-Holm Bay, Antarctica - Ushio, Shuki (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

De første skiturene i Antarktis - Barr, Susan (Snø & ski: årbok, 2007)
Keywords: Antarktis; ekspedisjoner; historie; logistikk

Norway and past International Polar Years—a historical account - Bones, Stian (Polar Research, 2007)
Surveying Norway’s role in past International Polar Years (IPYs), this essay by historian Stian Bones contributes to a broader understanding of Norway as a “polar nation”. He describes the strengths of Norway’s scientific traditions in the polar regions, and examines the varying motivations driving Norwegian involvement in the first three IPYs: 1882–83, 1932–33 and 1957–58 (also known as the International Geophysical Year).
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; historie; polarområdene; vitenskap

National and institutional productivity and collaboration in Antarctic science: an analysis of 25 years of journal publications (1980–2004) - Dastidar, Prabir G. (Polar Research, 2007)
Journal publications on Antarctic science were analysed for a period of 25 years (1980–2004) through a set of scientometrics and network analysis techniques. The study is based on 10 942 records (research articles, review articles, letters, etc.) with the word fragment “antarc*” in the title published in 961 international, peer-reviewed journals and retrieved from Thomson Scientific’s Science Citation Index database. During the period under investigation, productivity increased threefold and there was a 13-fold increase in journal publications co-written by authors from different countries. The five nations with the highest output were the USA (with 26.7% of the total output), the UK (13.8%), Australia (9.7%), Germany (8.8%) and Italy (6.0%). The top five institutions in terms of journal publications were the British Antarctic Survey (972 publications), the Alfred Wegener Institute of Polar and Marine Research, Germany (475), the Australian Antarctic Division (312), the University of Tasmania, Australia (305), and the National Aeronautics and Space Administration, USA (293).
Keywords: Antarktis; dataanalyse; forskning; scientometri; tidsskriftspublikasjoner

Polar Research evolves, and Norway and the IPY - Goldman, Helle V (Polar Research, 2007)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Henrik Bull, the Antarctic Exploration Committee and the first confirmed landing on the Antarctic continent - McConville, Andrew (Polar Record, 2007)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; D/S Antarctic; Henrik Johan Bull; Kapp Adare; Leonard Kristensen; Rosshavet; Victoria Land; ekspedisjoner; forskning; første landgang; oppdagelsesreiser

Til Antarktis for å simulere fremtiden - Sirevaag, Anders (AKA : tverrfaglig studentlektyre, 2007)
Keywords: Antarktis; klimaendringer; populærvitenskap

Seismic morphology and distribution of inferred glaciomarine deposits along the East Antarctic continental margin, 20°E–60°E - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandjukhin, V (Marine Geology, 2007)
Keywords: Antarktis; innlandsis; isstrøm; kontinentalstiging; marin geologi; morfologi; sedimentologi; seismologi

Widerøe kartlegger i Antarktis - Widerøe, Turi (Perspektiv, 2007)
Keywords: Antarktis; Dronning Maud Land; Lars Christensen; Norvegia ekspedisjoner; flyhistorie; hvalfangst; kartlegging

Perspectives on the Economic History of the Antarctic Region - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2006)
Keywords: Antarktis; ekspedisjoner; fiskeindustri; forskning; hvalfangst; ressurser; turisme; økonomi; økonomisk historie

Haul-out pattern of itinerant male Antarctic fur seals (Arctocephalus gazella) at Laurie Island, South Orkney Islands - Carlini, Alejandro R; Daneri, Gustavo A; Casaux, Ricardo; Márquez, María E I (Polar Research, 2006)
The seasonal haul-out pattern of itinerant male Antarctic fur seals (Arctocephalus gazella) was determined by regular counts at Mossman Peninsula, Laurie Island, South Orkney Islands, from 1996 to 2005. Small numbers of animals began to arrive at the beach in late December / early January (mean date 28 December ± 15 days, n = 10). Peak numbers of animals ashore changed considerably between seasons. In 1996, 1998 and 2001, peak numbers were registered in March (6/3, 18/3 and 6/3, respectively). Numbers peaked in 1997, 1999 and 2005 at the end of January / beginning of February (26/1, 2/2 and 28/1, respectively). In 2000, 2002, 2003 and 2004 peaks were registered in the third week of February (15/2, 22/2, 14/2 and 20/2, respectively). Peaks in numbers of seals ashore also varied between years, being minimum during 2001 (2531 individuals) and maximum during 2006 (16 610 individuals). In March 1998 the coasts of Laurie Island were surveyed by navigating inflatable boats near the shoreline; 18 haul-out places were identified. The big differences in peak numbers, as well as in the dates of peak events among years, suggest that local conditions could have an effect on the numbers of animals hauled out in a given year. It may therefore be difficult to predict trends from summer censuses in non-breeding places.
Keywords: Antarktis; pelsseler; zoologi

“Deckchair Explorers”: The Origin and Development of Organised Tourist Voyages to Northern and Southern Polar Regions - Kolltveit, Bård (International Journal of Maritime History, 2006)
Keywords: Antarktis; ekspedisjoner; historie; miljø; næringslivet; polarområdene; turisme

Effect of critical latitude and seasonal stratification on tidal current profiles along Ronne Ice Front, Antarctica - Makinson, Keith; Schröder, Michael; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2006)
Keywords: Antarktis; Weddellhavet; havstrømmer; isfront; isshelf; oseanografi; tidevannsstrømmer

Evaluation of Global Ozone Monitoring Experiment (GOME) ozone profiles from nine different algorithms - Meijer, Yasjka; Swart, Daan P; Baier, F; Bhartia, Pawan K; Bodeker, G E; Casadio, Stefano; Chance, Kelly V; Del Frate, F; Erbertseder, T; Felder, Martin D; Flynn, Lawrence E; Godin-Beekmann, Sophie; et al. (Journal of Geophysical Research: Atmospheres, 2006)
An evaluation is made of ozone profiles retrieved from measurements of the nadir-viewing Global Ozone Monitoring Experiment (GOME) instrument. Currently, four different approaches are used to retrieve ozone profile information from GOME measurements, which differ in the use of external information and a priori constraints. In total nine different algorithms will be evaluated exploiting the optimal estimation (Royal Netherlands Meteorological Institute, Rutherford Appleton Laboratory, University of Bremen, National Oceanic and Atmospheric Administration, Smithsonian Astrophysical Observatory), Phillips-Tikhonov regularization (Space Research Organization Netherlands), neural network (Center for Solar Energy and Hydrogen Research, Tor Vergata University), and data assimilation (German Aerospace Center) approaches. Analysis tools are used to interpret data sets that provide averaging kernels. In the interpretation of these data, the focus is on the vertical resolution, the indicative altitude of the retrieved value, and the fraction of a priori information. The evaluation is completed with a comparison of the results to lidar data from the Network for Detection of Stratospheric Change stations in Andoya (Norway), Observatoire Haute Provence (France), Mauna Loa (Hawaii), Lauder (New Zealand), and Dumont d'Urville (Antarctic) for the years 1997–1999. In total, the comparison involves nearly 1000 ozone profiles and allows the analysis of GOME data measured in different global regions and hence observational circumstances. The main conclusion of this paper is that unambiguous information on the ozone profile can at best be retrieved in the altitude range 15–48 km with a vertical resolution of 10 to 15 km, precision of 5–10%, and a bias up to 5% or 20% depending on the success of recalibration of the input spectra. The sensitivity of retrievals to ozone at lower altitudes varies from scheme to scheme and includes significant influence from a priori assumptions.
Keywords: Antarktis; fjernmåling; meteorologi; ozonlaget; stratosfæren

Insignificant change in Antarctic snowfall since the International Geophysical Year - Monaghan, Amdrew J; Bromwich, David H; Fogt, Ryan L; Wang, Sheng-Hung; Mayewski, Paul A; Dixon, Daniel A; Ekaykin, Alexey; Frezzotti, Massimo; Ian Goodwin, Ian; Isaksson, Elisabeth; Kaspari, Susan D; Morgan, Vin I; et al. (Science, 2006)
Keywords: Antarktis; glasiologi

Remembering Tore Gjelsvik (1916–2006) - Orheim, Olav (Polar Research, 2006)
Tore Gjelsvik, former director of the Norwegian Polar Institute, died at the beginning of this year. He is fondly remembered by a great many people. In this piece, Olav Orheim recalls the man and his key role in Norwegian polar activities. Orheim was head of Antarctic Research at the Norwegian Polar Institute in 1972–1993 and was the institute’s director from 1993 to 2005.
Keywords: Antarktis; Norsk Polarinstitutt; biografi; geologi; polarområdene

Spatial and temporal variations in the thermodynamics since the Last Glacial Maximum at Jutulstraumen drainage basin, East Antarctica - Rolstad, Cecilie (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2006)
Keywords: Antarktis; akkumulasjon; glasiologi; isstrøm; nunataker

Ozone profiles in the high-latitude stratosphere and lower mesosphere measured by the Improved Limb Atmospheric Spectrometer (ILAS)-II: Comparison with other satellite sensors and ozonesondes - Sugita, Takafumi; Nakajima, Hideaki; Yokota, T; Kanzawa, Hiroshi; Gernandt, Hartwig; Herber, A; von der Gathen, P; König-Langlo, Gert; Sato, Kaoru; Dorokhov, Valery; Yushkov, V A; Murayama, Yasuhiro; et al. (Journal of Geophysical Research: Atmospheres, 2006)
A solar occultation sensor, the Improved Limb Atmospheric Spectrometer (ILAS)-II, measured 5890 vertical profiles of ozone concentrations in the stratosphere and lower mesosphere and of other species from January to October 2003. The measurement latitude coverage was 54–71°N and 64–88°S, which is similar to the coverage of ILAS (November 1996 to June 1997). One purpose of the ILAS-II measurements was to continue such high-latitude measurements of ozone and its related chemical species in order to help accurately determine their trends. The present paper assesses the quality of ozone data in the version 1.4 retrieval algorithm, through comparisons with results obtained from comprehensive ozonesonde measurements and four satellite-borne solar occultation sensors. In the Northern Hemisphere (NH), the ILAS-II ozone data agree with the other data within ±10% (in terms of the absolute difference divided by its mean value) at altitudes between 11 and 40 km, with the median coincident ILAS-II profiles being systematically up to 10% higher below 20 km and up to 10% lower between 21 and 40 km after screening possible suspicious retrievals. Above 41 km, the negative bias between the NH ILAS-II ozone data and the other data increases with increasing altitude and reaches 30% at 61–65 km. In the Southern Hemisphere, the ILAS-II ozone data agree with the other data within ±10% in the altitude range of 11–60 km, with the median coincident profiles being on average up to 10% higher below 20 km and up to 10% lower above 20 km. Considering the accuracy of the other data used for this comparative study, the version 1.4 ozone data are suitably used for quantitative analyses in the high-latitude stratosphere in both the Northern and Southern Hemisphere and in the lower mesosphere in the Southern Hemisphere.
Keywords: Antarktis; klimatologi; meteorologi; ozonlaget; polarområdene; stratosfæren

Snow chemistry across Antarctica - Bertler, N.; Mayewski, Paul Andrew; Aristarain, A.; Barrett, P.; Becagli, S.; Bernardo, R.; Bo, S.; C, Xiao; Curran, M.; D, Qin; Dixon, D.; Ferrona, F.; et al. (Annals of Glaciology, 2005)
An updated compilation of published and new data of major-ion (Ca, Cl, K, Mg, Na, NO3, SO4) and methylsulfonate (MS) concentrations in snow from 520 Antarctic sites is provided by the national ITASE (International Trans-Antarctic Scientific Expedition) programmes of Australia, Brazil, China, Germany, Italy, Japan, Korea, New Zealand, Norway, the United Kingdom, the United States and the national Antarctic programme of Finland. The comparison shows that snow chemistry concentrations vary by up to four orders of magnitude across Antarctica and exhibit distinct geographical patterns. The Antarctic-wide comparison of glaciochemical records provides a unique opportunity to improve our understanding of the fundamental factors that ultimately control the chemistry of snow or ice samples. This paper aims to initiate data compilation and administration in order to provide a framework for facilitation of Antarctic-wide snow chemistry discussions across all ITASE nations and other contributing groups. The data are made available through the ITASE web page (http://www2.umaine.edu/itase/content/syngroups/snowchem.html) and will be updated with new data as they are provided. In addition, recommendations for future research efforts are summarized.
Keywords: Antarktis; geovitenskap; glasiokjemi; glasiologi; iskjerner; transantarktiske ekspedisjoner

Taxonomic turnover and abundance in Cretaceous to Tertiary wood floras of Antarctica: implications for changes in forest ecology - Cantrill, David J.; Poole, Imogen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2005)
Based on the temporal distribution, abundance, and taxonomic composition of wood floras, four phases of vegetation development are recognized through the Cretaceous to Early Tertiary of the Antarctic Peninsula: (1) Aptian to Albian communities dominated by podocarpaceous, araucarian, and minor taxodiaceous/cupressaceous conifers with rare extinct gymnosperms (Sahnioxylon). (2) Progressive replacement of these communities in ?Cenomanian to Santonian times by angiosperms, most without modern analogues. (3) Increasing dominance of angiosperms becoming important both in terms of diversity and abundance towards the mid-Late Cretaceous. (4) Modernization of the flora during the Campanian to Maastrichtian with the extinction of earlier forms, appearance of the Nothofagaceae and diversification of associated elements. These patterns broadly follow trends seen in the leaf and palynological record but with some important differences. During the Cretaceous, conifer composition undergoes a change whereby Phyllocladoxylon-type woods increase relative to the older Podocarpoxylon forms. During the Paleocene to Eocene period, a marked extinction in wood types occurs associated with an increase in the abundance of nothofagaceous wood. Detailed examination of wood abundance and distributions from sections within Maastrichtian and Paleocene formations points to strong environmental control on taxonomic compositions. Similar differences are encountered when comparing coeval floras from different geographic regions and palaeoenvironments.
Keywords: Antarktis; flora; geologi; paleobotanikk; paleogeografi; paleontologi

Modeling the middle Pliocene climate with a global atmospheric general circulation model - Jiang, Dabang; Wang, Huijun; Ding, Zhongli; Lang, Xianmei; Drange, Helge (Journal of Geophysical Research: Atmospheres, 2005)
A new climate simulation for the middle Pliocene (ca. 3 Ma BP) is performed by a global grid-point atmospheric general circulation model developed at the Institute of Atmospheric Physics (IAP AGCM) with boundary conditions provided by the U. S. Geological Survey's Pliocene Research, Interpretations, and Synoptic Mapping (PRISM) group. It follows that warmer and slightly wetter conditions dominated at the middle Pliocene with a globally annual mean surface temperature increase of 2.60°C, and an increase in precipitation of 4.0% relative to today. At the middle Pliocene, globally annual terrestrial warming was 1.86°C, with stronger warming toward high latitudes. Annual precipitation enhanced notably at high latitudes, with the augment reaching 33.5% (32.5%) of the present value at 60–90°N (60–90°S). On the contrary, drier conditions were registered over most parts at 0–30°N, especially in much of East Asia and the northern tropical Pacific. In addition, both boreal summer and winter monsoon significantly decreased in East Asia at the middle Pliocene. It is indicated that the IAP AGCM simulation is generally consistent with the results from other atmospheric models and agrees well with available paleoclimatic reconstructions in East Asia. Additionally, it is further revealed that the PRISM warmer sea surface temperature and reduced sea ice extent are main factors determining the middle Pliocene climate. The simulated climatic responses arising from the PRISM reconstructed vegetation and continental ice sheet cannot be neglected on a regional scale at mid to high latitudes (like over Greenland and the Qinghai-Tibetan Plateau, and around the circum-Antarctic) but have little influence on global climate.
Keywords: Antarktis; global klimamodell; global oppvarming; innlandsis; paleoklimatologi; polarområdene

Notes on two subantarctic pannariaceous lichens - Jørgensen, Per Magnus (Cryptogamie Mycologie, 2005)
It is shown by use of a newly discovered, old photo of the missing type that Siphulina orphnina (Hue) C. W. Dodge is identical with Pannaria caespitosa P. M. Jorg. The new combination Pannaria orphnina (Hue) R M. Jorg. is made, and the name neotypitied. Parmeliella austroshetlandica Sochting & Ovstedal is shown to be a species in the small subantarctic genus Peltularia R. Sant. (Coccocarpiaceae), and is transferred to that genus.
Keywords: Antarktis; biologi; botanikk; lav; planter

Belgica in the Arctic - Kjær, Kjell-G. (Polar Record, 2005)
Belgica, which Adrien de Gerlache used on the first expedition to winter in the Antarctic, was originally a bottlenose whaler named Patria, built in Norway in 1884. She was designed and constructed by Johan Chr. Jakobsen, renowned for his design of polar ships. Patria was sold to Adrien de Gerlache and renamed Belgica in 1896. In 1896–97 she was refitted and equipped in Sandefjord, Norway, for an Antarctic expedition. Nansen and Amundsen met for the first time on Belgica's deck. Late in 1899 Belgica returned to Antwerp after more than two years on an Antarctic expedition. From 1901 to 1904 Belgica returned to bottlenose whaling and, in addition, made a voyage to northeast Greenland to establish depots and build houses for the Baldwin-Ziegler Polar Expedition. In 1905 the Duc d'Orléans chartered her to survey the coast of northeast Greenland, and on her return he bought her. In 1907 and 1909 she sailed on Arctic expeditions led by the Duc d'Orléans and captained by de Gerlache. In 1916 she was sold to Det Norske Kulsyndikat and renamed Isfjord. She became a freighter carrying coal from Longyearbyen to ports in northern Norway. In 1918 she was sold and her new owner converted her into a floating cod-liver oil refinery and fish-processing plant. In 1940 she was impounded by British forces and used as a floating ammunition depot. On 19 May 1940 she was sunk during a German air raid. Her wreck was re-discovered in 1990.
Keywords: Antarktis; Belgica (skip); Belgica ekspedisjon; Roald Amundsen; overvintring; polarekspedisjoner; polarområdene

Interplay of turbidite and contourite deposition along the Cosmonaut Sea/Enderby Land margin, East Antarctica - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, V.; Løvås, O.; Sand, Morten; Brekke, Harald (Marine Geology, 2005)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes on the continental rise. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents redepositing the sediments into a large-scale plastered drift deposit prior to the main glacigenic input along the margin. High-relief elongated and sometimes semicircular depositional structures are found on the upper continental rise, stratigraphically above the regional sediment lens, and were mainly deposited by the action of closely spaced turbidity currents. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of down-slope turbidity transport and westward flowing bottom currents. The elongated sediment mounds on the upper and lower continental rise were deposited after initiation of glacigenic input to the slope and rise.
Keywords: Antarktis; Sørishavet; marin geofysikk; marin geologi

Quality assurance of the solar UV network in the Antarctic - Lakkala, Kaisa; Redondas, Alberto; Meinander, Outi; Torres, Carlos; Koskela, Tapani; Cuevas, Emilio; Taalas, Petteri; Dahlback, Arne; Deferrari, Guillermo Alejandro; Edvardsen, Kåre; Ochoa, Héctor (Journal of Geophysical Research: Atmospheres, 2005)
Measuring ultraviolet radiation in the Antarctic region, where weather conditions are extremely challenging, is a demanding task. Proper quality control of the measurements and quality assurance of the data, which are the basis of all scientific use of data, has to be especially well planned and executed. In this paper we show the importance of proper quality assurance and describe the methods used to successfully operate the NILU-UV multichannel radiometers of the Antarctic network stations at Ushuaia, 54°S, and Marambio, 64°S. According to our experience, even though multichannel instruments are supposed to be rather stable as a function of time, severe drifts can occur in the sensitivity of the channels under these harsh conditions. During 2000–2003 the biggest drifts were 35%, both at Ushuaia and Marambio, with the sensitivity of the channels dropping at different rates. Without proper corrections in the data, this would have seriously affected the calculated UV dose rates. As part of the quality assurance of the network a traveling reference NILU-UV, which was found to be stable, was used to transfer the desired irradiance scale to the site NILU-UV data. Relative lamp tests were used to monitor the stability of the instruments. Each site NILU-UV was scaled channel by channel to the traveling reference by performing solar comparisons. The method of scaling each channel separately was found to be successful, even though the differences between the raw data of the site NILU-UV and the reference instruments were, before the data correction, as much as 40%. After the correction, the mean ratios of erythemally weighted UV dose rates measured during the solar comparisons in 2000–2003 between the reference NILU-UV and the site NILU-UV were 1.007 ± 0.011 and 1.012 ± 0.012 for Ushuaia and Marambio, respectively, when the solar zenith angle varied up to 80°. These results make possible the scientific use of NILU-UV data measured simultaneously at quite different locations, e.g., the Antarctic and Arctic, and the method presented is also practicable for other multichannel radiometer networks.
Keywords: Antarktis; UV-stråling; meteorologi; målinger; ultrafiolett stråling

Antarctic surface and subsurface snow and ice melt fluxes - Liston, Glen E.; Winther, Jan-Gunnar (Journal of Climate, 2005)
This paper presents modeled surface and subsurface melt fluxes across near-coastal Antarctica. Simulations were performed using a physical-based energy balance model developed in conjunction with detailed field measurements in a mixed snow and blue-ice area of Dronning Maud Land, Antarctica. The model was combined with a satellite-derived map of Antarctic snow and blue-ice areas, 10 yr (1991–2000) of Antarctic meteorological station data, and a high-resolution meteorological distribution model, to provide daily simulated melt values on a 1-km grid covering Antarctica. Model simulations showed that 11.8% and 21.6% of the Antarctic continent experienced surface and subsurface melt, respectively. In addition, the simulations produced 10-yr averaged subsurface meltwater production fluxes of 316.5 and 57.4 km3 yr−1 for snow-covered and blue-ice areas, respectively. The corresponding figures for surface melt were 46.0 and 2.0 km3 yr−1, respectively, thus demonstrating the dominant role of subsurface over surface meltwater production. In total, computed surface and subsurface meltwater production values equal 31 mm yr−1 if evenly distributed over all of Antarctica. While, at any given location, meltwater production rates were highest in blue-ice areas, total annual Antarctic meltwater production was highest for snow-covered areas due to its larger spatial extent. The simulations also showed higher interannual meltwater variations for surface melt than subsurface melt. Since most of the produced meltwater refreezes near where it was produced, the simulated melt has little effect on the Antarctic mass balance. However, the melt contribution is important for the surface energy balance and in modifying surface and near-surface snow and ice properties such as density and grain size.
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

The International Trans-Antarctic Scientific Expedition (ITASE): an overview - Mayewski, Paul Andrew; Frezzotti, Massimo; Bertler, Nancy; Ommen, Tas V. A. N.; Hamilton, Gordon; Jacka, Tim H.; Welch, Brian; Frey, Markus; Dahe, Qin; Jiawen, Ren; Simões, Jefferson; Fily, Michel; et al. (Annals of Glaciology, 2005)
From its original formulation in 1990 the International Trans-Antarctic Scientific Expedition (ITASE) has had as its primary aim the collection and interpretation of a continent-wide array of environmental parameters assembled through the coordinated efforts of scientists from several nations. ITASE offers the ground-based opportunities of traditional-style traverse travel coupled with the modern technology of GPS, crevasse detecting radar, satellite communications and multidisciplinary research. By operating predominantly in the mode of an oversnow traverse, ITASE offers scientists the opportunity to experience the dynamic range of the Antarctic environment. ITASE also offers an important interactive venue for research similar to that afforded by oceanographic research vessels and large polar field camps, without the cost of the former or the lack of mobility of the latter. More importantly, the combination of disciplines represented by ITASE provides a unique, multidimensional (space and time) view of the ice sheet and its history. ITASE has now collected >20 000km of snow radar, recovered more than 240 firn/ice cores (total length 7000 m), remotely penetrated to ~4000m into the ice sheet, and sampled the atmosphere to heights of >20 km.
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; geovitenskap; glasiologi; klimatologi; transantarktiske ekspedisjoner

A comparison of the NW European glaciated margin with other glaciated margins - Nielsen, Tove; De Santis, L.; Dahlgren, K.I. Torbjørn; Kuijpers, A.; Laberg, J.S.; Nygård, Atlé; Praeg, D.; Stoker, M.S. (The STRATAGEM Project, 2005)
The present paper provides an overview of glacial related seabed features and sedimentary sequences found along the formerly glaciated NW European margin and compare it with those found on contemporary glaciated margins from both the Southern and Northern Hemispheres. A brief review of the seabed physiography and strata architecture of the margins under consideration is followed by comparison of the most relevant similarities and differences. Comparison of the present-day bathymetric setting of both former and contemporary glaciated margins reveals no clear link to the effect of neither ice sheet or sediment load. Three different types of glacially eroded shelf transverse troughs have been identified, while marginal troughs seem connected to similar geological settings everywhere. Beyond the shelf edge interaction between downslope and alongslope processes has occurred resulting, amongst others, in the formation of large sedimentary mounds on the rise. More frequent large-scale mass wasting occurs on the former glaciated NW European margin than the Greenland and Antarctic margins in the latest Neogene to recent times. A two-stage evolution of the shelf prograding wedges is observed on all margins under consideration, which may reflect a general development of an ice cover from an initial phase of non- to restricted glaciation, evolving to a mature stage of expansive glaciation.
Keywords: Antarktis; geofysikk; marin geologi

Seleksjon av personell til overvintring i Antarktis - Orre, Ingrid Jangård; Eriksen, Hege Randi; Ursin, Holger; Grant, Iain; Palinkas, Lawrence A; Suedfeld, Peter (Tidsskrift for Norsk psykologforening, 2005)
Keywords: Antarktis; ekspedisjoner; psykologi; stasjoner

An Observational Study of the Final Breakdown of the Southern Hemisphere Stratospheric Vortex in 2002 - Orsolini, Yvan J.; Randall, Cora E.; Manney, Gloria L.; Allen, Douglas R. (Journal of the Atmospheric Sciences, 2005)
The 2002 Southern Hemisphere final warming occurred early, following an unusually active winter and the first recorded major warming in the Antarctic. The breakdown of the stratospheric polar vortex in October and November 2002 is examined using new satellite observations from the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) instrument aboard the European Space Agency (ESA) Environment Satellite (ENVISA7-) and meteorological analyses, both high-resolution fields from the European Centre for Medium-Rangc Weather Forecasts and the coarser Met Office analyses. The results derived from MIPAS observations are compared to measurements and inferences from well-validated solar occultation satellite instruments [Halogen Occultation Experiment (HALOE), Polar Ozone and Aerosol Measurement lit (POAM III), and Stratospheric Aerosol and Gas Experiments II and III (SAGE II and III)] and to finescale tracer fields reconstructed by transporting trace gases based oil MIPAS or climatological data using a reverse-trajectory method. These comparisons confirm the features in the MIPAS data and the interpretation of the evolution of the flow during the vortex decay revealed by those features. Mapped ozone and water vapor from MIPAS and the analyzed isentropic potential vorticity vividly display the vortex breakdown, which occurred earlier than usual. A large tongue of vortex air was pulled out westward and coiled up in an anticyclone, while the vortex core remnant shrank and drifted eastward and equatorward over the South Atlantic. By roughly mid-November, the vortex remnant at 10 mb had shrunk below scales resolved by the satellite observations, while a vortex core remained in the lower stratosphere.
Keywords: Antarktis; klimatologi; meteorologi; polarvirvelen; stratosfæren

A multi-proxy approach to determine Antarctic terrestrial palaeoclimate during the Late Cretaceous and Early Tertiary - Poole, Imogen; Cantrill, David; Utescher, Torsten (Palaeogeography, Palaeoclimatology, Palaeoecology, 2005)
Fossil wood is abundant throughout the Cretaceous and Tertiary sequences of the northern Antarctic Peninsula region. The fossil wood represents the remains of the vegetation that once grew at the southern high palaeolatitudes at 59–62°S through the general decline in climate, from the Late Cretaceous global warmth through to the mid-Eocene cool period prior to the onset of glaciation. This study draws on the largest dataset ever compiled of Antarctic conifer and angiosperm woods in order to derive clearer insights into the palaeoclimate. Parameters including mean annual temperature, mean annual range in temperature, cold month mean, warm month mean, mean annual precipitation are recorded. The fossil wood assemblages have been analysed using anatomical (physiognomic) characteristics to determine the palaeoclimate variables from the Coniacian–Campanian to the middle Eocene. These results are compared with data derived from Coexistence Analysis of the fossil floras (composed of leaves, wood and palynomorphs) and published data based on leaf physiognomic characters. These studies indicate a relatively warm and wet Late Cretaceous that becomes drier and cooler in the Early Paleocene and subsequently returns to warmer, wetter conditions by the latest Early Paleocene. During the Eocene the climate becomes relatively cool and dry once again. The discrepancies obtained from these two methods coupled with other published data are discussed in the context of the fluctuations in the temperatures of the surrounding oceans and global patterns of climate change.
Keywords: Antarktis; paleobotanikk; paleogeografi; paleoklimatologi; paleontologi

Perturbation of hydrochemical conditions in natural microcosms entombed within Antarctic ice - Tranter, Martyn; Fountain, Andrew G; Fritsen, Christian H; Lyons, W Berry; Priscu, John C; Statham, Peter J; Welch, Kathy A (Ice and climate news, 2005)
Keywords: Antarktis; glasiologi; hydrokjemi

Chick survival in relation to nest site: is the Antarctic petrel hiding from its predator? - Varpe, Øystein; Tveraa, Torkild (Polar Biology, 2005)
In birds, the characteristics of the nest site may affect reproductive success. We found that shelter is an important characteristic of the Antarctic petrel (Thalassoica antarctica) nests because shelter prevents chick predation. However, the benefit of shelter was countervailed by melt water which mainly entered well-sheltered nests. Chick survival was monitored until the chick was left unattended for the first time. Late-hatched chicks had a higher survival probability than early-hatched chicks, possibly because late hatchers swamp the predator, the south polar skua (Catharacta maccormicki). Poorly sheltered nests tended to be occupied by parents with low body mass and late-hatched eggs. The results suggest that both shelter per se and parental characteristics may explain the relationship between predation risk and shelter. We need experiments to study the influence of nest site on reproductive success, and we need to map the frequency of melt water as a cause of reproductive failure.
Keywords: Antarktis; fugler; ornitologi; petreller; reproduksjon; zoologi

Decision Processes and Interactions During a Two-Woman Traverse of Antarctica - Atlis, Mera M.; Leon, Gloria R.; Sandal, Gro M.; Infante, Michael G. (Environment and Behavior, 2004)
This investigation assessed an international two-woman team engaged in a 97-day traverse of Antarctica. Measures consisted of preexpedition personality assessments; expedition weekly ratings of individual and team status and work performance; postexpedition semistructured interview. Both participants scored relatively highest on the Multidimensional Personality Questionnaire (MPQ) Absorption scale, the Personality Characteristics Inventory (PCI) Work and Positive Expressivity scales and lowest on the PCI Verbal Aggressiveness scale. One member reported sensed presence experiences, which served as an important motivating factor when fatigued or disappointed about daily progress. Enjoyment and awe of the environment were significant aspects of the daily trek and sources of psychological strength. Advantages of the co-equal dyad were evident in the cooperative nature of decision making and substantial similarities in approach to solving problems. Differences from the usual military command structure in decision-making processes and implications for planetary expeditions are discussed.
Keywords: Antarktis; kvinner; polarekspedisjoner; psykologi

Eight glacial cycles from an Antarctic ice core - Augustin, Laurent; Barbante, Carlo; Barnes, Piers R. F.; Marc Barnola, Jean; Bigler, Matthias; Castellano, Emiliano; Cattani, Olivier; Chappellaz, Jerome; Dahl-Jensen, Dorthe; Delmonte, Barbara; Dreyfus, Gabrielle; Durand, Gael; et al. (Nature, 2004)
The Antarctic Vostok ice core provided compelling evidence of the nature of climate, and of climate feedbacks, over the past 420,000 years. Marine records suggest that the amplitude of climate variability was smaller before that time, but such records are often poorly resolved. Moreover, it is not possible to infer the abundance of greenhouse gases in the atmosphere from marine records. Here we report the recovery of a deep ice core from Dome C, Antarctica, that provides a climate record for the past 740,000 years. For the four most recent glacial cycles, the data agree well with the record from Vostok. The earlier period, between 740,000 and 430,000 years ago, was characterized by less pronounced warmth in interglacial periods in Antarctica, but a higher proportion of each cycle was spent in the warm mode. The transition from glacial to interglacial conditions about 430,000 years ago (Termination V) resembles the transition into the present interglacial period in terms of the magnitude of change in temperatures and greenhouse gases, but there are significant differences in the patterns of change. The interglacial stage following Termination V was exceptionally long—28,000 years compared to, for example, the 12,000 years recorded so far in the present interglacial period. Given the similarities between this earlier warm period and today, our results may imply that without human intervention, a climate similar to the present one would extend well into the future.
Keywords: Antarktis; klimagasser; paleoklimatologi

Whaler's cross on Deception Island - Barr, Susan; Downie, Rod; Sánchez, Rodolfo (Polar Record, 2004)
The cemetery at Whalers Bay, Deception Island, was the largest in the Antarctic prior to being partially buried and partially washed away during a volcanic eruption in 1969. In 2002 a wooden cross at Argentina's Decepción Station was identified as being that of the Norwegian whaler Peder Knapstad. It was removed, secured in a base, and re-erected at Whalers Bay.
Keywords: Antarktis; Deceptionøya; Sørishavet; kulturminneforvaltning; kulturminner

Numerical simulation of three-dimensional, transient snow drifting around a cube - Beyers, Meiring; Sundsbø, Per Arne; Harms, Thomas M. (Journal of Wind Engineering and Industrial Aerodynamics, 2004)
This paper presents the results of the numerical simulation of drifting snow surrounding a simple 2m cubicle structure. These results are compared and verified against data from snow drifting experimental tests carried out at SANAE IV research station, Antarctica, during the summer research period of January 2002. In addition to the snow drifting field observations, wind profile data were also obtained from cup-type anemometers mounted on a 6m wind mast. These data were employed to derive the characteristic surface roughness, shear velocity and approaching wind profile functions. The present work numerically simulates a transient three-dimensional turbulent viscous flow in an Eulerian coordinate frame including snow advection. A modified turbulent wall law is employed that accounts for the effects of snow saltation on the effective aerodynamic surface roughness. The numerical simulation employed the commercial CFD code, FLOW-3D, with additional user Fortran coding added to model the snow entrainment, subsequent accumulation or erosion of snow as well as temporal snow surface changes. The snow accumulation and erosion model is presented and discussed. The snow accumulation predicted by this numerical simulation compares favourably with the experimental results obtained from the Antarctica field testing.
Keywords: Antarktis; forskningsstasjoner; geofysikk; ingeniørvitenskap; mekanikk; numerisk modellering

Slope failure dynamics and impacts from seafloor and shallow sub-seafloor geophysical data: case studies from the COSTA project - Canals, M.; Lastras, G.; Urgeles, R.; Casamor, J.L.; Mienert, Jürgen; Cattaneo, A.; De Batist, M.; Haflidason, Haflidi; Imbo, Y.; Laberg, J.S.; Locat, J.; Long, D.; et al. (COSTA - Continental Slope Stability, 2004)
Holocene and slightly pre-Holocene submarine landslide are found both in high-latitude glacial-dominated margins and in lower latitude, river-dominated margins. This paper constitutes a major assessment on some of the best-studied submarine instabilities in the world. We review and update from original data and literature reports the current state of knowledge of Storegga, Traenadjupet and Finneidfjord slides from the mid-Norwegian margin, Afen Slide from the Faeroe-Shetland Channel, BIG'95 Slide and Central Adriatic Deformation Belt (CADEB) from continental slope and inner continental shelf settings off the Ebro and Po rivers in the Mediterranean Sea, Canary Slide west of the westernmost, youngest Canary Islands and Gebra Slide off the northern tip of the Antarctic Peninsula in the southern hemisphere, i.e. those studied in the Continental Slope Stability (COSTA) project. The investigated slides range in size from the gigantic 90,000 km2 and almost 3000 km3 Storegga Slide to the tiny 1 km2 and 0.001 km3 Finneidfjord Slide. Not only do individual submarine landslides rarely involve processes precisely fitting with pre-established categories, mostly based on subaerial research, but also they display complex mechanical behaviors within the elastic and plastic fields. Individual events can involve simultaneous or successive vertical to translational movements including block detachment, block gliding, debris flow, mud flow and turbidity currents. The need for an in-depth revision of the classification criteria, and eventually for a new classification system, based on the new imaging capabilities provided by modern techniques, is more than obvious. We suggest a new system, which, for the moment, is restricted to debris flows and debris avalanches. Volume calculation methods are critically reviewed and the relations between some key geomorphic parameters are established for the selected slides. The assumed volume missing from scar areas does not necessarily match the actual volume of sediment remobilised by an individual event since in situ sediment can be remoulded and eventually incorporated during the slide downslope journey. CADEB, a shore-parallel prodelta detached from its source, is the exception to the good correlation found between across slope width and alongslope length with slide area. Height drop measured from the headwall upper rim to its foot correlates with the debris deposit maximum thickness unless the slide moves into restricted areas, which prevent farther forward expansion of the deposit, such as Gebra and BIG'95. In such cases, “over-thickened” deposits are found. A particularly loose and fluid behavior can be deduced for slides showing an “over-thinned” character, such as the Canary Slide that traveled 600 km. Scar areas and slip planes have been investigated with particular emphasis. Although slide headwalls might present locally steep gradients (up to 23° for Storegga Slide), the slope gradients of both the failed segment margins and the main slip planes are very low (max. 2° and usually around 1° and less). An exception is the Finneidfjord Slide (20°–<5°) that occurred in 1996 because of a combination of climatic and anthropogenic factors leading to excess pore pressure and failure. Mechanically distinct, low permeable clayey “weak layers” often correspond to slip planes beyond the slide headwall. Since not only formation of these “weak layers” but also sedimentation rates are climatically controlled, we can state that slide pre-conditioning is climatically driven too. Run-out distances reflect the degree of disintegration of the failed mass of sediment, the total volume of initially failed material and transport mechanisms, including hydroplanning. Commonly, specific run-outs could be attributed to distinct elements, such as cohesive blocks and looser matrix, as nicely illustrated by the BIG'95 Slide. Total run-outs usually correspond to matrix run-outs since the coarser elements tend to rest at shorter distances. Outrunner blocks are, finally, a very common feature proving the ability of those elements to glide over long distances with independence of the rest of the failed mass. In addition to pre-conditioning factors related to geological setting and sedimentation conditions, a final trigger is required for submarine landslides to take place, which is most often assumed to be an earthquake. In high latitude margins, earthquake magnitude intensification because of post-glacial isostatic rebound has likely played a major role in triggering landslides. Although it cannot be totally ruled out, there is little proof, at least amongst the COSTA slides, that gas hydrate destabilisation or other processes linked to the presence of shallow gas have acted as final triggers.
Keywords: Antarktis; batymetri; geofysikk; marin geologi

Fiskerier i Antarktis (6.4) - Dommasnes, Are; Iversen, Svein A; Løbach, Terje (Havets ressurser 2004 (Fisken og havet : Særnummer), 2004)
Keywords: Antarktis; fangst; fiskeindustri; fiskeriforskning; krill; ressurser

Antarktis: gamle gneiser og spektakulære granitter - Engvik, Ane K; Elvevold, Synnøve (Geo: energi & ressurser, 2004)
Keywords: Antarktis; Dronning Maud Land; geologi

Seasonal ventilation of the cavity beneath Filchner-Ronne Ice Shelf simulated with an isopycnic coordinate ocean model - Jenkins, Adrian; Holland, David M.; Nicholls, Keith W.; Schröder, Michael; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
The ocean cavity beneath Filchner-Ronne Ice Shelf is observed to respond to the seasonal cycle of water mass production on the continental shelf of the southern Weddell Sea. Here we use a numerical model to investigate the propagation of newly formed shelf waters into the cavity. We find that the model reproduces the most distinctive features of the observed seasonality and offers a plausible explanation for those features. The most saline shelf waters are produced in the far west, where the inflow to the cavity peaks twice each year. The major peak occurs during the short period around midwinter when convection reaches full depth and the densest waters are generated. Once the surface density starts to decline, dynamic adjustment of the restratified water column leads to a gradual fall in the salinity at depth and a secondary peak in the inflow that occurs in summer at the western coast. Beneath the ice shelf the arrival of the wintertime inflow at the instrumented sites is accompanied by a rapid warming, while the slower decline in the inflow leads to a more gradual cooling. Water brought in by the secondary, summer peak flows mainly to the eastern parts of the cavity. Here the seasonality is suppressed because the new inflows mix with older waters that recirculate within a topographic depression. This pooling of waters in the east, where the primary outflow of Ice Shelf Water is generated, dampens the impact of seasonality on the local production of Weddell Sea Bottom Water.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi

Pole-to-pole validation of Envisat GOMOS ozone profiles using data from ground-based and balloon sonde measurements - Meijer, Yasjka; Swart, Daan P J; Allaart, M; Andersen, S B; Bodeker, G; Boyd, I; Braathen, Geir; Calisesi, Yasmine; Claude, H; Dorokhov, Valery; von der Gathen, P; Gil, M; et al. (Journal of Geophysical Research: Atmospheres, 2004)
In March 2002 the European Space Agency (ESA) launched the polar-orbiting environmental satellite Envisat. One of its nine instruments is the Global Ozone Monitoring by Occultation of Stars (GOMOS) instrument, which is a medium-resolution stellar occultation spectrometer measuring vertical profiles of ozone. In the first year after launch a large group of scientists performed additional measurements and validation activities to assess the quality of Envisat observations. In this paper, we present validation results of GOMOS ozone profiles from comparisons to microwave radiometer, balloon ozonesonde, and lidar measurements worldwide. Thirty-one instruments/launch sites at twenty-five stations ranging from the Arctic to the Antarctic joined in this activity. We identified 6747 collocated observations that were performed within an 800-km radius and a maximum 20-hour time difference of a satellite observation, for the period between 1 July 2002 and 1 April 2003. The GOMOS data analyzed here have been generated with a prototype processor that corresponds to version 4.02 of the operational GOMOS processor. The GOMOS data initially contained many obviously unrealistic values, most of which were successfully removed by imposing data quality criteria. Analyzing the effect of these criteria indicated, among other things, that for some specific stars, only less than 10% of their occultations yield an acceptable profile. The total number of useful collocated observations was reduced to 2502 because of GOMOS data unavailability, the imposed data quality criteria, and lack of altitude overlap. These collocated profiles were compared, and the results were analyzed for possible dependencies on several geophysical (e.g., latitude) and GOMOS observational (e.g., star characteristics) parameters. We find that GOMOS data quality is strongly dependent on the illumination of the limb through which the star is observed. Data measured under bright limb conditions, and to a certain extent also in twilight limb, should be used with caution, as their usability is doubtful. In dark limb the GOMOS data agree very well with the correlative data, and between 14- and 64-km altitude their differences only show a small (2.5–7.5%) insignificant negative bias with a standard deviation of 11–16% (19–63 km). This conclusion was demonstrated to be independent of the star temperature and magnitude and the latitudinal region of the GOMOS observation, with the exception of a slightly larger bias in the polar regions at altitudes between 35 and 45 km.
Keywords: Antarktis; fjernmåling; meteorologi; målinger; ozonlaget; polarområdene; stratosfæren

Circulation and water masses beneath the northern Ronne Ice Shelf, Antarctica - Nicholls, Keith W.; Makinson, Keith; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
We present oceanographic data from beneath the northern Ronne Ice Shelf. The data were collected during the austral summer of 2002–2003 from four sites located near the ice front in the Ronne Depression. They consist of conductivity-temperature-depth (CTD) profiles and time series from moored instruments that vary in length from 9 to 20 weeks. A strong, tidally modulated inflow of relatively fresh water was found at the eastern margin of the Ronne Depression. This low-density inflow powers high basal melt rates that are responsible for a substantially thinned area of ice shelf. A northward flow of Ice Shelf Water along the western margin of the depression (the Antarctic Peninsula coast) was inferred from the CTD data. From the new CTD and current meter data, and from published results from cruises along the ice front, we suggest that the flows at the margins of the Ronne Depression establish east-west density gradients that drive an anticyclonic circulation within the depression. The barotropic component of the circulation forms a gyre of strength 5 × 105 m3 s−1 and occupies a bowl in the field of water column thickness in the northern portion of the depression. All water masses sampled had temperatures below the surface freezing point and are therefore classified as Ice Shelf Water. The relatively complex nature of the oceanographic regime in the Ronne Depression is overlain by a seasonal variability that is hinted at by the available time series, probably explaining the apparent absence of inflowing HSSW at the time of the measurements.
Keywords: Antarktis; geofysikk; isfront; isshelf; oseanografi; vannmasser

Interannual variability and ventilation timescales in the ocean cavity beneath Filchner-Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
Multiyear time series of ocean current and temperatures from beneath Filchner-Ronne Ice Shelf, Antarctica, demonstrate both seasonal and interannual variability. The seasonal signal is visible at all measurement sites, although it was swamped for a 2-year period (1999–2001) when extraordinarily light sea-ice cover in the southern Weddell Sea during the 1997–1998 Austral summer caused an anomalously large pulse of High Salinity Shelf Water to flush beneath the ice shelf. The pulse was observed twice at an instrumented site near the Berkner Island coast, once on its way to the Filchner Depression and once after the signal had propagated around the depression and returned to the site as an anomalously large pulse of Ice Shelf Water. The timings of the signal allow an estimate of 24–30 months for the flushing timescales of the sub-ice shelf ocean cavity, indicating that the cavity is highly responsive to external forcing. A timescale for the full ventilation of the cavity of 4–5 years is obtained from the length of time the sub-ice shelf conditions take to return to their original state, a timescale significantly shorter than previous estimates.
Keywords: Antarktis; Weddellhavet; geofysikk; havstrømmer; oseanografi

Holocene climate in the Atlantic sector of the Southern Ocean: Controlled by insolation or oceanic circulation? - Nielsen, Simon Harder Holm; Koç, Nalân; Crosta, Xavier (Geology, 2004)
The Holocene climate of the Southern Ocean is not well understood, mainly because of the lack of high-resolution reconstructions of ocean surface properties. Here we present a 12,500-yr-long, decadal-scale record of Holocene sea-surface temperatures and sea- ice presence from the Polar Front of the East Atlantic Southern Ocean. The record shows gradual climate change, with no abrupt Neoglacial cooling, and an unprecedented late Holocene warming. The dominant forcing factor appears to be precessional insolation; Northern Hemisphere summer insolation correlates to at least the early to middle Holocene climate trend. Spectral analysis reveals centennial-scale cyclic climate changes with periods of 1220, 1070, 400, and 150 yr. The record shows good correlation to East Antarctic ice cores and to climate records from South Georgia and Bunger Oasis. However, the record shows out-of-phase behavior with regard to climate records from the western Antarctic Peninsula and the Peru-Chile Current; such behavior hints at a climatic divide through Patagonia, the Drake Passage, and between West and East Antarctica.
Keywords: Antarktis; Sørishavet; geologi; havis; klimaendringer; paleoklimatologi

Additions and corrections to the Lichens of Antarctica and South Georgia - Øvstedal, Dag; Smith, Ronald I. Lewis (Cryptogamie, Mycologie, 2004)
The taxonomic listing given in Lichens of Antarctica and South Georgia (Øvstedal & Lewis Smith 2001) has been updated. 17 additional taxa of lichenised fungi are described, including several nomenclatural changes. 14 of these are considered as new records for the Antarctic and one is new to South Georgia. One is described as new to science.
Keywords: Antarktis; biogeografi; botanikk; lav; planter; taksonomi

Improved Seismic Stratigraphy of the Mesozoic Weddell Sea - Rogenhagen, Johannes; Jokat, Wilfried; Hinz, Karl; Kristoffersen, Yngve (Marine Geophysical Researches, 2004)
We present a compilation of more than 45,000 km of multichannel seismic data acquired in the last three decades in the Weddell Sea. In accordance with recent tectonic models and available drillhole information, a consistent stratigraphic model for depositional units W1–W5 is set up. In conjunction with existing aeromagnetic data, a chronostratigraphic timetable is compiled and units W1.5, W2 and W3 are tentatively dated to have ages of between 136 Ma and 114 Ma. The age of W3 is not well constrained, but might be younger than 114 Ma. The data indicate that the thickest sediments are present in the western and southern Weddell Sea. These areas formed the earliest basins in the Weddell Sea and so the distribution of Mesozoic sediments is in accordance with the tectonic development of the ocean basin. In terms of Cenozoic glacial sediments, the largest depocenters are situated in front of the Filchner–Ronne Shelf, i.e. at the Crary Fan, with a thickness of up to 3 km.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi; seismologi; stratigrafi; tektonikk

Frazil ice formation in an ice shelf water plume - Smedsrud, Lars H.; Jenkins, Adrian (Journal of Geophysical Research: Oceans, 2004)
We present a model for the growth of frazil ice crystals and their accumulation as marine ice at the base of Antarctic ice shelves. The model describes the flow of buoyant water upward along the ice shelf base and includes the differential growth of a range of crystal sizes. Frazil ice formation starts when the rising plume becomes supercooled. Initially, the majority of crystals have a radius of ?0.3 mm and concentrations are below 0.1 g/L. Depending on the ice shelf slope, which controls the plume speed, frazil crystals increase in size and number. Typically, crystals up to 1.0 mm in radius are kept in suspension, and concentrations reach a maximum of 0.4 g/L. The frazil ice in suspension decreases the plume density and thus increases the plume speed. Larger crystals precipitate upward onto the ice shelf base first, with smaller crystals following as the plume slows down. In this way, marine ice is formed at rates of up to 4 m/yr in some places, consistent with areas of observed basal accumulation on Filchner-Ronne Ice Shelf. The plume continues below the ice shelf as long as it is buoyant. If the plume reaches the ice front, its rapid rise produces high supercooling and the ice crystals attain a radius of several millimeters before reaching the surface. Similar ice crystals have been trawled at depth north of Antarctic ice shelves, but otherwise no observations exist to verify these first predictions of ice crystal sizes and volumes.
Keywords: Antarktis; geofysikk; glasiologi; numerisk modellering; oseanografi

Evidence for orbitally controlled size variations of the East Antarctic Ice Sheet during the late Miocene - Grützner, J.; Rebesco, M.A.; Cooper, A.K.; Forsberg, C.F.; Kryc, K.A.; Wefer, G. (Geology, 2003)
Ocean Drilling Program Site 1165 penetrated drift sediments on the East Antarctic continental rise and recovered sediments from a low-energy depositional environment. The sediments are characterized by prominent alternations between a green to greenish-gray diatom-bearing hemipelagic facies and gray to dark gray hemiturbiditic facies. Our investigation of an upper Miocene section, using high-resolution color spectra, multisensor core logs, and X-ray fluorescence scans, reveals that sedimentation changes occur at Milankovitch orbital frequencies of obliquity and precession. We use this finding to derive an astronomical calibrated time scale and to calculate iron mass-accumulation rates, as a proxy for sediment-accumulation rates. Terrigenous iron fluxes change by as much as 100% during each obliquity cycle. This change and an episodic pattern of enhanced ice-rafted debris deposition during times of deglaciation provide evidence for a dynamic and likely wet-based late Miocene East Antarctic Ice Sheet (EAIS) that underwent large size variations at orbital time scales. The dynamic behavior of the EAIS implies that a significant proportion of the variability seen in oxygen isotope records of the late Miocene reflects Antarctic ice-volume changes.
Keywords: Antarktis; Sørishavet; geologi; glasiologi; maringeologi; paleoklimatologi

Utfordringene for legene ved polarekspedisjoner omkring år 1900 - Albretsen, Carl Severin (Tidsskrift for den Norske Laegeforening, 2003)
Keywords: Antarktis; medisin; polarkespedisjoner

In the wake of Tønnessen and Johnsen : trends in whaling history research after 1970 - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2003)
Keywords: Antarktis; Norge; husholdning; hvalfangere; hvalfangst; pelagisk; økonomisk historie

Some features of electron density behaviour in the high latitude D-region derived from in situ measurements - Danilov, A.D.; Smirnova, N.V.; Blix, Tom Arild; Thrane, E.V.; Vanina, L.B. (Journal of Atmospheric and Solar-Terrestrial Physics, 2003)
A large database of rocket measurements of the D-region electron concentration has been studied. The data were obtained at four sites in the Antarctic (Molodezhnaya and Syowa) and Arctic (Heiss Island, and Andøya/Kiruna). The electron densities were analysed in terms of their variations with solar zenith angle, geomagnetic activity and atmospheric temperature. We found that there is a particle ionisation source in the auroral oval even in quiet conditions. The energy of the particles is such, that they penetrate down to 85km, are partially absorbed between 85 and 80km but do not penetrate (are completely absorbed) below 75km. Analysis of the dependence of the electron concentration [e] on the daily sum of Kp indices, ∑Kp, shows that at all heights considered there is an increase of [e] with ∑Kp up to some saturation value of ∑Kp and beyond this level [e] is either constant (with large scatter of the data) or even decreases. This indicates that when the auroral oval expands with increasing geomagnetic activity, a particular station may move from a position outside or at the boundary of the oval, to a position inside the polar cap. An attempt is made to find the temperature dependence of the electron concentration. It is found that [e] at 75 and 80km increases with temperature T. Analysis of the flights conducted during noctilucent cloud (NLC) events at Andøya/Kiruna reveals a strong dependence of [e] on ∑Kp at 80 and 85km. This dependence is stronger and better defined than that for the entire data set. This may be explained by the low mesopause temperatures observed in summer when NLC occur. A comparison of the electron density data sets with empirical and theoretical models is presented and during quiet magnetic conditions a good agreement with mid-latitude models is found.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

Magnitude scales for very local earthquakes. Application for Deception Island Volcano (Antarctica) - Havskov, Jens; Peña, José A; Ibáñez, Jesús M; Ottemöller, Lars; Martı́nez-Arévalo, Carmen (Putting Volcano Seismology in a Physical Context. In memory of Bruno Martinelli, 2003)
Different magnitude scales are calculated for a set of volcano-tectonic earthquakes recorded in Deception Island Volcano (Antarctica). The data set includes earthquakes recorded during an intense seismic series that occurred in January–February 1999, with hypocentral distances that range between 0.5 and 15 km. This data set is enlarged to include some regional earthquakes with hypocentral distances up to 200 km. The local magnitude scale, ML, fixed at a hypocentral distance of 17 km, is used as the reference for the other magnitude scales studied in the present work. ML is determined on a standard Wood–Anderson simulated trace assuming a gain of 2080. Maximum peak-to-peak amplitudes are measured on the vertical components of a short-period sensor. The Mw scale is calculated, in the vertical component, both for P and S waves. The attenuation correction of the ground motion displacement spectra is introduced using data from coda waves studied in the area. The comparison between ML values and Mw estimations indicates severe discrepancies between both values. A magnitude–duration scale is calibrated from the comparison between coda durations of the recorded events and their assigned local magnitude scales. In order to investigate the causes of the discrepancy between the ML and Mw values we analyze two possible error sources: a wrong coda Q value, or the effects of the near-surface attenuation that initially are not taken into account in the correction of the ground displacement spectra. The analysis reveals that the main cause of this discrepancy is the effect of the near-surface attenuation. The near-surface attenuation is also the cause of the determination of an anomalous spectral decay slope, after the corner frequency, and the determination of this corner frequency value. This near-surface attenuation, represented by κ, is estimated over the data set, obtaining an average value of 0.025. With this κ value, the Mw scale is recalculated using an automatic algorithm. The new Mw values are more consistent with the ML values, obtaining a relationship of Mw=0.78ML−0.02.
Keywords: Antarktis; Deceptionøya; geologi; vulkaner

Glacial and Climate History of the Antarctic Peninsula since the Last Glacial Maximum - Ingólfsson, Ólafur; Hjort, Christian; Humlum, Ole (Arctic, Antarctic, and Alpine Research, 2003)
During the Last Glacial Maximum (LGM), ice thickened considerably and expanded toward the outer continental shelf around the Antarctic Peninsula. Deglaciation occurred between >14 ka BP and ca. 6 ka BP, when interglacial climate was established in the region. Deglaciation of some local sites was as recent as 4?3 ka BP. After a climate optimum, peaking ca. 4?3 ka BP, a distinct climate cooling occurred. It is characterized at a number of sites by expanding glaciers and ice shelves. Rapid warming during the past 50 yr may be causing instability of some Antarctic Peninsula ice shelves. Detailed reconstructions of the glacial and climatic history of the Antarctic Peninsula since LGM are hampered by scarcity of available archives, low resolution of many datasets, and problems in dating samples. Consequently, the configuration of LGM ice sheets, pattern of subsequent deglaciation, and environmental changes are poorly constrained both temporally and spatially.
Keywords: Antarktis; glasiologi; klimaendringer; marin geologi; paleoklimatologi

Blant pelssel og pingvinar. Ei julereise til Sør-Georgia og Antarktis - Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2003)
Keywords: Antarktis; cruiseturisme; dagbøker; polareksspedisjoner; reisebeskrivelser; reiseskildringer

Women and couples in isolated extreme environments: applications for long-duration missions - Leon, Gloria R.; Sandal, Gro Mjeldheim (Acta Astronaut, 2003)
Expedition teams provide a number of analogs relevant to crew selection for long-duration space missions. Three groups were studied that varied in team composition. Group 1 was a two woman international dyad that traversed the Antarctic continent in 97 days. Similarities in problem solving approach, respect for each other's opinions, and a collaborative process of decision making were evident. Group 2 was composed of four women, all from different countries, engaged in a six week trek across Greenland. The most important factors in overcoming interpersonal difficulties and contributing to the successful completion of the expedition were mutual respect and motivation to maintain positive and supportive relationships. Group 3 consisted of three married couples from different countries icelocked on a boat in the High Arctic for a 9 month period. The emotional support of and ability to confide in their partner were extremely important in alleviating interpersonal tensions, and contributed to the generally effective functioning of the group. Women add an element of emotional support and help to other team members that is not as evident in all-male groups. Selection of couples with strong bonds to each other is another paradigm for crew selection for extended missions.
Keywords: Antarktis; polareksspedisjoner; polarforskere; polarområdene; psykologi

The making and unmaking of a supercontinent: Rodinia revisited - Meert, Joseph G.; Torsvik, Trond H. (Orogenic Belts, Regional and Global Tectonics: A Memorial Volume to Chris McAulay Powell, 2003)
During the Neoproterozoic, a supercontinent commonly referred to as Rodinia, supposedly formed at ca. 1100 Ma and broke apart at around 800–700 Ma. However, continental fits (e.g., Laurentia vs. Australia–Antarctica, Greater India vs. Australia–Antarctica, Amazonian craton [AC] vs. Laurentia, etc.) and the timing of break-up as postulated in a number of influential papers in the early–mid-1990s are at odds with palaeomagnetic data. The new data necessitate an entirely different fit of East Gondwana elements and western Gondwana and call into question the validity of SWEAT, AUSWUS models and other variants. At the same time, the geologic record indicates that Neoproterozoic and early Paleozoic rift margins surrounded Laurentia, while similar-aged collisional belts dissected Gondwana. Collectively, these geologic observations indicate the breakup of one supercontinent followed rapidly by the assembly of another smaller supercontinent (Gondwana). At issue, and what we outline in this paper, is the difficulty in determining the exact geometry of the earlier supercontinent. We discuss the various models that have been proposed and highlight key areas of contention. These include the relationships between the various ‘external’ Rodinian cratons to Laurentia (e.g., Baltica, Siberia and Amazonia), the notion of true polar wander (TPW), the lack of reliable paleomagnetic data and the enigmatic interpretations of the geologic data. Thus, we acknowledge the existence of a Rodinia supercontinent, but we can place only loose constraints on its exact disposition at any point in time.
Keywords: Antarktis; Dronning Maud Land; geologi; paleogeografi

Moment Magnitude Determination for Local and Regional Earthquakes Based on Source Spectra - Ottemöller, Lars; Havskov, Jens (Bulletin of the Seismological Society of America, 2003)
We investigated the use of an automated routine to determine moment magnitudes from the displacement spectra of local and regional earthquakes. Two algorithms, a genetic algorithm and a converging grid search, were developed and tested with earthquake data from Mexico, Norway, and Deception Island (Antarctica). It was found that compared with manual analysis, the algorithms give reliable automatic moment magnitude (Mw) estimates in the range -1 < M < 8. The converging grid search appeared to be more cost-effective than the genetic algorithm. Mw at local and regional distances seems superior to amplitude-based magnitudes that saturate for large earthquakes. The application of the automated algorithm in near real time may help to obtain a nonsaturated magnitude estimate in the case of a large earthquake immediately after the earthquake has occurred. Also, the method can be useful for processing large amounts of data.
Keywords: Antarktis; Deceptionøya; Sør-Shetlandsøyene; seismologi

Radionuclides deposition over Antarctica - Pourchet, Michel; Magand, Olivier; Frezzotti, Massimo; Ekaykin, Alexey A.; Winther, Jan Gunnar (Journal of Environmental Radioactivity, 2003)
A detailed and comprehensive map of the distribution patterns for both natural and artificial radionuclides over Antarctica has been established. This work integrates the results of several decades of international programs focusing on the analysis of natural and artificial radionuclides in snow and ice cores from this polar region. The mean value (37±20 Bq m−2) of 241Pu total deposition over 28 stations is determined from the gamma emissions of its daughter 241Am, presenting a long half-life (432.7 yrs). Detailed profiles and distributions of 241Pu in ice cores make it possible to clearly distinguish between the atmospheric thermonuclear tests of the fifties and sixties. Strong relationships are also found between radionuclide data (137Cs with respect to 241Pu and 210Pb with respect to 137Cs), make it possible to estimate the total deposition or natural fluxes of these radionuclides. Total deposition of 137Cs over Antarctica is estimated at 760 TBq, based on results from the 90–180° East sector. Given the irregular distribution of sampling sites, more ice cores and snow samples must be analyzed in other sectors of Antarctica to check the validity of this figure.
Keywords: Antarktis; geofysikk; geologi; glasiologi; radioaktivitet

Sea ice formation on a very cold surface - Smedsrud, Lars Henrik; Saloranta, Tuomo; Haugan, Peter M; Kangas, Tor-Villy (Geophysical Research Letters, 2003)
In this study laboratory experiments of sea ice formed on a vertical surface with initial temperature of −30 to −50°C are presented. The ice formation is rapid, and in 300 s >5 mm of sea ice is formed. Ice formation cooled and salinified the water, and induced a vertical down wards flow of ∼5 mm/s with a boundary layer about 5 mm thick. This ice has a structure with columnar crystals that have small circular cross sections (0.2–1.0 mm) and sea ice salinities are between 24 and 32. A simple model approach indicate that the thermal conductivity of such ice is lower than for other types of sea ice.
Keywords: Antarktis; geofysikk; glasiologi; havis; innlandsis; isshelf; laboratorieeksperimenter; polarområdene; sjøis

Tvers over Antarktis: Bancroft Arnesen Expedition Antarctica 2000-2001 - Arnesen, Liv (Polarboken, 2002)
Keywords: Antarktis; ekspedisjoner

Selv under ekstreme betingelser har man liv, finnes det også liv utenfor jorda? - Brunfelt, Arild O (Naturen, 2002)
Livets opprinnelse er et mysterium. Ikke desto mindre er mange forskere beskjeftiget med å forsøke og rekonstruere dette. Moderne forskning på livet under ekstreme betingelser på Jorda som f.eks. i dyphavet, i en innsjø under isen i Antarktis eller i en gruppe sjeldne meteoritter, har ført til en viss optimisme når det gjelder å finne liv på planeten Mars og på Jupiters månesatelliter Europa, Callisto og Ganymede.
Keywords: Antarktis; kjemiske analyser; mikrober; mikrobiologi; subglasial innsjø

Cryogenic grooves on a granite nunatak, Northern Victoria Land, Antarctica - French, Hugh; Guglielmin, Mauro (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2002)
Keywords: Antarktis; glasiologi; nunataker

Snow grain-size measurements in Antarctica - Gay, Michael; Fily, Michel; Genthon, Christophe; Frezzotti, Massimo; Oerter, Hans; Winther, Jan-Gunnar (Journal of Glaciology, 2002)
Grain-size is an important but not well-known characteristic of snow at the surface of Antarctica. In the past, grain-size has been reported using various methods, the reliability, reproducibility and intercomparability of which is not warranted. In this paper, we present and recommend, depending on available logistical support, three techniques of snow-grain sampling and/or imaging in the field as well as an original digital image-processing method, which we have proved provides reproducible and intercomparable measures of a snow grain-size parameter, the mean convex radius. Results from more than 500 samples and 3000 images of snow grains are presented, which yield a still spatially limited yet unprecedentedly wide picture of near-surface snow grain-size distribution from fieldwork in Antarctica. In particular, except at sites affected by a very particular meteorology, surface grains in the interior of the ice sheet are uniformly small (0.1–0.2 mm). The climate-related increase of grain-size with depth through metamorphism is, as expected, not spatially uniform. Our Antarctic snow grain-size database will continue to grow as field investigations bring new samples, images and measures of snow grain.
Keywords: Antarktis; glasiologi; paleoklimatologi

Glacial history of the Antarctic Peninsula since the Last Glacial Maximum–a synthesis - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 2002)
The extent of ice, thickness and dynamics of the Last Glacial Maximum (LGM) ice sheets in the Antarctic Peninsula region, as well as the pattern of subsequent deglaciation and climate development, are not well constrained in time and space. During the LGM, ice thickened considerably and expanded towards the middle–outer submarine shelves around the Antarctic Peninsula. Deglaciation was slow, occurring mainly between >14 Ky BP (14C kilo years before present) and ca. 6 Ky BP, when interglacial climate was established in the region. After a climate optimum, peaking ca. 4 - 3 Ky BP, a cooling trend started, with expanding glaciers and ice shelves. Rapid warming during the past 50 years may be causing instability to some Antarctic Peninsula ice shelves.
Keywords: Antarktis; glasiologi; klimaendringer; marin geologi; paleoklimatologi

Klarius Mikkelsen's landing site: some further notes on the 1935 Norwegian visit to the Vestfold Hills, East Antarctica - Norman, Frederick Ian; Gibson, John A E; Jones, R T; Burgess, J S (Polar Record, 2002)
Further details regarding the landing made by Klarius Mikkelsen in the Tryne Islands, Vestfold Hills, East Antarctica, are given, being derived mainly from newspaper accounts made by Leif Sørsdal. All involved in the landing on 20 February 1935 have been identified, details of material left in the depot under the raised flag are given, and more extended information relating to the voyage to and from the site and the area generally are presented. Some comparison is made between Sørsdal's accounts and others. While the national importance of the landing was commented on, only Sørsdal apparently realised (but did not state) the insular nature of the site. Recent observations at the site suggest that its location is 68°22′38.22″S, 78°24′50.10″E, rather than that previously stated; bracing of the flagpole itself has been modified at some stage since its erection. Finally, some discussion is made regarding on-going questions relating to the accepted time on board ship, and possible consequences of errors.
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser

The gastrointestinal tract of Adélie penguins – morphology and function - Olsen, Monica; Myklebust, Reidar; Kaino, Turid; Elbrønd, Vibeke; Mathiesen, Svein (Polar Biology, 2002)
Keywords: Antarktis; pingviner; zoologi

Comparison of measurements and model calculations of stratospheric bromine monoxide - Sinnhuber, Björn‐Martin; Arlander, D William; Bovensmann, H; Burrows, J P; Chipperfield, M P; Enell, Carl-Fredrick; Frieß, U; Hendrick, F; Johnston, P V; Jones, R L; Kreher, K; Mohamed-Tahrin, N; et al. (Journal of Geophysical Research: Atmospheres, 2002)
Ground-based zenith sky UV–visible measurements of stratospheric bromine monoxide (BrO) slant column densities are compared with simulations from the SLIMCAT three-dimensional chemical transport model. The observations have been obtained from a network of 11 sites, covering high and midlatitudes of both hemispheres. This data set gives for the first time a near-global picture of the distribution of stratospheric BrO from ground-based observations and is used to test our current understanding of stratospheric bromine chemistry. In order to allow a direct comparison between observations and model calculations, a radiative transfer model has been coupled to the chemical model to calculate simulated slant column densities. The model reproduces the observations in general very well. The absolute amount of the BrO slant columns is consistent with a total stratospheric bromine loading of 20 ± 4 ppt for the period 1998–2000, in agreement with previous estimates. The seasonal and latitudinal variations of BrO are well reproduced by the model. In particular, the good agreement between the observed and modeled diurnal variation provides strong evidence that the BrO-related bromine chemistry is correctly modeled. A discrepancy between observed and modeled BrO at high latitudes during events of chlorine activation can be resolved by increasing the rate constant for the reaction BrO + ClO → BrCl + O2 to the upper limit of current recommendations. However, other possible causes of the discrepancy at high latitudes cannot be ruled out.
Keywords: Antarktis; atmosfæren; fysikk; kjemiske analyser; meteorologi; miljø; målinger; polarområdene; stratosfæren

Mindre is i et varmere Antarktis - Smedsrud, Lars Henrik; Rolstad, Cecilie (Cicerone, 2002)
Keywords: Antarktis; global oppvarming; issmelting; klimaendringer; populærvitenskap

Helse på hvalfangst - Thoresen, Per (Vestfoldminne, 2002)
Keywords: Antarktis; arbeidsforhold; erindringer; helse; hvalfangere; hvalfangst; lege; medisin; pelagisk; sjøfolk; sjømenn

Body Condition and Parental Decisions in the Snow Petrel (Pagodroma nivea) - Tveraa, Torkild; Guttorm, N. Christensen (The Auk, 2002)
In Procellariiformes, parents guard the chick for some time after it has attained homeothermy. Such a strategy may have evolved to protect the chick from predation or inclement weather, but it is costly because only one parent can forage at a time. Therefore, the decision to leave the chick seems to be a trade-off between the chick's ability to care for itself, body condition of the parent present at the nest, and ability of the bird out foraging to return to the nest before its mate's body condition has degraded. We studied chick growth and survival together with number of days Snow Petrel (Pagodroma nivea) chicks were guarded before being left alone for the first time in relation to the parents body condition and ability to return to the nest in time. Parents in good body condition were more likely to produce a chick that survived the guard stage. They also guarded their chick for a longer period (range 2–8 days, x̄ = 4.5) and finally left it alone with a higher body mass than those in poor body condition. However, whether the foraging bird was able to return to the nest in time to relieve its mate was also strongly related to number of days the chick was guarded and its body mass. The chicks' survival from when they were left alone and until day 10 posthatch was positively related both to number of days they were guarded and their body condition (body mass corrected for age).
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi

Effect of isolation temperature on the characteristics of extracellular proteases produced by Antarctic bacteria - Vazquez, Susana C; Mac Cormack, Walter P (Polar Research, 2002)
Protease-producing psychrotolerant bacteria were isolated from Antarctic biotopes on casein agar plates using different incubation temperatures. Most of the isolates were non-spore-forming Gram-negative motile rods with catalase activity, 30% were pigmented and none of them were glucose fermenters. All the strains were grown in liquid cultures at 20°C and protease secretion was tested using the azocasein method. Despite their capacity for production of a clear zone of hydrolysis in agar plates, some strains did not produce detectable levels of proteolytic activity in liquid cultures. The lowest apparent optimum temperature for protease activity found in culture supernatants was 40°C. Almost all the strains showed activation energy values about 10-20 kJ-mol?1 lower than that observed for a mesophilic Subtilisin. Most of the proteases showed optimal activity at neutral or alkaline pH values and developed a multiple-band profile on gelatine-SDS-PAGE. It was observed that the lower the strain isolation temperature was, the more stongly cold-adapted–in terms of optimal temperature and activation energy–were the proteases produced by them. This dependence of the characteristics of the proteases on the isolation temperature is an important factor to take into account in the design of screening programmes directed towards the isolation of psychrotolerant bacteria able to produce proteases strongly or weakly adapted to work in the cold. The Antarctic area explored proved to be a promising source of proteolytic bacteria with potential use in industrial processes to be carried out at low or moderate temperatures.
Keywords: Antarktis; analyser; bakterier; ekspedisjoner; mikrobiologi

The protocol on environmental protection to the Antarctic Treaty: a ten-year review - Vidas, Davor (Yearbook of international co-operation on environment and development, 2002)
Keywords: Antarktis; jus; miljøvern

Research on Antarctic affairs at the FNI (Nansen news, 2001)
Keywords: Antarktis; forskning

Norwegian use of the polar oceans as occupational arenas and exploration routes - Barr, Susan (Polar Record, 2001)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; forskning; geografi; historie; oppdagelsesreiser; polarområdene

Holocene and pre-Holocene temporary disappearance of the George VI Ice Shelf, Antarctic Peninsula - Bentley, Michael J.; Hjort, Christian; Ingólfsson, Ólafur (Antarctic Science, 2001)
We present evidence for the absence of the George VI Ice Shelf during a brief period in the mid-Holocene and during one or more earlier interstadials or interglacials. Barnacle Bathylasma corolliforme shells sampled from ice shelf moraines at Two Step Cliffs on Alexander Island have been dated to c, 5750–6000 14C yr BP(c. 6550–6850 cal yr BP) and imply seasonally open water in the George VI Sound during this period. Other shells are beyond the range of radiocarbon dating and imply open water during one or more previous interglacial or interstadial period, prior to 40 000 14C yr BP. Our results show that the ongoing collapse of some Antarctic Peninsula ice shelves is not unprecedented.
Keywords: Antarktis; geomorfologi; glasiologi; holocene; isshelf

Electron density variations in the upper D region at high latitudes according to in situ measurements - Danilov, Alexey; Smirnova, N.V.; Vanina-Dart, Liudmila; Blix, Tom Arild; Thrane, Eivind (Geomagnetism and Aeronomy, 2001)
A large set of rocket measurements of the electron concentration [e] in the upper D region at four rocket sites (Molodezhnaya (Antarctic), Heiss Island (Arctic), Syowa (Antarctic), and Andoya/Kiruna (Arctic)) is considered. The dependence of [e] on the solar zenith angle X and geomagnetic activity index ∑Kp is analyzed. It has been shown that, the spread in [e] values reaches two orders of magnitude at any assigned value of χ. Nevertheless, it is possible to draw a lower envelope for the entire set of points and to obtain the [e] variation with χ in undisturbed conditions. In an analysis of the envelopes, it is seen that a corpuscular ionization source (presumably, electrons with an energy of above 40 keV) exists in the nonsunlit D region even in quiet conditions. An analysis of the electron concentration dependence on the daily sum of ∑Kp indices (∑Kp) shows that, at all heights considered, increases [e] with increasing ∑Kp to a certain boundary value ∑Kp and then remains either constant (with a rather wide spread in the data) or even decreases. This saturation effect may be caused by the auroral oval equatorward motion. As a result of this motion the site position may change: it may move toward the boundary between the auroral oval and polar cap or even be within the latter. The slope k of the [e] variation plotted versus ∑Kp at different χ is considered. It is shown that k grows with increasing χ and is maximal at χ> 100°.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

Current measurements near Ronne Ice Shelf: implications for circulation and melting - Foldvik, Arne; Gammelsrød, Tor; Nygaard, E.; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2001)
We present the first year-long current meter records ever obtained near the floating Filchner-Ronne Ice Shelf in the Weddell Sea. The currents are steered along the ice front, but in the lower layer where the bottom topography is descending toward the west the current has a component toward the ice front of about 3 cm s−1. During winter the temperature stayed near the surface freezing point, while the salinity increased, indicating that ice was formed and brine released. The seasonal variation in salinity was 0.15±0.05 psu, corresponding to the formation of 1–2 m of ice on a shelf depth of 400 m. The transport of High-Salinity Shelf Water (HSSW) into the ice shelf cavity was found to be of the order 0.5×106 m3 s−1. The production of this water due to oscillating tides and off shelf winds was found to be of the same order of magnitude. In contact with glacial ice at great depths, and because of the depression of the freezing point, the HSSW is transformed to Ice Shelf Water (ISW) by cooling and melting processes. The melting rate was estimated to 1×1011 ton yr−1. This corresponds to the melting of 0.2 m ice per year if the melting is evenly distributed over the Filchner-Ronne Ice Shelf. If the melting is concentrated along a path from the Berkner Shelf around the Berkner Island to the Filchner Depression, then melting rates up to 7 m yr−1 must be expected. A comparison of HSSW characteristics in the Ronne Depression, our winter observations on the Berkner Shelf, and the ISW flowing out of the Filchner Depression indicates that very little water passes through the cavity from the Ronne to the Filchner Depression. It appears that most of the ISW originating from processes on the Berkner Shelf escapes the cavity in the Filchner Depression. This leaves the Berkner Shelf as the important source of ISW and subsequently of the Weddell Sea Bottom Water formed from ISW.
Keywords: Antarktis; Weddellhavet; havstrømmer; isshelf; oseanografi

Tropospheric response to stratospheric ozone loss - Kindem, Ina T; Christiansen, Bo (Geophysical Research Letters, 2001)
The response to realistic total column ozone trends on the troposphere and the stratosphere as simulated by the ARPEGE General Circulation Model (GCM) has been investigated. In both hemispheres, the lower stratosphere cooled and the polar vortex strengthened significantly during spring/early summer. The cooling trend was weaker than the observed trend in the Northern Hemisphere (NH), but stronger than the observed trend in the Southern Hemisphere (SH). In the troposphere, the changes in geopotential height resembled the positive phase of the Arctic Oscillation (AO) in the NH in March and the positive phase of the Antarctic Oscillation (AAO) in the SH during summer (December–February).
Keywords: Antarktis; geofysikk; meteorologi; ozonhull; ozonlaget

Measuring snow and glacier ice properties from satellite - König, Max; Winther, Jan-Gunnar; Isaksson, Elisabeth (Reviews of Geophysics, 2001)
Satellite remote sensing is a convenient tool for studying snow and glacier ice, allowing us to conduct research over large and otherwise inaccessible areas. This paper reviews various methods for measuring snow and glacier ice properties with satellite remote sensing. These methods have been improving with the use of new satellite sensors, like the synthetic aperture radar (SAR) during the last decade, leading to the development of new and powerful methods, such as SAR interferometry for glacier velocity, digital elevation model generation of ice sheets, or snow cover mapping. Some methods still try to overcome the limitations of present sensors, but future satellites will have much increased capability, for example, the ability to measure the whole optical spectrum or SAR sensors with multiple polarization or frequencies. Among the methods presented are the satellite-derived determination of surface albedo, snow extent, snow volume, snow grain size, surface temperature, glacier facies, glacier velocities, glacier extent, and ice sheet topography. In this review, emphasis is put on the principles and theory of each satellite remote sensing method. An extensive list of references, with an emphasis on studies from the 1990s, allows the reader to delve into specific topics.
Keywords: Antarktis; glasiologi; satellite bilder

Rapid climate shifts in the southern African interior throughout the Mid to Late Holocene - Lee-Thorp, Julia; Holmgren, Karin; Lauritzen, Stein Erik; Linge, Henriette; Moberg, Anders; Partridge, Timothy C; Stevenson, Chris; Tyson Peter D. (Geophysical Research Letters, 2001)
A detailed climate proxy record based on δ18O, δ13O, and grey index of a well-dated stalagmite from Cold Air Cave in the Makapansgat Valley of north-eastern South Africa suggests that regional precipitation, temperatures and vegetation oscillated markedly and rapidly over the last ∼6500 years on centennial and multi-decadal scales. The mid-Holocene prior to 5200 years ago was humid and warm. A fundamental transition occurred 3200 years ago, leading to drier and cooler conditions that culminated at 1750 AD. Comparisons with ice core records suggest synchronous changes implicating rapid global teleconnections.
Keywords: Antarktis; arkeologi; geografi; geologi; klimaendringer; klimatologi; paleontologi

Growing Gondwana and Rethinking Rodinia: A Paleomagnetic Perspective - Meert, Joseph G. (Gondwana Research, 2001)
The formation of Gondwana during the late Neoproterozoic to early Cambrian times (550-530 Ma) was traditionally viewed as the welding of two, more or less contiguous, Proterozoic continental masses called East and West Gondwana. The notion of a united West Gondwana is no longer tenable as a wealth of geochronologic and structural data indicate major orogenesis amongst its constituent cratons during the final stages of greater Gondwana assembly. The idea that East Gondwana may also have formed through the amalgamation of a collage of cratonic nuclei during the Cambrian is controversial. Recent paleomagnetic, geochronologic and structural data from elements of East Gondwana indicate that its formation may have extended well into Cambrian time. Thus, the terms ‘East’ and ‘West’ Gondwana may be relegated to convenient geographical terms rather than any connotation of tectonic coherence during the Proterozoic. In addition, the paleomagnetic data also challenge the conventional views of the Neoproterozoic supercontinent Rodinia and the SWEAT fit. Alternative variants including Protopangea and AUSWUS are not supported by paleomagnetic data during the interval 800–700 Ma.
Keywords: Antarktis; geokronologi; geologi; paleomagnetisme

Oceanographic conditions south of Berkner Island, beneath Filchner-Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Østerhus, Svein; Makinson, Keith; Johnson, Michaela R. (Journal of Geophysical Research: Oceans, 2001)
We have made oceanographic measurements at two sites beneath the southern Filchner-Ronne Ice Shelf. Hot-water drilled access holes were made during January 1999, allowing conductivity-temperature-depth (CTD) profiling and the deployment of instrument moorings. The CTD profiles show that the entire water column is below the surface freezing point. We estimate the (summer) flux of water between the two sites to be 2×106 m3 s−1. The summer potential temperature-salinity properties of the water column suggest that this flow is part of a recirculation in the deepest part of the subice shelf cavity and the Filchner Depression. The recirculation is driven by a combination of the melting of deep basal ice and the freezing that results from the depressurization of the cold buoyant water as it ascends the ice shelf base. The source of the water was high-salinity shelf water (HSSW) produced in the Ronne Depression. This is the water that provides the external heat necessary for the strong melting at the deep grounding lines in the vicinity of Foundation Ice Stream. Instruments moored at the drill sites show that during the winter HSSW formed on the Berkner Shelf flows beneath the ice shelf and largely displaces the recirculating water from the two sites. This provides an externally driven through flow that is warmer (nearer the surface freezing point) and slower than the internal recirculation and which is low enough in density to escape the Filchner Depression.
Keywords: Antarktis; geofysikk; havstrømmer; oseanografi

Quantitative models for reconstructing catchment ice-extent using physical-chemical characteristics of lake sediments - Noon, P.E.; Birks, H.J.B.; Jones, V.J.; Ellis-Evans, J.C. (Journal of Paleolimnology, 2001)
The physical characteristics of surface sediments from a suite of pristine lakes on Signy Island, maritime Antarctic, were used to develop a quantitative link between catchment ice-extent and lake-sediment response. Percentage dry weight, median particle size, percentage loss-on-ignition and wet density of the lakes' surface sediments were the most significant variables explaining contemporary catchment ice-extent. Two independent reconstruction models – Partial Least Squares (PLS) and a Modern Analog Technique (MAT) – were applied to dated sediment cores at two sites on Signy Island. The validity of the reconstructions was tested against historical information on catchment ice-extent. With sufficiently high sedimentation rates and sampling resolution, the models can predict sub-decadal changes in ice-extent. The model results are best regarded as indicators of erosion resulting from meltwater activity in the catchment. Comparison of results with Twentieth Century climate records affirms the hypothesis that climatic warming is the most likely cause for the ice retreat observed on Signy Island during the last 40 yrs. Similar reconstruction models using these simple sedimentary measures could be developed for analogous locations in the Antarctic and in Arctic and Alpine regions.
Keywords: Antarktis; innsjø; klimaendringer; paleolimnologi; sedimenter; økologi

Historien om skuta Vesleper - Olsen, Else Mehren (Follominne: årbok, 2001)
Keywords: Antarktis; Bouvetøya; Peter I. Øy; Sørishavet; ekspedisjoner; historie; hvalfangst

Blue-ice areas in Antarctica derived from NOAA AVHRR satellite data - Winther, Jan-Gunnar; Jespersen, Martin Nørman; Liston, Glen E. (Journal of Glaciology, 2001)
We have mapped Antarctic blue-ice areas using the U.S. National Oceanic and Atmospheric Administration (NOAA) Advanced Very High Resolution Radiometer (AVHRR) Antarctica cloud-free image mosaic established by the United States Geological Survey. The mosaic consists of 38 scenes acquired from 1980 to 1994. Our results show that approximately 60 000 km2 of blue ice exist for each of the two main types of blue ice: “melt-induced” and “wind-induced”. Normally, the former type is located on slopes in coastal areas where climate conditions (i.e. persistent winds and temperature), together with favourable surface orientation, sustain conditions for surface and near surface melt. The latter blue-ice category occurs near mountains or on outlet glaciers, often at higher elevations, where persistent winds erode snow away year-round, and combined with sublimation creates areas of net ablation. Furthermore, we have identified an additional area of 121 000 km2 as having potential for blue ice. However, in these areas features such as mixed pixels, glazed snow surfaces, crevasses and/or shadows make interpretation more uncertain. In conclusion, a conservative estimate of Antarctic blue-ice area coverage by this method is found to be 120 000 km2 (∼0.8% of the Antarctic continent), with a potential maximum of 241 000 km2 (∼1.6% of the Antarctic continent).
Keywords: Antarktis; Dronning Maud Land; blåis; fjernmåling; glasiologi; satellite bilder; teknologi

South through the Pole 1997-98 - Arnesen, Liv (Polarboken, 2000)
Keywords: Antarktis; ekspedisjoner

Man in extreme environments - Brubakk, Alf O. (Aviation, space, and environmental medicine, 2000)
Humans have demonstrated the ability to live and work in many adverse environments. Many examples demonstrate that our understanding of humans ability to adapt to extreme environments is limited, but it is reasonable to assume that the main problems in space exploration will be psychological and social. It is argued that polar expeditions of an earlier age are a better model for space exploration than confinement studies or Antarctic overwintering. Some aspects of the reason for the success of these expeditions are discussed and the lessons that can be used are pointed out.
Keywords: Antarktis; fysiologi; overvintring; polarekspedisjoner; polarområdene

Lipids, trophic relationships, and biodiversity in Arctic and Antarctic krill - Falk-Petersen, Stig; Hagen, Wilhelm; Kattner, Gerhard; Clarke, Andrew; Sargent, John (Canadian Journal of Fisheries and Aquatic Sciences, 2000)
Environmental seasonality is a critical factor in structuring polar marine ecosystems. The extensive data now available on the lipids of Arctic and Antarctic euphausiids show that all species are characterised by a seasonally high lipid content, and neutral lipids, whether wax esters or triacylglycerols, are primarily accumulated for reproduction. The Arctic Thysanoessa inermis and the Antarctic Euphausia crystallorophias contain high levels of wax esters and higher concentrations of 18:4(n-3) and 20:5(n-3) and a lower ratio of 18:1(n-9)/(n-7) fatty acids in their neutral lipids than the Arctic Thysanoessa raschii and the Antarctic Thysanoessa macrura and Euphausia superba. Large amounts of phytol in the lipids of T. raschii and E. crystallorophias during winter suggest the ingestion of decaying algae originating in sedimenting material or in sea ice. Thysanoessa raschii, T. macrura, and E. superba have a high ratio of 18:1(n-9)/ (n-7) fatty acids, indicating animal carnivory. We conclude that T. inermis and E. crystallorophias are true high polar herbivores, while T. raschii, T. macrura, and E. superba are omnivores with a more boreal distribution. The Arctic species Thysanoessa longicaudata and Meganyctiphanes norvegica are carnivores feeding on Calanus, as indicated by high amounts of 20:1(n-9) and 22:1(n-11) fatty acids.
Keywords: Antarktis; biodiversitet; copepoder; krill; marin biologi; marine økosystemer; plankton

Geochronologic evidence for Early Cretaceous volcanic activity on Barton Peninsula, King George Island, Antarctica - Kim, Hyeoncheol; Ik Lee, Jong; Young Chose, Moon; Cho, Moonsup; Zheng, Xiangshen; Sang, Haiquing; Qiu, Ji (Polar Research, 2000)
Ages of six volcanic and plutonic rocks on Barton Peninsula, King George Island, were determined using 40Ar/39Ar and K-Ar isotopic systems. The 40Ar/39Ar and K-Ar ages of basaltic andesite and diorite range from 48 My to 74 My and systematically decrease toward the upper stratigraphic section. Two specimens of basaltic andesite which occur in the lowermost sequence of the peninsula, however, apparently define two distinct plateau ages of 52-53 My and 119-120 My. The latter is interpreted to represent the primary cooling age of basaltic andesite, whereas the former is interpreted as the thermally-reset age caused by the intrusion of Tertiary granitic pluton. The isochron ages calculated from the isotope correlation diagram corroborate our interpretation based on the apparent plateau ages. It is therefore likely that volcanism was active during the Early Cretaceous on Barton Peninsula. When the K-Ar ages of previous studies are taken into account with our result, the ages of basaltic andesite in the northern part of the Barton Peninsula are significantly older than those in the southern part. Across the north-west-south-east trending Barton fault bounding the two parts, there are significant differences in geochronologic and geologic aspects.
Keywords: Antarktis; geokronologi; geologi; vulkaner

Effort explores 130 Million years of Antarctic paleoenvironment - Kristoffersen, Yngve; Goodwin, Ian D; Cooper, Alan K (Eos, Transactions American Geophysical Union, 2000)
Antarctic climate history has been dominated by events and turning points with causes that are poorly understood. To fill the gaps in our knowledges new effort is underway in the international geologic community to acquire and coordinate the circum-Antarctic geologic data needed to derive and model paleoenvironments of the past 130 m.y. The effort, which focuses principally on using shallow (<100 m) stratigraphic drilling and coring to acquire the geologic data, is being led by the Antarctic Offshore Stratigraphy Project (ANTOSTRAT), a group that works under the aegis of the Scientific Committee on Antarctic Research (SCAR). About 40 scientists from 12 countries met this past summer in Wellington, New Zealand, at an ANTOSTRAT meeting to discuss strategies for implementing the desired paleoenvironmental field and modeling studies. The meeting was held in conjunction with the 8th International Symposium on Antarctic Earth Sciences.
Keywords: Antarktis; geologi; geovitenskap; klimatologi; paleontologi; stratigrafi

Combined characterisation of GOME and TOMS total ozone measurements from space using ground-based observations from the NDSC - Lambert, J.-C.; Van Roozendael, M.; Simon, P.C.; Pommereau, J.-P.; Goutail, F.; Gleason, J.F.; Andersen, S.B.; Arlander, D.W.; Bui Van, N.A.; Claude, H.; de La Noë, J.; De Mazière, M.; et al. (Advances in Space Research, 2000)
Several years of total ozone measured from space by the ERS-2 GOME, the Earth Probe TOMS, and the ADEOS TOMS, are compared with high-quality ground-based observations associated with the Network for the Detection of Stratospheric Change (NDSC), over an extended latitude range and a variety of geophysical conditions. The comparisons with each spaceborne sensor are combined altogether for investigating their respective solar zenith angle (SZA) dependence, dispersion, and difference of sensitivity. The space- and ground-based data are found to agree within a few percent on average. However, the analysis highlights for both GOME and TOMS several sources of discrepancies: (i) a SZA dependence with TOMS beyond 80° SZA; (ii) a seasonal SZA dependence with GOME beyond 70° SZA; (iii) a difference of sensitivity with GOME at high latitudes; (iv) a difference of sensitivity to low ozone values between satellite and SAOZ sensors around the southern tropics; (v) a north/south difference of TOMS with the ground-based observations; and (vi) internal inconsistencies in GOME total ozone.
Keywords: Antarktis; fjernmåling; geofysikk; meteorologi; ozonlaget; polarområdene; satellitt observasjoner

IFIX - inductive data acquisition system: system for sub ice shelf data acquisition - Lothe, Torleif (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Antarktis; Sørishavet; forskning; teknologi

Subglacial topography of Jutulstraumen outlet glacier, East Antarctica, mapped from ground-penetrating radar, optical and interferometric synthetic aperture radar satellite data - Melvold, Kjetil; Rolstad, Cecilie Eie (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2000)
Keywords: Antarktis; geologi; glasiologi; isstrøm; topografi

Arctic and Antarctic ozone layer observations: chemical and dynamical aspects of variability and long-term changes in the polar stratosphere - Rex, Markus; Dethloff, Klaus; Handorf, Dörthe; Herber, Andreas; Lehmann, Ralph; Neuber, Roland; Notholt, Justus; Rinke, Annette; von der Gathen, Peter; Weisheimer, Antje; Gernandt, Hartwig (Polar Research, 2000)
The altitude dependent variability of ozone in the polar stratosphere is regularly observed by balloon-borne ozonesonde observations at Neumayer Station (70°S) in the Antarctic and at Koldewey Station (79°N) in the Arctic. The reasons for observed seasonal and interannual variability and long-term changes are discussed. Differences between the hemispheres are identified and discussed in light of differing dynamical and chemical conditions. Since the mid- 1980s, rapid chemical ozone loss has been recorded in the lower Antarctic stratosphere during the spring season. Using coordinated ozone soundings in some Arctic winters, similar chemical ozone loss rates have been detected related to periods of low temperatures. The currently observed cooling trend of the stratosphere, potentially caused by the increase of anthropogenic greenhouse gases, may further strengthen chemical ozone removal in the Arctic. However, the role of internal climate oscillations in observed temperature trends is still uncertain. First results of a 10000 year integration of a low order climate model indicate significant internal climate variability. on decadal time scales, that may alter the effect of increasing levels of greenhouse gases in the polar stratosphere.
Keywords: Antarktis; drivhusgasser; klimaendringer; klimagasser; meteorologi; observasjoner; ozonlaget; polarområdene; stratosfæren

Coping in Antarctica: is it possible to generalize results across settings? - Sandal, Gro Mjeldheim (Aviation Space and Environmental Medicine, 2000)
Background: To gain knowledge about psychological issues in space, data have been collected from groups in isolated and confined settings on Earth. This study examines the possibility of generalizing psychological findings across such environments. HYPOTHESIS: Psychological reactions among personnel in different Antarctic environments show similar time patterns. Antarctic personnel differ in personality from submariners to crews confined in hyperbaric chambers to military recruits. METHOD: Psychological reactions were evaluated by the Revised Antarctic Questionnaire. The Personality Characteristic Inventory was used to measure personality. RESULTS: Personnel stationed on a ship (n = 19) showed high coping during the whole mission, whereas personnel on land bases (n = 18) showed a marked decline around the third quarter. Reduced coping in the land-based groups was associated with stress from interpersonal relationships. Compared with submariners (n = 54) and hyperbaric chamber crews (n = 20), Antarctic personnel scored lower on competitiveness and higher on achievement striving. CONCLUSIONS: Similarities in physical, individual and group characteristics should be considered before extrapolating psychological findings across settings.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

The impact of greenhouse gases and halogenated species on future solar UV radiation doses - Taalas, Petteri; Kaurola, Jussi; Kylling, Arve; Shindell, Drew; Sausen, Robert; Dameris, Martin; Grewe, Volker; Herman, Jay; Damski, Juhani; Steil, Benedikt (Geophysical Research Letters, 2000)
The future development of stratospheric ozone layer depends on the concentration of chlorine and bromine containing species. The stratosphere is also expected to be affected by future enhanced concentrations of greenhouse gases. These result in a cooling of the winter polar stratosphere and to more stable polar vortices which leads to enhanced chemical depletion and reduced transport of ozone into high latitudes. One of the driving forces behind the interest in stratospheric ozone is the impact of ozone on solar UV-B radiation. In this study UV scenarios have been constructed based on ozone predictions from the chemistry-climate model runs carried out by GISS, UKMO and DLR. Since cloudiness, albedo and terrain height are also important factors, climatological values of these quantities are taken into account in the UV calculations. Relative to 1979–92 conditions, for the 2010–2020 time period the GISS model results indicate a springtime enhancement of erythemal UV doses of up to 90% in the 60–90 °N region and an enhancement of 100% in the 60–90 °S region. The corresponding maximum increases in the annual Northern Hemispheric UV doses are estimated to be 14% in 2010–20, and 2% in 2040–50. In the Southern Hemisphere 40% enhancement is expected during 2010–20 and 27% during 2040–50.
Keywords: Antarktis; UV-stråling; drivhusgasser; klimaendringer; klimatologi; ozonlaget; polarområdene; ultrafiolett stråling

Determination of Q1, an unknown organochlorine contaminant, in human milk, Antarctic air, and further environmental samples - Vetter, Walter; Alder, Lutz; Kallenborn, Roland; Schlabach, Martin (Environmental Pollution, 2000)
Q1, an organochlorine component with the molecular formula C(9)H(3)Cl(7)N(2) and of unknown origin was recently identified in seal blubber samples from the Namibian coast (southwest of Africa) and the Antarctic. In these samples, Q1 was more abundant than PCBs and on the level of DDT residues. Furthermore, Q1 was more abundant in seals from the Antarctic than the Arctic. To prove this assumption, gas chromatography-electron-capture negative ion mass spectrometry (GC/ECNI-MS), which is sensitive and selective for Q1, allowed for screening of traces of Q1 even in samples with particularly high levels of other organochlorine contaminants. Q1 was isolated by high-performance liquid chromatography (HPLC) from a skua liver sample. A 1:1 mixture with trans-nonachlor in electron-capture detectors (ECDs) was used to determine the relative response factor with ECNI-MS. The ECNI-MS response of Q1 turned out to be 4.5 times higher than that of trans-nonachlor in an ECD. With GC/ECNI-MS in the selected ion-monitoring mode, four Antarctic and four Arctic air samples were investigated for the presence of Q1. In the Antarctic air samples, Q1 levels ranged from 0.7 to 0.9 fg/m(3). In Arctic air samples, however, Q1 was below the detection limit (<0.06 fg/m(3) or 60 ag/m(3)). We also report on high Q1 levels in selected human milk samples (12-230 microg/kg lipid) and, therefore, suggested that the unknown Q1 is an environmental compound whose origin and distribution should be investigated in detail. Our data confirm that Q1 is a bioaccumulative natural organochlorine product. Detection of a highly chlorinated natural organochlorine compound in air and human milk is novel.
Keywords: Antarktis; forurensning; kromatografi; miljøgifter; miljøovervåking; toksikologi

Emerging Law of the Sea Issues in the Antarctic Maritime Area: A Heritage for the New Century? - Vidas, Davor (Ocean Development & International Law, 2000)
This article focuses on three emerging law of the sea issues for states cooperating in management of the Antarctic and its maritime area. The first of these is no newcomer: How to regulate the dramatic increase in illegal, unregulated and unreported fishing of Patagonian toothfish (Dissostichus eleginoides) in the Southern Ocean? The second question, according to the letter of the UN Convention on the Law of the Sea, awaits the countries claiming sovereignty over portions of territory in the Antarctic 10 years from the entry into force of the Convention for each of them. The question here is what to do with the requirement contained in that Convention relating to the submission of information on the outer limit of the continental shelf beyond 200 nautical miles to the Commission on the Continental Shelf? Finally, there is a third tricky question: Who is competent to regulate, and accordingly to ban, mineral activities in the Southern Ocean seabed? Is it the International Seabed Authority as the global body, or the Antarctic Treaty Consultative Parties through their regional cooperation? This question may well never be put on the policy agenda for any global forum; but it may well be posed at any time and by any third party, whether in the UN General Assembly or, more likely, in the Assembly of the International Seabed Authority.
Keywords: Antarktis; Antarktistraktaten; Sørishavet; fiskeri; havrett; internasjonal rett; kontinentalsokkel

The importance of charged aerosols in the polar mesosphere in connection with Noctilucent Clouds and Polar Mesosphere Summer Echoes - Blix, Tom Arild (The Antarctic and Arctic Middle Atmospheres: Their Differences and Similarities, 1999)
A number of campaigns have been conducted in order to study Polar Mesosphere Summer Echos (PMSE) and Noctilucent Clouds (NLC) in the period 1991–1994. Several sounding rockets have been launched through these layers with measurements being performed on upleg as well as downleg. These include measurements of positive ions and electrons in both ram and wake positions, as well as measurements of charged aerosols in ram on upleg. In this paper we will review these measurements and make a preliminary classification of the data based upon the presence of PMSE and/or NLC. One of the mechanisms responsible for PMSE is the presence of neutral air turbulence in combination with a high Schmidt number. We will briefly discuss this type of echo using in situ rocket data. Differences and similarities of PMSE and NLC as observed both in the Arctic and the Antarctic will be discussed. Observations show that especially PMSE are much more frequent in the Arctic. This may be due to a difference in the water vapour content or the temperature at mesopause heights. Lack of data in the Antarctic makes it difficult to decide which of these two factors are the most important. More measurements, especially co-ordinated in situ and ground-based lidar and radar measurements, are needed to discuss the Arctic and Antarctic similarities and differences in further detail.
Keywords: Antarktis; astrofysikk; atmosfæren; geofysikk; mesosfæren; meteorologi; polarområdene

The cryosphere: an early indicator and global player - Grassl, Hartmut (Polar Research, 1999)
Ice at or below the surface of the planet Earth is an important part of the climate system. The solid phase of water has two unique characteristics which make it both an early indicator of climate change and a global player. First, if warmed to the melting point at 0°C, higher air temperatures and/or higher long-wave back radiation just increase the melting rate but not - as with all other surfaces- the temperature, which stays at 0°C. Small icecaps and mountain glaciers thus become early indicators of a changed climate. Second. If seawater is cooled to the freezing point at about- 1.8"C. the sea ice formation process ejects salt causing the denser water to sink, thereby filling the global ocean interior with very cold water. The location where most of this deep convection occurs is strongly dependent on the freshwater balance and thus on the average salinity of ocean basins. Present ocean configuration and ocean topography, as well as precipitation distribution, make the northern North Atlantic more saline than any other high latitude ocean part and thus the site with most of this deep water formation. Sea ice formation is therefore of high significance for the European climate. Since it drives the near surface warm North Atlantic current northward off the European coast in compensation for southward deep water flow in the western Atlantic, northwestern Europe is warmer by about 4°C than the same latitudes on the eastern Pacific coast of America.
Keywords: Antarktis; isbreer; klimaendringer; kryosfæren; polarområdene; sjøvann; vann

Predicted present-day evolution patterns of ice thickness and bedrock elevation over Greenland and Antarctica - Huybrechts, Philippe; Le Meur, Emmanuel (Polar Research, 1999)
This paper discusses predicted evolution patterns of present-day changes of ice thickness, surface elevation, and bedrock elevation over the Greenland and Antarctic continents. These were obtained from calculations with dynamic 3-D ice sheet models which were coupled to a visco-elastic solid Earth model. The experiments were initialized over the last two glacial cycles and subsequently averaged over the last 200 years to obtain the current evolution. The calculations indicate that the Antarctic Ice Sheet is still adjusting to the last glacial-interglacial transition yielding a decreasing ice volume and a rising bedrock elevation of the order of several centimetres per year. The Greenland Ice Sheet was found to be close to a stationary state with a mean thickness change of only a few millimetres per year, but the calculations revealed large spatial differences. Predicted patterns over Greenland are characterized by a small thickening over the ice sheet interior and a general thinning of the ablation area. In Antarctica, almost all of the predicted changes are concentrated in the West Antarctic Ice Sheet, which is still retreating at both the Weddell and Ross Sea margins. Over most of both ice sheets, the model indicates that the surface elevation trend is dominated by ice thickness changes rather than by bedrock elevation changes.
Keywords: Antarktis; glasiologi; innlandsis; polarområdene

The Antarctic contribution to Holocene global sea level rise - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 1999)
The Holocene glacial and climatic development in Antarctica differed considerably from that in the Northern Hemisphere. Initial deglaciation of inner shelf and adjacent land areas in Antarctica dates back to between 10-8 Kya, when most Northern Hemisphere ice sheets had already disappeared or diminished considerably. The continued deglaciation of currently ice-free land in Antarctica occurred gradually between ca. 8-5 Kya. A large southern portion of the marine-based Ross Ice Sheet disintegrated during this late deglaciation phase. Some currently ice-free areas were deglaciated as late as 3 Kya. Between 8-5 Kya, global glacio-eustatically driven sea level rose by 10-17m, with 4-8 m of this increase occurring after 7 Kya. Since the Northern Hemisphere ice sheets had practically disappeared by 8-7 Kya, we suggest that Antarctic deglaciation caused a considerable part of the global sea level rise between 8-7 Kya, and most of it between 7-5 Kya. The global mid-Holocene sea level high stand, broadly dated to between 8-4 Kya, and the Littorina-Tapes transgressions in Scandinavia and simultaneous transgressions recorded from sites e.g. in Svalbard and Greenland, dated to 7-5 Kya, probably reflect input of meltwater from the Antarctic deglaciation.
Keywords: Antarktis; geologi; glasiologi; havnivåstigning; innlandsis; paleoglasiologi; polarområdene

Ultraviolet radiation and health effects in the Antarctic - Lugg, Desmond J.; Roy, Colin R. (Polar Research, 1999)
With the recognition that global climate change may adversely affect human health, there has been an increase in relevant research worldwide. In the Antarctic medical research has been largely directed at the potential health effects of stratospheric ozone depletion. For over a decade continuous broad-band measurements of ultraviolet radiation (UVR) have been made at all Australian stations. Results of UV measurements are presented and comparisons made with the “ozone hole” moving over the stations, erythemal UVR increasing by a factor of more than 2.5 over a three day period. During late spring and despite the large difference in latitude, Davis, Antarctica, and Melbourne, Australia, are very similar in erythemal UVR. Antarctic immunological and photo biological research is presented and the role of UVR discussed. Epidemiological data is reviewed for short-term links between UVR and related disease. With increased awareness of the dangers of UVR and consequent changes in sun-related behavior, the incidence of the acute effects of UVR is much lower than decades ago. As the itinerant Antarctic population spends a maximum of 12-18 months at a time in that location it is an excellent control group for studies on the health effects of UVR on permanent populations at similar latitudes in the Arctic.
Keywords: Antarktis; epidemiologi; fotobiologi; immunologi; klimaendringer; ozonlaget; ultrafiolett stråling

Photosynthetic responses of selected Antarctic plants to solar radiation in the southern maritime Antarctic - Montiel, Pedro; Smith, Andrew; Keiller, Don (Polar Research, 1999)
The effects of UV-B exclusion and enhancement of solar radiation on photosynthesis of the two phanerogams which occur in the maritime Antarctic, Deschampsia antarctica and Colobanthus quitensis, and the moss Sanionia uncinats were investigated. Data on air temperature and solar radiation illustrate a drastic seasonal variation. Daily O3 column mean values and UV-B measured at ground level document the occurrence of the O3“hole” in the spring of 1997, with a concomitant increase in UV-B. The grass, D. antarctica, exhibited a broad temperature optimum for photosynthesis between 10–25°C while photosynthesis did not saturate even at high irradiance. The high water use efficiencies measured in the grass may be one of the features explaining the presence of this species in the maritime Antarctic. The net photosynthesis response to intercellular CO2 (A/ci) for D. antarctica was typical of a C3 plant. Exposure to a biologically effective UV-B irradiance of 0.74 W M-2 did not result in any significant change in either the maximum rate of photosynthesis at saturating CO2 and light, or in the initial carboxylation efficiency of Rubisco. (Vc,max). Furthermore while ambient (or enhanced) solar UV-B did not affect photochemical yield, measured in the field, of C. quitensis and D. antarctica, UV-B enhancement did affect negatively photochemical yield in S. uncinata. In D. antarctica plants, exposure to UV-B at low irradiances elicited increased flavonoid synthesis. The observed effects of UV-B enhancement on the moss (decreased photochemical yield) and the grass (increase in flavonoids) require further, separate investigation.
Keywords: Antarktis; botanikk; fotosyntese; klimaendringer; moser; planter

Global change and the polar regions - Rapley, Chris (Polar Research, 1999)
Keywords: Antarktis; klimaendringer; polarområdene

A global model tool for three-dimensional multiyear stratospheric chemistry simulations: Model description and first results - Rummukainen, Markku; Isaksen, Ivar S A; Rognerud, Bjørg; Stordal, Frode (Journal of Geophysical Research: Atmospheres, 1999)
The paper presents a new global modeling tool, Stratospheric Chemical Transport Model 2. It has been developed for effective three-dimensional multiyear stratospheric chemistry studies, featuring an extensive chemistry scheme, heterogeneous processing on sulfate aerosols, and some polar stratospheric cloud processes. The transport algorithm maintains sub-grid-scale distributions and connects vertically the stratospheric layers, even in a coarse vertical grid. The model has been integrated for 49 months, recycling 1 year of precalculated transport from a middle atmosphere general circulation model. One year of daily National Centers for Environmental Prediction global analyses are used as temperatures. Diurnal cycles of photolysis rates are recalculated every 7 days to give interaction with ozone changes. The model is able to describe most of the geographical and seasonal ozone variability and the meridional distributions of ozone, reactive nitrogen, chlorine, and bromine. Stratospheric diurnal cycles for nitrogen, hydrogen, chlorine, and bromine species are captured in detail. The upper stratosphere ozone deficiency, typical to models, is large. Its sensitivity to different ways of tuning are explored. Midlatitude, rather than polar, wintertime processes have so far been the focus in this model tool. The present transport and grid resolution are not suited for realistic simulations at high latitudes. As there is only a limited inclusion of polar stratospheric cloud (PSC) microphysics, chemical processing in the cold polar lower stratosphere also cannot be well simulated. For example, the Antarctic ozone hole is not simulated, but the modeled chemistry should be suitable for warm Arctic winters when type II PSCs and particle sedimentation do not occur.
Keywords: Antarktis; geofysikk; meteorologi; ozonlaget; polarområdene; stratosfæren; stratosfærisk kjemi

Climatic trend and the retreat and disintegration of ice shelves on the Antarctic Peninsula: an overview - Skvarca, Pedro; Rack, Wolfgang; Rott, Helmut; Ibarzábal Donángelo, Teresa (Polar Research, 1999)
Observation of the retreat and disintegration of ice shelves around the Antarctic Peninsula during the last three decades and associated changes in air temperature, measured at various meteorological stations on the Antarctic Peninsula, are reviewed. The climatically induced retreat of the northern Larsen Ice Shelf on the east coast and of the Wordie, George VI, and Wilkins ice shelves on the west coast amounted to about 10 000 km2 since the mid-1960s. A summary is presented on the recession history of the Larsen Ice Shelf and on the collapse of those sections north of Robertson Island in early 1995. The area changes were derived from images of various satellites, dating back to a late 1963 image from the recently declassified US Argon space missions. This photograph reveals a previously unknown, minor advance of the northern Larsen Ice Shelf before 1975. During the period of retreat a consistent and pronounced warming trend was observed at the stations on both east and west coasts of the Antarctic Peninsula, but a major cause of the fast retreat and final collapse of the northernmost sections of the Larsen Ice Shelf were several unusually warm summers. Temperature records from the nearby station Marambio show that a positive mean summer temperature was reached for the first time in 1992-93. Recent observations indicate that the process of ice shelf disintegration is proceeding further south on both sides of the Antarctic Peninsula.
Keywords: Antarktis; brehylle; glasiologi; isbrem; isshelf; klimaendringer; meteorologi; satellittbilder

Distribution and Abundance of the Antarctic Petrel - van Franeker, J. A.; Gavrilo, M.; Mehlum, Fridtjof; Veit, R. R.; Woehler, E. J. (Waterbirds: The International Journal of Waterbird Biology, 1999)
Published and unpublished information on the distribution and abundance of the Antarctic Petrel (Thalassoica antarctica) is reviewed. Currently 35 colonies with approximately half a million breeding pairs are known. All but one of these known colonies are situated in East Antarctica. However, an estimate derived from at sea studies in three of four apparent centers of oceanic occurrence suggests a population as high as four to seven million breeding pairs (10 to 20 million individuals). In spite of the tentative nature of such an estimate, the difference with the colony-derived figure strongly suggests the existence of large, currently undiscovered colonies, particularly in western Antarctica and Victoria Land, where a complete mismatch exists between bird observations at sea and known colonies. In eastern Antarctica, in addition to undiscovered colonies, some known ones could be considerably larger than currently documented.
Keywords: Antarktis; Dronning Maud Land; fugler; ornitologi; petreller; zoologi

The interplay of global and polar regimes - Young, Oran R. (Polar Research, 1999)
The growing salience of interactions between the functionally broad but geographically narrow regimes for the polar regions and the geographically broad but functionally specific regimes emerging to deal with global environmental changes directs attention to the issue of institutional interplay. Interplay among regimes can cause mutual interference or foster synergy. Adopting a pragmatic stance that assumes no fundamental changes in international society, this essay suggests ways to: (1) adapt global regimes dealing with ozone depletion, climate change and biodiversity to the conditions prevailing in the polar regions; and (2) ensure that concerns arising in the polar regions receive serious consideration in global forums. Specific suggestions range from modest initiatives involving monitoring and assessment to more ambitious initiatives, such as the establishment of a chamber of regions in global regimes.
Keywords: Antarktis; biodiversitet; internasjonal samarbeid; klimaendringer; klimapolitikk; ozonlaget; polarområdene

Ice sheet history from Antarctic Continental Margin sediments: The ANTOSTRAT approach - Barker, Peter; Barrett, Peter; Camerlenghi, Angelo; Cooper, Alan; Davey, Frederick; Domack, Eugene; Escutia, Carlota; Kristoffersen, Yngve; O'Brien, Philip (Terra Antarctica, 1998)
Keywords: Antarktis; glasiologi; innlandsis; sedimentologi

Polare jubileer i 1997 og 1998 - Barr, Susan (Polarboken, 1998)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie

The Floating Factory: Dominant Designs and Technological Development of Twentieth-CenturyWhaling Factory Ships - Basberg, Bjørn L (The Northern Mariner/Le Marin du nord, 1998)
Keywords: Antarktis; historie; hvalfangere; hvalfangst; hvalkokeri

On the cost of reproduction in long-lived birds: the influence of environmental variability - Erikstad, Kjell Einar; Fauchald, Per; Tveraa, Torkild; Steen, Harald (Ecology, 1998)
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi

Estimate of the subglacier dielectric constant of an ice shelf using a ground-penetrating step-frequency radar - Hamran, Svein Erik; Erlingsson, Bjørn; Gjessing, Yngvar; Mo, Per (IEEE Transactions on Geoscience and Remote Sensing, 1998)
The mass balance of the Antarctic ice cap, its stability, and the role of the surrounding ice shelf in bottomwater mass formation is, to a large extent, dictated by processes associated with subsurface freezing and melting, where the submerged ice meets the surrounding ocean. It is demonstrated how multifrequency ground-penetrating radar data collected at the Riiser-Larsenisen can be used to examine the physical conditions of the ice-shelf subsurface. The received radar signal from three different frequency intervals, 10-30, 155-170, and 330-360 MHz (range of wavelengths from 15 to 0.5 m in the ice), was analyzed by using a plane reflector model. It is demonstrated that the data can be successfully used to distinguish between types of ice at the ice-ocean interface, such as for freezing marine ice, melting marine ice, melting meteoric ice from the ice cap, and melting firn/ice. The data analysis shows that the subsurface can be regarded as rough on length scales in the order of 1 m.
Keywords: Antarktis; brehylle; fjernanalyse; geofysikk; georadar; glasiologi; isbreer; isbrem; isshelf; oseanografi

Ambient air levels and atmospheric long-range transport of persistent organochlorines to Signy Island, Antarctica - Kallenborn, Roland; Oehme, Michael; Wynn-Williams, David D; Schlabach, Martin; Harris, Joyce (Science of The Total Environment, 1998)
Levels of persistent organic pollutants (POPs), such as polychlorinated biphenyls and pesticides have been determined in ambient air at Signy Island, Antarctica, over a period of 17 weeks. Mean concentrations for single polychlorinated biphenyls (0.02–17 pg/m3), for chlordanes (0.04–0.9 pg/m3), DDT compounds (0.07–0.40 pg/m3) and γ-hexachlorocyclohexane (HCH, 22 pg/m3) were comparable to those in Arctic air. However, α-HCH levels were approximately one order of magnitude lower. Compared to the Arctic, differences were also observed in the concentration ratios of α-/γ-HCH and chlordane compounds. Two possible atmospheric long-range transport episodes from South America were found by comparing 10-day back trajectories with observed concentration changes. The lower limits of determination (LOD) were mainly governed by the field blanks. They were satisfactory for the most volatile PCBs. However, many concentrations for DDT and chlordane compounds were below the LODs (range 0.1–1 pg/m3) or even the instrumental detection limit (0.01–0.03 pg/m3).
Keywords: Antarktis; atmosfæren; forurensning; langtransport; luftforurensning; meteorologi; miljøgifter; polarområdene

Klarius Mikkelsen's 1935 landing in the Vestfold Hills, East Antarctica: some fiction and some facts - Norman, Frederick Ian; Gibson, John A E; Burgess, J S (Polar Record, 1998)
Exploratory activities of Norwegians, particularly those directed by Lars Christensen, off eastern Antarctica are discussed briefly in relation to contemporary Antarctic investigations and politics. The interests of Norway there and Christensen's role in establishing an understanding of the local coastline are indicated. Particular attention is paid to the landing made by Klarius Mikkelsen in the Vestfold Hills, East Antarctica, on 20 February 1935. Note is taken of the site's recent re-discovery, and the symbolic role of the landing in the national aspirations of Norway, Britain, and Australia is discussed. Mikkelsen operated under commercial and scientific interests promoted by Christensen, and his landing was, at least in published material, seen as an extension of them. However, there is a suggestion that not only had a new Norwegian land been discovered, and a landing made, but that a claim to it was at least considered. Such a claim was not appropriate given previous agreements between Norway and Britain. The site's location and environs are discussed, as are subsequent flights over it and visits made there by Australian expeditioners. The ambiguity associated with claims that Caroline Mikkelsen was the first woman to land on the Antarctic mainland is also examined. Since Mikkelsen's site was on an island within the Tryne Group, to the north of Davis station, if a mainland location is required to establish such an event, then an alternative (Scullin Monolith) is proposed; however, on this occasion four women were involved, but who was first ashore remains uncertain.
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser

Tvers over Antarktis alene - Ousland, Børge (Polarboken, 1998)
Keywords: Antarktis; ekspedisjoner

A new species of Parmelia (lichenized Ascomycotina) from the Antarctic - Øvstedal, Dag Olav; Elix, John A.; Smith, Ronald I. Lewis (Mycotaxon, 1998)
A new species of Parmelia (lichenized Ascomycotina) from the Antarctic. Parmelia lindsayana Ovstedal & Elix from Signy Island (South Orkney Islands) is described as new. This species resembles P. protosulcata Hale and P. cunninghamii Crombie, but differs in morphological details and in containing usnic, alpha-collatolic and alectoronic acids.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

A Comparison of the CCM3 Model Climate Using Diagnosed and Predicted Condensate Parameterizations - Rasch, Philip J.; Kristjánsson, Jón Egill (Journal of Climate, 1998)
A parameterization is introduced for the prediction of cloud water in the National Center for Atmospheric Research Community Climate Model version 3 (CCM3). The new parameterization makes a much closer connection between the meteorological processes that determine condensate formation and the condensate amount. The parameterization removes some constraints from the simulation by allowing a substantially wider range of variation in condensate amount than in the standard CCM3 and tying the condensate amount to local physical processes. The parameterization also allows cloud drops to form prior to the onset of grid-box saturation and can require a significant length of time to convert condensate to a precipitable form, or to remove the condensate. The free parameters of the scheme were adjusted to provide reasonable agreement with top of atmosphere and surface fluxes of energy. The parameterization was evaluated by a comparison with satellite and in situ measures of liquid and ice cloud amounts. The effect of the parameterization on the model simulation was then examined by comparing long model simulations to a similar run with the standard CCM and through comparison with climatologies based upon meteorological observations. Global ice and liquid water burdens are higher in the revised model than in the control simulation, with an accompanying increase in height of the center of mass of cloud water. Zonal averages of cloud water contents were 20%–50% lower near the surface and much higher above. The range of variation of cloud water contents is much broader in the new parameterization but was still not as large as measurements suggest. Differences in the simulation were generally small. The largest significant changes found to the simulation were seen in polar regions (winter in the Arctic and all seasons in the Antarctic). The new parameterization significantly changes the Northern Hemisphere winter distribution of cloud water and improves the simulation of temperature and cloud amount there. Small changes were introduced in the cloud fraction to improve consistency of the meteorological parameterizations and to attempt to alleviate problems in the model (in particular, in the marine stratocumulus regime). The small changes did not make any appreciable improvement to the model simulation. The new parameterization adds significantly to the flexibility in the model and the scope of problems that can be addressed. Such a scheme is needed for a reasonable treatment of scavenging of atmospheric trace constituents, and cloud aqueous or surface chemistry. The addition of a more realistic condensate parameterization provides opportunities for a closer connection between radiative properties of the clouds, and their formation and dissipation. These processes must be treated for many problems of interest today (e.g., anthropogenic aerosol–climate interactions).
Keywords: Antarktis; klimamodeller; klimatologi; meteorologi; polarområdene

The effects of personality and interpersonal relations on crew performance during space simulation studies - Sandal, Gro Mjeldheim (Life Support & Biosphere Science, 1998)
There has been a substantial increase in the number of people living and operating in isolated, confined, and artificially engineered environments, such as spacecraft, deep diving, weather stations, submarines, and polar outposts. This article gives an overview of research undertaken in a variety of extreme environments in an effort to better understand how semiautonomous, task-oriented groups operating within these environments develop over time, as well as identification of the individual characteristics that promote performance under such circumstances. Research reviewed includes space simulation studies for the European Space Agency (ESA) where groups were isolated in hyperbaric chambers, as well as findings from polar expeditions, space missions, submarine missions, and other military settings. Findings from the space simulation studies in hyperbaric chambers provided empirical evidence for interpersonal issues anecdotally reported in Antarctica and in other isolated, operational team environments, such as "scapegoating" of deviant crew members, displacement of aggression to outside personnel, and time patterns in psychological reactions. No indications of a "psychological limit" for how long people can tolerate remaining in isolation and confinement were found. Certain personality characteristics were consistently associated with coping, and individuals characterized by strong achievement motivation combined with interpersonal sensitivity seemed to adapt better than others. Together, these results have implications for selection and training of people operating within extreme environments.
Keywords: Antarktis; polarekspedisjoner; polarforskere; polarområdene; psykologi

Caloplaca Lewis-Smithii, a new lichen species from continental Antarctica - Søchting, Ulrik; Øvstedal, Dag Olav (Mycotaxon, 1998)
A new muscicolous lichen species, Caloplaca lewis-smithii Søchting & Øvst., is described from Victoria Land, continental Antarctica. It is characterized by a grey to blackish brown microlobate thallus and a blackish apothecial disk with a white pruinose thalline margin.
Keywords: Antarktis; botanikk; lav; planter; sopper

The semi-annual oscillation and Antarctic climate. Part 1: influence on near surface temperatures (1957–79) - Van Den Broeke, Michiel R. (Antarctic Science, 1998)
We studied the influence of the semi-annual oscillation (SAO) on near-surface temperatures in Antarctica, using observations of 27 stations that were operational during (part of) the period 1957–79. For the annual cycle of surface pressure, the second harmonic explains 17–36% of the total variance on the Antarctic Plateau, 36–68% along the East Antarctic coast and almost 80% on the west coast of the Peninsula, and decreases further to the north. As a result of the amplification of the wave-3 structure of the circulation around Antarctica, a significant modification of the seasonal cooling is observed at many stations. The magnitude of this modification is largely determined by the strength of the temperature inversion at the surface: the percentage of the variance explained by the second harmonic of the annual temperature cycle is then largest on the Antarctic Plateau (11–18%), followed by the large ice shelves and coastal East Antarctica (6–12%) and stations at or close to the Peninsula (0–5%). A significant coupling between the half-yearly wave in surface pressure and that in surface temperature is found for coastal East Antarctica, which can be directly explained by the changes in meridional circulation brought about by the SAO. We show that the coupling of Antarctic temperatures to the meridional circulation is not only valid on the seasonal time scale of the SAO, but probably also on daily and interannual time scales. This has important implications for the interpretation of time series of Antarctic temperatures, a problem that will be addressed in part 2 of this paper.
Keywords: Antarktis; fysisk geografi; klimatologi; meteorologi

The semi-annual oscillation and Antarctic climate. Part 2: recent changes - Van Den Broeke, Michiel R. (Antarctic Science, 1998)
Following a weakening of the semi-annual oscillation (SAO) since the mid-1970s, the half-yearly pressure wave in the Southern Hemisphere has become less significant. As a result, May/June temperatures have decreased in East Antarctica, which has moderated Antarctic warming. Spectral analysis of 87 years of pressure data at Orcadas suggest that the recent weakening of the SAO is part of the natural variability of the Southern Hemisphere circulation on decadal timescales. We interpret the time series of composite Antarctic temperature in terms of the historical strengthening and weakening of the SAO. If the dominant oscillations that occurred in the past prove to be persistent, an accelerated East Antarctic warming trend is expected for the coming decades. There are indications that the strength of the SAO is linked to the Southern Oscillation, in the sense that warm phases of the Southern Oscillation coincide with strong westerlies, a weakly developed SAO and below-average temperatures in East Antarctica. Temperatures on the west coast of the Antarctic Peninsula show strongly deviant patterns, which can not be explained by the same mechanism that applies to East Antarctica.
Keywords: Antarktis; fysisk geografi; klimatologi; meteorologi

Validation of Ground-Based Visible Measurements of Total Ozone by Comparison with Dobson and Brewer Spectrophotometers - Van Roozendael, Michel; Peeters, P.; Roscoe, H. K.; De Backer, H.; Jones, A. E.; Bartlett, L.; Vaughan, G.; Goutail, Florence; Pommereau, Jean-Pierre; Kyro, E.; Wahlstrom, C.; Braathen, Geir; et al. (Journal of Atmospheric Chemistry, 1998)
Comparisons of total column ozone measurements from Dobson, Brewer and SAOZ instruments are presented for the period 1990 to 1995 at seven stations covering the mid- and the high northern latitudes, as well as the Antarctic region. The main purpose of these comparisons is to assess, by reference to the well established Dobson network, the accuracy of the zenith-sky visible spectroscopy for the measurement of total ozone. The strengths and present limitations of this latter technique are investigated. As a general result, the different instruments are found to agree within a few percent at all stations, the best agreement being obtained at mid-latitudes. On average, for the mid-latitudes, SAOZ O3 measurements are approximately 2% higher than Dobson ones, with a scatter of about 5%. At higher latitudes, both scatter and systematic deviation tend to increase. In all cases, the relative differences between SAOZ and Dobson or Brewer column ozone are characterised by a significant seasonal signal, the amplitude of which increases from about 2.5% at mid-latitude to a maximum of 7.5% at Faraday, Antarctica. Although it introduces a significant contribution to the seasonality at high latitude, the temperature sensitivity of the O3 absorption coefficients of the Dobson and Brewer instruments is shown to be too small to account for the observed SAOZ/Dobson differences. Except for Faraday, these differences can however be largely reduced if SAOZ AMFs are calculated with realistic climatological profiles of ozone, pressure and temperature. Other sources of uncertainties that might affect the comparison are investigated. Evidence is found that the differences in the air masses sampled by the SAOZ and the other instruments contribute significantly to the scatter, and the impact of the tropospheric clouds on SAOZ measurements is displayed.
Keywords: Antarktis; klimatologi; ozon; polarområdene; spektrofotometri; stratosfæren

Expedition photography in polar areas - Barr, Susan (Photoresearcher, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Productivity in the 20th century Antarctic pelagic shore station whaling: growth and stagnation in two technological regimes. - Basberg, Bjørn L (The Great Circle, 1997)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangststasjoner; hvalindustri; pelagisk

Kulturhistorisk forskning i Antarktis - Basberg, Bjørn Lorens (HIFO-nytt : medlemsblad for Norsk historikerforening, 1997)
Keywords: Antarktis; hvalfangst; kulturhistorie; kulturminner

Analysis of merged SMMR-SSMI time series of Arctic and Antarctic sea ice parameters 1978–1995 - Bjørgo, Einar; Johannessen, Ola M.; Miles, Martin W. (Geophysical Research Letters, 1997)
The most consistent means of investigating the global sea ice cover is by satellite passive microwave sensors, as these are independent of illumination and cloud cover. The Nimbus 7 Scanning Multichannel Microwave Radiometer (SMMR) and the Defense Meteorological Satellite Program (DMSP) Special Sensor Microwave Imager (SSMI) provide information on the global sea ice cover from 1978 to present. The two instruments flew simultaneously during a 6-week overlap period in July and August 1987, thus enabling intercomparison of the two sensors. Brightness temperatures are corrected for instrument drift and calibration differences in order to produce continuous time series of monthly averaged Arctic and Antarctic sea ice extent and sea ice area through the use of the NOrwegian Remote Sensing EXperiment (NORSEX) algorithm, which relates brightness temperatures to ice concentration. Statistical analysis on the time series estimates the decreases in Arctic ice extent and ice area to be 4.5% and 5.7%, respectively, during the 16.8-year observation period. The overall trends established here serve to better define and strengthen earlier assertions of a reduced ice cover, based on analysis of SMMR and SSMI data taken separately. These results are consistent with GCM simulations that suggest retreat of the sea ice cover under global warming scenarios.
Keywords: Antarktis; global oppvarming; havis; klimaendringer; meteorologi; polarområdene; satellite mikrobølgesensorer

Representation of Antarctic Katabatic Winds in a High-Resolution GCM and a Note on Their Climate Sensitivity - Broeke, Michiel R. van den; Wal, Roderik S. W. van de; Wild, Martin (Journal of Climate, 1997)
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

Responses of terrestrial plants and invertebrates to environmental change at high latitudes - Callaghan, Terry V.; Sonesson, Mats; Sømme, Lauritz; Walton, D. W. H.; Christensen, T.; Block, W. C.; Drewry, D. J.; Laws, Richard Maitland; Pyle, John Adrian (Philosophical Transactions of the Royal Society of London. Series B: Biological Sciences, 1997)
Many invertebrates show flexibility in their life cycles and are likely to respond to changes in climate as they have in the past. However, changes in temperature and photoperiod may disturb the life cycles of some existing polar invertebrates while continuing to constrain the polewards migration of more temperate species. Higher plants are likely to have higher productivity as temperatures and atmospheric CO2 levels increase but this productivity will be reduced by exposure to increasing UV-B radiation. Higher plants migrate more slowly than the rate at which climate is predicted to change and many species will be trapped in supra-optimal climates. Both mosses and lichens can migrate faster than higher plants, propagules of non-polar species already reaching the Antarctic, but they have fewer mechanisms of responding to changing environments. Polar vegetation and ecosystems provide feedback to the climate system: positive feedbacks are associated with decreases in reflectivity and increased carbon emissions from warm ing soils. In the Antarctic, feedback and responses to environmental change will be smaller than in the Arctic because of the less responsive cryptogams which dominate the Antarctic, the paucity of Antarctic soils, and geographical barriers to plant and invertebrate migrations.
Keywords: Antarktis; biologi; botanikk; klimaendringer; lav; moser; virvelløse dyr

Indentation testing on ice from the Filchner Ronne Ice Shelf area, Antarctica: preliminary results - Gerland, Sebastian (Filchner-Ronne Ice Shelf Programme. Report, 1997)
Keywords: Antarktis; Sørishavet; glasiologi; havis

Belgica-ekspedisjonen : et hundreårsminne - Lie, Svein B (Norvegiana Nytt, 1997)
Keywords: Antarktis; Belgica ekspedisjon; forskning; oppdagelsesreiser; polarekspedisjoner

Hvalfangstbase og kulturminne, Hektor Hvalfangststasjon : den sørligste av de norske landstasjonene i Antarktis - Rossnes, Gustav (Norsk sjøfartsmuseum. Årsberetning, 1997)
Keywords: Antarktis; Deceptionøya; Norge; fangststasjoner; hvalfangere; hvalfangst; hvalfangststasjoner

Convergent flow of ice within the Astrolabe subglacial basin, Terre Adélie, East Antarctica: an hypothesis derived from numerical modelling experiments - Siegert, Martin J; Glasser, Neil F (Polar Research, 1997)
Keywords: Antarktis; geologi; geomorfologi; glasiologi; innlandsis; subglasial innsjø

Spatial and temporal variation of sublimation on Antarctica: Results of a high-resolution general circulation model - van den Broeke, Michiel R. (Journal of Geophysical Research: Atmospheres, 1997)
In this paper we use output of a high-resolution general circulation model (ECHAM-3 T106, resolution 1.1°?1.1°) to study the spatial and temporal variation of sublimation on Antarctica. First, we compare model results with available observations of sublimation rates. The yearly cycle, with small latent heat fluxes during the winter, is well reproduced, and the agreement with sparsely available spot observations is fair. The model results suggest that a significant 10?15% of the annual precipitation over Antarctica is lost through sublimation and that sublimation plays an important role in the formation of blue ice areas. A preliminary analysis of the atmospheric boundary layer moisture budget shows that the spatial variation of sublimation in the coastal zone of East Antarctica can be explained by variations of horizontal advection of dry air. Dry air advection, and thus surface sublimation, is enhanced in areas where katabatic winds are strong and have a large downslope component and where the Antarctic topography drops suddenly from the plateau to the coastal zone. In areas where horizontal advection is small, like the plateau and the large ice shelves, special conditions must be met to make significant sublimation at the surface possible.
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

Cold resistance and metabolic activity of lichens below 0°C - Kappen, Ludger; Schroeter, Burkhard; Scheidegger, Christoph; Sommerkorn, Martin; Hestmark, Geir (Proceedings of the F3.1, F3.4, F2.4 and F3.8 Symposia of COSPAR Scientific Commission F, 1996)
Laboratory measurements show that lichens are extremely tolerant of freezing stress and of low-temperature exposure. Metabolic activity recovered quickly after severe and extended cold treatment. Experimental results demonstrate also that CO2 exchange is already active at around −20°C. The psychrophilic character of polar lichen species is demonstrated by optimum temperatures for net photosynthesis between 0 and 15°C. In situ measurements show that lichens begin photosynthesizing below 0°C if the dry thalli receive fresh snow. The lowest temperature measured in active lichens was −17°C at a continental Antarctic site. The fine structure and the hydration state of photobiont and mycobiont cells were studied by low-temperature scanning electron microscopy (LTSEM) of frozen hydrated specimens. Water potentials of the frozen system are in the range of or even higher than those allowing dry lichens to start photosynthesis by water vapor uptake at +10°C. The great success of lichens in polar and high alpine regions gives evidence of their physiological adaptation to low temperatures. In general lichens are able to persist through glacial periods, but extended snow cover and glaciation are limiting factors.
Keywords: Antarktis; botanikk; frostresistens; lav; planter; polarområdene

Sydpolen, fra drøm til virkelighet - Arnesen, Liv (Polarboken, 1996)
Keywords: Antarktis; ekspedisjoner

Et eksperiment i egenmestring - Pedersen, Cato Zahl (Polarboken, 1996)
Keywords: Antarktis; ekspedisjoner

Anhydrobiosis and cold tolerance in tardigrades - Sømme, Lauritz (European Journal of Entomology, 1996)
A review of the literature regarding anhydrobiosis and cold tolerance in tardigrades is presented. During increasing desiccation, invertebrates like tardigrades, rotifers, nematodes and some collembolans are able to shut down metabolism to undetectable levels. When tardigrades are entering anhydrobiosis, a tun-like structure is formed, facilitated by structural adaptations of the cuticle. Slow dehydration is essential for tun formation, and the accumulation of trehalose during this process may help to stabilize phospholipids and proteins. Wax extrusion on the cuticle surface reduces transpiration. A fraction of 5-15% of the initial body water is retained during anhydrobiosis. Tardigrades are principally aquatic organisms, but anhydrobiosis makes it possible for some species to live in habitats with changing moisture conditions. Tardigrades in anhydrobiosis may tolerate exposure to freezing temperatures of liquid gases, and some species also survive such temperatures in their hydrated state. Few investigations are available on the relation of tardigrades to temperatures more representative to their natural environments. Experimental studies, however, from Greenland and the Antarctic Continent suggest that some species overwinter both in a hydrated frozen state and in anhydrobiosis. During the summer, a number of tardigrade species have been recorded from cryoconite holes, formed on the surface of glaciers. These species are freeze tolerant since their habitats are permanently frozen during the winter.
Keywords: Antarktis; Dronning Maud Land; biomonitorering; bjørnedyr; entomologi; kuldetoleranse; polarområdene; virvelløse dyr

Using multiple data sources to enhance photogrammetry for mapping Antarctic terrain - Fox, Adrian J (Polar Research, 1995)
Keywords: Antarktis; flyfoto; geografi; kartlegging; luftfoto; satellittbilder

Immune responses during an antarctic summer - Lugg, Desmond J.; Ursin, Holger; Donovan, Kevin; Konrad Muller, H.; Quinn, Dennis (Pathology, 1995)
The immune status of 29 members of the Australian National Antarctic Research Expeditions (ANARE) was investigated before, during, and after a 56 day summer voyage to Antarctica and correlated with psychological and physiological parameters. All subjects were healthy. Expedition personnel demonstrated decreased cell mediated immune responses (CMI) assessed by the CMI Multi-test; 21% were hypoergic. The major associated observation was a significant negative correlation with anxiety in Antarctica. However, perceived anxiety was greater before and after the voyage. No significant changes were found in T and B lymphocyte subsets, immunoglobulin and complement components and cutaneous blood flow, nor was there any clinical evidence of illness. Of the hormones examined only cortisol was low predeparture which may reflect increased perceived anxiety at that time. Changes in immune control mechanism were apparent as shown by reduced CMI responses and lowered tetanus antibody levels. Stress factors are postulated to induce depression of the immune response in Antarctica. The association with anxiety suggests that brain peptides or associated cytokines may have a role in mediating these immune events. Such alterations in immune status have implications for health management in isolated and extreme conditions.
Keywords: Antarktis; fysiologi; immunologi; psykologi

Forskrift om vern av miljøet i Antarktis - Miljøverndepartementet (1995)
Keywords: Antarktis; jus; miljøvern

Polychlorinated Dibenzo-p-Dioxins, Dibenzofurans and Coplanar Biphenyls in Antarctic Fur Seal Blubber - Oehme, Michael; Schlabach, Martin; Boyd, Ian (Ambio, 1995)
Levels of polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDF) as well as of coplanar (non-ortho substituted) polychlorinated biphenyls (CB-77, CB-126 and CB-169) have been determined in 11 fur-seal blubber samples from female Antarctic fur seals. Measurable PCDD/PCDF concentrations averaging 2 ppt TEQ (Nordic model) were found. This is considerably less than in Arctic seals. In addition, the PCDD/PCDF congener patterns differed between Antarctic and Arctic seals. The levels of CB-77, CB-126 and CB-169 (8.5-41 pg g-1 for single congeners in average) in Antarctic fur seals were also much lower than in Arctic ringed and harp seals. A possible explanation of these differences is the overall lower environmental pollution of the Southern Hemisphere, though an influence of different age and sex distributions cannot be excluded. The data passed all quality assurance criteria that had been established for such low levels.
Keywords: Antarktis; forurensning; marin biologi; miljøgifter; pinnipedier; polarområdene; seler

Two further bipolar lichens - Øvstedal, Dag Olav; Gremmen, Niek J M (Graphis scripta, 1995)
Keywords: Antarktis; botanikk; lav; planter

The Vestfold Hills: the Norwegian connection - Patterson, D (ANARE News, 1995)
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Sydpolekspedisjoner (Polarboken, 1994)
Keywords: Antarktis; ekspedisjoner

Teltet på Sydpolen - Dannevig, Alv (Vær & klima, 1994)
Keywords: Antarktis; ekspedisjoner; logistikk

Alene til Sydpolen - Kagge, Erling (Polarboken, 1994)
Keywords: Antarktis; ekspedisjoner

A model of ice shelf-ocean interaction with application to the Filchner-Ronne and Ross Ice Shelves - Nøst, Ole Anders; Foldvik, Arne (Journal of Geophysical Research: Oceans, 1994)
A simple analytical model has been developed to study the formation of Ice Shelf Water (ISW). ISW is assumed to flow as a buoyancy-driven layer underneath the ice shelf. A relation between potential temperature and salinity in the ISW layer is calculated from the mass and energy balance. This temperature-salinity relation is shown to depend only on the temperature and the salinity of the source water mass and to be practically independent of entrainment and melt rates. The model results are obtained without making any assumptions about entrainment and melt rates. The model is in good agreement with observations under the Ronne Ice Shelf, and it indicates that ISW in the Filchner Depression is formed from Western Shelf Water (WSW) with salinity higher than 34.75 practical salinity units. Such high-salinity water is only observed in the Ronne Depression in the western part of the continental shelf. This implies a circulation of WSW, under the Filchner-Ronne Ice Shelf, from the Ronne Depression into the Filchner Depression. Similarly, the model shows that the ISW observed under J9 at the Ross Ice Shelf has been formed from Low Salinity Shelf Water (LSSW) from the eastern parts of the Ross Sea continental shelf. LSSW must therefore circulate under the eastern parts of the Ross Ice Shelf.
Keywords: Antarktis; geofysikk; isshelf; kontinentalsokkel; oseanografi

Rock mapping of glaciated areas by satellite image processing - Salvini, Francesco; Della Maggiore, Roberto; Fortunati, Luciano; Mazzarini, Francesco (Polar Research, 1994)
Keywords: Antarktis; geologi; polarområdene; satellitt bilder

Solorina Spongiosa in Antarctica: An Extremely Disjunct Bipolar Lichen - Smith, R. I. Lewis; Øvstedal, Dag Olav (The Lichenologist, 1994)
The bipolar foliose lichen Solorina spongiosa (Sm.) Anzi is reported from James Ross Island, Antarctica, where it grows on moss. This is only the third known occurrence of this lichen from the Southern Hemisphere, the other localities being in Tierra del Fuego and New Zealand. Its morphology resembles that of the New Zealand population and arctic-alpine populations from the Northern Hemisphere, although there are some differences in apothecial and spore size. As elsewhere, it occupies base-rich habitats colonized by predominantly calcicolous mosses and lichens.
Keywords: Antarktis; botanikk; lav; moser; planter

The Antarctic Treaty system and Antarctic tourism: towards a legal regime? - Vidas, Davor (International Challenges, 1994)
Keywords: Antarktis; jus; turisme

Regulation of parental effort in a long-lived seabird an experimental manipulation of the cost of reproduction in the antarctic petrel, Thalassoica antarctica - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Behavioral Ecology and Sociobiology, 1993)
The fitness of a parent in an altricial bird species is likely to be a function of the proportion of resources allocated to offspring production in relation to the amount spent on its own survival. Here we report an experiment on the Antarctic petrel in which we manipulated the costs of rearing an offspring by placing small lead loads on the legs of one parent. The bird could then either decrease its own body reserves or reduce the food load to the chick. The manipulated birds decreased their food load and increased the feeding interval, compared with unmanipulated birds. Consequently, the rate of chick loss increased. No significant difference was found between the body weights of experimental and control birds during the experiment.
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi; økologi

Antarctic tourism: a challenge to the legitimacy of the Antarctic treaty system? - Vidas, Davor (German yearbook of international law, 1993)
Keywords: Antarktis; jus; turisme

Den Norske Sydpol-ekspedisjonen 1990-91 (Polarboken, 1992)
Keywords: Antarktis; ekspedisjoner

Søker fortiden og framtiden på Sydpolen - Bakka, Toril (Statoil magasin, 1992)
Keywords: Antarktis; biografi; ekspedisjoner

Do glaciers tell a true atmospheric CO2 story? - Jaworowski, Zbigniew; Segalstad, Tom Victor; Ono, Nobuo (Science of The Total Environment, 1992)
Until 1985 most studies of CO2 in gas inclusions in pre-industrial ice indicated that CO2 concentrations (up to 2450 ppm) were higher than the current atmospheric level. After 1985, lower pre-industrial CO2 values were reported, and used as evidence for a recent man-made CO2 increase. The errors in these revised values, however, are of a similar magnitude to the apparent increase in atmospheric CO2 level. The assumptions used in estimating lower CO2 values in past atmospheres have been: no liquid phase in polar ice; younger age of air than of ice due to free gas exchange between deep firn and the atmosphere; and no change in composition of air inclusions. These assumptions are shown to be invalid. Liquid saline water exists in ice at low temperatures, even below −70°C; airtight ice layers are ubiquitous in Antarctic firn; and more than 20 physico-chemical processes operating in situ and in ice cores contribute to the alteration of the chemical composition of air inclusions. The permeable ice sheet with its capillary liquid network acts as a sieve which redistributes elements, isotopes, and micro-particles. Thirty-six to 100% of air recovered from old ice is contaminated by recent atmospheric air during field and laboratory operations. The value of ∼290 ppm, widely accepted from glacier studies for the pre-industrial atmospheric CO2 level, apparently results from: invalid assumptions; processes in ice sheets; artifacts in ice cores; and arbitrary rejection of high readings. To date, glaciological studies are not able to provide a reliable reconstruction of either the CO2 level in pre-industrial and ancient atmospheres or paleoclimates. Instead these studies have led to a widely accepted false dogma of man-made climatic warming. This dogma may have enormous negative impact on our common future.
Keywords: Antarktis; drivhuseffekt; glasiologi; global oppvarming; isbreer; karbondioksid; paleoklimatologi; stabile isotoper

Activities within the Aurora Programme field season 1991/92 - Kristensen, Monica (Filchner-Ronne Ice Shelf Programme. Report, 1992)
Keywords: Antarktis; ekspedisjoner; glasiologi; meteorologi

Negotiating the mineral regime in the Antarctic: a review - Mørkved, Berit (International Challenges, 1992)
Keywords: Antarktis; jus; mineraler; politikk

Pertusaria signyae (Lichenes), a new species from the Antarctic - Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A saxicolous Pertusaria species is described as new to science: P. signyae Ovst. from South Orkney Islands. It has an isidiate thallus, subglobose fertile verrucae with poriform apothecia, and contains 2'-0-methylperlatolic acid.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

Determination of sulphur- and chlorine-containing compounds using capillary gas chromatography and atomic emission detection - Pedersen-Bjergaard, Stig; Asp, Tone Normann; Greibrokk, Tyge (Analytica Chimica Acta, 1992)
The potential of universal calibration using capillary gas chromatography combined with atomic emission detection was evaluated for several chlorine- and sulphur-containing compounds of environmental interest. The elemental responses obtained for C, H, Cl and S were found to be affected by the molecular structure. Rapid determination of several analytes was accomplished using a single calibration graph based on one randomly selected reference compound, but 10–30% errors relative to the actual concentrations were observed in several instances. The results were significantly improved by using reference compounds with structures similar to those of the analytes of interest. the practical utility of universal calibration is illustrated by the determination of pesticides in stomach oil deposits from birds living in Antarctica.
Keywords: Antarktis; biokjemi; fugler; kjemi; kromatografi; petreller

Contributions to the Caloplaca flora of the western Antarctic region - Søchting, Ulrik; Øvstedal, Dag Olav (Nordic Journal of Botany, 1992)
Fourteen species of the lichen genus Caloplaca are recorded from the western Antarctic region and described morphologically and anatomically, viz.: C. ammiospila, C. approximata, C. athallina, C. cirrochrooides, C. citrina, C. isidioclada, C. lucens, C. millegrana, C. regalis, C. sublobulata, C. tenuis, C. aff. anchon-phoeniceon. Type specimens of critical species have been studied. A key is provided to the species. Caloplaca ammiospila and C. approximata are reported as new to the Antarctic region.
Keywords: Antarktis; botanikk; lav; planter

Protecting the frozen south - Stokke, Olav Schram (Green globe yearbook, 1992)
Keywords: Antarktis; jus; miljøvern; politikk

Eine neue Gyalecta-Art aus der Antarctis: G. pezizoides sp. n. (lichensierte Fungi, Gyalectaceae) - Vezda, A.; Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A new species of the genus Gyalecta, G. pezizoides sp. n. (lichenized Fungi, Gyalectaceae), is described and illustrated. This new species is taxonomically near to the holarctic Gyalecta peziza (Mont.) Anzi.
Keywords: Antarktis; botanikk; lav; planter

Vel blåst! Kommandør Chr. Christensens Hvalfangstmuseum gjennom 75 år 1917-1992 - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1992)
Keywords: Antarktis; Christen Christensen; Nordmenn; Vestfold; historie; hvalfangere; hvalfangstindustri; pelagisk; polarekspedisjoner

The ecophysiology of under-ice fauna - Aarset, Arne V (Polar Research, 1991)
Keywords: Antarktis; amfipoder; fauna; havis; polarområdene; sjøis; zoologi; økofysiologi

Foraging economics and performance of polar and subpolar Atlantic seabirds - Croxall, John P; Briggs, Dirk R (Polar Research, 1991)
Keywords: Antarktis; fugler; næring; ornitologi; pingviner; zoologi; økologi

Occurrence of polar seabirds at sea in relation to prey concentrations and oceanographic factors - Hunt Jr, George L (Polar Research, 1991)
Keywords: Antarktis; næring; ornitologi; oseanografi; polarområdene; sjøfugler; økosystemer

The Eleventh Antarctic Treaty Consultative Meeting - Scully, Richard Tucker (International Challenges, 1991)
Keywords: Antarktis; jus; politikk

The lichen genus Stereocaulon in Antarctica and South Georgia - Smith, Ronald I Lewis; Øvstedal, Dag Olav (Polar Biology, 1991)
Six species of Stereocaulon and one unnamed taxon (close to S. glabrum) are reported from South Georgia, the maritime Antarctic islands and Antarctic Peninsula. S. caespitosum is new to the western sub-Antarctic. Variations in morphology and secondary chemistry are provided, and the ecology and geographical distribution in the sub-Antarctic and Antarctic biomes are given for each taxon.
Keywords: Antarktis; botanikk; lav; planter

Symposium report: "The Antarctic Treaty System in World Politics" - Stokke, Olav Schram (International Challenges, 1991)
Keywords: Antarktis; Sørishavet; forvaltning; jus; politikk

Psychobiological Studies of Individuals in Small, Isolated Groups in the Antarctic and in Space Analogues - Ursin, Holger; Bergan, Tom; Collet, Jérôme; Endresen, Inger M.; Lugg, Desmond; Maki, Pauline; Matre, Roald; Molvær, Otto Inge; Müller, Helmut K.; Olff, Miranda; Pettersen, Roger C.; Sandal, Gro Mjeldheim; et al. (Environment and Behavior, 1991)
Mental and physical health are both at risk under conditions of prolonged remoteness from home and removal from normal social support networks. This article examines relevant data from small groups isolated in (a) Antarctic summer stations, (b) a Transantarctic traverse expedition, and (c) a spacecraft simulator capsule.
Keywords: Antarktis; forskningsstasjoner; fysiologi; immunologi; psykobiologi; psykologi

Sandefjord - et naturlig polarforskningssenter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1991)
Keywords: Antarktis; Norsk Polarinstitutt; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Predatory feeding behavior of an Antarctic marine copepod, Euchaeta antarctica - Yen, Jeannette (Polar Research, 1991)
Keywords: Antarktis; fytoplankton; hoppekreps; marin biologi

Negtiationg a new regime: how CRAMRA came into existence - Andersen, Rolf Trolle (International Challenges, 1990)
Keywords: Antarktis; forvaltning; historie; mineraler; politikk

Protection of the environment in Antarctica: are present regimes sufficient? - Barnes, James N (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern

Antarctica's cultural heritage: can ICOMOS help? - Barr, Susan (Icomos information, 1990)
Keywords: Antarktis; Sørishavet; historie; kulturminneforvaltning

The resource conventions implemented: the consequences for the sovereignty issue - Beck, Peter J (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

Consultative status under the Antarctic Treaty: redefining the criteria? - Bos, Adrian (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The design of CRAMRA: how appropriate for the protection of the environment? - Brown, Alan D (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern; mineraler

The Antarctic in world politics - Dumas, Roland (International Challenges, 1990)
Keywords: Antarktis; politikk

Antarctica Treaty System: are there viable alternatives? - Falk, Richard (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The ability of the Antarctic Treaty System to adapt to external challenges - Haron, Mohamed (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The influence of the United Nations on the Antarctic system: a source of erosion or cohesion? - Harris, Stuart (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

Høyest oppe, lengst borte: Mt. Vinson, 5200 m, høyeste fjell i Antarktis - Høibakk, Ralph (Polarboken, 1990)
Keywords: Antarktis; ekspedisjoner; fjellklatring

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L. (Polar Research, 1990)
Keywords: Antarktis; fugler; marin ornitologi; næring; polarområdene

The pelagic distribution of marine birds in a heterogeneous environment - Hunt Jr, George L (Polar Research, 1990)
Keywords: Antarktis; fugler; ornitologi; polarområdene; zoologi

Antarctic science in a historical perspective: changing roles and functional development - Indreeide, Thor Vidar (International Challenges, 1990)
Keywords: Antarktis; forskning; historie; vitenskap

The legitimacy of the ATS - Jørgensen-Dahl, Arnfinn (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

CRAMRA: the ugly duckling of the Antarctic Treaty System? - Joyner, Christopher C (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern; mineraler

CRAMRA and other enviromental regimes in the ATS: how well does CRAMRA fit? - Kimball, Lee A (International Challenges, 1990)
Keywords: Antarktis; forvaltning; jus; miljøvern

Some Nitzschia and related diatom species from fast ice samples in the Arctic and Antarctic - Medlin, Linda K.; Hasle, Grethe Rytter (Polar Biology, 1990)
Some Nitzschia and closely related species have been examined in the light and electron microscopes from fast ice samples in the Arctic and Antarctic. Nitzschia neofrigida, forming arborescent colonies, and Nitzschia promare, forming loose ribbon colonies, are described as new species, both probably included in the distribution of other similar species. A new combination, Auricula compacta, represents the first report of this genus from ice samples. Colony formation is reported for the first time in Nitzschia arctica and Nitzschia taeniiformis. No biopolar species were found and several reports of Arctic species in Antarctic ice samples have been refuted.
Keywords: Antarktis; alger; biodiversitet; biologi; botanikk; diatomeer; fytoplankton; planteplankton; polarområdene

Towards firmer institutionalization of the ATS? Future role of the consultative meeting and the issue of a permanent secretariat - Messer, Kurt (International Challenges, 1990)
Keywords: Antarktis; forvaltning; jus

SCAR in the ATS: conflict or harmony? - Rinaldi, Carlos (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning; politikk

The relationship between the ATS and the LOS convention of 1982 - Safronchuk, Vasiliy S (International Challenges, 1990)
Keywords: Antarktis; Sørishavet; havrett; jus; politikk

Resource management and the changing profile of science in Antarctica: a growing pressure for relevance? - Scully, Richard Tucker (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning

The relevance of the ATS as a model for international cooperation - Stokke, Olav Schram (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

Frimerkespalten - Tandberg, Arne Ingar (Skipet, 1990)
Keywords: Antarktis; Bouvetøya; ekspedisjoner; filateli; historie; logistikk; skip

An Antarctic crossing as an analogue for long-term manned spaceflight - Ursin, Holger; Collet, Jérôme; Etienne, Jean L. (ESA Bulletin, 1990)
The long-duration space missions planned for the end of this century will involve both physiological and psychological problems for the crew who will fly them. If Europe is to achieve autonomy in space, it must increase its expertise in these associated disciplines. One means of acquiring relevant experience is to study human behaviour in environments that are similar from a psychological viewpoint. A planned crossing of the Antarctic by a six-man international team therefore offered ESA a unique opportunity to observe the psychological problems that can occur during an international expedition involving prolonged isolation in a hostile environment.
Keywords: Antarktis; fysiologi; psykologi

The unfinished task: CRAMRA and the question of liability - Wolfrum, Rüdiger (International Challenges, 1990)
Keywords: Antarktis; jus; mineraler

Kulturminnevern i Antarktis: noe for ICOMOS? - Barr, Susan (Icomos nytt, 1989)
Keywords: Antarktis; Peter I. Øy; historie; kulturminneforvaltning

Late Quaternary ice-surface fluctuations of Beardmore Glacier, Transantarctic Mountains - Denton, George H; Bockheim, James G; Wilson, Scott C; Leide, James E; Andersen, Björn G (Quaternary Research, 1989)
Former longitudinal profiles of Beardmore Glacier, an outlet through the Transantarctic Mountains, constrain polar plateau elevations near the center of Antarctica and ice-shelf grouding in the southern Ross Embayment. Three gravel drift sheets of late Quaternary age occur alongside Beardmore Glacier. Plunket drift, the youngest, is parallel to and 7–30 m above the present ice surface. The upper limit of Beardmore drift, intermediate in age, is within 35–40 m of the present ice surface near the polar plateau but about 1100 m above the present ice surface near the glacier mouth. The upper limit of Meyer drift, the oldest, is parallel to and 30–50 m above Beardmore drift. From correlation with numerically dated drifts farther north, we assign an early Holocene age to Plunket drift, a late Wisconsin age to Beardmore drift, and an age of marine isotope Stage 6 to Meyer drift. By our age model, Beardmore Glacier was close to current elevations in its upper reaches and thickened considerably in its middle and lower reaches during the last two global glaciations represented by Beardmore and Meyer drifts. Most likely, grounded ice in the southern Ross Embayment caused such thickening of Beardmore Glacier almost to the polar plateau. A concomitant decline in precipitation is implied by ice-cap retreat on the nearby Dominion Range and is consistent with little change of upper Beardmore Glacier. Ice-shelf grounding most likely resulted from lowered sea level and/or basal melting. Lower than present precipitation was probably caused by colder air temperatures and more-distant open water. The Plunket profile records Holocene ice-surface lowering from increased surface ablation, decreased ice flow, or grounding-line recession.
Keywords: Antarktis; geologi

Excess and deficit of sulfate in polar snow - Gjessing, Yngvar (Atmospheric Environment (1967), 1989)
Keywords: Antarktis; analyser; kjemisk; meteorologi; sjøvann; snø

The relationship between science and politics in international management of marine living resources: the case of CCAMLR - Indreeide, Thor Vidar (International Challenges, 1989)
Keywords: Antarktis; Sørishavet; forvaltning; jus; politikk

Iceberg scouring and sea bed morphology on the eastern Weddell Sea shelf, Antarctica - Lien, Reidar; Solheim, Anders; Elverhøi, Anders; Rokoengen, Kare (Polar Research, 1989)
Keywords: Antarktis; glasiologi; havbunnen; isberg; isshelf; kontinentalsokkel; morfologi; seismologi

Former extension of the East Antarctic Ice Sheet - Lundqvist, Jan (Polar Research, 1989)
Keywords: Antarktis; geologi; glasiologi; innlandsis

A hundred years of Norwegian exploration of the polar regions - Orheim, Olav (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1989)
Keywords: Antarktis; Norge; ekspedisjoner; oppdagelsesreiser; polarområdene

I fotsporene til Robert Falcon Scott - Danning, Petter (Været: populærvitenskapelig tidsskrift, 1988)
Keywords: Antarktis; ekspedisjoner; historie

Proposed terminology and reporting units for sea ice algal assemblages - Horner, Rita A; Syvertsen, Erik E; Thomas, David P; Lange, Carina (Polar Biology, 1988)
Keywords: Antarktis; alger; havis; marin biologi; polarområdene; sjøis

Borekjerner fra Antarktis - hva kan de fortelle om fortidens klima? - Kanestrøm, Ingolf (Været: populærvitenskapelig tidsskrift, 1988)
Keywords: Antarktis; iskjerner; klimaforskning

Mot 90⁰ syd, en rapport - Kristensen, Monica (Polarboken, 1988)
Keywords: Antarktis; ekspedisjoner; glasiologi

Aeromagnetic reconnaissance over the Riiser-Larsen Ice Shelf, east Antarctica - Kristoffersen, Yngve; Aalerud, Jan (Polar Research, 1988)
Keywords: Antarktis; glasiologi; havbunnen; isbreer; isfront; seismologi

Cladonia galindezii, a new Antarctic lichen species - Øvstedal, Dag Olav (Cryptogamie, Bryologieet Lichénologie, 1988)
Keywords: Antarktis; botanikk; lav; planter

On the variation of Ochrolechia parella in the western Antarctic and Subantarctic area - Øvstedal, Dag Olav (Polarforschung, 1988)
Keywords: Antarktis; botanikk; lav; planter

Amundsens sydpolferd 1910-12: vitenskapelige resultater sett i lys av nyere målinger - Dannevig, Petter (Været: populærvitenskapelig tidsskrift, 1987)
Keywords: Antarktis; ekspedisjoner; historie; meteorologi

Fra Monica Kristensens antarktisekspedisjon 1986-87 - Dannevig, Petter (Været: populærvitenskapelig tidsskrift11, 1987)
Keywords: Antarktis; ekspedisjoner

Geology, geophysics, and hydrocarbon potential of Antarctica continental margin of Weddell Sea - Hinz, K.; Kristoffersen, Yngve (AAPG Bulletin, 1987)
A prominent escarpment, called the Explora-Andenes Escarpment, has been recognized between long. 40°W, lat. 72°40^primeS and long. 10°W, lat. 69°20^primeS. It separates the continental margin from the Weddell Sea basin. Our recent MCS data have revealed the presence of some remarkably symmetric structures beneath a thick pile of tectonically undisturbed sediments. For example, two extensive wedge-shaped basement units occur between 20°W and 40°W. These units are characterized by a pattern of divergent reflectors which surround an elongated depression in basement. The northern wedge terminates against the Explora-Andenes Escarpment between 25°W and 30°W. The southern wedge, known as the Explora Wedge, shows a northward-dipping reflection pattern. The seismic characteristics suggest that both wedges consist of volcanic rocks. The basement depression is interpreted as a failed rift basin. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of "dipping reflectors." The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of dipping reflectors. The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures.
Keywords: Antarktis; Sørishavet; Weddellhavet; geofysikk; geologi

Rosshavets base på Stewart Island - Hoff, Stein (Norsk sjøfartsmuseum. Årsberetning, 1987)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; historie; hvalfangere; hvalfangststasjoner; pelagisk

Mannen med pappnesen (Polarboken, 1986)
Keywords: Antarktis; ekspedisjoner; fotografi; historie

Det internasjonale samarbeid i Antarktis og forhandlingene om et mineralregime - Andersen, Rolf Trolle (Polarboken, 1986)
Keywords: Antarktis; mineraler; politikk

Monica på veg til 90° syd - Heimark, Kjell Gunnar (Været: populærvitenskapelig tidsskrift, 1986)
Keywords: Antarktis; ekspedisjoner

Antarctic ozone depletion: 2-D model studies - Isaksen, Ivar S. A.; Stordal, Frode (Geophysical Research Letters, 1986)
Antarctic ozone depletion is estimated in a 2-D global model as a result of increase in chlorine levels from 1 ppb to 2.7 ppb and an increase in bromine levels from 15 ppt to 30 ppt. The adopted increase is assumed to be the anthropogenic influence on the stratospheric concentrations of chlorine and bromine species in 1985. Heterogeneous formation of ClO from the reaction between ClONO2 and HCl is included in the calculations, hypothesizing this is the dominant reaction path for chlorinated species on particle surfaces. A total ozone depletion as high as 14-20% may have occurred during the month of October at 80°S when maximum depletion is obtained. Both the magnitude and the time period when the maximum depletion occurs, agree with observed depletion over the last 8 years.
Keywords: Antarktis; geofysikk; meteorologi; ozonhull; ozonlaget

Geophysical evidence for the East Antarctic plate boundary in the Weddell Sea - Kristoffersen, Yngve; Haugland, Kristen (Nature, 1986)
An improved Gondwanaland reconstruction compatible with geological and geophysical information from the surrounding oceans and continents seems to require microplates to solve the enigmatic pre-early-Mesozoic tectonic relation between West and East Antarctica1. New multi-channel seismic reflection data from the southeastern Weddell Sea acquired during the 1984–85 Norwegian Antarctic Research Expedition (NARE) have outlined a linear WSW–ENE-trending basement ridge buried below the continental slope over a distance of 700 km. This structural high truncates the trend of the large sedimentary basins below the Filchner and Ronne ice shelves and may continue to within a few hundred kilometres of the Antarctic Penninsula. We interpret the basement ridge as part of the East Antarctic plate boundary during the break-up of Gondwana. The morphology and structure of this boundary show greater apparent similarity to a rifted or obliquely rifted margin than to the sheared margin which is predicted by current reconstructions2,3. A linear East Antarctic plate margin extending to the vicinity of the Antarctic Peninsula makes any post-rift micro-plate motion in the Weddell Embayment unlikely.
Keywords: Antarktis; NARE 1984/85; Weddellhavet; geofysikk; geologi; tektonikk

Suksess i syd: utvidet forskning i Antarktis (Forsvarets forum, 1985)
Keywords: Antarktis; Bouvetøya; Sørishavet; ekspedisjoner; forskning; logistikk

Flykatastrofe i antarktisk "white out" - Dannevig, Petter (Været: populærvitenskapelig tidsskrift, 1985)
Keywords: Antarktis; luftfart

Seismic investigations in the Weddell Sea Embayment - Haugland, Kristen; Kristoffersen, Yngve; Velde, Anders (Tectonophysics, 1985)
Keywords: Antarktis; NARE 1976/77; NARE 1978/79; Weddellhavet; ekspedisjoner; seismologi

På ekspedisjon til Sørpolen - Moberg, John (Norsk barneblad, 1985)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; ekspedisjoner; geofysikk; glasiologi; teknologi

Isfjell og isbreer i Antarktis - Orheim, Olav (Det norske videnskaps-akademi. Årbok, 1985)
Keywords: Antarktis; glasiologi

Prinsipper, problemer og praksis i Antarktis-utviklingen - Sollie, Finn (Internasjonal politikk, 1985)
Keywords: Antarktis; politikk

Alvorlig uhell på Vostok-basen (Polarboken, 1984)
Keywords: Antarktis; forskningsstasjoner; logistikk

Iceberg calving and deterioration in Antarctica - Kristensen, Monica (Progress in Physical Geography: Earth and Environment, 1983)
Keywords: Antarktis; glasiologi; innlandsis; isbreer; isbrem; kalving

Automatic collection of tilt and strain data from tabular icebergs - Kristensen, Monica; Squire, Vernon A (Annals of Glaciology, 1983)
Keywords: Antarktis; forskning; glasiologi; isbreer

Modelling of antarctic tabular icebergs in ocean waves - Kristensen, Monica; Squire, Vernon A (Annals of Glaciology, 1983)
The prediction of the motions of a tabular iceberg in a seaway is a problem which cannot be solved with a simple approach. The main difficulty lies in the size and mass of the iceberg, which produce frequency-dependent hydrodynamical effects as it moves in the water. Specifically, any solution must take into account both the added inertia and the generation of surface waves caused by the motions of the berg. Early attempts at modelling, which did not include these terms, could not accurately predict the complicated response behaviour seen in field data. In this paper we discuss some modifications to a two-dimensional simulation of floating bodies in waves, which must be applied when the motions and the hydro-dynamical pressures beneath tabular icebergs are required.
Keywords: Antarktis; Sørishavet; bølger; glasiologi; isbreer

Norge og den sovjetiske polarforskning i nord og sør - Magnus, Morten H (Farmand, 1983)
Keywords: Antarktis; ekspedisjoner; polarforskning; polarområdene

Cold Hardiness of Terrestrial Mites at Signy Island, Maritime Antarctic - Block, William; Sømme, Lauritz (Oikos, 1982)
The cold hardiness of four species was studied in respect of supercooling ability, cryoprotective substances, chill-coma temperatures and survival under anaerobiosis. The effects of low temperature acclimation and starvation on cold hardiness were examined experimentally. (2) Mean supercooling points of field animals ranged from -6.1° to -28.8°C during Jan-Mar 1980. In Nanorchestes antarcticus (Strandtmann) and Alaskozetes antarcticus (Michael), a bimodal distribution of individual supercooling points occurred with the low group (LG) consisting of animals without gut nucleators. In Stereotydeus villosus (Trouessart) and Gamasellus racovitzai (Trouessart) only a high group (HG) was present in the supercooling-point distributions. (3) In all species, except the predatory G. racovitzai, starvation combined with low temperature exposure for various time periods lowered the mean supercooling point. This was associated with increased concentrations of glycerol in the body fluid. Glucose, ribitol and mannitol together with straight chain hydrocarbons were also detected in the extracts by GLC techniques. (4) Chill-coma temperatures varied from -4.5° to -8.0°C. (5) Under anoxia at 0°C, survival of A. antarcticus was greater than that of G. racovitzai, with the later nymphal stages being slightly more resistant than adults.
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; midder; miter; virvelløse dyr

Nye fossile virveldyr fra Antarktis - Heintz, Natascha (Naturen, 1982)
Keywords: Antarktis; fossiler; paleontologi

Carsten Borchgrevink: lederen for den første overvintring i Antarktis - Ingstad, Helge (Polarboken, 1982)
Keywords: Antarktis; biografi; ekspedisjoner; historie

Tabular icebergs in ocean waves - Kristensen, Monica; Squire, Vernon A; Moore, Stuart C (Nature, 1982)
Keywords: Antarktis; bølger; ekspedisjoner; glasiologi; havet; isbreer

Present-day glaciation in the South Shetland Islands - Orheim, Olav; Govorukha, Leonid Sergeevich (Annals of Glaciology, 1982)
Keywords: Antarktis; firnsnø; forskning; glasiologi; isbreer; stratigrafi; vulkaner

Falklandskonflikten og Antarktis-spørsmålene - Sollie, Finn (Fridtjof Nansen-stiftelsen på Polhøgda. Nyhetsbrev, 1982)
Keywords: Antarktis; politikk

Supercooling and winter survival in terrestrial arthropods - Sømme, Lauritz (Comparative Biochemistry and Physiology Part A: Physiology, 1982)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Cold Hardiness of Collembola at Signy Island, Maritime Antarctic - Sømme, Lauritz; Block, William (Oikos, 1982)
The cold hardiness of two Antarctic species of Collembola, Cryptopygus antarcticus Willem and Parisotoma octooculata (Willem), was studied in field fresh, starved and low temperature acclimated specimens at Signy Island, in the South Orkney Islands. Supercooling points of both species clearly fell in a high group (HG) and a low group (LG) with a division at ca. -15°C. Field fresh specimens mainly had HG supercooling points, while starvation at 5° and 15°C greatly increased the number of LG animals. Further evidence of the relation between supercooling and feeding status was obtained in C. antarcticus. Specimens fed moss turf homogenate almost entirely returned to HG supercooling points, indicating the presence of efficient nucleators in this substrate. In specimens fed purified green algae a high proportion of LG supercooling points was retained, which suggests a lack of nucleators in this kind of food. Increased ability of LG specimens to supercool was demonstrated in C. antarcticus following acclimation at -5°C, and in P. octooculata at 0°C. In C. antarcticus an increase in concentrations of cryoprotective substances took place at -5°C concurrent with the lowering of the mean supercooling point. The main substances of the multicomponent cryoprotectant system of this species were trehalose, mannitol and glycerol. Chill-coma temperatures of specimens collected in the field differed in C. antarcticus and P. octooculata with mean values of -8.3° and -4.8°C, respectively. P. octooculata was less resistant to anaerobic conditions than C. antarcticus. All specimens of the former species were killed within 8 d in nitrogen at 0°C, while ca. 30% of C. antarcticus specimens survived after 28 d.
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Studies of arthropod cold hardiness - Block, William; Sømme, Lauritz (British Antarctic Survey Bulletin, 1981)
Keywords: Antarktis; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Cold tolerance of alpine, Arctic, and Antarctic Collembola and mites - Sømme, Lauritz (Cryobiology, 1981)
Because of their dominant role in the fauna of alpine, Arctic and Antarctic locations Collembola and mites are of particular interest regarding adaptations to low temperatures. No freezing-tolerant species have been found in these groups of terrestrial arthropods, and it appears that all species depend entirely on supercooling to survive the lower temperatures of their habitats. While summer animals have high supercooling points, an increase in supercooling ability occurs during autumn and early winter, and can be explained as a two-step process. Initially gut content has to be eliminated to avoid heterogeneous nucleation at high subzero temperatures due to foreign nucleating agents. Second, supercooling is further enhanced through accumulation of glycerol or other lowmolecular cryoprotective substances. Further studies are needed on the ability of such animals to avoid inoculative freezing in their microhabitats.
Keywords: Antarktis; entomologi; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

De to siste fra Sydpol-ferdene 1910-12 - Omberg, Asbjørn (Polarboken, 1980)
Keywords: Antarktis; biografi; ekspedisjoner; historie

Huntfords bok om Scott og Roald Amundsen - Omberg, Asbjørn (Polarboken, 1980)
Keywords: Antarktis; ekspedisjoner; historie; litteratur

Amundsen's route to the South Pole - Drewry, David John; Huntford, Roland (Polar Record, 1979)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Flow of Antarctic ice shelves between long. 29° E. and 44° W - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: Antarktis; glasiologi; innlandsis; isfront; isshelf; isstrøm; kalving

Ice-shelf underwater morphology - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: Antarktis; NARE 1976/77; ekspedisjoner; forskning; glasiologi; isshelf; morfologi

Scott's transport 1911-1912 - Jones, A G E (Polarboken, 1978)
Keywords: Antarktis; ekspedisjoner; historie; logistikk

Norsk polarpolitikk ut av tåkeheimen - Leistad, Geirr I (Farmand, 1978)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene; polarpolitikk

Den norske Antarktis-ekspedisjonen 1976/77 - Orheim, Olav (Naturen, 1978)
Keywords: Antarktis; ekspedisjoner; forskning

Biota of the antarctic pack ice: R/V Hero cruise 77-5 - Siniff, D.; Laws, R.; Oritsland, T.; Stirling, I.; Bengtson, J.; Demaster, D.; Reichle, R. (Antarctic Journal of the United States, 1978)
Between 22 October and 20 November 1977, we used National Science Foundation's R/v Hero to conduct studies of Antarctic seals in pack-ice areas of the Antarctic Peninsula. Our principal focus was on crabeater seals, but we also were interested in other pack-ice species, particularly leopard seals. Our work centered on (a) collecting female crabeater and leopard seals for reproductive material depicting various stages of the reproductive cycle, (b) documenting further the social structure and reproductive behavior of crabeater seals, (c) observing daily activity patterns and local movements of crabeater seals at fast-ice concentrations, and (d) investigating crabeater seal behavior at weaning and their interaction with leopard seals.
Keywords: Antarktis; Sørishavet; marin biologi; seler

Kuldetoleranse hos alpine og arktiske collemboler - Sømme, Lauritz (Entomologisk tidskrift, 1978)
Keywords: Antarktis; ekspedisjoner; entomologi; forskning; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Norge i Antarktis - Børde, Haakon (Samtiden: tidsskrift for politikk, litteratur og samfunnsspørsmål, 1977)
Keywords: Antarktis; Antarktistraktaten; Dronning Maud Land; historie; internasjonal; politikk

Med "Polarsirkel" til Antarktis! - Orheim, Olav (Rieco-nytt, 1977)
Keywords: Antarktis; Bouvetøya; ekspedisjoner; reisebeskrivelser

Kåre Holts bok om Roald Amundsen (Polarboken, 1976)
Keywords: Antarktis; litteratur

En glemt polaforsker: Carsten Egeberg Borchgrevink - Evans, Hugh B; Jones, A G E (Polarboken, 1976)
Keywords: Antarktis; biografi; ekspedisjoner; historie

Med Amundsen til Sudpolen. Dagbokblad - Bjaaland, Olav (Syn og segn, 1975)
Keywords: Antarktis; Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; polarområdene

Antarktis i fokus - hva gjør norsk forskning? - Orheim, Olav (Forskningsnytt, 1975)
Keywords: Antarktis; NARE ekspedisjoner; geologi; glasiologi; havis; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; polarområdene

Naturressursene i Antarktis - Antonsen, Per (Internasjonal politikk, 1974)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; ressurser

A forgotten explorer: Carsten Egeberg Borchgrevink - Evans, Hugh B; Jones, A G E (Polar Record, 1974)
Keywords: Antarktis; biografi; ekspedisjoner; forskning; oppdagelsesreiser

Some notes on the future of the Antarctic Treaty collaboration - Hambro, Edvard (American journal of international law, 1974)
politikk jus
Keywords: Antarktis

Glaciological studies in the South Shetland Islands - Orheim, Olav (Antarctic Journal of the United States, 1974)
Keywords: Antarktis; Sør-Shetlandsøyene; geofysikk; glasiologi

Antarktis i sikkerhetspolitisk perspektiv - Skagestad, Odd Gunnar (Internasjonal politikk, 1974)
Keywords: Antarktis; politikk

The New Development in the Polar Regions - Sollie, Finn (Cooperation and Conflict, 1974)
Due to factors connected with modern technological developments and with the increasing global demand for new sources of raw materials, there is today a growing interest in the possibilities for economic exploitation of the polar regions. This makes for a new development in these regions; a development comprising and affecting such fields as science and technology as well as economy, transportation, military strategy and ecology. The present paper discusses this new development and its implications in an international perspective. Special attention is paid to the significance - in the physical/ geographical sense and otherwise - of the polar regions in the global context. A special section deals, on a general level, with 'the problem of the new territories', and the polar regions are discussed as new territories. Pointing out the risks and dangers inherent in the present and emerging developments, the author emphasizes the need for action, especially international cooperation, to meet and solve such problems. Cooperation may be facilitated through regular consultations between the states concerned, as is the case under the Antarctic Treaty. For the Arctic in particular, the author suggests a distinction between three basic zones (viz. the 'Central' the 'Intermediate' and the 'National' Arctic) as a possible point of departure for future discussion of measures of international cooperation.
Keywords: Antarktis; internasjonal politikk; polarområdene

Antarktis og den internasjonale havbunnsorganisasjon - Traavik, Kim (Internasjonal politikk, 1974)
Keywords: Antarktis; Antarktistraktaten; havbunnen; havrett; internasjonal; politikk; ressurser; rett

Innsjøer under isen i Antarktis - Fægri, Knut (Naturen, 1973)
Keywords: Antarktis; geofysikk; glasiologi

Moderne sydpolsproblemer - Hambro, Edvard (Samtiden, 1973)
Keywords: Antarktis; jus; politikk; økonomi

Antarktis, i fare for forurensing, som mulig dumpeplass for radioaktivt kjernefysisk avfall - Lund, Thoralv (Polarposten, 1973)
Keywords: Antarktis; miljøvern; radioaktivitet

Hvem bestemmer hva i Antarktis? - Rey (Polarposten, 1973)
Keywords: Antarktis; jus; politikk

The Antarctic: 'troubles' revisited - Skagestad, Odd Gunnar (Bulletin of peace proposals, 1973)
Keywords: Antarktis; politikk

Bergens deltakelse i den moderne hvalfangst - Tønnessen, Johan Nicolay (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1973)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; skipsfart

Isfjell kan brukes til overrisling - Haraldsen, Gunnar (Polarposten, 1972)
Keywords: Antarktis; isfjell; teknologi

Fossile virveldyr fra Antarktis - Heintz, Natascha (Naturen, 1972)
Keywords: Antarktis; paleontologi

Diurnal wind variations in Antarctica - Hisdal, Vidar (Quarterly Journal of the Royal Meteorological Society, 1972)
For the three Antarctic ice shelf stations considered (Norway Station, Maudheim, and Halley Bay) it is shown that from spring to autumn a systematic diurnal variation of the mean vector wind at the surface exists. Different factors that may be responsible for this variation are discussed. The results seem to agree well with the assumption that in areas far from the ice front (the seaward edge of the ice shelf) the main cause is the larger net gain of momentum in the lowest layers during the middle of the day, while closer to the ice front there is an additional effect of the varying contrast between the air temperature over the sea and over the ice shelf.
Keywords: Antarktis; Dronning Maud Land; glasiologi; meteorologi

Forurensing av polarområdene? Et spørsmål om regulering av utviklingen - Sollie, Finn (Internasjonal politikk, 1972)
Keywords: Antarktis; Antarktistraktaten; forurensning; internasjonal; miljø; politikk; økologi

En reise til Sydpolskontinentet "Antarktis" (Polarposten, 1971)
Keywords: Antarktis; Sørishavet; turisme

Inspections in Antarctica - Hanevold, Truls (Cooperation and Conflict, 1971)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; rett

The Antarctic Treaty consultative meetings : form and procedure - Hanevold, Truls (Cooperation and Conflict, 1971)
Keywords: Antarktis; Antarktistraktaten; forskning; internasjonal; politikk

Sydpolisen opptil 4000 m tykk: Sydpollandet har 95 pst. av isen i verden! - Lund, Thoralv (Polarposten, 1971)
Keywords: Antarktis; forskning

Antarktis i sikkerhetspolitisk perspektiv - Skagestad, Odd Gunnar (Internasjonal politikk, 1971)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; ressurser; rett

Norge og Antarktis - Tønnessen, Johan Nicolay (Historisk tidsskrift, 1971)
Keywords: Antarktis; Dronning Maud Land; historie; litteratur

The Last of "The Ten". Antarctic Pioneer Still Lives On (Antarctic, 1970)
Keywords: Antarktis; Hugh Blackwall Evans; Southern Cross; biografi; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; overvintring

Antarktis uten ispanser - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; geofysikk; geologi

Ønske om fortsatt Antarktis-innsats - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; politikk

Tolv lands polarforskere til Antarktis-møte i Oslo - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; forskning

Glaciological investigations on Deception Island - Orheim, Olav (Antarctic Journal of the United States, 1970)
Keywords: Antarktis; glasiologi

The political experiment in Antarctica - Sollie, Finn (Bulletin of the Atomic Scientists, 1970)
General discussion of international cooperation in Antarctica. In special issue Antarctica since the IGY; international laboratory for science and diplomacy.
Keywords: Antarktis; Antarktistraktaten; internasjonal politikk; internasjonal rett; internasjonal samarbeid

Ny amerikansk forskningsstasjon på Sydpolen vil bli oppkalt etter polfarerne Amundsen og Scott - Grossman, Joseph (Polarposten, 1969)
Keywords: Antarktis; stasjoner

Glaciology and glacial geology on Deception Island - Kläy, Jean-Roland; Orheim, Olav (Antarctic Journal of the United States, 1969)
Keywords: Antarktis; geologi; glasiologi

Amerikanske kvinnelige vitenskapsmenn studerer pingviner i Antarktis - Schroth, Charles (Polarposten, 1969)
Keywords: Antarktis; forskning

Arctic and Antarctic : current problems in the Polar region - Sollie, Finn (Cooperation and Conflict, 1969)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; rett

Arctic and Antarctic : current problems in the Polar region - Sollie, Finn (Cooperation and Conflict, 1969)
Sætrykk
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

Antarktistraktaten, territorialkravene, forskningssamarbeidet - Bolin, Fredrik Th. (Polarboken, 1968)
Keywords: Antarktis; forskning; jus; politikk

Folkerettslige spørsmål vedrørende suverenitetsspørsmål i Antarktis - Krogdahl, Trygve (Internasjonal politikk, 1968)
Keywords: Antarktis; jus; politikk

De første fossiler av landvirveldyr oppdaget i Antarktis - Lund, Thoralv (Polarposten, 1968)
Keywords: Antarktis; paleontologi

Mennesket i kamp mot naturkreftene: slaget om Antarktis - Lund, Thoralv (Polarposten, 1968)
Keywords: Antarktis; stasjoner

Amerikansk forskningsskip klargjøres for Antarktis-tur - Schroth, Charles S. (Polarboken, 1968)
Keywords: Antarktis; teknologi

Arktis og Antarktis : aktuelle problemstillinger - Sollie, Finn (Internasjonal politikk, 1968)
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

I telt på evig is: norsk polarekspedisjon til sydpollandet - Torkildsen, Torbjørn (Nå, 1968)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; forskning; politikk

Hvorfor døde Scott? - Zapffe, Peter Wessel (Polarboken, 1968)
Keywords: Antarktis; ekspedisjoner; historie

Konsul Lars Christensen 6. april 1884—10. desember 1965 - Holtedahl, Olaf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1967)
Keywords: Antarktis; historie; hvalfangst; oppdagelsesreiser

Olav Bjålands museum i Morgedal - Bjåland, Olav S (Polarboken, 1966)
Keywords: Antarktis; historie

Minnetale over konsul Lars Christensen. Holdt i fellesmøte den 4de februar 1966 - Holtedahl, Olaf (Det Norske Videnskaps-akademi i Oslo, 1966)
Keywords: Antarktis; historie; hvalfangst; oppdagelsesreiser

Lave temperaturer i Antarktis - Orheim, Olav (Polarboken, 1966)
Keywords: Antarktis; klima; meteorologi

En epoke var over. I desember 1965 døde Lars Christensen - Tønnessen, Johan Nicolay (Thor-glimt, 1966)
Keywords: Antarktis; historie; hvalfangst; oppdagelsesreiser

"Norge burde få sin egen stasjon ved Rosshavet" - Lund, Thoralv; Rønne, Finn (Polarposten, 1965)
Keywords: Antarktis; stasjoner

USA på Sydpollandet (Polarboken, 1964)
Keywords: Antarktis; logistikk; politikk

Profile of Martin Richard Ronne: a life in exploration - Ronne, Edith (Polarboken, 1964)
Keywords: Antarktis; biografi; ekspedisjoner; historie

In Amundsen's Tracks on the Axel Heiberg Glacier - Herbert, Walter William (The Geographical Journal, 1963)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Samer i polarforskningen - Nissen, Kristian (Sameliv : Samisk selskaps årbok, 1963)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

Til Amundsen-jubileet på Sydpolen - Bolin, Fredrik Th. (Polarboken, 1962)
ekspedisjoner
Keywords: Antarktis

Spotlight on the Antarctic - Friis, Erik J (The American-Scandinavian Review, 1962)
Omhandler 50 års-jubileet for Sydpolens erobring, med bl.a. overrekkelse av minneplakett, og Tore Gjelsvik til stede.
Keywords: Antarktis; Nordmenn; Norsk Polarinstitutt; Roald Amundsen; Sydpolsekspedisjonen

Et 50 års polarminne - Gran, Tryggve (Polarboken, 1962)
Keywords: Antarktis; ekspedisjoner; historie

Lys over "tåkeheimen" i sør: den videnskapelige serie fra Lars Christensens ekspedisjoner avlsuttet - Isachsen, Fridtjov (Norsk hvalfangst-tidende, 1962)
Keywords: Antarktis; Sørishavet; forskning; litteratur; naturvitenskap; vitenskap

Norges "tapte kontinenter" I - Lunde, Erik (Nå, 1962)
Keywords: Antarktis; historie; politikk; stasjoner

Thermal and metabolic responses of men in the Antarctic to a standard cold stress - Milan, Frederick A; Elsner, Robert W; Rodahl, Kaare (Journal of Applied Physiology, 1961)
Thermal and metabolic responses of eight male subjects exposed nude for 2 hr to a standard cold stress (17 α 1.0 C air temperature) were examined in the austral fall, winter, and spring at Little America in the Antarctic. Mean body, average skin and foot temperatures increased significantly after 3 months. Neither rectal nor finger temperatures were changed over the year. Although basal metabolic rates were unchanged, there was a significant decrease in the metabolic responses to the standard cold stress after 3 months in the Antarctic. It is suggested that these changes represent physiological adaptations to chronic cold. Submitted on November 14, 1960
Keywords: Antarktis; fysiologi; kuldeeksponering; kuldetoleranse; medisin

The lure of exploration - Rønne, Finn (Polarboken, 1960)
Keywords: Antarktis; ekspedisjoner

A nineteenth-century "new Australian" in the Antarctic: the remarkable achievements of Carsten Egeberg Borchgrevink, leader of the British Antarctic Expedition 1898 to 1900 - Swan, Robert Arthur (Royal Australian Historical Society. Journal and proceedings, 1960)
Keywords: Antarktis; ekspedisjoner; historie

Norsk Polarinstitutts målevirksomhet - Luncke, Bernhard (Norsk tidsskrift for jordskifte og landmåling, 1959)
Keywords: Antarktis; botanikk; ekspedisjoner; forskning; geodesi; geologi; glasiologi; kartlegging; meteorologi; ornitologi; oseanografi; zoologi

Some corrections to: Hans Bogen. Main events in the history of Antarctic exploration - Richter, Søren (Norsk hvalfangst-tidende, 1958)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; litteratur

De første i Antarktis - [Borchgrevink, Carsten Egeberg] (Vi Menn, 1957)
Keywords: Antarktis; Southern Cross; biografier; ekspedisjonen; oppdagelsesreiser

Norway and the Antarctic - Evensen, Jens (The American Scandinavian review, 1957)
Keywords: Antarktis; historie; internasjonal politikk; norske ekspedisjoner

Norsk kartleggingsarbeid i Antarktis: kaptein H.E. Hansen fyller 70 år = Norwegian mapping in the Antarctic: captain H.E. Hansen reaches his 70th birthday - Ruud, Johan T (Norsk hvalfangst-tidende, 1957)
Keywords: Antarktis; Sørishavet; biografi; historie; kartlegging

Air operations of the Norwegian-British-Swedish Antarctic Expedition in 1952 - Essen, Reinhold von (Polar Record, 1956)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; flyfoto; forskning; geografi; luftfoto

Antarktis' rettslige og politiske stilling - Nilsen, Frode (Nordisk tidsskrift for international ret, 1956)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY) 1957/1958; ekspedisjoner; internasjonal; politikk; rett; samarbeid

Noen av de ekspedisjoner som skal av gårde (Polarboken, 1955)
Keywords: Antarktis; ekspedisjoner

60 år siden mennesket første gang betrådte Sydpollandet = 60 years since men first set foot on the Antarctic continent - Bogen, Hans (Norsk hvalfangst-tidende, 1955)
Keywords: Antarktis; ekspedisjoner; historie; skip

60 år siden mennesket første gang betrådte Sydpolfastlandet: litt historikk - Richter, Søren (Norsk hvalfangst-tidende, 1955)
Keywords: Antarktis; ekspedisjoner; historie

Oversikt over store ekspedisjoner (Polarboken, 1954)
Keywords: Antarktis; ekspedisjoner

Konsul Lars Christensen 70 år - Gunnestad, Alf (Polarboken, 1954)
Keywords: Antarktis; biografi

Et forsøk på måling av breforandring i Antarktis - Liestøl, Olav (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1954)
Keywords: Antarktis; glasiologi; isbreer; klimaendringer

Sledge dogs of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1954)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; sledehunder

Mechanical Transport of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Swithinbank, Charles (Polar Record, 1953)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

A Radar Survey of the Ice Barrier - Higgins, Robert (Journal of Navigation, 1952)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geografi; geologi

Da Roald Amundsen reiste til Nordpolen, og Engelbregt Gravningen kom hjem fra Sydpolen = When Roald Amundsen left for the Northpole, and Engelbregt Gravningen came home from the Soutpole (Norsk polar-tidende, 1951)
Keywords: Antarktis; ekspedisjoner; historie

The Norwegian-British-Swedish Antarctic Expedition (The Geographical Journal, 1951)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Roberts, Brian Birley (Polar Record, 1950)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner

An international expedition to Antarctica. The Voyage to Queen Maud Land - Roots, Ernest Frederick (Geographical Magazine, 1950)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geologi

Antarctica. An Airman's view - Walford, G Brian (Geographical Magazine, 1950)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner

Preliminary Glaciological Plans for the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Ahlmann, Hans Wilhelmsson (Journal of Glaciology, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

The Norwegian-Swedish-British Antarctic Expedition - Ahlmann, Hans Wilhelmsson (Tellus, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

An international expedition to Antarctica - Kirwan, Laurence Patrick (Geographical Magazine, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

The Antarctic Continent - Law, Phillip Garth (Walkabout, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner

Norwegian-British-Swedish expedition to the Antarctic (The Geographical Journal, 1948)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Flyplasser på snø og is - Pedersen, Gunnar S. (Teknisk ukeblad : Norges fremste på teknologi, 1948)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY) 1957/1958; ekspedisjoner; logistikk; polarområdene

Proposed British-Norwegian-Swedish Antarctic Expedition, 1948–50 (Polar Record, 1947)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

The Falkland Islands Dependencies Survey, 1943-46 - Wordie, James Mann (Norsk hvalfangst-tidende, 1947)
Keywords: Antarktis; Sørishavet; ekspedisjoner; forskning; kartlegging; logistikk

Historien om Antarktis (Norsk hvalfangst-tidende, 1945)
Keywords: Antarktis; Sørishavet; historie; hvalfangst; litteratur; selfangst

Fra seksti grader nord til seksti grader syd - Bogen, Hans (Polar-årboken, 1945)
Keywords: Antarktis; hvalfangst

Lars Christensen-ekspedisjonenes videnskapelige resultater - Holtedahl, Olaf (Polar-årboken, 1945)
Keywords: Antarktis; ekspedisjoner; forskning

Entdeckungen und Ansprüche in der Antarktis - Drygalski, Erich von (Geographische Zeitschrift, 1944)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; internasjonal; polarhistorie; politikk

Norges livsrom - Hoel, Adolf (Det nye Norge, 1944)
Keywords: Antarktis; hvalfangst; internasjonal politikk; polarområdene; økonomi

Den antarktiske fugleverden - Holgersen, Holger (Naturen, 1944)
Keywords: Antarktis; fugler; ornitologi

Politisk spenning også i Sydpoltraktene - Manthe, Heinz ([Utsyn], 1943)
Keywords: Antarktis; internasjonal politikk

Minner fra sydpolsturen - Hanssen, Helmer (Polar-årboken, 1941)
Keywords: Antarktis; ekspedisjoner; oppdagelsesreiser

Admiral Byrds antarktiske ferd 1939-1940: snekrysseren helt ubrukelig? (Polar-årboken, 1940)
Keywords: Antarktis; ekspedisjoner; logistikk

Hvem oppdaget Antarktika? - Aagaard, Bjarne (Polar-årboken, 1940)
Keywords: Antarktis; oppdagelsesreiser

Mine fire antarktiske ferder - Ellsworth, Lincoln (Polar-årboken, 1940)
Keywords: Antarktis; ekspedisjoner

Några drag av den antarktiska kontinentens biologiska historia - Skottsberg, Carl (Det Kongelige norske videnskabers selskab. Forhandlinger, 1940)
Keywords: Antarktis; Sørishavet; biologi; botanikk; evolusjon; paleogeografi

Arktis i skuddet (Polar-årboken, 1939)
Keywords: Antarktis; politikk

Det Norske Geografiske Selskap (The Geographical Journal, 1939)
Keywords: Antarktis; Det Norske Geografiske Selskap; ekspedisjoner; geografi; polarområdene

De norske opdagelser i Sydishavet: fra C. A. Larsens tid til Christensens ekspedisjon 1937 - Aagaard, Bjarne (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; hvalfangst; oppdagelsesreiser

Han som gav oss Sydpollandet - Brøgger, A W (Verden i bilder, 1939)
Keywords: Antarktis; Lars Christensen; biografier

Charting the Antarctic - Christensen, Lars (The Polar times, 1939)
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Recent Reconnaissance Flights in the Antarctic - Christensen, Lars (The Geographical Journal, 1939)
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; flyfoto; geografi; hvalfangere; hvalfangst; luftfoto; oppdagelsesreiser

The Course of Antarctic Exploration between Longitudes 20° W. and 110° E. Notes on the map compiled to accompany the paper by Mr. Lars Christensen - Christensen, Lars (The Geographical Journal, 1939)
Keywords: Antarktis; Lars Christensen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Med Ellsworth til Sydpollandet - Rønneberg, Harald jr. (Polar-årboken, 1939)
Keywords: Antarktis; ekspedisjoner

Minneord om kaptein Gustav Bruun Bull - Bogen, Hans (Polar-årboken, 1938)
Keywords: Antarktis; biografi; hvalfangst

Charting the Antarctic - Christensen, Lars (American-Scandinavian Review, 1938)
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Kong Leopold og Dronning Astrid Land - Hoel, Adolf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1938)
Keywords: Antarktis; ekspedisjoner; kartlegging; oppdagelsesreiser

Konsul Lars Christensens ekspedisjon til Antarktis sesongen 1936-37 og dens kartografiske resultater - Hansen, Hans Edvard (Polar-årboken, 1937)
Keywords: Antarktis; ekspedisjoner; kartlegging

Sledge Dogs on Amundsen's South Polar Journey - Hanssen, Helmer (Polar Record, 1937)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; oppdagelsesreiser; polarområdene; sledehunder; sydpolen

Ekspansjonen i hvalfangsten. Hvaloljeprisen. - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Keywords: Antarktis; Lars Christensen; Sørishavet; hvalfangere; hvalfangstindustri; hvalindustri; hvalolje; pelagisk

Hjemkomsten. Hvlafangsten historie fra dens første begynnelse - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Den norske luftkartlegging i Antarktis 1937 - Romnæs, Nils; Bogen, Hans (Polar-årboken, 1937)
Keywords: Antarktis; ekspedisjoner; kartlegging

Noen tekniske detaljer vedrørende våre flyvninger i Antarktis - Widerøe, Viggo (Fly, 1937)
Keywords: Antarktis; Thorshavn ekspedisjon; flyging; flyvere; kartografi; oppdagelsesreiser

Mot Fremtidenn - Brøgger, Anton Wilhelm (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1936)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; polarområdene; sydpolen

Modifications des Noms de lieu du Continent Antarctique - Hansen, Hans Edvard (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1936)
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; flyfoto; geografi; kartografi; luftfoto; oppdagelsesreiser

Kartskisse av nyopdaget kyststrekning mellem 72° og 81° ost lengde samt M/T Thorshavnsfører, kaptein Klarius Mikkelsen, Mars 1935 - Heyerdahl, Eilif Fredrik (1936)
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Antarktis geografi = Antarctic geography - Paulsen, Harald B (Norsk hvalfangst-tidende, 1936)
Keywords: Antarktis; geografi; kart; kartlegging; litteratur

Norske ekspedisjoners virksomhet i Antarktis - Paulsen, Harald B (Polar-årboken, 1936)
Keywords: Antarktis; Sørishavet; kartlegging

Ergebnisse der Norwegischen Antarktischen Expeditionen - Wüst, Georg (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1936)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; forskning; oppdagelsesreiser

Consul Lars Christensen's Antarctic Cruise, 1933–34 (Polar Record, 1935)
Keywords: Antarktis; Thorshavn ekspedisjon; hydrografi; meteorologi; oseanografi

Nytt norsk land i Antarktis (Polar-årboken, 1935)
Keywords: Antarktis; ekspedisjoner; oppdagelsesreiser

Carsten Borchgrevink - Hoel, Adolf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1935)
Keywords: Antarktis; Carsten Borchgrevink; ekspedisjoner; oppdagelsesreiser; polarområdene

Norwegian Discoveries in the Antarctic, 1935 - [Mikkelsen, Klarius] (Polar Record, 1935)
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Opdagelsen Av Ingrid Christensen Land - Mikkelsen, Klarius (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1935)
Keywords: Antarktis; Ingrid Christensen Land; Thorshavn ekspedisjon; geografi; kartlegging; kartografi; oppdagelsesreiser

Consul Lars Christensen's Antarctic Cruise, 1933–34 (Polar Record, 1934)
Keywords: Antarktis; Thorshavn ekspedisjon; hydrografi; meteorologi; oseanografi

Mr. C.E. Borchgrevink - Brown, R N Rudmose (Nature, 1934)
Keywords: Antarktis; biografi; ekspedisjoner; historie

Mr. Carsten E. Borchgrevink - Mill, Hugh Robert (Geographical journal, 1934)
Keywords: Antarktis; biografi; ekspedisjoner

The Norwegian Expedition to the Antarctic (The Geographical Journal, 1933)
Keywords: Antarktis; Hjalmar Riiser; Larsen; ekspedisjoner; oppdagelsesreiser; sledehunder

Fly og bikkjer i polaregnene - Balchen, Bernt (Polar-årboken, 1933)
Keywords: Antarktis; ekspedisjoner; logistikk

Hungeren efter å løse uopklarede gåter - Borchgrevink, Carsten Egeberg (Polar-årboken, 1933)
Keywords: Antarktis; ekspedisjoner; oppdagelsesreiser

Det uendelige øde, men likevel så levende verden - Christensen, Lars (Polar-årboken, 1933)
Keywords: Antarktis; ekspedisjoner; oppdagelsesreiser

The Japanese South Polar Expedition of 1911-1912: A Little-Known Episode in Antarctic Exploration - Hamre, Ivar (The Geographical Journal, 1933)
Keywords: Antarktis; Choku Shirase; Den japanske antarktisekspedisjonen 1910–12; Sydpolen; ekspedisjoner; oppdagelsesreiser

Walfang und Forschung in der Antarktis - Steinert, Hermann (Geographische Zeitschrift, 1933)
Keywords: Antarktis; Nordmenn; Norge; Norvegia ekspedisjonene; forskning; hvalfangst; pelagisk

Skjørbuk- og rakit-vitaminene - Baashuus-Jessen, J (Norsk Veterinærtidsskrift, 1932)
Keywords: Antarktis; ekspedisjoner; medisin; sjøfolk

Norwegian Explorations in the Antarctic, 1930-1931 - Isachsen, Gunnar (Geographical Review, 1932)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjoner; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Relation of the Work of the Mawson and Norwegian Antarctic Expeditions, 1930-1931 - Joerg, Wolfgang Louis Gottfried (Geographical Review, 1932)
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjoner; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Antarctic Circumnavigation by the "Norvegia" (Geographical Review, 1931)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; polarområdene

Aviation lessons in the Antarctic - Balchen, Bernt (Mechanical Engineering, 1931)
Keywords: Antarktis; ekspedisjoner; flyvere; opdagelsesreiser; oppdagelsesreiser; polarflyving

Bemerkungen zu K.Lampe: Versuch einer politischen Geographie der Polargebiete - Braastad, Johan (Geographischer Anzeiger, 1931)
Keywords: Antarktis; geografi; polarområdene; politikk

Antarctic Research by the "Norvegia" Expeditions and Others: Discussion - Goodenough, William; Christensen, Lars; Kemp, Stanley; Wordie, James Mann; Mill, Hugh Robert (The Geographical Journal, 1931)
Keywords: Antarktis; Norvegia ekspedisjonen; ekspedisjoner; forsking; hvalfangst

The "Norvegia" Antarctic expedition of 1929-1930 - Long, A T (The Hydrographic Review, 1931)
Keywords: Antarktis; Dronning Maud Land; Sørishavet; ekspedisjoner; geografi; kartlegging; logistikk; oseanografi

The Antarctic (The Geographical Journal, 1930)
Keywords: Antarktis; Bouvetøya; Christen Christensen; Hjalmar Riiser; Larsen; Norvegia ekspedisjonen; Peter I. Øy; kartlegging; oppdagelsesreiser

Geografisk kronikk - Haffner, Einar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1930)
Keywords: Antarktis; ekspedisjoner; historie; polarforskning; polarområdene

Scott, der Held des Südpols - Nansen, Fridtjof (Atlantis (Freiburg), 1930)
Keywords: Antarktis; ekspedisjoner; historie; utforskning

The "Norvegia" Antarctic Expedition of 1929-1930 - Riiser-Larsen, Hjalmar (Geographical Review, 1930)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; lutfart; oppdagelsesreiser

Recent Antarctic discoveries - Brown, R N Rudmose (Scottish Geographical Magazine, 1929)
Keywords: Antarktis; Carl Anton Larsen; Jason (skip); hvalfangere; oppdagelsesreiser

Amundsen: Supreme Adventurer - Finley, John H (Geographical Review, 1929)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; forskning; polarområdene

Til hvalfangerne: videnskabelige samlerarbeide - Holtedahl, Olaf (Norsk hvalfangst-tidende, 1928)
Keywords: Antarktis; Sørishavet; museer; vitenskap

Trekk av Sydishavets dyreliv - Olstad, Ola (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Keywords: Antarktis; Bouvetøya; Lars Christensen; Norvegia ekspedisjoner; Peter I. Øy; dyreliv; forskning; zoologi

Rosshavet - Tofte, Eyvind (Norsk hvalfangst-tidende, 1926)
Keywords: Antarktis; Sørishavet; ekspedisjoner; hvalfangst

Johan Koren : (4. oktober 1879 - 4. mars 1919) - Schaanning, Hans Thomas Lange (Norsk Jæger- og Fisker-Forenings Tidsskrift, 1920)
Keywords: Antarktis; Belgica ekspedisjon; Johan Koren; Nordmenn; oppdagelsesreiser; polarforskning; zoologi

Fangst i Sydhavet (Norsk hvalfangst-tidende, 1917)
Keywords: Antarktis; Sørishavet; ekspedisjoner; fangst; historie; hvalfangst; selfangst

The Norwegian South Polar Expedition - Amundsen, Roald (Scottish Geographical Magazine, 1913)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarområdene

The Norwegian South Polar Expedition - Amundsen, Roald (The Geographical Journal, 1913)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; ekspedisjoner; geografi; oppdagelsesreiser; polarområdene

Amundsen's 'South Pole': A Review - Mill, Hugh Robert (The Geographical Journal, 1913)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; bokanmeldelser; oppdagelsesreiser

The Norwegian South Polar Expedition: Discussion - Shackleton, Ernest; Bruce, W S (The Geographical Journal, 1913)
Keywords: Antarktis; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarområdene

Amundsen`s Attainment of the South Pole (The National geographic magazine, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Amundsen's Expedition to the South Pole (Bulletin of the American Geographical Society, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Amundsen's expedition to the South Pole - Amundsen, Roald (Bulletin of the American Geographical Society, 1912)
Keywords: Antarktis; Sørpolen; ekspedisjoner

Litt om vore ski, bindinger og fotbeklaedning samt deres betydning for sydpolsfaerden - Amundsen, Roald (Foreningen Til Ski-Idrettens Fremme. Årbok, 1912)
Keywords: Antarktis; ekspedisjoner; oppdagelsesreiser; polarområdene; ski; skisport; sydpolen

Meine Reise zum Südpol - Amundsen, Roald (Zeitschrift der Gesellschaft für Erdkunde zu Berlin, 1912)
Keywords: Antarktis; Sørpolen; ekspedisjoner

Recent Antarctic Discoveries - Balch, Edwin Swift (Bulletin of the American Geographical Society, 1912)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser

Amundsen`s Antarctic Explorations - Brown, R N Rudmose (Scottish Geographical Magazine, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Ten Years of Antarctic Exploration - Mill, Hugh Robert (The Geographical Journal, 1912)
Keywords: Antarktis; Carsten Borchgrevink; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; oppdagelsesreiser

The race for the South Pole: future of polar exploration - Nansen, Fridtjof (Scribner's Magazine, 1912)
Keywords: Antarktis; ekspedisjoner; utforskning

La conquête du Pôle Sud - Voll, Nils (Revue de géographie commerciale, 1912)
Keywords: Antarktis; Sørpolen; ekspedisjoner

Plan for en polarfærd 1910-1917. Foredrag tirsdag den 10.november 1908 med efterfølgende bemerkninger af professorene Mohn og Nansen - Amundsen, Roald (Det Norske Geografiske Selskabs Aarbok, 1909)
Keywords: Antarktis; ekspedisjoner; oppdagelsesreiser; polarområdene

Antarctics sidste Færd. Foredrag den 18de februar 1904 - Larsen, Carl Anton (Det Norske geografiske selskabs aarbok, 1904)
Keywords: Antarctic (skip); Antarktis; Carl Anton Larsen; Den svenske antarktisekspedisjonen 1901–03; Otto Nordenskjöld; Sørishavet; vitenskapelige ekspedisjoner

Topography of South Victoria Land (Antarctic) - Bernacchi, Louis Charles (The Geographical Journal, 1901)
Keywords: Antarktis; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; geologi; oppdagelsesreiser; topografi

The "Southern Cross" Expedition to the Antarctic, 1899-1900 - Borchgrevink, Carsten Egeberg (The Geographical Journal, 1900)
Keywords: Antarktis; Southern Cross; biologi; ekspedisjonen; ekspedisjoner; forskning; geografi; meteorologi; oppdagelsesreiser; overvintring; zoologi

Mr. C.E. Borchgrevink - Fitzgerald, William G (Strand Magazine, 1900)
Keywords: Antarktis; biografi; ekspedisjoner

Borchgrevinks Südpolar-Expedition - Mewius., F; Supan, Alexander (ed.) (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1900)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; ekspedisjoner; oppdagelsesreiser

The Antarctic Expeditions - Markham, Clements (The Geographical Journal, 1899)
Keywords: Antarktis; Carl Anton Larsen; Jason (skip); ekspedisjoner; oppdagelsesreiser

The "Southern Cross" Antarctic expedition - Newnes, George (The Strand Magazine, 1899)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; ekspedisjoner; første landgang; oppdagelsesreiser; overvintring

Borchgrevinks antarktische Expedition auf dem „Southern Cross“ - Supan, Alexander (ed.) (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1899)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; ekspedisjoner; oppdagelsesreiser

Den antarctiske expedition. Foredrag den 18de mai 1898 - Borchgrevink, Carsten Egeberg (Det Norske geografiske selskabs aarbok, 1898)
Keywords: Antarktis; Southern Cross (skip); forskning; oppdagelsesreiser; polarekspedisjoner; vitenskapelige ekspedisjoner

Antarctic exploration - Borchgrevink, Carsten Egeberg (Strand Magazine, 1897)
Keywords: Antarktis; Southern Cross; ekspedisjonen; ekspedisjoner; forskning; geografi; oppdagelsesreiser; overvintring

The First Landing On The Antarctic Continent : being An Account of the Recent Voyage Of The Whaler "Antarctic" - Borchgrevink, Carsten Egeberg (The Century illustrated monthly magazine, 1896)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

Den sidste antarctiske reise og foreløbig plan for en ny expedition. Foredrag den 30te oktober 1895 - Borchgrevink, Carsten Egeberg; Bull, Henrik Johan (Det Norske geografiske selskabs aarbok, 1896)
Keywords: Antarktis; Kapp Adare; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner

Borchgrevink and Antarctic exploration - Greely, Adolphus W (Century illustrated monthly magazine, 1896)
Keywords: Antarktis; ekspedisjoner

Journal of the Right-Whaling Cruise of the Norwegian Steamship "Antarctic", in South Polar Seas under the Command of Captain Leonard Kristensen during the Years 1894-95 - Kristensen, Leonard (Transactions of the Royal Geographical Society of Australasia, Victorian Branch, 1896)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; ekspedisjoner; første landgang; geografi; oppdagelsesreiser

Brief Survey of Antarctic Exploration - Potter, William (Transactions of the Royal Geographical Society of Australasia, Victorian Branch, 1896)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Leonard Kristensen; Rosshavet; Victoria Land; ekspedisjoner; første landgang; geografi; oppdagelsesreiser

Is Antarctic exploration possible? (The Spectator, 1895)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; ekspedisjoner; forskning; oppdagelsesreiser; overvintring

A Voyage to the Antarctic Sea - Borchgrevink, Carsten Egeberg (Report of the Sixty-Fifth meeting of the British Association for the Advancement of Science helt at Ipswich in September 1895, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The "Antarctic's" Voyage to the Antarctic - Borchgrevink, Carsten Egeberg (The Geographical Journal, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The Voyage of the “Antarctic” to Victoria Land - Borchgrevink, Carsten Egeberg (Nature, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

Begleitworte zur Karte des Dirck Gherritz Archipels - Friedrichsen, Ludwig (Mitteilungen der Geographischen Gesellschaft in Hamburg, 1895)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Vestantarktis; ekspedisjoner; geografi; geologi; oppdagelsesreiser

Kapit. Larsens antarktische Entdeckungen - Petersen, J; Larsen, Carl Anton; Wichmann, Hugo (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1895)
Keywords: Antarktis; Carl Anton Larsen; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Die Reisen des "Jason" und der "Hertha" in das Antarktische Meer 1893/94 : und die wissenschaftliche Ergebnisse dieser Reisen - Petersen, Johannes; Friedrichsen, Ludwig (Mitteilungen der Geographischen Gesellschaft in Hamburg, 1895)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Hertha (skip); Vestantarktis; dagbok; ekspedisjoner; forskning; geologi; hvalfangere; oppdagelsesreiser

Das Wiedererwachen der antarktischen Forschung - Wichmann, Hugo; [Hassenstein, Bruno] (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1895)
Keywords: Antarktis; Carl Anton Larsen; D/S Antarctic; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Notes on an important geographical discovery in the Antarctic Regions - Murray, John (Scottish Geographical Magazine, 1894)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Vestantarktis; dagbok; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Das neu entdeckte Land im antarktischen Gebiet - Schück, Albert (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1894)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; dagbøker; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Souveränitätsverhältnisse der Polargebiete : III. die südpolaren Gebiete - Smedal, Gustav ([Nordländer])
Keywords: Antarktis; Bouvetøya; Peter I. Øy; internasjonal; polarområdene; politikk